Prospective study of the G20210A polymorphism in the prothrombin gene, plasma prothrombin concentration, and incidence of venous thromboembolism. - Folsom, Aaron R; Cushman, Mary; Tsai, Michael Y; Heckbert, Susan R; Aleksic, Nena (Am J Hematol, 2002)
Case-control studies have indicated increased risk of venous thrombosis associated with the prothrombin gene G20210A polymorphism and with elevated plasma prothrombin levels. We sought to confirm these results in a prospective population-based study of 21,690 persons. We measured G20210A and prothrombin antigen on pre-event blood samples of 302 participants who developed venous thromboembolism (VTE) and 626 participants who remained free of VTE. Approximately 4.0% of cases and 2.4% of controls carried the G20210A polymorphism, but only one of 137 African Americans did. The odds ratio in whites was 1.87 (95% CI = 0.85, 4.11)--higher for those who reported a prior history of VTE (OR = 5.44) than those reporting no VTE history (OR = 1.41) and in those with idiopathic VTE (OR = 2.51) than those with secondary VTE (OR = 1.38). There was no association between venous thromboembolism and plasma prothrombin antigen level. We estimated that the G20210A polymorphism may account for approximately 2.5% of venous thromboembolism events in United States whites.
Keywords: African Continental Ancestry Group; Age Factors; Aged; Case-Control Studies; European Continental Ancestry Group; Genotype; Humans; Incidence; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide; Prospective Studies; Prothrombin; Recurrence; Research Design; Risk Factors; Thromboembolism; United States

Population structure, admixture, and aging-related phenotypes in African American adults: the Cardiovascular Health Study. - Reiner, Alexander P; Ziv, Elad; Lind, Denise L; Nievergelt, Caroline M; Schork, Nicholas J; Cummings, Steven R; Phong, Angie; Burchard, Esteban González; Harris, Tamara B; Psaty, Bruce M; Kwok, Pui-Yan (Am J Hum Genet, 2005)
U.S. populations are genetically admixed, but surprisingly little empirical data exists documenting the impact of such heterogeneity on type I and type II error in genetic-association studies of unrelated individuals. By applying several complementary analytical techniques, we characterize genetic background heterogeneity among 810 self-identified African American subjects sampled as part of a multisite cohort study of cardiovascular disease in older adults. On the basis of the typing of 24 ancestry-informative biallelic single-nucleotide-polymorphism markers, there was evidence of substantial population substructure and admixture. We used an allele-sharing-based clustering algorithm to infer evidence for four genetically distinct subpopulations. Using multivariable regression models, we demonstrate the complex interplay of genetic and socioeconomic factors on quantitative phenotypes related to cardiovascular disease and aging. Blood glucose level correlated with individual African ancestry, whereas body mass index was associated more strongly with genetic similarity. Blood pressure, HDL cholesterol level, C-reactive protein level, and carotid wall thickness were not associated with genetic background. Blood pressure and HDL cholesterol level varied by geographic site, whereas C-reactive protein level differed by occupation. Both ancestry and genetic similarity predicted the number and quality of years lived during follow-up, but socioeconomic factors largely accounted for these associations. When the 24 genetic markers were tested individually, there were an excess number of marker-trait associations, most of which were attenuated by adjustment for genetic ancestry. We conclude that the genetic demography underlying older individuals who self identify as African American is complex, and that controlling for both genetic admixture and socioeconomic characteristics will be required in assessing genetic associations with chronic-disease-related traits in African Americans. Complementary methods that identify discrete subgroups on the basis of genetic similarity may help to further characterize the complex biodemographic structure of human populations.
Keywords: African Americans; Aged; Aging; Algorithms; Cardiovascular Diseases; Cohort Studies; Female; Genetics, Population; Genotype; Humans; Male; Models, Genetic; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors; Socioeconomic Factors

Association of polymorphisms in the CRP gene with circulating C-reactive protein levels and cardiovascular events. - Lange, Leslie A; Carlson, Christopher S; Hindorff, Lucia A; Lange, Ethan M; Walston, Jeremy; Durda, J Peter; Cushman, Mary; Bis, Joshua C; Zeng, Donglin; Lin, Danyu; Kuller, Lewis H; Nickerson, Deborah A; et al. (JAMA, 2006)
CONTEXT: C-reactive protein (CRP) is an inflammation protein that may play a role in the pathogenesis of cardiovascular disease (CVD). OBJECTIVE: To assess whether polymorphisms in the CRP gene are associated with plasma CRP, carotid intima-media thickness (CIMT), and CVD events. DESIGN, SETTING, AND PARTICIPANTS: In the prospective, population-based Cardiovascular Health Study, 4 tag single-nucleotide polymorphisms (SNPs) (1919A/T, 2667G/C, 3872G/A, 5237A/G) were genotyped in 3941 white (European American) participants and 5 tag SNPs (addition of 790A/T) were genotyped in 700 black (African American) participants, aged 65 years or older, all of whom were without myocardial infarction (MI) or stroke before study entry. Median follow-up was 13 years (1989-2003). MAIN OUTCOME MEASURES: Baseline CIMT; occurrence of MI, stroke, and CVD mortality during follow-up. RESULTS: In white participants, 461 incident MIs, 491 incident strokes, and 490 CVD-related deaths occurred; in black participants, 67 incident MIs, 78 incident strokes, and 75 CVD-related deaths occurred. The 1919T and 790T alleles were associated with higher CRP levels in white and black participants, respectively. The 3872A allele was associated with lower CRP levels in both populations, and the 2667C allele was associated with lower CRP levels in white participants only. There was no association between CIMT and any CRP gene polymorphism in either population. In white participants, the 1919T allele was associated with increased risk of stroke for TT vs AA (hazard ratio [HR], 1.40; 95% confidence interval [CI], 1.06-1.87) and for CVD mortality (HR, 1.40; 95% CI, 1.10-1.90). In black participants, homozygosity for the 790T allele was associated with a 4-fold increased risk of MI compared with homozygosity for the 790A allele (95% CI, 1.58-10.53). The minor alleles of the 2 SNPs associated with lower plasma CRP concentration in white participants (2667C and 3872A) were associated with decreased risk of CVD mortality. CONCLUSIONS: Genetic variation in the CRP gene is associated with plasma CRP levels and CVD risk in older adults.
Keywords: African Continental Ancestry Group; Aged; C-Reactive Protein; Cardiovascular Diseases; Carotid Arteries; European Continental Ancestry Group; Female; Genotype; Humans; Male; Myocardial Infarction; Polymorphism, Single Nucleotide; Proportional Hazards Models; Risk; Stroke; Tunica Intima

Beta2-adrenergic receptor genetic variants and risk of sudden cardiac death. - Sotoodehnia, Nona; Siscovick, David S; Vatta, Matteo; Psaty, Bruce M; Tracy, Russell P; Towbin, Jeffrey A; Lemaitre, Rozenn N; Rea, Thomas D; Durda, J Peter; Chang, Joel M; Lumley, Thomas S; Kuller, Lewis H; et al. (Circulation, 2006)
BACKGROUND: Sympathetic activation influences the risk of ventricular arrhythmias and sudden cardiac death (SCD), mediated in part by the beta2-adrenergic receptor (B2AR). We investigated whether variation in the B2AR gene is associated with SCD risk. METHODS AND RESULTS: In this study, 4441 white and 808 black Cardiovascular Health Study (CHS) participants were followed up prospectively for SCD and genotyped for B2AR Gly16Arg and Gln27Glu polymorphisms. The study was replicated in 155 case and 144 control white subjects in a population-based case-control study of SCD, the Cardiac Arrest Blood Study (CABS). In CHS, Gly16 and Gln27 allele frequencies were 62.4% and 57.1% among white and 50.1% and 81.4% among black participants. Over a median follow-up of 11.1 years, 156 and 39 SCD events occurred in white and black participants, respectively. The Gln27Glu variant was associated with SCD risk (P=0.008 for general model). SCD risk was higher in Gln27 homozygous participants than in Glu27 carriers (ethnicity-adjusted hazard ratio [HR], 1.56; 95% confidence interval [CI], 1.17 to 2.09; P=0.003). The increased risk did not differ significantly between white (HR, 1.62; 95% CI, 1.18 to 2.23) and black (HR, 1.23; 95% CI, 0.61 to 2.48) participants, although the confidence interval was wide in blacks. In the CABS replication study, Gln27 homozygous participants similarly had higher SCD risk than Glu27 carriers (odds ratio, 1.64; 95% CI, 1.02 to 2.63; P=0.040). Gly16Arg was not associated with SCD risk in either study. CONCLUSIONS: Gln27 homozygous individuals have an increased risk of SCD in 2 study populations. Our findings suggest that B2AR plays a role in SCD in humans. Study of genetic variation within the B2AR gene may help identify those at increased SCD risk.
Keywords: African Continental Ancestry Group; Aged; Case-Control Studies; Death, Sudden, Cardiac; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Glutamine; Haplotypes; Homozygote; Humans; Male; Polymorphism, Single Nucleotide; Receptors, Adrenergic, beta-2; Reproducibility of Results

Genome-wide association of sleep and circadian phenotypes. - Gottlieb, Daniel J; O'Connor, George T; Wilk, Jemma B (BMC Med Genet, 2007)
BACKGROUND: Numerous studies suggest genetic influences on sleepiness and circadian rhythms. The Sleep Heart Health Study collected questionnaire data on sleep habits and sleepiness from 2848 Framingham Heart Study Offspring Cohort participants. More than 700 participants were genotyped using the Affymetrix 100K SNP GeneChip, providing a unique opportunity to assess genetic linkage and association of these traits. METHODS: Sleepiness (defined as the Epworth Sleepiness Scale score), usual bedtime and usual sleep duration were assessed by self-completion questionnaire. Standardized residual measures adjusted for age, sex and BMI were analyzed. Multipoint variance components linkage analysis was performed. Association of SNPs to sleep phenotypes was analyzed with both population-based and family-based association tests, with analysis limited to 70,987 autosomal SNPs with minor allele frequency > or =10%, call rate > or =80%, and no significant deviation from Hardy-Weinberg equilibrium (p > or = 0.001). RESULTS: Heritability of sleepiness was 0.29, bedtime 0.22, and sleep duration 0.17. Both genotype and sleep phenotype data were available for 749 subjects. Linkage analysis revealed five linkage peaks of LOD >2: four to usual bedtime, one to sleep duration. These peaks include several candidate sleep-related genes, including CSNK2A2, encoding a known component of the circadian molecular clock, and PROK2, encoding a putative transmitter of the behavioral circadian rhythm from the suprachiasmatic nucleus. Association tests identified an association of usual bedtime with a non-synonymous coding SNP in NPSR1 that has been shown to encode a gain of function mutation of the neuropeptide S receptor, whose endogenous ligand is a potent promoter of wakefulness. Each copy of the minor allele of this SNP was associated with a 15 minute later mean bedtime. The lowest p value was for association of sleepiness with a SNP located in an intron of PDE4D, which encodes a cAMP-specific phosphodiesterase widely expressed in human brain. Full association results are posted at http://www.ncbi.nlm.nih.gov/projects/gap/cgi-bin/study.cgi?id=phs000007 webcite. CONCLUSION: This analysis confirms prior reports of significant heritability of sleepiness, usual bedtime, and usual sleep duration. Several genetic loci with suggestive linkage to these traits are identified, including linkage peaks containing circadian clock-related genes. Association tests identify NPSR1 and PDE4D as possible mediators of bedtime and sleepiness.
Keywords: Adult; Alleles; Cardiovascular Diseases; Circadian Rhythm; Cohort Studies; Female; Gene Frequency; Genetic Linkage; Genome, Human; Genotype; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Sleep; Surveys and Questionnaires

IL-6 gene variation is associated with IL-6 and C-reactive protein levels but not cardiovascular outcomes in the Cardiovascular Health Study. - Walston, Jeremy D; Fallin, M Daniele; Cushman, Mary; Lange, Leslie; Psaty, Bruce; Jenny, Nancy; Browner, Warren; Tracy, Russell; Durda, Peter; Reiner, Alex (Hum Genet, 2007)
Interleukin-6 (IL-6) and C-reactive protein (CRP) levels increase with age and likely play a role in adverse health outcomes in older adults. The relationship between IL-6 gene tag single nucleotide polymorphisms (SNPs) and circulating IL-6 and CRP levels, cardiovascular disease (CVD) outcomes, and mortality in Caucasian (CA) and African American (AA) participants of the Cardiovascular Health Study (CHS) was evaluated using ANCOVA and Cox proportional hazards models. The minor allele of the promoter SNP 1510 and intronic SNP 3572 associates with significantly higher serum IL-6 and CRP levels in CA but not AA. The CRP association persisted after CA and AA populations were combined and after accounting for multiple comparisons. These associations did not carry through to cardiovascular disease outcomes. Decreased risk of stroke was identified in CA, with the minor allele of SNP 1111 (HRR 0.71, 95% CI 0.52, 0.95), P = 0.02, and increased risk of CVD and all-cause mortality (HRR 1.31, 95% CI 1.05-1.64) in AAs heterozygote for SNP 2989. While genetic variation in the IL-6 gene was associated with circulating IL-6 and especially with CRP concentrations in this study, there is little evidence for association between common IL-6 gene variation and adverse health outcomes in this population of older adults.
Keywords: African Americans; Aged; Alleles; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Humans; Interleukin-6; Introns; Longitudinal Studies; Male; Polymorphism, Single Nucleotide; Promoter Regions, Genetic

USF1 gene variants, cardiovascular risk, and mortality in European Americans: analysis of two US cohort studies. - Reiner, Alexander P; Carlson, Christopher S; Jenny, Nancy S; Durda, J Peter; Siscovick, David S; Nickerson, Deborah A; Tracy, Russell P (Arterioscler Thromb Vasc Biol, 2007)
OBJECTIVE: A common haplotype of the upstream transcription factor 1 gene (USF1) has been associated with decreased susceptibility to familial combined hyperlipidemia (FCHL) and, paradoxically, with increased risk of cardiovascular disease (CVD) and all-cause mortality. METHODS AND RESULTS: We assessed associations between USF1 tagSNPs, CVD risk factors, and aging-related phenotypes using data from 2 large population-based cohorts, Coronary Artery Risk Development in Young Adults (CARDIA) and the Cardiovascular Health Study (CHS), comprising younger and older adults, respectively. In CARDIA, each additional copy of the FCHL low-risk allele was associated with 2.4 mg/dL lower levels of LDL cholesterol (P=0.01) and decreased risk of subclinical atherosclerosis as assessed by coronary artery calcium (odds ratio 0.79; 95%CI 0.63 to 0.98). Whereas there was little association between USF1 genotype and metabolic or CVD traits in older adults from CHS, the USF1 low-risk dyslipidemia allele was associated with higher plasma C-reactive protein and interleukin (IL)-6 levels and with increased risk of mortality, particularly attributable to noncardiovascular causes. CONCLUSIONS: There appears to be a complex and possibly age-dependent relationship between USF1 genotype, atherosclerosis phenotypes, and CVD risk. USF1 may influence mortality through pathways distinct from atherosclerosis. Alternatively, linkage disequilibrium with neighboring polymorphisms in other genes such as F11R may be responsible for the observed USF1 genotype-phenotype associations in older adults.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Aging; Blood Glucose; C-Reactive Protein; Calcium; Cardiovascular Diseases; Carotid Artery, Common; Cohort Studies; Coronary Artery Disease; Coronary Vessels; European Continental Ancestry Group; Female; Follow-Up Studies; Genetic Predisposition to Disease; Humans; Hyperlipidemia, Familial Combined; Insulin; Interleukin-6; Linkage Disequilibrium; Lipids; Male; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States; Upstream Stimulatory Factors

Association of gene variants with incident myocardial infarction in the Cardiovascular Health Study. - Shiffman, Dov; O'Meara, Ellen S; Bare, Lance A; Rowland, Charles M; Louie, Judy Z; Arellano, Andre R; Lumley, Thomas; Rice, Kenneth; Iakoubova, Olga; Luke, May M; Young, Bradford A; Malloy, Mary J; et al. (Arterioscler Thromb Vasc Biol, 2008)
OBJECTIVE: We asked whether single nucleotide polymorphisms (SNPs) that had been nominally associated with cardiovascular disease in antecedent studies were also associated with cardiovascular disease in a population-based prospective study of 4522 individuals aged 65 or older. METHODS AND RESULTS: Based on antecedent studies, we prespecified a risk allele and an inheritance model for each of 74 SNPs. We then tested the association of these SNPs with myocardial infarction (MI) in the Cardiovascular Health Study (CHS). The prespecified risk alleles of 8 SNPs were nominally associated (1-sided P<0.05) with increased risk of MI in White CHS participants. The false discovery rate for these 8 was 0.43, suggesting that about 4 of these 8 are likely to be true positives. The 4 of these 8 SNPs that had the strongest evidence for association with cardiovascular disease before testing in CHS (association in 3 antecedent studies) were in KIF6 (CHS HR=1.29; 90%CI 1.1 to 1.52), VAMP8 (HR=1.2; 90%CI 1.02 to 1.41), TAS2R50 (HR=1.13; 90%CI 1 to 1.27), and LPA (HR=1.62; 90%CI 1.09 to 2.42). CONCLUSIONS: Although most of the SNPs investigated were not associated with MI in CHS, evidence from this investigation combined with previous studies suggests that 4 of these SNPs are likely associated with MI.
Keywords: African Americans; Aged; Aged, 80 and over; Coronary Disease; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Humans; Longitudinal Studies; Male; Myocardial Infarction; National Heart, Lung, and Blood Institute (U.S.); Polymorphism, Single Nucleotide; Proportional Hazards Models; United States

Associations between common fibrinogen gene polymorphisms and cardiovascular disease in older adults. The Cardiovascular Health Study. - Carty, Cara L; Cushman, Mary; Jones, Daniel; Lange, Leslie A; Hindorff, Lucia A; Rice, Kenneth; Jenny, Nancy S; Durda, J Peter; Walston, Jeremy; Carlson, Christopher S; Nickerson, Debbie; Tracy, Russell P; et al. (Thromb Haemost, 2008)
Elevated plasma fibrinogen is a risk factor for cardiovascular disease (CVD), but associations between fibrinogen single nucleotide polymorphisms (SNPs) and disease risk are inconsistent. We investigated whether common (> or = 5% minor allele frequency) variation in the fibrinogen genes (FGA, FGB, FGG) is associated with fibrinogen concentration, carotid artery intima-medial thickness (IMT) and risk of incident myocardial infarction (MI), ischemic stroke and CVD mortality in European- (EA) and African-descent (AA) adults (> or = 65 years) from the Cardiovascular Health Study. TagSNPs were genotyped in 3,969 EA and 719 AA free of MI or stroke at baseline. Race-specific models included multiple testing correction and adjustment for sex, age and site. Among EA, minor alleles of FGA3807, FGB1437 and FGG902 were associated with higher fibrinogen levels; whereas FGA251, FGA2224, FGA6534 and FGG10034 were associated with lower levels, p<0.004 for each. Strongest associations were seen for FGB1437; each additional copy of the minor allele was associated with 13 mg/dl (95%CI: 9-16) higher fibrinogen level. Similar trends in AA were not significant. Fibrinogen haplotypes were not significantly associated with internal or common carotid IMT. No associations with MI or CVD mortality were seen in EA, though FGB1038 and FGG902 were significantly associated with increased and decreased risk of stroke in men, respectively, as were related haplotypes. FGB1038 was also associated with CVD mortality in AA, HR = 1.9 (95%CI: 1.3-2.7). In conclusion, while fibrinogen genetic variation was strongly associated with fibrinogen levels, there was less evidence of association with the more complex outcomes of IMT and CVD events.
Keywords: African Americans; Age Factors; Aged; Brain Ischemia; Cardiovascular Diseases; Carotid Artery Diseases; European Continental Ancestry Group; Female; Fibrinogen; Gene Frequency; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Myocardial Infarction; Polymorphism, Single Nucleotide; Population Surveillance; Proportional Hazards Models; Prospective Studies; Reproducibility of Results; Risk Assessment; Risk Factors; Sex Factors; Stroke; United States

Biomarkers of Inflammation and MRI-Defined Small Vessel Disease of the Brain: The Cardiovascular Health Study. - Fornage, Myriam; Chiang, Y Aron; O'Meara, Ellen S; Psaty, Bruce M; Reiner, Alexander P; Siscovick, David S; Tracy, Russell P; Longstreth, W T (Stroke, 2008)
BACKGROUND AND PURPOSE: To clarify the role of inflammation in the pathogenesis of small vessel disease of the brain, we investigated the association between common variation in the C-reactive protein (CRP) and interleukin (IL)-6 genes, plasma CRP and IL6 levels, and presence of MRI-defined white matter lesions (WML) and brain infarcts (BI) in elderly participants of the Cardiovascular Health Study. METHODS: Tag single nucleotide polymorphisms (SNPs) in the CRP and IL6 genes were selected from the SeattleSNPs database. In cross-sectional analyses, logistic regression models adjusting for known cardiovascular disease risk factors were constructed to assess the associations of plasma CRP and IL6 levels and common CRP and IL6 gene haplotypes with presence of WML or BI in Blacks (n=532) and Whites (n=2905). RESULTS: Plasma IL6 and CRP levels were associated with presence of WML and BI in both races. In Whites, common haplotypes of the IL6 gene were significantly associated with WML and BI. The common haplotype tagged by the -174G/C promoter polymorphism was associated with an increased risk of WML (OR=1.14; 95% CI: [1.02; 1.28]). The common haplotype tagged by the -572G/C promoter polymorphism was associated with an increased risk of BI (OR=1.57; 95% CI: [1.15; 2.14]). Significant associations were lacking for WML or BI with IL6 gene variation in Blacks, or with CRP gene variation in either race. CONCLUSIONS: This study provides evidence of a genetic basis underlying the relationship between plasma biomarkers of inflammation and small vessel disease of the brain. Further studies to elucidate the specific role of IL6 in disease pathogenesis are warranted.
Keywords: African Continental Ancestry Group; Aged; Biomarkers; Brain Infarction; C-Reactive Protein; Cohort Studies; European Continental Ancestry Group; Female; Haplotypes; Humans; Inflammation; Interleukin-6; Magnetic Resonance Imaging; Male; Polymorphism, Single Nucleotide

Common genetic variants associated with plasma fibrin D-dimer concentration in older European- and African-American adults. - Lange, L A; Reiner, A P; Carty, C L; Jenny, N S; Cushman, M; Lange, E M (J Thromb Haemost, 2008)
BACKGROUND AND OBJECTIVES: D-dimer is a hemostasis marker that reflects ongoing fibrin formation and degradation. There is significant inter-individual and inter-population variability in D-dimer concentration, but whether genetic factors underlie these differences is largely unknown. We hypothesized that common coagulation gene variants contribute to differences in circulating D-dimer concentration. METHODS: The setting was European-American (EA; n = 1858) and African-American (AA; n = 327) unrelated older adults from the Cardiovascular Health Study (CHS), in which we genotyped SNPs in 42 genes related to blood coagulation and fibrinolysis. RESULTS: Several fibrinogen gene polymorphisms, including the Thr312Ala Aalpha chain variant and the FGG-10034 C/T variant, were associated with approximately 20% higher plasma D-dimer levels in EA (false discovery rate < 5% for covariate-adjusted model). There was also some evidence that a Pro41Leu variant of the PLAU gene encoding urinary plasminogen activator and non-coding polymorphism of the plasminogen activator inhibitor type 1 gene (SERPINE1) were associated with higher plasma D-dimer in EA. There were no significant associations between the studied coagulation or fibrinolysis gene SNPs and plasma D-dimer levels in the smaller AA sample. However, each standard deviation increase in European ancestry assessed by ancestry-informative gene markers was associated with approximately 10% lower mean D-dimer levels in AA. CONCLUSIONS: Together, common coagulation/fibrinolysis gene SNPs explained only approximately 2% of the variance in plasma D-dimer levels in EA. These findings suggest that the association of D-dimer with risk of vascular outcomes may be mediated largely by environmental factors, other genes, and/or genetic interactions.
Keywords: Africa; African Americans; Aged; Aged, 80 and over; Blood Coagulation; Europe; European Continental Ancestry Group; Female; Fibrin Fibrinogen Degradation Products; Fibrinogen; Fibrinolysis; Genotype; Humans; Male; Middle Aged; Plasminogen Activator Inhibitor 1; Polymorphism, Single Nucleotide; Prospective Studies; United States; Urokinase-Type Plasminogen Activator

Common variants in the CRP gene in relation to longevity and cause-specific mortality in older adults: the Cardiovascular Health Study. - Hindorff, Lucia A; Rice, Kenneth M; Lange, Leslie A; Diehr, Paula; Halder, Indrani; Walston, Jeremy; Kwok, Pui; Ziv, Elad; Nievergelt, Caroline; Cummings, Steven R; Newman, Anne B; Tracy, Russell P; et al. (Atherosclerosis, 2008)
Common polymorphisms in the CRP gene are associated with plasma CRP levels in population-based studies, but associations with age-related events are uncertain. A previous study of CRP haplotypes in older adults was broadened to include longevity and cause-specific mortality (all-cause, noncardiovascular (non-CV), and cardiovascular (CV)). Common haplotypes were inferred from four tagSNPs in 4512 whites and five tagSNPs in 812 blacks from the Cardiovascular Health Study, a longitudinal cohort of adults over age 65. Exploratory analyses addressed early versus late mortality. CRP haplotypes were not associated with all-cause mortality or longevity overall in either population, but associations with all-cause mortality differed during early and late periods. In blacks, the haplotype tagged by 3872A (rs1205) was associated with increased risk of non-CV mortality, relative to other haplotypes (adjusted hazard ratio for each additional copy: 1.42, 95% CI: 1.07, 1.87). Relative to other haplotypes, this haplotype was associated with decreased risk of early but not decreased risk of late CV mortality in blacks; among whites, a haplotype tagged by 2667C (rs1800947) gave similar but nonsignificant findings. If confirmed, CRP genetic variants may be weakly associated with CV and non-CV mortality in older adults, particularly in self-identified blacks.
Keywords: African Americans; Aged; C-Reactive Protein; Cardiovascular Diseases; Cause of Death; Cohort Studies; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Linear Models; Longevity; Male; Polymorphism, Single Nucleotide; Proportional Hazards Models; United States

Polymorphisms of the HNF1A gene encoding hepatocyte nuclear factor-1 alpha are associated with C-reactive protein. - Reiner, Alexander P; Barber, Mathew J; Guan, Yongtao; Ridker, Paul M; Lange, Leslie A; Chasman, Daniel I; Walston, Jeremy D; Cooper, Gregory M; Jenny, Nancy S; Rieder, Mark J; Durda, J Peter; Smith, Joshua D; et al. (Am J Hum Genet, 2008)
Data from the Pharmacogenomics and Risk of Cardiovascular Disease (PARC) study and the Cardiovascular Health Study (CHS) provide independent and confirmatory evidence for association between common polymorphisms of the HNF1A gene encoding hepatocyte nuclear factor-1 alpha and plasma C-reactive protein (CRP) concentration. Analyses with the use of imputation-based methods to combine genotype data from both studies and to test untyped SNPs from the HapMap database identified several SNPs within a 5 kb region of HNF1A intron 1 with the strongest evidence of association with CRP phenotype.
Keywords: Aged; Bayes Theorem; C-Reactive Protein; Female; Hepatocyte Nuclear Factor 1-alpha; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Polymorphism, Single Nucleotide; Pravastatin; Simvastatin

Association of common genetic variation in the insulin/IGF1 signaling pathway with human longevity. - Pawlikowska, Ludmila; Hu, Donglei; Huntsman, Scott; Sung, Andrew; Chu, Catherine; Chen, Justin; Joyner, Alexander H; Schork, Nicholas J; Hsueh, Wen-Chi; Reiner, Alexander P; Psaty, Bruce M; Atzmon, Gil; et al. (Aging Cell, 2009)
The insulin/IGF1 signaling pathways affect lifespan in several model organisms, including worms, flies and mice. To investigate whether common genetic variation in this pathway influences lifespan in humans, we genotyped 291 common variants in 30 genes encoding proteins in the insulin/IGF1 signaling pathway in a cohort of elderly Caucasian women selected from the Study of Osteoporotic Fractures (SOF). The cohort included 293 long-lived cases (lifespan > or = 92 years (y), mean +/- standard deviation (SD) = 95.3 +/- 2.2y) and 603 average-lifespan controls (lifespan < or = 79y, mean = 75.7 +/- 2.6y). Variants were selected for genotyping using a haplotype-tagging approach. We found a modest excess of variants nominally associated with longevity. Nominally significant variants were then replicated in two additional Caucasian cohorts including both males and females: the Cardiovascular Health Study and Ashkenazi Jewish Centenarians. An intronic single nucleotide polymorphism in AKT1, rs3803304, was significantly associated with lifespan in a meta-analysis across the three cohorts (OR = 0.78 95%CI = 0.68-0.89, adjusted P = 0.043); two intronic single nucleotide polymorphisms in FOXO3A demonstrated a significant lifespan association among women only (rs1935949, OR = 1.35, 95%CI = 1.15-1.57, adjusted P = 0.0093). These results demonstrate that common variants in several genes in the insulin/IGF1 pathway are associated with human lifespan.
Keywords: Aged; Aged, 80 and over; Female; Follow-Up Studies; Forkhead Box Protein O3; Forkhead Transcription Factors; Genome, Human; Genotype; Humans; Insulin; Insulin-Like Growth Factor I; Longevity; Male; Osteoporosis; Polymorphism, Single Nucleotide; Proto-Oncogene Proteins c-akt; Signal Transduction

Association of genetic variation in serum amyloid-A with cardiovascular disease and interactions with IL6, IL1RN, IL1beta and TNF genes in the Cardiovascular Health Study. - Carty, Cara L; Heagerty, Patrick; Heckbert, Susan R; Enquobahrie, Daniel A; Jarvik, Gail P; Davis, Scott; Tracy, Russell P; Reiner, Alexander P (J Atheroscler Thromb, 2009)
AIM: Since inflammation is an important contributor to atherosclerosis, gene variants mediating inflammation are of interest. We investigated gene variants in acute phase serum amyloid-A (SAA), a sensitive indicator of inflammatory activity, and their associations with cardiovascular disease (CVD) and HDL cholesterol. Interaction of the SAA genes with genetic variants of their regulators, IL-1, IL-6 and TNF-alpha in influencing CVD was also explored. METHODS: SNPs characterizing common variation in the SAA1 and SAA2 genes were genotyped in European-(EA) and African-American (AA) participants (n=3969 and n=719) of the Cardiovascular Health Study. Using linear and Cox proportional hazards regression, we assessed associations of SNPs with baseline carotid artery intima-media thickness (cIMT) and risk of incident myocardial infarction, ischemic stroke, total CVD events or mortality during 14 years of follow-up. RESULTS: No associations between SAA SNPs and outcomes were observed in EA, with the exception of total CVD events; each rs4638289 minor allele was associated with an increased risk in obese individuals, HR=1.2 (95%CI: 0.981.4; p=0.086) and decreased risk among non-obese, HR=0.9 (95%CI: 0.80.99; p=0.026). In AA, we observed modest associations between SAA SNPs and cIMT, potentially modified by HDL. SAA SNPs were also associated with lower HDL in EA and AA. Suggestive gene-gene interaction findings for cIMT in AA and CVD mortality in EA were not significant in subsequent model selection tests. CONCLUSION: Associations of SAA SNPs with cIMT, HDL and total CVD events were identified, unadjusted for multiple testing. These findings should be regarded as hypothesis-generating until confirmed by other studies.
Keywords: Aged; Cardiovascular Diseases; Cholesterol, HDL; Cytokines; Female; Gene Regulatory Networks; Humans; Inflammation Mediators; Interleukin 1 Receptor Antagonist Protein; Interleukin-1beta; Interleukin-6; Male; Polymorphism, Single Nucleotide; Proportional Hazards Models; Serum Amyloid A Protein; Tumor Necrosis Factor-alpha; Tunica Intima

Association of novel genetic Loci with circulating fibrinogen levels: a genome-wide association study in 6 population-based cohorts. - Dehghan, Abbas; Yang, Qiong; Peters, Annette; Basu, Saonli; Bis, Joshua C; Rudnicka, Alicja R; Kavousi, Maryam; Chen, Ming-Huei; Baumert, Jens; Lowe, Gordon D O; McKnight, Barbara; Tang, Weihong; et al. (Circ Cardiovasc Genet, 2009)
BACKGROUND: Fibrinogen is both central to blood coagulation and an acute-phase reactant. We aimed to identify common variants influencing circulation fibrinogen levels. METHODS AND RESULTS: We conducted a genome-wide association analysis on 6 population-based studies, the Rotterdam Study, the Framingham Heart Study, the Cardiovascular Health Study, the Atherosclerosis Risk in Communities Study, the Monitoring of Trends and Determinants in Cardiovascular Disease/KORA Augsburg Study, and the British 1958 Birth Cohort Study, including 22 096 participants of European ancestry. Four loci were marked by 1 or more single-nucleotide polymorphisms that demonstrated genome-wide significance (P<5.0 x 10(-8)). These included a single-nucleotide polymorphism located in the fibrinogen beta chain (FGB) gene and 3 single-nucleotide polymorphisms representing newly identified loci. The high-signal single-nucleotide polymorphisms were rs1800789 in exon 7 of FGB (P=1.8 x 10(-30)), rs2522056 downstream from the interferon regulatory factor 1 (IRF1) gene (P=1.3 x 10(-15)), rs511154 within intron 1 of the propionyl coenzyme A carboxylase (PCCB) gene (P=5.9 x 10(-10)), and rs1539019 on the NLR family pyrin domain containing 3 isoforms (NLRP3) gene (P=1.04 x 10(-8)). CONCLUSIONS: Our findings highlight biological pathways that may be important in regulation of inflammation underlying cardiovascular disease.
Keywords: Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; Genetic Loci; Genome-Wide Association Study; Humans; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Young Adult

Common coding variants of the HNF1A gene are associated with multiple cardiovascular risk phenotypes in community-based samples of younger and older European-American adults: the Coronary Artery Risk Development in Young Adults Study and The Cardiovascula - Reiner, Alexander P; Gross, Myron D; Carlson, Christopher S; Bielinski, Suzette J; Lange, Leslie A; Fornage, Myriam; Jenny, Nancy S; Walston, Jeremy; Tracy, Russell P; Williams, O Dale; Jacobs, David R; Nickerson, Deborah A (Circ Cardiovasc Genet, 2009)
BACKGROUND: The transcription factor hepatocyte nuclear factor (HNF)-1 alpha regulates the activity of a number of genes involved in innate immunity, blood coagulation, lipid and glucose transport and metabolism, and cellular detoxification. Common polymorphisms of the HNF-1 alpha gene (HNF1A) were recently associated with plasma C-reactive protein and gamma-glutamyl transferase concentration in middle-aged to older European Americans (EA). METHODS AND RESULTS: We assessed whether common variants of HNF1A are associated with C-reactive protein, gamma-glutamyl transferase, and other atherosclerotic and metabolic risk factors, in the large, population-based Coronary Artery Risk Development in Young Adults Study of healthy young EA (n=2154) and African American (AA; n=2083) adults. The minor alleles of Ile27Leu (rs1169288) and Ser486Asn (rs2464196) were associated with 0.10 to 0.15 standard deviation units lower C-reactive protein and gamma-glutamyl transferase levels in EA. The same HNF1A coding variants were associated with higher low-density lipoprotein cholesterol, apolipoprotein B, creatinine, and fibrinogen in EA. We replicated the associations between HNF1A coding variants and C-reactive protein, fibrinogen, low-density lipoprotein cholesterol, and renal function in a second population-based sample of EA adults 65 years and older from the Cardiovascular Health Study. The HNF1A Ser486Asn and/or Ile27Leu variants were also associated with increased risk of subclinical coronary atherosclerosis in Coronary Artery Risk Development in Young Adults and with incident coronary heart disease in Cardiovascular Health Study. The Ile27Leu and Ser486Asn variants were 3-fold less common in AA than in EA. There was little evidence of association between HNF1A genotype and atherosclerosis-related phenotypes in AA. CONCLUSIONS: Common polymorphisms of HNF1A seem to influence multiple phenotypes related to cardiovascular risk in the general population of younger and older EA adults.
Keywords: Adolescent; Adult; African Americans; Aged; Aged, 80 and over; C-Reactive Protein; Cardiovascular Diseases; Cholesterol, LDL; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; gamma-Glutamyltransferase; Genetic Predisposition to Disease; Genotype; Hepatocyte Nuclear Factor 1-alpha; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

Common variants at ten loci influence QT interval duration in the QTGEN Study. - Newton-Cheh, Christopher; Eijgelsheim, Mark; Rice, Kenneth M; de Bakker, Paul I W; Yin, Xiaoyan; Estrada, Karol; Bis, Joshua C; Marciante, Kristin; Rivadeneira, Fernando; Noseworthy, Peter A; Sotoodehnia, Nona; Smith, Nicholas L; et al. (Nat Genet, 2009)
QT interval duration, reflecting myocardial repolarization on the electrocardiogram, is a heritable risk factor for sudden cardiac death and drug-induced arrhythmias. We conducted a meta-analysis of three genome-wide association studies in 13,685 individuals of European ancestry from the Framingham Heart Study, the Rotterdam Study and the Cardiovascular Health Study, as part of the QTGEN consortium. We observed associations at P < 5 x 10(-8) with variants in NOS1AP, KCNQ1, KCNE1, KCNH2 and SCN5A, known to be involved in myocardial repolarization and mendelian long-QT syndromes. Associations were found at five newly identified loci, including 16q21 near NDRG4 and GINS3, 6q22 near PLN, 1p36 near RNF207, 16p13 near LITAF and 17q12 near LIG3 and RFFL. Collectively, the 14 independent variants at these 10 loci explain 5.4-6.5% of the variation in QT interval. These results, together with an accompanying paper, offer insights into myocardial repolarization and suggest candidate genes that could predispose to sudden cardiac death and drug-induced arrhythmias.
Keywords: Adaptor Proteins, Signal Transducing; Adult; Aged; Arrhythmias, Cardiac; Chromosome Mapping; Death, Sudden, Cardiac; Electroencephalography; ERG1 Potassium Channel; Ether-A-Go-Go Potassium Channels; European Continental Ancestry Group; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; Humans; KCNQ1 Potassium Channel; Meta-Analysis as Topic; Muscle Proteins; NAV1.5 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Potassium Channels, Voltage-Gated; Risk Factors; Sodium Channels

C-reactive protein, interleukin-6, and prostate cancer risk in men aged 65 years and older. - Pierce, Brandon L; Biggs, Mary L; DeCambre, Marvalyn; Reiner, Alexander P; Li, Christopher; Fitzpatrick, Annette; Carlson, Christopher S; Stanford, Janet L; Austin, Melissa A (Cancer Causes Control, 2009)
Inflammation is believed to play a role in prostate cancer (PCa) etiology, but it is unclear whether inflammatory markers C-reactive protein (CRP) and interleukin-6 (IL-6) associate with PCa risk in older men. Using Cox regression, we assessed the relationship between baseline concentrations of CRP and IL-6 and the subsequent PCa risk in the Cardiovascular Health Study, a population-based cohort study of mostly European American men of ages >64 years (n = 2,234; mean follow-up = 8.7 years; 215 incident PCa cases). We also tested associations between CRP and IL-6 tagSNPs and PCa risk, focusing on SNPs that are known to associate with circulating CRP and/or IL-6. Neither CRP nor IL-6 blood concentrations was associated with PCa risk. The C allele of IL-6 SNP rs1800795 (-174), a known functional variant, was associated with increased risk in a dominant model (HR = 1.44; 95% CI = 1.03-2.01; p = 0.03), but was not statistically significant after accounting for multiple tests (permutation p = 0.21). Our results suggest that circulating CRP and IL-6 do not influence PCa risk. SNPs at the CRP locus are not associated with PCa risk in this cohort, while the association between rs1800795 and PCa risk warrants further investigation.
Keywords: African Americans; Aged; Aged, 80 and over; Biomarkers; C-Reactive Protein; European Continental Ancestry Group; Humans; Inflammation; Interleukin-6; Male; Polymorphism, Single Nucleotide; Prospective Studies; Prostatic Neoplasms; Risk Factors

Gene variants associated with ischemic stroke: the cardiovascular health study. - Luke, May M; O'Meara, Ellen S; Rowland, Charles M; Shiffman, Dov; Bare, Lance A; Arellano, Andre R; Longstreth, W T; Lumley, Thomas; Rice, Kenneth; Tracy, Russell P; Devlin, James J; Psaty, Bruce M (Stroke, 2009)
BACKGROUND AND PURPOSE: The purpose of this study was to determine whether 74 single nucleotide polymorphisms (SNPs), which had been associated with coronary heart disease, are associated with incident ischemic stroke. METHODS: Based on antecedent studies of coronary heart disease, we prespecified the risk allele for each of the 74 SNPs. We used Cox proportional hazards models that adjusted for traditional risk factors to estimate the associations of these SNPs with incident ischemic stroke during 14 years of follow-up in a population-based study of older adults: the Cardiovascular Health Study (CHS). RESULTS: In white CHS participants, the prespecified risk alleles of 7 of the 74 SNPs (in HPS1, ITGAE, ABCG2, MYH15, FSTL4, CALM1, and BAT2) were nominally associated with increased risk of stroke (one-sided P<0.05, false discovery rate=0.42). In black participants, the prespecified risk alleles of 5 SNPs (in KRT4, LY6G5B, EDG1, DMXL2, and ABCG2) were nominally associated with stroke (one-sided P<0.05, false discovery rate=0.55). The Val12Met SNP in ABCG2 was associated with stroke in both white (hazard ratio, 1.46; 90% CI, 1.05 to 2.03) and black (hazard ratio, 3.59; 90% CI, 1.11 to 11.6) participants of CHS. Kaplan-Meier estimates of the 10-year cumulative incidence of stroke were greater among Val allele homozygotes than among Met allele carriers in both white (10% versus 6%) and black (12% versus 3%) participants of CHS. CONCLUSIONS: The Val12Met SNP in ABCG2 (encoding a transporter of sterols and xenobiotics) was associated with incident ischemic stroke in white and black participants of CHS.
Keywords: African Continental Ancestry Group; Aged; Alleles; Brain Ischemia; Cardiovascular Diseases; Coronary Disease; Ethnic Groups; European Continental Ancestry Group; Female; Gene Frequency; Genetic Variation; Humans; Kaplan-Meier Estimate; Male; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Stroke; United States

Genetic variants associated with cardiac structure and function: a meta-analysis and replication of genome-wide association data. - Vasan, Ramachandran S; Glazer, Nicole L; Felix, Janine F; Lieb, Wolfgang; Wild, Philipp S; Felix, Stephan B; Watzinger, Norbert; Larson, Martin G; Smith, Nicholas L; Dehghan, Abbas; Grosshennig, Anika; Schillert, Arne; et al. (JAMA, 2009)
CONTEXT: Echocardiographic measures of left ventricular (LV) structure and function are heritable phenotypes of cardiovascular disease. OBJECTIVE: To identify common genetic variants associated with cardiac structure and function by conducting a meta-analysis of genome-wide association data in 5 population-based cohort studies (stage 1) with replication (stage 2) in 2 other community-based samples. DESIGN, SETTING, AND PARTICIPANTS: Within each of 5 community-based cohorts comprising the EchoGen consortium (stage 1; n = 12 612 individuals of European ancestry; 55% women, aged 26-95 years; examinations between 1978-2008), we estimated the association between approximately 2.5 million single-nucleotide polymorphisms (SNPs; imputed to the HapMap CEU panel) and echocardiographic traits. In stage 2, SNPs significantly associated with traits in stage 1 were tested for association in 2 other cohorts (n = 4094 people of European ancestry). Using a prespecified P value threshold of 5 x 10(-7) to indicate genome-wide significance, we performed an inverse variance-weighted fixed-effects meta-analysis of genome-wide association data from each cohort. MAIN OUTCOME MEASURES: Echocardiographic traits: LV mass, internal dimensions, wall thickness, systolic dysfunction, aortic root, and left atrial size. RESULTS: In stage 1, 16 genetic loci were associated with 5 echocardiographic traits: 1 each with LV internal dimensions and systolic dysfunction, 3 each with LV mass and wall thickness, and 8 with aortic root size. In stage 2, 5 loci replicated (6q22 locus associated with LV diastolic dimensions, explaining <1% of trait variance; 5q23, 12p12, 12q14, and 17p13 associated with aortic root size, explaining 1%-3% of trait variance). CONCLUSIONS: We identified 5 genetic loci harboring common variants that were associated with variation in LV diastolic dimensions and aortic root size, but such findings explained a very small proportion of variance. Further studies are required to replicate these findings, identify the causal variants at or near these loci, characterize their functional significance, and determine whether they are related to overt cardiovascular disease.
Keywords: Adult; Aged; Aged, 80 and over; Aorta; Cardiovascular Diseases; Echocardiography; European Continental Ancestry Group; Female; Genome-Wide Association Study; Genotype; Heart Atria; Heart Ventricles; Humans; Male; Middle Aged; Organ Size; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; Ventricular Dysfunction, Left; Ventricular Function, Left

Genetic variations in nitric oxide synthase 1 adaptor protein are associated with sudden cardiac death in US white community-based populations. - Kao, W H Linda; Arking, Dan E; Post, Wendy; Rea, Thomas D; Sotoodehnia, Nona; Prineas, Ronald J; Bishe, Bryan; Doan, Betty Q; Boerwinkle, Eric; Psaty, Bruce M; Tomaselli, Gordon F; Coresh, Josef; et al. (Circulation, 2009)
BACKGROUND: The ECG QT interval is associated with risk of sudden cardiac death (SCD). A previous genome-wide association study demonstrated that allelic variants (rs10494366 and rs4657139) in the nitric oxide synthase 1 adaptor protein (NOS1AP), which encodes a carboxy-terminal PDZ ligand of neuronal nitric oxide synthase, are associated with the QT interval in white adults. The present analysis was conducted to validate the association between NOS1AP variants and the QT interval and to examine the association with SCD in a combined population of 19 295 black and white adults from the Atherosclerosis Risk In Communities Study and the Cardiovascular Health Study. METHODS AND RESULTS: We examined 19 tagging single-nucleotide polymorphisms in the genomic blocks containing rs10494366 and rs4657139 in NOS1AP. SCD was defined as a sudden pulseless condition of cardiac origin in a previously stable individual. General linear models and Cox proportional hazards regression models were used. Multiple single-nucleotide polymorphisms in NOS1AP, including rs10494366, rs4657139, and rs16847548, were significantly associated with adjusted QT interval in whites (P<0.0001). In whites, after adjustment for age, sex, and study, the relative hazard of SCD associated with each C allele at rs16847548 was 1.31 (95% confidence interval 1.10 to 1.56, P=0.002), assuming an additive model. In addition, a downstream neighboring single-nucleotide polymorphism, rs12567209, which was not correlated with rs16847548 or QT interval, was also independently associated with SCD in whites (relative hazard 0.57, 95% confidence interval 0.39 to 0.83, P=0.003). Adjustment for QT interval and coronary heart disease risk factors attenuated but did not eliminate the association between rs16847548 and SCD, and such adjustment had no effect on the association between rs12567209 and SCD. No significant associations between tagging single-nucleotide polymorphisms in NOS1AP and either QT interval or SCD were observed in blacks. CONCLUSIONS: In a combined analysis of 2 population-based prospective cohort studies, sequence variations in NOS1AP were associated with baseline QT interval and the risk of SCD in white US adults.
Keywords: Adaptor Proteins, Signal Transducing; Aged; Death, Sudden, Cardiac; Electrocardiography; European Continental Ancestry Group; Genotype; Humans; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Genomewide association studies of stroke. - Ikram, M Arfan; Seshadri, Sudha; Bis, Joshua C; Fornage, Myriam; DeStefano, Anita L; Aulchenko, Yurii S; Debette, Stephanie; Lumley, Thomas; Folsom, Aaron R; van den Herik, Evita G; Bos, Michiel J; Beiser, Alexa; et al. (N Engl J Med, 2009)
BACKGROUND: The genes underlying the risk of stroke in the general population remain undetermined. METHODS: We carried out an analysis of genomewide association data generated from four large cohorts composing the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, including 19,602 white persons (mean [+/-SD] age, 63+/-8 years) in whom 1544 incident strokes (1164 ischemic strokes) developed over an average follow-up of 11 years. We tested the markers most strongly associated with stroke in a replication cohort of 2430 black persons with 215 incident strokes (191 ischemic strokes), another cohort of 574 black persons with 85 incident strokes (68 ischemic strokes), and 652 Dutch persons with ischemic stroke and 3613 unaffected persons. RESULTS: Two intergenic single-nucleotide polymorphisms on chromosome 12p13 and within 11 kb of the gene NINJ2 were associated with stroke (P<5x10(-8)). NINJ2 encodes an adhesion molecule expressed in glia and shows increased expression after nerve injury. Direct genotyping showed that rs12425791 was associated with an increased risk of total (i.e., all types) and ischemic stroke, with hazard ratios of 1.30 (95% confidence interval [CI], 1.19 to 1.42) and 1.33 (95% CI, 1.21 to 1.47), respectively, yielding population attributable risks of 11% and 12% in the discovery cohorts. Corresponding hazard ratios were 1.35 (95% CI, 1.01 to 1.79; P=0.04) and 1.42 (95% CI, 1.06 to 1.91; P=0.02) in the large cohort of black persons and 1.17 (95% CI, 1.01 to 1.37; P=0.03) and 1.19 (95% CI, 1.01 to 1.41; P=0.04) in the Dutch sample; the results of an underpowered analysis of the smaller black cohort were nonsignificant. CONCLUSIONS: A genetic locus on chromosome 12p13 is associated with an increased risk of stroke.
Keywords: African Continental Ancestry Group; Aged; Chromosomes, Human, Pair 12; Cohort Studies; European Continental Ancestry Group; Female; Genetic Markers; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Risk Factors; Stroke

Hypertension genes and retinal vascular calibre: the Cardiovascular Health Study. - Sun, C; Wang, J J; Islam, F M; Heckbert, S R; Klein, R; Siscovick, D S; Klein, B E K; Wong, T Y (J Hum Hypertens, 2009)
We examined the associations of single nucleotide polymorphisms (SNPs) in three candidate hypertension genes, alpha-adducin (ADD1/G460W), beta2-adrenergic receptor (ADRB2/Arg16Gly and Gln27Glu) and G-protein beta3 subunit (GNB3/C825T), with retinal arteriolar calibre (an intermediate marker of chronic hypertension) and venular calibre. Data in 1842 participants (1554 whites and 288 African Americans) aged 69-96 years from the Cardiovascular Health Study with genotype and retinal vascular calibre data were included. A computer-assisted method was used to measure retinal vascular calibre. We analysed four SNPs and multilocus interaction for three genes. All SNPs were in Hardy-Weinberg equilibrium in whites and African Americans. The study had sufficient power to detect 0.5% of the total variance of retinal vascular calibre contributed by each SNP in the total population, except for the GNB3 gene variant. No significant associations between these SNPs in the genes studied and mean retinal arteriolar and venular calibre were found in single-gene or multilocus analysis (for example, age-, gender-, race-adjusted mean retinal arteriolar calibre was similar between participants who were ADD1/460W homozygotes and ADD1/G allele carriers, 166.2 vs 167.7 microm). In conclusion, this study found no evidence of an association of SNPs in candidate hypertension genes studied here with retinal vascular calibre.
Keywords: African Americans; Aged; Aged, 80 and over; Arterioles; Calmodulin-Binding Proteins; European Continental Ancestry Group; Heterotrimeric GTP-Binding Proteins; Humans; Hypertension; Longitudinal Studies; Polymorphism, Single Nucleotide; Receptors, Adrenergic, beta-2; Retinal Vessels

Multiple independent genetic factors at NOS1AP modulate the QT interval in a multi-ethnic population. - Arking, Dan E; Khera, Amit; Xing, Chao; Kao, W H Linda; Post, Wendy; Boerwinkle, Eric; Chakravarti, Aravinda (PLoS One, 2009)
Extremes of electrocardiographic QT interval are associated with increased risk for sudden cardiac death (SCD); thus, identification and characterization of genetic variants that modulate QT interval may elucidate the underlying etiology of SCD. Previous studies have revealed an association between a common genetic variant in NOS1AP and QT interval in populations of European ancestry, but this finding has not been extended to other ethnic populations. We sought to characterize the effects of NOS1AP genetic variants on QT interval in the multi-ethnic population-based Dallas Heart Study (DHS, n = 3,072). The SNP most strongly associated with QT interval in previous samples of European ancestry, rs16847548, was the most strongly associated in White (P = 0.005) and Black (P = 3.6 x 10(-5)) participants, with the same direction of effect in Hispanics (P = 0.17), and further showed a significant SNP x sex-interaction (P = 0.03). A second SNP, rs16856785, uncorrelated with rs16847548, was also associated with QT interval in Blacks (P = 0.01), with qualitatively similar results in Whites and Hispanics. In a previously genotyped cohort of 14,107 White individuals drawn from the combined Atherosclerotic Risk in Communities (ARIC) and Cardiovascular Health Study (CHS) cohorts, we validated both the second locus at rs16856785 (P = 7.63 x 10(-8)), as well as the sex-interaction with rs16847548 (P = 8.68 x 10(-6)). These data extend the association of genetic variants in NOS1AP with QT interval to a Black population, with similar trends, though not statistically significant at P<0.05, in Hispanics. In addition, we identify a strong sex-interaction and the presence of a second independent site within NOS1AP associated with the QT interval. These results highlight the consistent and complex role of NOS1AP genetic variants in modulating QT interval.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Adult; African Americans; Aged; Death, Sudden, Cardiac; Electrocardiography; Ethnic Groups; European Continental Ancestry Group; Female; Genome-Wide Association Study; Heart Diseases; Heart Rate; Hispanic Americans; Humans; Linear Models; Linkage Disequilibrium; Male; Middle Aged; Polymorphism, Single Nucleotide; Sex Factors; Young Adult

Multiple loci associated with indices of renal function and chronic kidney disease. - Köttgen, Anna; Glazer, Nicole L; Dehghan, Abbas; Hwang, Shih-Jen; Katz, Ronit; Li, Man; Yang, Qiong; Gudnason, Vilmundur; Launer, Lenore J; Harris, Tamara B; Smith, Albert V; Arking, Dan E; et al. (Nat Genet, 2009)
Chronic kidney disease (CKD) has a heritable component and is an important global public health problem because of its high prevalence and morbidity. We conducted genome-wide association studies (GWAS) to identify susceptibility loci for glomerular filtration rate, estimated by serum creatinine (eGFRcrea) and cystatin C (eGFRcys), and CKD (eGFRcrea < 60 ml/min/1.73 m(2)) in European-ancestry participants of four population-based cohorts (ARIC, CHS, FHS, RS; n = 19,877; 2,388 CKD cases), and tested for replication in 21,466 participants (1,932 CKD cases). We identified significant SNP associations (P < 5 × 10(-8)) with CKD at the UMOD locus, with eGFRcrea at UMOD, SHROOM3 and GATM-SPATA5L1, and with eGFRcys at CST and STC1. UMOD encodes the most common protein in human urine, Tamm-Horsfall protein, and rare mutations in UMOD cause mendelian forms of kidney disease. Our findings provide new insights into CKD pathogenesis and underscore the importance of common genetic variants influencing renal function and disease.
Keywords: Chromosome Mapping; Cohort Studies; Genetic Variation; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Meta-Analysis as Topic; Mucoproteins; Netherlands; Polymorphism, Single Nucleotide; Prevalence; Uromodulin

Multiple loci influence erythrocyte phenotypes in the CHARGE Consortium. - Ganesh, Santhi K; Zakai, Neil A; van Rooij, Frank J A; Soranzo, Nicole; Smith, Albert V; Nalls, Michael A; Chen, Ming-Huei; Köttgen, Anna; Glazer, Nicole L; Dehghan, Abbas; Kuhnel, Brigitte; Aspelund, Thor; et al. (Nat Genet, 2009)
Measurements of erythrocytes within the blood are important clinical traits and can indicate various hematological disorders. We report here genome-wide association studies (GWAS) for six erythrocyte traits, including hemoglobin concentration (Hb), hematocrit (Hct), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) and red blood cell count (RBC). We performed an initial GWAS in cohorts of the CHARGE Consortium totaling 24,167 individuals of European ancestry and replication in additional independent cohorts of the HaemGen Consortium totaling 9,456 individuals. We identified 23 loci significantly associated with these traits in a meta-analysis of the discovery and replication cohorts (combined P values ranging from 5 x 10(-8) to 7 x 10(-86)). Our findings include loci previously associated with these traits (HBS1L-MYB, HFE, TMPRSS6, TFR2, SPTA1) as well as new associations (EPO, TFRC, SH2B3 and 15 other loci). This study has identified new determinants of erythrocyte traits, offering insight into common variants underlying variation in erythrocyte measures.
Keywords: Blood Pressure; Cell Line; Cohort Studies; Endothelial Cells; Erythrocytes; Gene Expression; Genome, Human; Genome-Wide Association Study; Humans; Hypertension; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

NRXN3 is a novel locus for waist circumference: a genome-wide association study from the CHARGE Consortium. - Heard-Costa, Nancy L; Zillikens, M Carola; Monda, Keri L; Johansson, Asa; Harris, Tamara B; Fu, Mao; Haritunians, Talin; Feitosa, Mary F; Aspelund, Thor; Eiriksdottir, Gudny; Garcia, Melissa; Launer, Lenore J; et al. (PLoS Genet, 2009)
Central abdominal fat is a strong risk factor for diabetes and cardiovascular disease. To identify common variants influencing central abdominal fat, we conducted a two-stage genome-wide association analysis for waist circumference (WC). In total, three loci reached genome-wide significance. In stage 1, 31,373 individuals of Caucasian descent from eight cohort studies confirmed the role of FTO and MC4R and identified one novel locus associated with WC in the neurexin 3 gene [NRXN3 (rs10146997, p = 6.4x10(-7))]. The association with NRXN3 was confirmed in stage 2 by combining stage 1 results with those from 38,641 participants in the GIANT consortium (p = 0.009 in GIANT only, p = 5.3x10(-8) for combined analysis, n = 70,014). Mean WC increase per copy of the G allele was 0.0498 z-score units (0.65 cm). This SNP was also associated with body mass index (BMI) [p = 7.4x10(-6), 0.024 z-score units (0.10 kg/m(2)) per copy of the G allele] and the risk of obesity (odds ratio 1.13, 95% CI 1.07-1.19; p = 3.2x10(-5) per copy of the G allele). The NRXN3 gene has been previously implicated in addiction and reward behavior, lending further evidence that common forms of obesity may be a central nervous system-mediated disorder. Our findings establish that common variants in NRXN3 are associated with WC, BMI, and obesity.
Keywords: Aged; Body Mass Index; Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Obesity; Polymorphism, Single Nucleotide; Waist Circumference

Replication of findings on the association of genetic variation in 24 hemostasis genes and risk of incident venous thrombosis. - Smith, N L; Wiggins, K L; Reiner, A P; Lange, L A; Cushman, M; Heckbert, S R; Lumley, T; Rice, K M; Folsom, A R; Psaty, B M (J Thromb Haemost, 2009)
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Case-Control Studies; Cohort Studies; Female; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Haplotypes; Hemostasis; Humans; Incidence; Male; Menopause; Middle Aged; Polymorphism, Single Nucleotide; Reproducibility of Results; Risk; Thrombophilia; Venous Thrombosis; Young Adult

Variants in ZFHX3 are associated with atrial fibrillation in individuals of European ancestry. - Benjamin, Emelia J; Rice, Kenneth M; Arking, Dan E; Pfeufer, Arne; van Noord, Charlotte; Smith, Albert V; Schnabel, Renate B; Bis, Joshua C; Boerwinkle, Eric; Sinner, Moritz F; Dehghan, Abbas; Lubitz, Steven A; et al. (Nat Genet, 2009)
We conducted meta-analyses of genome-wide association studies for atrial fibrillation (AF) in participants from five community-based cohorts. Meta-analyses of 896 prevalent (15,768 referents) and 2,517 incident (21,337 referents) AF cases identified a new locus for AF (ZFHX3, rs2106261, risk ratio RR = 1.19; P = 2.3 x 10(-7)). We replicated this association in an independent cohort from the German AF Network (odds ratio = 1.44; P = 1.6 x 10(-11); combined RR = 1.25; combined P = 1.8 x 10(-15)).
Keywords: Atrial Fibrillation; Chromosomes, Human, Pair 16; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Homeodomain Proteins; Humans; Meta-Analysis as Topic; Mutation; Polymorphism, Single Nucleotide; Reproducibility of Results

Admixture mapping of ankle-arm index: identification of a candidate locus associated with peripheral arterial disease. - Scherer, M L; Nalls, M A; Pawlikowska, L; Ziv, E; Mitchell, G; Huntsman, S; Hu, D; Sutton-Tyrrell, K; Lakatta, E G; Hsueh, W-C; Newman, A B; Tandon, A; et al. (J Med Genet, 2010)
BACKGROUND: Peripheral arterial disease (PAD) is associated with significant morbidity and mortality, and has a higher prevalence in African Americans than Caucasians. Ankle-arm index (AAI) is the ratio of systolic blood pressure in the leg to that in the arm, and, when low, is a marker of PAD. METHODS: The authors used an admixture mapping approach to search for genetic loci associated with low AAI. Using data from 1040 African American participants in the observational, population based Health, Aging, and Body Composition Study who were genotyped at 1322 single nucleotide polymorphisms (SNPs) that are informative for African versus European ancestry and span the entire genome, we estimated genetic ancestry in each chromosomal region and then tested the association between AAI and genetic ancestry at each locus. RESULTS: The authors found a region of chromosome 11 that reaches its peak between 80 and 82 Mb associated with low AAI (p<0.001 for rs12289502 and rs9665943, both within this region). 753 African American participants in the observational, population based Cardiovascular Health Study were genotyped at rs9665943 to test the reproducibility of this association, and this association was also statistically significant (odds ratio (OR) for homozygous African genotype 1.59, 95% confidence interval (CI) 1.12 to 2.27). Another candidate SNP (rs1042602) in the same genomic region was tested in both populations, and was also found to be significantly associated with low AAI in both populations (OR for homozygous African genotype 1.89, 95% CI 1.29 to 2.76). CONCLUSION: This study identifies a novel region of chromosome 11 representing an area with a potential candidate gene associated with PAD in African Americans.
Keywords: African Americans; Aged; Ankle Brachial Index; Chromosome Mapping; Chromosomes, Human, Pair 11; Female; Genetic Loci; Genotype; Humans; Male; Odds Ratio; Peripheral Vascular Diseases; Polymorphism, Single Nucleotide

Association analyses of 249,796 individuals reveal 18 new loci associated with body mass index. - Speliotes, Elizabeth K; Willer, Cristen J; Berndt, Sonja I; Monda, Keri L; Thorleifsson, Gudmar; Jackson, Anne U; Lango Allen, Hana; Lindgren, Cecilia M; Luan, Jian'an; Mägi, Reedik; Randall, Joshua C; Vedantam, Sailaja; et al. (Nat Genet, 2010)
Obesity is globally prevalent and highly heritable, but its underlying genetic factors remain largely elusive. To identify genetic loci for obesity susceptibility, we examined associations between body mass index and ∼ 2.8 million SNPs in up to 123,865 individuals with targeted follow up of 42 SNPs in up to 125,931 additional individuals. We confirmed 14 known obesity susceptibility loci and identified 18 new loci associated with body mass index (P < 5 × 10⁻⁸), one of which includes a copy number variant near GPRC5B. Some loci (at MC4R, POMC, SH2B1 and BDNF) map near key hypothalamic regulators of energy balance, and one of these loci is near GIPR, an incretin receptor. Furthermore, genes in other newly associated loci may provide new insights into human body weight regulation.
Keywords: Body Height; Body Mass Index; Body Size; Body Weight; Chromosome Mapping; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Obesity; Polymorphism, Single Nucleotide

Association of genome-wide variation with the risk of incident heart failure in adults of European and African ancestry: a prospective meta-analysis from the cohorts for heart and aging research in genomic epidemiology (CHARGE) consortium. - Smith, Nicholas L; Felix, Janine F; Morrison, Alanna C; Demissie, Serkalem; Glazer, Nicole L; Loehr, Laura R; Cupples, L Adrienne; Dehghan, Abbas; Lumley, Thomas; Rosamond, Wayne D; Lieb, Wolfgang; Rivadeneira, Fernando; et al. (Circ Cardiovasc Genet, 2010)
BACKGROUND: Although genetic factors contribute to the onset of heart failure (HF), no large-scale genome-wide investigation of HF risk has been published to date. We have investigated the association of 2,478,304 single-nucleotide polymorphisms with incident HF by meta-analyzing data from 4 community-based prospective cohorts: the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study. METHODS AND RESULTS: Eligible participants for these analyses were of European or African ancestry and free of clinical HF at baseline. Each study independently conducted genome-wide scans and imputed data to the approximately 2.5 million single-nucleotide polymorphisms in HapMap. Within each study, Cox proportional hazards regression models provided age- and sex-adjusted estimates of the association between each variant and time to incident HF. Fixed-effect meta-analyses combined results for each single-nucleotide polymorphism from the 4 cohorts to produce an overall association estimate and P value. A genome-wide significance P value threshold was set a priori at 5.0x10(-7). During a mean follow-up of 11.5 years, 2526 incident HF events (12%) occurred in 20 926 European-ancestry participants. The meta-analysis identified a genome-wide significant locus at chromosomal position 15q22 (1.4x10(-8)), which was 58.8 kb from USP3. Among 2895 African-ancestry participants, 466 incident HF events (16%) occurred during a mean follow-up of 13.7 years. One genome-wide significant locus was identified at 12q14 (6.7x10(-8)), which was 6.3 kb from LRIG3. CONCLUSIONS: We identified 2 loci that were associated with incident HF and exceeded genome-wide significance. The findings merit replication in other community-based settings of incident HF.
Keywords: African Americans; Aged; Aged, 80 and over; Cohort Studies; Endopeptidases; European Continental Ancestry Group; Female; Genome-Wide Association Study; Heart Failure; Humans; Incidence; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk; Ubiquitin-Specific Proteases

Bayesian methods for meta-analysis of causal relationships estimated using genetic instrumental variables. - Burgess, Stephen; Thompson, Simon G; Burgess, S; Thompson, S G; Andrews, G; Samani, N J; Hall, A; Whincup, P; Morris, R; Lawlor, D A; Davey Smith, G; Timpson, N; et al. (Stat Med, 2010)
Genetic markers can be used as instrumental variables, in an analogous way to randomization in a clinical trial, to estimate the causal relationship between a phenotype and an outcome variable. Our purpose is to extend the existing methods for such Mendelian randomization studies to the context of multiple genetic markers measured in multiple studies, based on the analysis of individual participant data. First, for a single genetic marker in one study, we show that the usual ratio of coefficients approach can be reformulated as a regression with heterogeneous error in the explanatory variable. This can be implemented using a Bayesian approach, which is next extended to include multiple genetic markers. We then propose a hierarchical model for undertaking a meta-analysis of multiple studies, in which it is not necessary that the same genetic markers are measured in each study. This provides an overall estimate of the causal relationship between the phenotype and the outcome, and an assessment of its heterogeneity across studies. As an example, we estimate the causal relationship of blood concentrations of C-reactive protein on fibrinogen levels using data from 11 studies. These methods provide a flexible framework for efficient estimation of causal relationships derived from multiple studies. Issues discussed include weak instrument bias, analysis of binary outcome data such as disease risk, missing genetic data, and the use of haplotypes.
Keywords: Bayes Theorem; Biostatistics; C-Reactive Protein; Fibrinogen; Genetic Markers; Humans; Meta-Analysis as Topic; Models, Statistical; Phenotype; Polymorphism, Single Nucleotide

Biological, clinical and population relevance of 95 loci for blood lipids. - Teslovich, Tanya M; Musunuru, Kiran; Smith, Albert V; Edmondson, Andrew C; Stylianou, Ioannis M; Koseki, Masahiro; Pirruccello, James P; Ripatti, Samuli; Chasman, Daniel I; Willer, Cristen J; Johansen, Christopher T; Fouchier, Sigrid W; et al. (Nature, 2010)
Plasma concentrations of total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol and triglycerides are among the most important risk factors for coronary artery disease (CAD) and are targets for therapeutic intervention. We screened the genome for common variants associated with plasma lipids in >100,000 individuals of European ancestry. Here we report 95 significantly associated loci (P < 5 x 10(-8)), with 59 showing genome-wide significant association with lipid traits for the first time. The newly reported associations include single nucleotide polymorphisms (SNPs) near known lipid regulators (for example, CYP7A1, NPC1L1 and SCARB1) as well as in scores of loci not previously implicated in lipoprotein metabolism. The 95 loci contribute not only to normal variation in lipid traits but also to extreme lipid phenotypes and have an impact on lipid traits in three non-European populations (East Asians, South Asians and African Americans). Our results identify several novel loci associated with plasma lipids that are also associated with CAD. Finally, we validated three of the novel genes-GALNT2, PPP1R3B and TTC39B-with experiments in mouse models. Taken together, our findings provide the foundation to develop a broader biological understanding of lipoprotein metabolism and to identify new therapeutic opportunities for the prevention of CAD.
Keywords: African Americans; Animals; Asian Continental Ancestry Group; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; Europe; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Lipid Metabolism; Lipids; Liver; Male; Mice; N-Acetylgalactosaminyltransferases; Phenotype; Polymorphism, Single Nucleotide; Protein Phosphatase 1; Reproducibility of Results; Triglycerides

Candidate gene association resource (CARe): design, methods, and proof of concept. - Musunuru, Kiran; Lettre, Guillaume; Young, Taylor; Farlow, Deborah N; Pirruccello, James P; Ejebe, Kenechi G; Keating, Brendan J; Yang, Qiong; Chen, Ming-Huei; Lapchyk, Nina; Crenshaw, Andrew; Ziaugra, Liuda; et al. (Circ Cardiovasc Genet, 2010)
BACKGROUND: The National Heart, Lung, and Blood Institute's Candidate Gene Association Resource (CARe), a planned cross-cohort analysis of genetic variation in cardiovascular, pulmonary, hematologic, and sleep-related traits, comprises >40,000 participants representing 4 ethnic groups in 9 community-based cohorts. The goals of CARe include the discovery of new variants associated with traits using a candidate gene approach and the discovery of new variants using the genome-wide association mapping approach specifically in African Americans. METHODS AND RESULTS: CARe has assembled DNA samples for >40,000 individuals self-identified as European American, African American, Hispanic, or Chinese American, with accompanying data on hundreds of phenotypes that have been standardized and deposited in the CARe Phenotype Database. All participants were genotyped for 7 single-nucleotide polymorphisms (SNPs) selected based on prior association evidence. We performed association analyses relating each of these SNPs to lipid traits, stratified by sex and ethnicity, and adjusted for age and age squared. In at least 2 of the ethnic groups, SNPs near CETP, LIPC, and LPL strongly replicated for association with high-density lipoprotein cholesterol concentrations, PCSK9 with low-density lipoprotein cholesterol levels, and LPL and APOA5 with serum triglycerides. Notably, some SNPs showed varying effect sizes and significance of association in different ethnic groups. CONCLUSIONS: The CARe Pilot Study validates the operational framework for phenotype collection, SNP genotyping, and analytic pipeline of the CARe project and validates the planned candidate gene study of approximately 2000 biological candidate loci in all participants and genome-wide association study in approximately 8000 African American participants. CARe will serve as a valuable resource for the scientific community.
Keywords: African Americans; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Databases, Genetic; European Continental Ancestry Group; Genetic Association Studies; Genotype; Humans; Phenotype; Pilot Projects; Polymorphism, Single Nucleotide; Research Design; Triglycerides

Common genetic determinants of vitamin D insufficiency: a genome-wide association study. - Wang, Thomas J; Zhang, Feng; Richards, J Brent; Kestenbaum, Bryan; van Meurs, Joyce B; Berry, Diane; Kiel, Douglas P; Streeten, Elizabeth A; Ohlsson, Claes; Koller, Daniel L; Peltonen, Leena; Cooper, Jason D; et al. (Lancet, 2010)
BACKGROUND: Vitamin D is crucial for maintenance of musculoskeletal health, and might also have a role in extraskeletal tissues. Determinants of circulating 25-hydroxyvitamin D concentrations include sun exposure and diet, but high heritability suggests that genetic factors could also play a part. We aimed to identify common genetic variants affecting vitamin D concentrations and risk of insufficiency. METHODS: We undertook a genome-wide association study of 25-hydroxyvitamin D concentrations in 33 996 individuals of European descent from 15 cohorts. Five epidemiological cohorts were designated as discovery cohorts (n=16 125), five as in-silico replication cohorts (n=9367), and five as de-novo replication cohorts (n=8504). 25-hydroxyvitamin D concentrations were measured by radioimmunoassay, chemiluminescent assay, ELISA, or mass spectrometry. Vitamin D insufficiency was defined as concentrations lower than 75 nmol/L or 50 nmol/L. We combined results of genome-wide analyses across cohorts using Z-score-weighted meta-analysis. Genotype scores were constructed for confirmed variants. FINDINGS: Variants at three loci reached genome-wide significance in discovery cohorts for association with 25-hydroxyvitamin D concentrations, and were confirmed in replication cohorts: 4p12 (overall p=1.9x10(-109) for rs2282679, in GC); 11q12 (p=2.1x10(-27) for rs12785878, near DHCR7); and 11p15 (p=3.3x10(-20) for rs10741657, near CYP2R1). Variants at an additional locus (20q13, CYP24A1) were genome-wide significant in the pooled sample (p=6.0x10(-10) for rs6013897). Participants with a genotype score (combining the three confirmed variants) in the highest quartile were at increased risk of having 25-hydroxyvitamin D concentrations lower than 75 nmol/L (OR 2.47, 95% CI 2.20-2.78, p=2.3x10(-48)) or lower than 50 nmol/L (1.92, 1.70-2.16, p=1.0x10(-26)) compared with those in the lowest quartile. INTERPRETATION: Variants near genes involved in cholesterol synthesis, hydroxylation, and vitamin D transport affect vitamin D status. Genetic variation at these loci identifies individuals who have substantially raised risk of vitamin D insufficiency. FUNDING: Full funding sources listed at end of paper (see Acknowledgments).
Keywords: Canada; Chromosomes, Human, Pair 11; Chromosomes, Human, Pair 4; Cohort Studies; Dietary Supplements; Europe; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Heterozygote; Homozygote; Humans; Immunoassay; International Cooperation; Linkage Disequilibrium; Polymorphism, Single Nucleotide; Seasons; United States; Vitamin D; Vitamin D Deficiency

Common genetic variants associate with serum phosphorus concentration. - Kestenbaum, Bryan; Glazer, Nicole L; Köttgen, Anna; Felix, Janine F; Hwang, Shih-Jen; Liu, Yongmei; Lohman, Kurt; Kritchevsky, Stephen B; Hausman, Dorothy B; Petersen, Ann-Kristin; Gieger, Christian; Ried, Janina S; et al. (J Am Soc Nephrol, 2010)
Phosphorus is an essential mineral that maintains cellular energy and mineralizes the skeleton. Because complex actions of ion transporters and regulatory hormones regulate serum phosphorus concentrations, genetic variation may determine interindividual variation in phosphorus metabolism. Here, we report a comprehensive genome-wide association study of serum phosphorus concentration. We evaluated 16,264 participants of European ancestry from the Cardiovascular Heath Study, Atherosclerosis Risk in Communities Study, Framingham Offspring Study, and the Rotterdam Study. We excluded participants with an estimated GFR <45 ml/min per 1.73 m(2) to focus on phosphorus metabolism under normal conditions. We imputed genotypes to approximately 2.5 million single-nucleotide polymorphisms in the HapMap and combined study-specific findings using meta-analysis. We tested top polymorphisms from discovery cohorts in a 5444-person replication sample. Polymorphisms in seven loci with minor allele frequencies 0.08 to 0.49 associate with serum phosphorus concentration (P = 3.5 x 10(-16) to 3.6 x 10(-7)). Three loci were near genes encoding the kidney-specific type IIa sodium phosphate co-transporter (SLC34A1), the calcium-sensing receptor (CASR), and fibroblast growth factor 23 (FGF23), proteins that contribute to phosphorus metabolism. We also identified genes encoding phosphatases, kinases, and phosphodiesterases that have yet-undetermined roles in phosphorus homeostasis. In the replication sample, five of seven top polymorphisms associate with serum phosphorous concentrations (P < 0.05 for each). In conclusion, common genetic variants associate with serum phosphorus in the general population. Further study of the loci identified in this study may help elucidate mechanisms of phosphorus regulation.
Keywords: Adult; Aged; European Continental Ancestry Group; Female; Fibroblast Growth Factors; Gene Frequency; Genetic Loci; Genetic Variation; Genome-Wide Association Study; Humans; Kidney; Male; Middle Aged; Phosphorus; Polymorphism, Single Nucleotide; Receptors, Calcium-Sensing; Sex Factors; Sodium-Phosphate Cotransporter Proteins, Type IIa

Common variants in 22 loci are associated with QRS duration and cardiac ventricular conduction. - Sotoodehnia, Nona; Isaacs, Aaron; de Bakker, Paul I W; Dörr, Marcus; Newton-Cheh, Christopher; Nolte, Ilja M; van der Harst, Pim; Müller, Martina; Eijgelsheim, Mark; Alonso, Alvaro; Hicks, Andrew A; Padmanabhan, Sandosh; et al. (Nat Genet, 2010)
The QRS interval, from the beginning of the Q wave to the end of the S wave on an electrocardiogram, reflects ventricular depolarization and conduction time and is a risk factor for mortality, sudden death and heart failure. We performed a genome-wide association meta-analysis in 40,407 individuals of European descent from 14 studies, with further genotyping in 7,170 additional Europeans, and we identified 22 loci associated with QRS duration (P < 5 × 10(-8)). These loci map in or near genes in pathways with established roles in ventricular conduction such as sodium channels, transcription factors and calcium-handling proteins, but also point to previously unidentified biologic processes, such as kinase inhibitors and genes related to tumorigenesis. We demonstrate that SCN10A, a candidate gene at the most significantly associated locus in this study, is expressed in the mouse ventricular conduction system, and treatment with a selective SCN10A blocker prolongs QRS duration. These findings extend our current knowledge of ventricular depolarization and conduction.
Keywords: Animals; Animals, Newborn; Chromosomes, Human; Computational Biology; Electrocardiography; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Humans; Mice; Mice, Transgenic; Models, Animal; Myocytes, Cardiac; NAV1.8 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Sodium Channels

Common variants in KCNN3 are associated with lone atrial fibrillation. - Ellinor, Patrick T; Lunetta, Kathryn L; Glazer, Nicole L; Pfeufer, Arne; Alonso, Alvaro; Chung, Mina K; Sinner, Moritz F; de Bakker, Paul I W; Mueller, Martina; Lubitz, Steven A; Fox, Ervin; Darbar, Dawood; et al. (Nat Genet, 2010)
Atrial fibrillation (AF) is the most common sustained arrhythmia. Previous studies have identified several genetic loci associated with typical AF. We sought to identify common genetic variants underlying lone AF. This condition affects a subset of individuals without overt heart disease and with an increased heritability of AF. We report a meta-analysis of genome-wide association studies conducted using 1,335 individuals with lone AF (cases) and 12,844 unaffected individuals (referents). Cases were obtained from the German AF Network, Heart and Vascular Health Study, the Atherosclerosis Risk in Communities Study, the Cleveland Clinic and Massachusetts General Hospital. We identified an association on chromosome 1q21 to lone AF (rs13376333, adjusted odds ratio = 1.56; P = 6.3 x 10(-12)), and we replicated this association in two independent cohorts with lone AF (overall combined odds ratio = 1.52, 95% CI 1.40-1.64; P = 1.83 x 10(-21)). rs13376333 is intronic to KCNN3, which encodes a potassium channel protein involved in atrial repolarization.
Keywords: Adolescent; Adult; Aged; Atrial Fibrillation; Case-Control Studies; Cohort Studies; Female; Genome-Wide Association Study; Humans; Introns; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Small-Conductance Calcium-Activated Potassium Channels; Young Adult

Common variants in the calcium-sensing receptor gene are associated with total serum calcium levels. - O'Seaghdha, Conall M; Yang, Qiong; Glazer, Nicole L; Leak, Tennille S; Dehghan, Abbas; Smith, Albert V; Kao, W H Linda; Lohman, Kurt; Hwang, Shih-Jen; Johnson, Andrew D; Hofman, Albert; Uitterlinden, André G; et al. (Hum Mol Genet, 2010)
Serum calcium levels are tightly regulated. We performed genome-wide association studies (GWAS) in population-based studies participating in the CHARGE Consortium to uncover common genetic variations associated with total serum calcium levels. GWAS of serum calcium concentrations was performed in 20 611 individuals of European ancestry for ∼2.5 million genotyped and imputed single-nucleotide polymorphisms (SNPs). The SNP with the lowest P-value was rs17251221 (P = 2.4 * 10(-22), minor allele frequency 14%) in the calcium-sensing receptor gene (CASR). This lead SNP was associated with higher serum calcium levels [0.06 mg/dl (0.015 mmol/l) per copy of the minor G allele] and accounted for 0.54% of the variance in serum calcium concentrations. The identification of variation in CASR that influences serum calcium concentration confirms the results of earlier candidate gene studies. The G allele of rs17251221 was also associated with higher serum magnesium levels (P = 1.2 * 10(-3)), lower serum phosphate levels (P = 2.8 * 10(-7)) and lower bone mineral density at the lumbar spine (P = 0.038), but not the femoral neck. No additional genomic loci contained SNPs associated at genome-wide significance (P < 5 * 10(-8)). These associations resemble clinical characteristics of patients with familial hypocalciuric hypercalcemia, an autosomal-dominant disease arising from rare inactivating mutations in the CASR gene. We conclude that common genetic variation in the CASR gene is associated with similar but milder features in the general population.
Keywords: Adult; Calcium; Female; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Calcium-Sensing

CRP gene variation and risk of community-acquired pneumonia. - Mukamal, Kenneth J; Pai, Jennifer K; O'Meara, Ellen S; Tracy, Russell P; Psaty, Bruce M; Kuller, Lewis H; Newman, Anne B; Yende, Sachin; Curhan, Gary C; Siscovick, David S; Rimm, Eric B (Respirology, 2010)
BACKGROUND AND OBJECTIVE: CRP has several potentially antibacterial effects, and variation in the CRP gene is known to influence CRP levels. Whether this variation influences risk of infection, and hence whether CRP has anti-infective activity in humans, is uncertain. METHODS: We evaluated a series of haplotype-tagging single nucleotide polymorphisms among 5374 individuals in the Cardiovascular Health Study, a cohort of older adults from four communities, who were followed for community-acquired pneumonia for 12-13 years. Secondarily, we evaluated whether these polymorphisms varied among men in the Health Professionals Follow-up Study who self-reported pneumonia on biennial questionnaires. RESULTS: There were 581 (507 white and 74 black) Cardiovascular Health Study participants with incident hospitalizations for pneumonia. No single nucleotide polymorphism or haplotypes were associated with risk among white Cardiovascular Health Study participants. Among black participants, the haplotype tagged by A790T was associated with lower risk of incident pneumonia (hazard ratio 0.5; 95% confidence interval: 0.3-0.9) and with higher CRP levels. In Health Professionals Follow-up Study, a separate haplotype was associated with less frequent self-reported pneumonia but not with circulating CRP levels. CONCLUSIONS: Some genetic variants in CRP may be associated with risk of pneumonia, but haplotypes associated with risk are variably associated with baseline CRP levels. If CRP is a relevant component of innate immunity in humans, the inducibility or tissue-specificity of expression may be at least as important as chronic circulating levels.
Keywords: African Americans; Aged; Aged, 80 and over; Body Mass Index; C-Reactive Protein; Cohort Studies; Community-Acquired Infections; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Pneumonia; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Smoking

Four novel Loci (19q13, 6q24, 12q24, and 5q14) influence the microcirculation in vivo. - Ikram, M Kamran; Sim, Xueling; Xueling, Sim; Jensen, Richard A; Cotch, Mary Frances; Hewitt, Alex W; Ikram, M Arfan; Wang, Jie Jin; Klein, Ronald; Klein, Barbara E K; Breteler, Monique M B; Cheung, Ning; et al. (PLoS Genet, 2010)
There is increasing evidence that the microcirculation plays an important role in the pathogenesis of cardiovascular diseases. Changes in retinal vascular caliber reflect early microvascular disease and predict incident cardiovascular events. We performed a genome-wide association study to identify genetic variants associated with retinal vascular caliber. We analyzed data from four population-based discovery cohorts with 15,358 unrelated Caucasian individuals, who are members of the Cohort for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, and replicated findings in four independent Caucasian cohorts (n  =  6,652). All participants had retinal photography and retinal arteriolar and venular caliber measured from computer software. In the discovery cohorts, 179 single nucleotide polymorphisms (SNP) spread across five loci were significantly associated (p<5.0×10(-8)) with retinal venular caliber, but none showed association with arteriolar caliber. Collectively, these five loci explain 1.0%-3.2% of the variation in retinal venular caliber. Four out of these five loci were confirmed in independent replication samples. In the combined analyses, the top SNPs at each locus were: rs2287921 (19q13; p  =  1.61×10(-25), within the RASIP1 locus), rs225717 (6q24; p = 1.25×10(-16), adjacent to the VTA1 and NMBR loci), rs10774625 (12q24; p  =  2.15×10(-13), in the region of ATXN2,SH2B3 and PTPN11 loci), and rs17421627 (5q14; p = 7.32×10(-16), adjacent to the MEF2C locus). In two independent samples, locus 12q24 was also associated with coronary heart disease and hypertension. Our population-based genome-wide association study demonstrates four novel loci associated with retinal venular caliber, an endophenotype of the microcirculation associated with clinical cardiovascular disease. These data provide further insights into the contribution and biological mechanisms of microcirculatory changes that underlie cardiovascular disease.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Child; Child, Preschool; Chromosomes, Human, Pair 12; Chromosomes, Human, Pair 19; Chromosomes, Human, Pair 5; Chromosomes, Human, Pair 6; Cohort Studies; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Microcirculation; Middle Aged; Polymorphism, Single Nucleotide; Retinal Vessels; Young Adult

Fucosyltransferase 2 (FUT2) non-secretor status is associated with Crohn's disease. - McGovern, Dermot P B; Jones, Michelle R; Taylor, Kent D; Marciante, Kristin; Yan, Xiaofei; Dubinsky, Marla; Ippoliti, Andy; Vasiliauskas, Eric; Berel, Dror; Derkowski, Carrie; Dutridge, Deb; Fleshner, Phil; et al. (Hum Mol Genet, 2010)
Genetic variation in both innate and adaptive immune systems is associated with Crohn's disease (CD) susceptibility, but much of the heritability to CD remains unknown. We performed a genome-wide association study (GWAS) in 896 CD cases and 3204 healthy controls all of Caucasian origin as defined by multidimensional scaling. We found supportive evidence for 21 out of 40 CD loci identified in a recent CD GWAS meta-analysis, including two loci which had only nominally achieved replication (rs4807569, 19p13; rs991804, CCL2/CCL7). In addition, we identified associations with genes involved in tight junctions/epithelial integrity (ASHL, ARPC1A), innate immunity (EXOC2), dendritic cell biology [CADM1 (IGSF4)], macrophage development (MMD2), TGF-beta signaling (MAP3K7IP1) and FUT2 (a physiological trait that regulates gastrointestinal mucosal expression of blood group A and B antigens) (rs602662, P=3.4x10(-5)). Twenty percent of Caucasians are 'non-secretors' who do not express ABO antigens in saliva as a result of the FUT2 W134X allele. We demonstrated replication in an independent cohort of 1174 CD cases and 357 controls between the four primary FUT2 single nucleotide polymorphisms (SNPs) and CD (rs602662, combined P-value 4.90x10(-8)) and also association with FUT2 W143X (P=2.6x10(-5)). Further evidence of the relevance of this locus to CD pathogenesis was demonstrated by the association of the original four SNPs and CD in the recently published CD GWAS meta-analysis (rs602662, P=0.001). These findings strongly implicate this locus in CD susceptibility and highlight the role of the mucus layer in the development of CD.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; Cohort Studies; Crohn Disease; Female; Fucosyltransferases; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Young Adult

Genetic predictors of medically refractory ulcerative colitis. - Haritunians, Talin; Taylor, Kent D; Targan, Stephan R; Dubinsky, Marla; Ippoliti, Andrew; Kwon, Soonil; Guo, Xiuqing; Melmed, Gil Y; Berel, Dror; Mengesha, Emebet; Psaty, Bruce M; Glazer, Nicole L; et al. (Inflamm Bowel Dis, 2010)
BACKGROUND: Acute severe ulcerative colitis (UC) remains a significant clinical challenge and the ability to predict, at an early stage, those individuals at risk of colectomy for medically refractory UC (MR-UC) would be a major clinical advance. The aim of this study was to use a genome-wide association study (GWAS) in a well-characterized cohort of UC patients to identify genetic variation that contributes to MR-UC. METHODS: A GWAS comparing 324 MR-UC patients with 537 non-MR-UC patients was analyzed using logistic regression and Cox proportional hazards methods. In addition, the MR-UC patients were compared with 2601 healthy controls. RESULTS: MR-UC was associated with more extensive disease (P = 2.7 × 10(-6)) and a positive family history of UC (P = 0.004). A risk score based on the combination of 46 single nucleotide polymorphisms (SNPs) associated with MR-UC explained 48% of the variance for colectomy risk in our cohort. Risk scores divided into quarters showed the risk of colectomy to be 0%, 17%, 74%, and 100% in the four groups. Comparison of the MR-UC subjects with healthy controls confirmed the contribution of the major histocompatibility complex to severe UC (peak association: rs17207986, P = 1.4 × 10(-16)) and provided genome-wide suggestive association at the TNFSF15 (TL1A) locus (peak association: rs11554257, P = 1.4 × 10(-6)). CONCLUSIONS: A SNP-based risk scoring system, identified here by GWAS analyses, may provide a useful adjunct to clinical parameters for predicting the natural history of UC. Furthermore, discovery of genetic processes underlying disease severity may help to identify pathways for novel therapeutic intervention in severe UC.
Keywords: Acute Disease; Adolescent; Adult; Cohort Studies; Colectomy; Colitis, Ulcerative; Female; Genetic Loci; Genome-Wide Association Study; Humans; Major Histocompatibility Complex; Male; Polymorphism, Single Nucleotide; Risk Factors; Severity of Illness Index; Tumor Necrosis Factor Ligand Superfamily Member 15; Young Adult

Genome-wide analysis of genetic loci associated with Alzheimer disease. - Seshadri, Sudha; Fitzpatrick, Annette L; Ikram, M Arfan; DeStefano, Anita L; Gudnason, Vilmundur; Boada, Merce; Bis, Joshua C; Smith, Albert V; Carassquillo, Minerva M; Lambert, Jean Charles; Harold, Denise; Schrijvers, Elisabeth M C; et al. (JAMA, 2010)
CONTEXT: Genome-wide association studies (GWAS) have recently identified CLU, PICALM, and CR1 as novel genes for late-onset Alzheimer disease (AD). OBJECTIVES: To identify and strengthen additional loci associated with AD and confirm these in an independent sample and to examine the contribution of recently identified genes to AD risk prediction in a 3-stage analysis of new and previously published GWAS on more than 35,000 persons (8371 AD cases). DESIGN, SETTING, AND PARTICIPANTS: In stage 1, we identified strong genetic associations (P < 10(-3)) in a sample of 3006 AD cases and 14,642 controls by combining new data from the population-based Cohorts for Heart and Aging Research in Genomic Epidemiology consortium (1367 AD cases [973 incident]) with previously reported results from the Translational Genomics Research Institute and the Mayo AD GWAS. We identified 2708 single-nucleotide polymorphisms (SNPs) with P < 10(-3). In stage 2, we pooled results for these SNPs with the European AD Initiative (2032 cases and 5328 controls) to identify 38 SNPs (10 loci) with P < 10(-5). In stage 3, we combined data for these 10 loci with data from the Genetic and Environmental Risk in AD consortium (3333 cases and 6995 controls) to identify 4 SNPs with P < 1.7x10(-8). These 4 SNPs were replicated in an independent Spanish sample (1140 AD cases and 1209 controls). Genome-wide association analyses were completed in 2007-2008 and the meta-analyses and replication in 2009. MAIN OUTCOME MEASURE: Presence of Alzheimer disease. RESULTS: Two loci were identified to have genome-wide significance for the first time: rs744373 near BIN1 (odds ratio [OR],1.13; 95% confidence interval [CI],1.06-1.21 per copy of the minor allele; P = 1.59x10(-11)) and rs597668 near EXOC3L2/BLOC1S3/MARK4 (OR, 1.18; 95% CI, 1.07-1.29; P = 6.45x10(-9)). Associations of these 2 loci plus the previously identified loci CLU and PICALM with AD were confirmed in the Spanish sample (P < .05). However, although CLU and PICALM were confirmed to be associated with AD in this independent sample, they did not improve the ability of a model that included age, sex, and APOE to predict incident AD (improvement in area under the receiver operating characteristic curve from 0.847 to 0.849 in the Rotterdam Study and 0.702 to 0.705 in the Cardiovascular Health Study). CONCLUSIONS: Two genetic loci for AD were found for the first time to reach genome-wide statistical significance. These findings were replicated in an independent population. Two recently reported associations were also confirmed. These loci did not improve AD risk prediction. While not clinically useful, they may implicate biological pathways useful for future research.
Keywords: Age of Onset; Aged; Alzheimer Disease; Case-Control Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Odds Ratio; Polymorphism, Single Nucleotide

Genome-wide association analysis identifies multiple loci related to resting heart rate. - Eijgelsheim, Mark; Newton-Cheh, Christopher; Sotoodehnia, Nona; de Bakker, Paul I W; Müller, Martina; Morrison, Alanna C; Smith, Albert V; Isaacs, Aaron; Sanna, Serena; Dörr, Marcus; Navarro, Pau; Fuchsberger, Christian; et al. (Hum Mol Genet, 2010)
Higher resting heart rate is associated with increased cardiovascular disease and mortality risk. Though heritable factors play a substantial role in population variation, little is known about specific genetic determinants. This knowledge can impact clinical care by identifying novel factors that influence pathologic heart rate states, modulate heart rate through cardiac structure and function or by improving our understanding of the physiology of heart rate regulation. To identify common genetic variants associated with heart rate, we performed a meta-analysis of 15 genome-wide association studies (GWAS), including 38,991 subjects of European ancestry, estimating the association between age-, sex- and body mass-adjusted RR interval (inverse heart rate) and approximately 2.5 million markers. Results with P < 5 × 10(-8) were considered genome-wide significant. We constructed regression models with multiple markers to assess whether results at less stringent thresholds were likely to be truly associated with RR interval. We identified six novel associations with resting heart rate at six loci: 6q22 near GJA1; 14q12 near MYH7; 12p12 near SOX5, c12orf67, BCAT1, LRMP and CASC1; 6q22 near SLC35F1, PLN and c6orf204; 7q22 near SLC12A9 and UfSp1; and 11q12 near FADS1. Associations at 6q22 400 kb away from GJA1, at 14q12 MYH6 and at 1q32 near CD34 identified in previously published GWAS were confirmed. In aggregate, these variants explain approximately 0.7% of RR interval variance. A multivariant regression model including 20 variants with P < 10(-5) increased the explained variance to 1.6%, suggesting that some loci falling short of genome-wide significance are likely truly associated. Future research is warranted to elucidate underlying mechanisms that may impact clinical care.
Keywords: Adult; Aged; Base Pairing; Cohort Studies; Female; Genetic Loci; Genome, Human; Genome-Wide Association Study; Heart Rate; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Rest

Genome-wide association identifies multiple ulcerative colitis susceptibility loci. - McGovern, Dermot P B; Gardet, Agnès; Törkvist, Leif; Goyette, Philippe; Essers, Jonah; Taylor, Kent D; Neale, Benjamin M; Ong, Rick T H; Lagacé, Caroline; Li, Chun; Green, Todd; Stevens, Christine R; et al. (Nat Genet, 2010)
Ulcerative colitis is a chronic, relapsing inflammatory condition of the gastrointestinal tract with a complex genetic and environmental etiology. In an effort to identify genetic variation underlying ulcerative colitis risk, we present two distinct genome-wide association studies of ulcerative colitis and their joint analysis with a previously published scan, comprising, in aggregate, 2,693 individuals with ulcerative colitis and 6,791 control subjects. Fifty-nine SNPs from 14 independent loci attained an association significance of P < 10(-5). Seven of these loci exceeded genome-wide significance (P < 5 x 10(-8)). After testing an independent cohort of 2,009 cases of ulcerative colitis and 1,580 controls, we identified 13 loci that were significantly associated with ulcerative colitis (P < 5 x 10(-8)), including the immunoglobulin receptor gene FCGR2A, 5p15, 2p16 and ORMDL3 (orosomucoid1-like 3). We confirmed association with 14 previously identified ulcerative colitis susceptibility loci, and an analysis of acknowledged Crohn's disease loci showed that roughly half of the known Crohn's disease associations are shared with ulcerative colitis. These data implicate approximately 30 loci in ulcerative colitis, thereby providing insight into disease pathogenesis.
Keywords: Colitis, Ulcerative; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Membrane Proteins; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Receptors, IgG

Genome-wide association identifies OBFC1 as a locus involved in human leukocyte telomere biology. - Levy, Daniel; Neuhausen, Susan L; Hunt, Steven C; Kimura, Masayuki; Hwang, Shih-Jen; Chen, Wei; Bis, Joshua C; Fitzpatrick, Annette L; Smith, Erin; Johnson, Andrew D; Gardner, Jeffrey P; Srinivasan, Sathanur R; et al. (Proc Natl Acad Sci U S A, 2010)
Telomeres are engaged in a host of cellular functions, and their length is regulated by multiple genes. Telomere shortening, in the course of somatic cell replication, ultimately leads to replicative senescence. In humans, rare mutations in genes that regulate telomere length have been identified in monogenic diseases such as dyskeratosis congenita and idiopathic pulmonary fibrosis, which are associated with shortened leukocyte telomere length (LTL) and increased risk for aplastic anemia. Shortened LTL is observed in a host of aging-related complex genetic diseases and is associated with diminished survival in the elderly. We report results of a genome-wide association study of LTL in a consortium of four observational studies (n = 3,417 participants with LTL and genome-wide genotyping). SNPs in the regions of the oligonucleotide/oligosaccharide-binding folds containing one gene (OBFC1; rs4387287; P = 3.9 x 10(-9)) and chemokine (C-X-C motif) receptor 4 gene (CXCR4; rs4452212; P = 2.9 x 10(-8)) were associated with LTL at a genome-wide significance level (P < 5 x 10(-8)). We attempted replication of the top SNPs at these loci through de novo genotyping of 1,893 additional individuals and in silico lookup in another observational study (n = 2,876), and we confirmed the association findings for OBFC1 but not CXCR4. In addition, we confirmed the telomerase RNA component (TERC) as a gene associated with LTL (P = 1.1 x 10(-5)). The identification of OBFC1 through genome-wide association as a locus for interindividual variation in LTL in the general population advances the understanding of telomere biology in humans and may provide insights into aging-related disorders linked to altered LTL dynamics.
Keywords: Cohort Studies; Genome-Wide Association Study; Genotype; Humans; Leukocytes; Polymorphism, Single Nucleotide; Receptors, CXCR4; Telomere; Telomere-Binding Proteins

Genome-wide association studies of MRI-defined brain infarcts: meta-analysis from the CHARGE Consortium. - Debette, Stephanie; Bis, Joshua C; Fornage, Myriam; Schmidt, Helena; Ikram, M Arfan; Sigurdsson, Sigurdur; Heiss, Gerardo; Struchalin, Maksim; Smith, Albert V; van der Lugt, Aad; DeCarli, Charles; Lumley, Thomas; et al. (Stroke, 2010)
BACKGROUND AND PURPOSE: Previous studies examining genetic associations with MRI-defined brain infarct have yielded inconsistent findings. We investigated genetic variation underlying covert MRI infarct in persons without histories of transient ischemic attack or stroke. We performed meta-analysis of genome-wide association studies of white participants in 6 studies comprising the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. METHODS: Using 2.2 million genotyped and imputed single nucleotide polymorphisms, each study performed cross-sectional genome-wide association analysis of MRI infarct using age- and sex-adjusted logistic regression models. Study-specific findings were combined in an inverse-variance-weighted meta-analysis, including 9401 participants with mean age 69.7 (19.4% of whom had >or=1 MRI infarct). RESULTS: The most significant association was found with rs2208454 (minor allele frequency, 20%), located in intron 3 of MACRO domain containing 2 gene and in the downstream region of fibronectin leucine-rich transmembrane protein 3 gene. Each copy of the minor allele was associated with lower risk of MRI infarcts (odds ratio, 0.76; 95% confidence interval, 0.68-0.84; P=4.64x10(-7)). Highly suggestive associations (P<1.0x10(-5)) were also found for 22 other single nucleotide polymorphisms in linkage disequilibrium (r(2)>0.64) with rs2208454. The association with rs2208454 did not replicate in independent samples of 1822 white and 644 black participants, although 4 single nucleotide polymorphisms within 200 kb from rs2208454 were associated with MRI infarcts in the black population sample. CONCLUSIONS: This first community-based, genome-wide association study on covert MRI infarcts uncovered novel associations. Although replication of the association with top single nucleotide polymorphisms failed, possibly because of insufficient power, results in the black population sample are encouraging, and further efforts at replication are needed.
Keywords: African Americans; Aged; Brain; Brain Infarction; Cohort Studies; DNA Mutational Analysis; Female; Gene Frequency; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Genetic Variation; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Magnetic Resonance Imaging; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies

Genome-wide association studies of serum magnesium, potassium, and sodium concentrations identify six Loci influencing serum magnesium levels. - Meyer, Tamra E; Verwoert, Germaine C; Hwang, Shih-Jen; Glazer, Nicole L; Smith, Albert V; van Rooij, Frank J A; Ehret, Georg B; Boerwinkle, Eric; Felix, Janine F; Leak, Tennille S; Harris, Tamara B; Yang, Qiong; et al. (PLoS Genet, 2010)
Magnesium, potassium, and sodium, cations commonly measured in serum, are involved in many physiological processes including energy metabolism, nerve and muscle function, signal transduction, and fluid and blood pressure regulation. To evaluate the contribution of common genetic variation to normal physiologic variation in serum concentrations of these cations, we conducted genome-wide association studies of serum magnesium, potassium, and sodium concentrations using approximately 2.5 million genotyped and imputed common single nucleotide polymorphisms (SNPs) in 15,366 participants of European descent from the international CHARGE Consortium. Study-specific results were combined using fixed-effects inverse-variance weighted meta-analysis. SNPs demonstrating genome-wide significant (p<5 x 10(-8)) or suggestive associations (p<4 x 10(-7)) were evaluated for replication in an additional 8,463 subjects of European descent. The association of common variants at six genomic regions (in or near MUC1, ATP2B1, DCDC5, TRPM6, SHROOM3, and MDS1) with serum magnesium levels was genome-wide significant when meta-analyzed with the replication dataset. All initially significant SNPs from the CHARGE Consortium showed nominal association with clinically defined hypomagnesemia, two showed association with kidney function, two with bone mineral density, and one of these also associated with fasting glucose levels. Common variants in CNNM2, a magnesium transporter studied only in model systems to date, as well as in CNNM3 and CNNM4, were also associated with magnesium concentrations in this study. We observed no associations with serum sodium or potassium levels exceeding p<4 x 10(-7). Follow-up studies of newly implicated genomic loci may provide additional insights into the regulation and homeostasis of human serum magnesium levels.
Keywords: Adult; Aged; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Magnesium; Male; Middle Aged; Polymorphism, Single Nucleotide; Potassium; Sodium

Genome-wide association study identifies GPC5 as a novel genetic locus protective against sudden cardiac arrest. - Arking, Dan E; Reinier, Kyndaron; Post, Wendy; Jui, Jonathan; Hilton, Gina; O'Connor, Ashley; Prineas, Ronald J; Boerwinkle, Eric; Psaty, Bruce M; Tomaselli, Gordon F; Rea, Thomas; Sotoodehnia, Nona; et al. (PLoS One, 2010)
BACKGROUND: Existing studies indicate a significant genetic component for sudden cardiac arrest (SCA) and genome-wide association studies (GWAS) provide an unbiased approach for identification of novel genes. We performed a GWAS to identify genetic determinants of SCA. METHODOLOGY/PRINCIPAL FINDINGS: We used a case-control design within the ongoing Oregon Sudden Unexpected Death Study (Oregon-SUDS). Cases (n = 424) were SCAs with coronary artery disease (CAD) among residents of Portland, OR (2002-07, population approximately 1,000,000) and controls (n = 226) were residents with CAD, but no history of SCA. All subjects were of White-European ancestry and GWAS was performed using Affymetrix 500K/5.0 and 6.0 arrays. High signal markers were genotyped in SCA cases (n = 521) identified from the Atherosclerosis Risk in Communities Study (ARIC) and the Cardiovascular Health Study (CHS) (combined n = 19,611). No SNPs reached genome-wide significance (p<5x10(-8)). SNPs at 6 loci were prioritized for follow-up primarily based on significance of p<10(-4) and proximity to a known gene (CSMD2, GPR37L1, LIN9, B4GALNT3, GPC5, and ZNF592). The minor allele of GPC5 (GLYPICAN 5, rs3864180) was associated with a lower risk of SCA in Oregon-SUDS, an effect that was also observed in ARIC/CHS whites (p<0.05) and blacks (p<0.04). In a combined Cox proportional hazards model analysis that adjusted for race, the minor allele exhibited a hazard ratio of 0.85 (95% CI 0.74 to 0.98; p<0.01). CONCLUSIONS/SIGNIFICANCE: A novel genetic locus for SCA, GPC5, was identified from Oregon-SUDS and successfully validated in the ARIC and CHS cohorts. Three other members of the Glypican family have been previously implicated in human disease, including cardiac conditions. The mechanism of this specific association requires further study.
Keywords: Aged; Alleles; Case-Control Studies; Cohort Studies; Death, Sudden, Cardiac; Ethnic Groups; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glypicans; Heart Diseases; Humans; Male; Middle Aged; Models, Genetic; Oligonucleotide Array Sequence Analysis; Oregon; Polymorphism, Single Nucleotide

Genome-wide meta-analyses identify multiple loci associated with smoking behavior. (Nat Genet, 2010)
Consistent but indirect evidence has implicated genetic factors in smoking behavior. We report meta-analyses of several smoking phenotypes within cohorts of the Tobacco and Genetics Consortium (n = 74,053). We also partnered with the European Network of Genetic and Genomic Epidemiology (ENGAGE) and Oxford-GlaxoSmithKline (Ox-GSK) consortia to follow up the 15 most significant regions (n > 140,000). We identified three loci associated with number of cigarettes smoked per day. The strongest association was a synonymous 15q25 SNP in the nicotinic receptor gene CHRNA3 (rs1051730[A], beta = 1.03, standard error (s.e.) = 0.053, P = 2.8 x 10(-73)). Two 10q25 SNPs (rs1329650[G], beta = 0.367, s.e. = 0.059, P = 5.7 x 10(-10); and rs1028936[A], beta = 0.446, s.e. = 0.074, P = 1.3 x 10(-9)) and one 9q13 SNP in EGLN2 (rs3733829[G], beta = 0.333, s.e. = 0.058, P = 1.0 x 10(-8)) also exceeded genome-wide significance for cigarettes per day. For smoking initiation, eight SNPs exceeded genome-wide significance, with the strongest association at a nonsynonymous SNP in BDNF on chromosome 11 (rs6265[C], odds ratio (OR) = 1.06, 95% confidence interval (Cl) 1.04-1.08, P = 1.8 x 10(-8)). One SNP located near DBH on chromosome 9 (rs3025343[G], OR = 1.12, 95% Cl 1.08-1.18, P = 3.6 x 10(-8)) was significantly associated with smoking cessation.
Keywords: Age Factors; Alleles; Chromosome Mapping; Female; Genome; Genome-Wide Association Study; Genotype; Humans; Male; Molecular Epidemiology; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Receptors, Nicotinic; Smoking

Genomic variation associated with mortality among adults of European and African ancestry with heart failure: the cohorts for heart and aging research in genomic epidemiology consortium. - Morrison, Alanna C; Felix, Janine F; Cupples, L Adrienne; Glazer, Nicole L; Loehr, Laura R; Dehghan, Abbas; Demissie, Serkalem; Bis, Joshua C; Rosamond, Wayne D; Aulchenko, Yurii S; Wang, Ying A; Haritunians, Talin; et al. (Circ Cardiovasc Genet, 2010)
BACKGROUND: Prognosis and survival are significant concerns for individuals with heart failure (HF). To better understand the pathophysiology of HF prognosis, the association between 2,366,858 single-nucleotide polymorphisms (SNPs) and all-cause mortality was evaluated among individuals with incident HF from 4 community-based prospective cohorts: the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study. METHODS AND RESULTS: Participants were 2526 individuals of European ancestry and 466 individuals of African ancestry who experienced an incident HF event during follow-up in the respective cohorts. Within each study, the association between genetic variants and time to mortality among individuals with HF was assessed by Cox proportional hazards models that included adjustment for sex and age at the time of the HF event. Prospective fixed-effect meta-analyses were conducted for the 4 study populations of European ancestry (N=1645 deaths) and for the 2 populations of African ancestry (N=281 deaths). Genome-wide significance was set at P=5.0x10(-7). Meta-analytic findings among individuals of European ancestry revealed 1 genome-wide significant locus on chromosome 3p22 in an intron of CKLF-like MARVEL transmembrane domain containing 7 (CMTM7, P=3.2x10(-7)). Eight additional loci in individuals of European ancestry and 4 loci in individuals of African ancestry were identified by high-signal SNPs (P<1.0x10(-5)) but did not meet genome-wide significance. CONCLUSIONS: This study identified a novel locus associated with all-cause mortality among individuals of European ancestry with HF. This finding warrants additional investigation, including replication, in other studies of HF.
Keywords: African Americans; Aged; Aged, 80 and over; Chemokines; Cohort Studies; European Continental Ancestry Group; Female; Genome-Wide Association Study; Genotype; Heart Failure; Humans; Introns; Male; MARVEL Domain-Containing Proteins; Membrane Proteins; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Hundreds of variants clustered in genomic loci and biological pathways affect human height. - Lango Allen, Hana; Estrada, Karol; Lettre, Guillaume; Berndt, Sonja I; Weedon, Michael N; Rivadeneira, Fernando; Willer, Cristen J; Jackson, Anne U; Vedantam, Sailaja; Raychaudhuri, Soumya; Ferreira, Teresa; Wood, Andrew R; et al. (Nature, 2010)
Most common human traits and diseases have a polygenic pattern of inheritance: DNA sequence variants at many genetic loci influence the phenotype. Genome-wide association (GWA) studies have identified more than 600 variants associated with human traits, but these typically explain small fractions of phenotypic variation, raising questions about the use of further studies. Here, using 183,727 individuals, we show that hundreds of genetic variants, in at least 180 loci, influence adult height, a highly heritable and classic polygenic trait. The large number of loci reveals patterns with important implications for genetic studies of common human diseases and traits. First, the 180 loci are not random, but instead are enriched for genes that are connected in biological pathways (P = 0.016) and that underlie skeletal growth defects (P < 0.001). Second, the likely causal gene is often located near the most strongly associated variant: in 13 of 21 loci containing a known skeletal growth gene, that gene was closest to the associated variant. Third, at least 19 loci have multiple independently associated variants, suggesting that allelic heterogeneity is a frequent feature of polygenic traits, that comprehensive explorations of already-discovered loci should discover additional variants and that an appreciable fraction of associated loci may have been identified. Fourth, associated variants are enriched for likely functional effects on genes, being over-represented among variants that alter amino-acid structure of proteins and expression levels of nearby genes. Our data explain approximately 10% of the phenotypic variation in height, and we estimate that unidentified common variants of similar effect sizes would increase this figure to approximately 16% of phenotypic variation (approximately 20% of heritable variation). Although additional approaches are needed to dissect the genetic architecture of polygenic human traits fully, our findings indicate that GWA studies can identify large numbers of loci that implicate biologically relevant genes and pathways.
Keywords: Body Height; Chromosomes, Human, Pair 3; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Metabolic Networks and Pathways; Multifactorial Inheritance; Phenotype; Polymorphism, Single Nucleotide

Independent susceptibility markers for atrial fibrillation on chromosome 4q25. - Lubitz, Steven A; Sinner, Moritz F; Lunetta, Kathryn L; Makino, Seiko; Pfeufer, Arne; Rahman, Rosanna; Veltman, Caroline E; Barnard, John; Bis, Joshua C; Danik, Stephan P; Sonni, Akshata; Shea, Marisa A; et al. (Circulation, 2010)
BACKGROUND: Genetic variants on chromosome 4q25 are associated with atrial fibrillation (AF). We sought to determine whether there is more than 1 susceptibility signal at this locus. METHODS AND RESULTS: Thirty-four haplotype-tagging single-nucleotide polymorphisms (SNPs) at the 4q25 locus were genotyped in 790 case and 1177 control subjects from Massachusetts General Hospital and tested for association with AF. We replicated SNPs associated with AF after adjustment for the most significantly associated SNP in 5066 case and 30 661 referent subjects from the German Competence Network for Atrial Fibrillation, Atherosclerosis Risk In Communities Study, Cleveland Clinic Lone AF Study, Cardiovascular Health Study, and Rotterdam Study. All subjects were of European ancestry. A multimarker risk score composed of SNPs that tagged distinct AF susceptibility signals was constructed and tested for association with AF, and all results were subjected to meta-analysis. The previously reported SNP, rs2200733, was most significantly associated with AF (minor allele odds ratio 1.80, 95% confidence interval 1.50 to 2.15, P=1.2 x 10(-20)) in the discovery sample. Adjustment for rs2200733 genotype revealed 2 additional susceptibility signals marked by rs17570669 and rs3853445. A graded risk of AF was observed with an increasing number of AF risk alleles at SNPs that tagged these 3 susceptibility signals. CONCLUSIONS: We identified 2 novel AF susceptibility signals on chromosome 4q25. Consideration of multiple susceptibility signals at chromosome 4q25 identifies individuals with an increased risk of AF and may localize regulatory elements at the locus with biological relevance in the pathogenesis of AF.
Keywords: Aged; Aged, 80 and over; Atrial Fibrillation; Chromosome Mapping; Chromosomes, Human, Pair 4; European Continental Ancestry Group; Female; Genetic Markers; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Interaction between fibrinogen and IL-6 genetic variants and associations with cardiovascular disease risk in the Cardiovascular Health Study. - Carty, Cara L; Heagerty, Patrick; Heckbert, Susan R; Jarvik, Gail P; Lange, Leslie A; Cushman, Mary; Tracy, Russell P; Reiner, Alexander P (Ann Hum Genet, 2010)
The inflammatory cytokine interleukin-6 (IL-6) is a main regulator of fibrinogen synthesis, though its interaction with fibrinogen genes (FGA, FGB, FGG) and subsequent impact on cardiovascular disease (CVD) risk is not well-studied. We investigated joint associations of fibrinogen and IL6 tagSNPs with fibrinogen concentrations, carotid intima-media thickness, and myocardial infarction or ischemic stroke in 3900 European-American Cardiovascular Health Study participants. To identify combinations of genetic main effects and interactions associated with outcomes, we used logic regression. We also evaluated whether the relationship between fibrinogen SNPs and fibrinogen level varied by IL-6 level using linear regression models with multiplicative interaction terms. Combinations of fibrinogen and IL6 SNPs were significantly associated with fibrinogen level (p < 0.005), but not with other outcomes. Fibrinogen levels were higher in individuals having FGB1437 (rs1800790) and lacking FGA6534 (rs6050) minor alleles; these SNPs interacted with IL6 rs1800796 to influence fibrinogen level. Marginally significant (p= 0.03) interactions between IL-6 level and FGA and FGG promoter SNPs associated with fibrinogen levels were detected. We identified potential gene-gene interactions influencing fibrinogen levels. Although IL-6 responsive binding sites are present in fibrinogen gene promoter regions, we did not find strong evidence of interaction between fibrinogen SNPs and IL6 SNPs or levels influencing CVD.
Keywords: Aged; Cardiovascular Diseases; Carotid Arteries; Female; Fibrinogen; Genetic Predisposition to Disease; Genetic Variation; Humans; Interleukin-6; Male; Models, Biological; Myocardial Infarction; Polymorphism, Single Nucleotide; Risk; Stroke

Interactions of dietary whole-grain intake with fasting glucose- and insulin-related genetic loci in individuals of European descent: a meta-analysis of 14 cohort studies. - Nettleton, Jennifer A; McKeown, Nicola M; Kanoni, Stavroula; Lemaitre, Rozenn N; Hivert, Marie-France; Ngwa, Julius; van Rooij, Frank J A; Sonestedt, Emily; Wojczynski, Mary K; Ye, Zheng; Tanaka, Tosh; Garcia, Melissa; et al. (Diabetes Care, 2010)
OBJECTIVE: Whole-grain foods are touted for multiple health benefits, including enhancing insulin sensitivity and reducing type 2 diabetes risk. Recent genome-wide association studies (GWAS) have identified several single nucleotide polymorphisms (SNPs) associated with fasting glucose and insulin concentrations in individuals free of diabetes. We tested the hypothesis that whole-grain food intake and genetic variation interact to influence concentrations of fasting glucose and insulin. RESEARCH DESIGN AND METHODS: Via meta-analysis of data from 14 cohorts comprising ∼ 48,000 participants of European descent, we studied interactions of whole-grain intake with loci previously associated in GWAS with fasting glucose (16 loci) and/or insulin (2 loci) concentrations. For tests of interaction, we considered a P value <0.0028 (0.05 of 18 tests) as statistically significant. RESULTS: Greater whole-grain food intake was associated with lower fasting glucose and insulin concentrations independent of demographics, other dietary and lifestyle factors, and BMI (β [95% CI] per 1-serving-greater whole-grain intake: -0.009 mmol/l glucose [-0.013 to -0.005], P < 0.0001 and -0.011 pmol/l [ln] insulin [-0.015 to -0.007], P = 0.0003). No interactions met our multiple testing-adjusted statistical significance threshold. The strongest SNP interaction with whole-grain intake was rs780094 (GCKR) for fasting insulin (P = 0.006), where greater whole-grain intake was associated with a smaller reduction in fasting insulin concentrations in those with the insulin-raising allele. CONCLUSIONS: Our results support the favorable association of whole-grain intake with fasting glucose and insulin and suggest a potential interaction between variation in GCKR and whole-grain intake in influencing fasting insulin concentrations.
Keywords: Adult; Aged; Blood Glucose; Edible Grain; European Continental Ancestry Group; Fasting; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide

Meta-analyses of genome-wide association studies identify multiple loci associated with pulmonary function. - Hancock, Dana B; Eijgelsheim, Mark; Wilk, Jemma B; Gharib, Sina A; Loehr, Laura R; Marciante, Kristin D; Franceschini, Nora; van Durme, Yannick M T A; Chen, Ting-Hsu; Barr, R Graham; Schabath, Matthew B; Couper, David J; et al. (Nat Genet, 2010)
Spirometric measures of lung function are heritable traits that reflect respiratory health and predict morbidity and mortality. We meta-analyzed genome-wide association studies for two clinically important lung-function measures: forced expiratory volume in the first second (FEV(1)) and its ratio to forced vital capacity (FEV(1)/FVC), an indicator of airflow obstruction. This meta-analysis included 20,890 participants of European ancestry from four CHARGE Consortium studies: Atherosclerosis Risk in Communities, Cardiovascular Health Study, Framingham Heart Study and Rotterdam Study. We identified eight loci associated with FEV(1)/FVC (HHIP, GPR126, ADAM19, AGER-PPT2, FAM13A, PTCH1, PID1 and HTR4) and one locus associated with FEV(1) (INTS12-GSTCD-NPNT) at or near genome-wide significance (P < 5 x 10(-8)) in the CHARGE Consortium dataset. Our findings may offer insights into pulmonary function and pathogenesis of chronic lung disease.
Keywords: Databases, Genetic; Female; Forced Expiratory Volume; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Lung; Lung Diseases; Male; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Spirometry; Vital Capacity

Meta-analysis identifies 13 new loci associated with waist-hip ratio and reveals sexual dimorphism in the genetic basis of fat distribution. - Heid, Iris M; Jackson, Anne U; Randall, Joshua C; Winkler, Thomas W; Qi, Lu; Steinthorsdottir, Valgerdur; Thorleifsson, Gudmar; Zillikens, M Carola; Speliotes, Elizabeth K; Mägi, Reedik; Workalemahu, Tsegaselassie; White, Charles C; et al. (Nat Genet, 2010)
Waist-hip ratio (WHR) is a measure of body fat distribution and a predictor of metabolic consequences independent of overall adiposity. WHR is heritable, but few genetic variants influencing this trait have been identified. We conducted a meta-analysis of 32 genome-wide association studies for WHR adjusted for body mass index (comprising up to 77,167 participants), following up 16 loci in an additional 29 studies (comprising up to 113,636 subjects). We identified 13 new loci in or near RSPO3, VEGFA, TBX15-WARS2, NFE2L3, GRB14, DNM3-PIGC, ITPR2-SSPN, LY86, HOXC13, ADAMTS9, ZNRF3-KREMEN1, NISCH-STAB1 and CPEB4 (P = 1.9 × 10⁻⁹ to P = 1.8 × 10⁻⁴⁰) and the known signal at LYPLAL1. Seven of these loci exhibited marked sexual dimorphism, all with a stronger effect on WHR in women than men (P for sex difference = 1.9 × 10⁻³ to P = 1.2 × 10⁻¹³). These findings provide evidence for multiple loci that modulate body fat distribution independent of overall adiposity and reveal strong gene-by-sex interactions.
Keywords: Adipose Tissue; Age Factors; Chromosome Mapping; Female; Genome, Human; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Sex Characteristics; Waist-Hip Ratio

A meta-analysis of four genome-wide association studies of survival to age 90 years or older: the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. - Newman, Anne B; Walter, Stefan; Lunetta, Kathryn L; Garcia, Melissa E; Slagboom, P Eline; Christensen, Kaare; Arnold, Alice M; Aspelund, Thor; Aulchenko, Yurii S; Benjamin, Emelia J; Christiansen, Lene; D'Agostino, Ralph B; et al. (J Gerontol A Biol Sci Med Sci, 2010)
BACKGROUND: Genome-wide association studies (GWAS) may yield insights into longevity. METHODS: We performed a meta-analysis of GWAS in Caucasians from four prospective cohort studies: the Age, Gene/Environment Susceptibility-Reykjavik Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study participating in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Longevity was defined as survival to age 90 years or older (n = 1,836); the comparison group comprised cohort members who died between the ages of 55 and 80 years (n = 1,955). In a second discovery stage, additional genotyping was conducted in the Leiden Longevity Study cohort and the Danish 1905 cohort. RESULTS: There were 273 single-nucleotide polymorphism (SNP) associations with p < .0001, but none reached the prespecified significance level of 5 x 10(-8). Of the most significant SNPs, 24 were independent signals, and 16 of these SNPs were successfully genotyped in the second discovery stage, with one association for rs9664222, reaching 6.77 x 10(-7) for the combined meta-analysis of CHARGE and the stage 2 cohorts. The SNP lies in a region near MINPP1 (chromosome 10), a well-conserved gene involved in regulation of cellular proliferation. The minor allele was associated with lower odds of survival past age 90 (odds ratio = 0.82). Associations of interest in a homologue of the longevity assurance gene (LASS3) and PAPPA2 were not strengthened in the second stage. CONCLUSION: Survival studies of larger size or more extreme or specific phenotypes may support or refine these initial findings.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Alleles; Cohort Studies; Confidence Intervals; Female; Genome-Wide Association Study; Genotype; Humans; Longevity; Male; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide

New genetic loci implicated in fasting glucose homeostasis and their impact on type 2 diabetes risk. - Dupuis, Josée; Langenberg, Claudia; Prokopenko, Inga; Saxena, Richa; Soranzo, Nicole; Jackson, Anne U; Wheeler, Eleanor; Glazer, Nicole L; Bouatia-Naji, Nabila; Gloyn, Anna L; Lindgren, Cecilia M; Mägi, Reedik; et al. (Nat Genet, 2010)
Levels of circulating glucose are tightly regulated. To identify new loci influencing glycemic traits, we performed meta-analyses of 21 genome-wide association studies informative for fasting glucose, fasting insulin and indices of beta-cell function (HOMA-B) and insulin resistance (HOMA-IR) in up to 46,186 nondiabetic participants. Follow-up of 25 loci in up to 76,558 additional subjects identified 16 loci associated with fasting glucose and HOMA-B and two loci associated with fasting insulin and HOMA-IR. These include nine loci newly associated with fasting glucose (in or near ADCY5, MADD, ADRA2A, CRY2, FADS1, GLIS3, SLC2A2, PROX1 and C2CD4B) and one influencing fasting insulin and HOMA-IR (near IGF1). We also demonstrated association of ADCY5, PROX1, GCK, GCKR and DGKB-TMEM195 with type 2 diabetes. Within these loci, likely biological candidate genes influence signal transduction, cell proliferation, development, glucose-sensing and circadian regulation. Our results demonstrate that genetic studies of glycemic traits can identify type 2 diabetes risk loci, as well as loci containing gene variants that are associated with a modest elevation in glucose levels but are not associated with overt diabetes.
Keywords: Adolescent; Adult; Alleles; Blood Glucose; Child; Databases, Genetic; Diabetes Mellitus, Type 2; DNA Copy Number Variations; Fasting; Gene Expression Regulation; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Homeostasis; Humans; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Reproducibility of Results

Novel associations of multiple genetic loci with plasma levels of factor VII, factor VIII, and von Willebrand factor: The CHARGE (Cohorts for Heart and Aging Research in Genome Epidemiology) Consortium. - Smith, Nicholas L; Chen, Ming-Huei; Dehghan, Abbas; Strachan, David P; Basu, Saonli; Soranzo, Nicole; Hayward, Caroline; Rudan, Igor; Sabater-Lleal, Maria; Bis, Joshua C; de Maat, Moniek P M; Rumley, Ann; et al. (Circulation, 2010)
BACKGROUND: Plasma levels of coagulation factors VII (FVII), VIII (FVIII), and von Willebrand factor (vWF) influence risk of hemorrhage and thrombosis. We conducted genome-wide association studies to identify new loci associated with plasma levels. METHODS AND RESULTS: The setting of the study included 5 community-based studies for discovery comprising 23 608 European-ancestry participants: Atherosclerosis Risk In Communities Study, Cardiovascular Health Study, British 1958 Birth Cohort, Framingham Heart Study, and Rotterdam Study. All subjects had genome-wide single-nucleotide polymorphism (SNP) scans and at least 1 phenotype measured: FVII activity/antigen, FVIII activity, and vWF antigen. Each study used its genotype data to impute to HapMap SNPs and independently conducted association analyses of hemostasis measures using an additive genetic model. Study findings were combined by meta-analysis. Replication was conducted in 7604 participants not in the discovery cohort. For FVII, 305 SNPs exceeded the genome-wide significance threshold of 5.0x10(-8) and comprised 5 loci on 5 chromosomes: 2p23 (smallest P value 6.2x10(-24)), 4q25 (3.6x10(-12)), 11q12 (2.0x10(-10)), 13q34 (9.0x10(-259)), and 20q11.2 (5.7x10(-37)). Loci were within or near genes, including 4 new candidate genes and F7 (13q34). For vWF, 400 SNPs exceeded the threshold and marked 8 loci on 6 chromosomes: 6q24 (1.2x10(-22)), 8p21 (1.3x10(-16)), 9q34 (<5.0x10(-324)), 12p13 (1.7x10(-32)), 12q23 (7.3x10(-10)), 12q24.3 (3.8x10(-11)), 14q32 (2.3x10(-10)), and 19p13.2 (1.3x10(-9)). All loci were within genes, including 6 new candidate genes, as well as ABO (9q34) and VWF (12p13). For FVIII, 5 loci were identified and overlapped vWF findings. Nine of the 10 new findings were replicated. CONCLUSIONS: New genetic associations were discovered outside previously known biological pathways and may point to novel prevention and treatment targets of hemostasis disorders.
Keywords: Adult; Factor VII; Factor VIII; Female; Genome-Wide Association Study; Hemostasis; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Thrombosis; von Willebrand Factor

Study of the relationship between the interleukin-6 gene and obstructive sleep apnea. - Larkin, Emma K; Patel, Sanjay R; Zhu, Xiaofeng; Tracy, Russell P; Jenny, Nancy S; Reiner, Alex P; Walston, Jeremy; Redline, Susan (Clin Transl Sci, 2010)
Keywords: Adult; African Americans; Alleles; Female; Humans; Interleukin-6; Male; Middle Aged; Polymorphism, Single Nucleotide; Sleep Apnea, Obstructive

Triglyceride-mediated pathways and coronary disease: collaborative analysis of 101 studies. - Sarwar, Nadeem; Sandhu, Manjinder S; Ricketts, Sally L; Butterworth, Adam S; Di Angelantonio, Emanuele; Boekholdt, S Matthijs; Ouwehand, Willem; Watkins, Hugh; Samani, Nilesh J; Saleheen, Danish; Lawlor, Debbie; Reilly, Muredach P; et al. (Lancet, 2010)
BACKGROUND: Whether triglyceride-mediated pathways are causally relevant to coronary heart disease is uncertain. We studied a genetic variant that regulates triglyceride concentration to help judge likelihood of causality. METHODS: We assessed the -1131T>C (rs662799) promoter polymorphism of the apolipoprotein A5 (APOA5) gene in relation to triglyceride concentration, several other risk factors, and risk of coronary heart disease. We compared disease risk for genetically-raised triglyceride concentration (20,842 patients with coronary heart disease, 35,206 controls) with that recorded for equivalent differences in circulating triglyceride concentration in prospective studies (302 430 participants with no history of cardiovascular disease; 12,785 incident cases of coronary heart disease during 2.79 million person-years at risk). We analysed -1131T>C in 1795 people without a history of cardiovascular disease who had information about lipoprotein concentration and diameter obtained by nuclear magnetic resonance spectroscopy. FINDINGS: The minor allele frequency of -1131T>C was 8% (95% CI 7-9). -1131T>C was not significantly associated with several non-lipid risk factors or LDL cholesterol, and it was modestly associated with lower HDL cholesterol (mean difference per C allele 3.5% [95% CI 2.6-4.6]; 0.053 mmol/L [0.039-0.068]), lower apolipoprotein AI (1.3% [0.3-2.3]; 0.023 g/L [0.005-0.041]), and higher apolipoprotein B (3.2% [1.3-5.1]; 0.027 g/L [0.011-0.043]). By contrast, for every C allele inherited, mean triglyceride concentration was 16.0% (95% CI 12.9-18.7), or 0.25 mmol/L (0.20-0.29), higher (p=4.4x10(-24)). The odds ratio for coronary heart disease was 1.18 (95% CI 1.11-1.26; p=2.6x10(-7)) per C allele, which was concordant with the hazard ratio of 1.10 (95% CI 1.08-1.12) per 16% higher triglyceride concentration recorded in prospective studies. -1131T>C was significantly associated with higher VLDL particle concentration (mean difference per C allele 12.2 nmol/L [95% CI 7.7-16.7]; p=9.3x10(-8)) and smaller HDL particle size (0.14 nm [0.08-0.20]; p=7.0x10(-5)), factors that could mediate the effects of triglyceride. INTERPRETATION: These data are consistent with a causal association between triglyceride-mediated pathways and coronary heart disease. FUNDING: British Heart Foundation, UK Medical Research Council, Novartis.
Keywords: Apolipoprotein A-V; Apolipoproteins; Apolipoproteins A; Coronary Disease; Gene Frequency; Genotype; Humans; Lipids; Lipoproteins, HDL; Lipoproteins, LDL; Lipoproteins, VLDL; Mendelian Randomization Analysis; Particle Size; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Risk Factors; Triglycerides

Association of coagulation-related and inflammation-related genes and factor VIIc levels with stroke: the Cardiovascular Health Study. - Zakai, N A; Lange, L; Longstreth, W T; O'Meara, E S; Kelley, J L; Fornage, M; Nikerson, D; Cushman, M; Reiner, A P (J Thromb Haemost, 2011)
BACKGROUND: Thrombosis and inflammation are critical in stroke etiology, but associations of coagulation and inflammation gene variants with stroke, and particularly factor VII levels, are inconclusive. OBJECTIVES: To test the associations between 736 single-nucleotide polymorphisms (SNPs) between tagging haplotype patterns of 130 coagulation and inflammation genes, and stroke events, in the 5888 participants aged ≥ 65 years of the observational Cardiovascular Health Study cohort. PATIENTS/METHODS: With 16 years of follow-up, age-adjusted and sex-adjusted Cox models were used to estimate associations of SNPs and FVIIc levels with future stroke. RESULTS: Eight hundred and fifteen strokes occurred in 5255 genotyped participants without baseline stroke (748 ischemic strokes; 586 among whites). Among whites, six SNPs were associated with stroke, with a nominal P-value of < 0.01: rs6046 and rs3093261 (F7); rs4918851 and rs3781387 (HABP2); and rs3138055 (NFKB1A) and rs4648004 (NFKB1). Two of these SNPs were associated with FVIIc levels (units of percentage activity): rs6046 (β = -18.5, P = 2.38 × 10(-83)) and rs3093261 (β = 2.99, P = 3.93 × 10(-6)). After adjustment for age, sex, race, and cardiovascular risk factors, the association of FVIIc quintiles (Q) with stroke were as follows (hazard ratio; 95% confidence interval): Q1, reference; Q2, 1.4, 1.1-1.9); Q3, 1.1, 0.8-1.5); Q4, 1.5, 1.1-2.0); and Q5, 1.6, 1.2-2.2). Associations between SNPs and stroke were independent of FVIIc levels. CONCLUSIONS: Variations in FVII-related genes and FVIIc levels were associated with risk of incident ischemic stroke in this elderly cohort, suggesting a potential causal role for FVII in stroke etiology.
Keywords: Blood Coagulation Factors; Cardiovascular Diseases; Cohort Studies; Factor VII; Female; Humans; Inflammation; Male; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Stroke

Association of eGFR-Related Loci Identified by GWAS with Incident CKD and ESRD. - Böger, Carsten A; Gorski, Mathias; Li, Man; Hoffmann, Michael M; Huang, Chunmei; Yang, Qiong; Teumer, Alexander; Krane, Vera; O'Seaghdha, Conall M; Kutalik, Zoltán; Wichmann, H-Erich; Haak, Thomas; et al. (PLoS Genet, 2011)
Family studies suggest a genetic component to the etiology of chronic kidney disease (CKD) and end stage renal disease (ESRD). Previously, we identified 16 loci for eGFR in genome-wide association studies, but the associations of these single nucleotide polymorphisms (SNPs) for incident CKD or ESRD are unknown. We thus investigated the association of these loci with incident CKD in 26,308 individuals of European ancestry free of CKD at baseline drawn from eight population-based cohorts followed for a median of 7.2 years (including 2,122 incident CKD cases defined as eGFR <60ml/min/1.73m(2) at follow-up) and with ESRD in four case-control studies in subjects of European ancestry (3,775 cases, 4,577 controls). SNPs at 11 of the 16 loci (UMOD, PRKAG2, ANXA9, DAB2, SHROOM3, DACH1, STC1, SLC34A1, ALMS1/NAT8, UBE2Q2, and GCKR) were associated with incident CKD; p-values ranged from p = 4.1e-9 in UMOD to p = 0.03 in GCKR. After adjusting for baseline eGFR, six of these loci remained significantly associated with incident CKD (UMOD, PRKAG2, ANXA9, DAB2, DACH1, and STC1). SNPs in UMOD (OR = 0.92, p = 0.04) and GCKR (OR = 0.93, p = 0.03) were nominally associated with ESRD. In summary, the majority of eGFR-related loci are either associated or show a strong trend towards association with incident CKD, but have modest associations with ESRD in individuals of European descent. Additional work is required to characterize the association of genetic determinants of CKD and ESRD at different stages of disease progression.
Keywords: Adaptor Proteins, Signal Transducing; Adult; Aged; Chronic Disease; Creatinine; European Continental Ancestry Group; Female; Follow-Up Studies; Genetic Association Studies; Humans; Kidney Diseases; Kidney Failure, Chronic; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptor, Epidermal Growth Factor; Uromodulin

Association of genetic variants and incident coronary heart disease in multiethnic cohorts: the PAGE study. - Franceschini, Nora; Carty, Cara; Bůzková, Petra; Reiner, Alex P; Garrett, Tiana; Lin, Yi; Vöckler, Jens-S; Hindorff, Lucia A; Cole, Shelley A; Boerwinkle, Eric; Lin, Dan-Yu; Bookman, Ebony; et al. (Circ Cardiovasc Genet, 2011)
BACKGROUND: Genome-wide association studies identified several single nucleotide polymorphisms (SNP) associated with prevalent coronary heart disease (CHD), but less is known of associations with incident CHD. The association of 13 published CHD SNPs was examined in 5 ancestry groups of 4 large US prospective cohorts. METHODS AND RESULTS: The analyses included incident coronary events over an average 9.1 to 15.7 follow-up person-years in up to 26 617 white individuals (6626 events), 8018 black individuals (914 events), 1903 Hispanic individuals (113 events), 3669 American Indian individuals (595 events), and 885 Asian/Pacific Islander individuals (66 events). We used Cox proportional hazards models (with additive mode of inheritance) adjusted for age, sex, and ancestry (as needed). Nine loci were statistically associated with incident CHD events in white participants: 9p21 (rs10757278; P=4.7 × 10(-41)), 16q23.1 (rs2549513; P=0.0004), 6p24.1 (rs499818; P=0.0002), 2q36.3 (rs2943634; P=6.7 × 10(-6)), MTHFD1L (rs6922269, P=5.1 × 10(-10)), APOE (rs429358; P=2.7×10(-18)), ZNF627 (rs4804611; P=5.0 × 10(-8)), CXCL12 (rs501120; P=1.4 × 10(-6)) and LPL (rs268; P=2.7 × 10(-17)). The 9p21 region showed significant between-study heterogeneity, with larger effects in individuals age 55 years or younger and in women. Inclusion of coronary revascularization procedures among the incident CHD events introduced heterogeneity. The SNPs were not associated with CHD in black participants, and associations varied in other US minorities. CONCLUSIONS: Prospective analyses of white participants replicated several reported cross-sectional CHD-SNP associations.
Keywords: Aged; Aged, 80 and over; Continental Population Groups; Coronary Disease; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies

The association of genetic variants in interleukin-1 genes with cognition: findings from the cardiovascular health study. - Benke, K S; Carlson, M C; Doan, B Q; Walston, J D; Xue, Q L; Reiner, A P; Fried, L P; Arking, D E; Chakravarti, A; Fallin, M D (Exp Gerontol, 2011)
The inflammatory cytokine interleukin-1 (IL1) potentially plays a role in cognitive deterioration through pathology due to a dementing disorder or due to an aging process. Study of genetic variants in the IL1 genes has been mostly limited to diseases such as Alzheimer's, however, there may be benefit to studying a continuous measure of cognition. Using data from the Cardiovascular Health Study, we evaluate genetic variation in the genes encoding inflammatory agonists IL1A and IL1B, and the antagonist IL1RN, with repeated measures of global cognition (3MS) and processing speed (DSST), using mixed effects models. We found statistically significant minor allele SNP associations with baseline performance on the 3MS in the IL1RN gene for Caucasians (rs17042917: beta=0.47, 95%CI=0.09, 0.85, p=0.016; rs4251961: beta=-0.36, 95%CI=-0.13,-0.60, p=0.0027; rs931471: beta=0.39, 95%CI=0.13, 0.65, p=0.0032), and the IL1B gene for African Americans (rs1143627: beta=1.6, 95%CI=0.48, 2.8; p=0.006 and rs1143634: beta=2.09, 95%CI=0.39, 3.8; p=0.016). Associations appear to be weaker in a subgroup with higher education level. Upon removing those diagnosed with dementia, effect sizes and statistical significance attenuated. These results provide supporting evidence that genetic variants in IL1 genes may be involved in inflammatory-related lowered cognition, that higher education may modify genetic predisposition, and that these associations may be driven by a dementia process.
Keywords: African Americans; Aged; Aged, 80 and over; Cognition; Cognition Disorders; Dementia; Educational Status; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Interleukin 1 Receptor Antagonist Protein; Interleukin-1alpha; Interleukin-1beta; Linkage Disequilibrium; Longitudinal Studies; Male; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; United States

Association of genetic variation with systolic and diastolic blood pressure among African Americans: the Candidate Gene Association Resource study. - Fox, Ervin R; Young, J Hunter; Li, Yali; Dreisbach, Albert W; Keating, Brendan J; Musani, Solomon K; Liu, Kiang; Morrison, Alanna C; Ganesh, Santhi; Kutlar, Abdullah; Ramachandran, Vasan S; Polak, Josef F; et al. (Hum Mol Genet, 2011)
The prevalence of hypertension in African Americans (AAs) is higher than in other US groups; yet, few have performed genome-wide association studies (GWASs) in AA. Among people of European descent, GWASs have identified genetic variants at 13 loci that are associated with blood pressure. It is unknown if these variants confer susceptibility in people of African ancestry. Here, we examined genome-wide and candidate gene associations with systolic blood pressure (SBP) and diastolic blood pressure (DBP) using the Candidate Gene Association Resource (CARe) consortium consisting of 8591 AAs. Genotypes included genome-wide single-nucleotide polymorphism (SNP) data utilizing the Affymetrix 6.0 array with imputation to 2.5 million HapMap SNPs and candidate gene SNP data utilizing a 50K cardiovascular gene-centric array (ITMAT-Broad-CARe [IBC] array). For Affymetrix data, the strongest signal for DBP was rs10474346 (P= 3.6 × 10(-8)) located near GPR98 and ARRDC3. For SBP, the strongest signal was rs2258119 in C21orf91 (P= 4.7 × 10(-8)). The top IBC association for SBP was rs2012318 (P= 6.4 × 10(-6)) near SLC25A42 and for DBP was rs2523586 (P= 1.3 × 10(-6)) near HLA-B. None of the top variants replicated in additional AA (n = 11 882) or European-American (n = 69 899) cohorts. We replicated previously reported European-American blood pressure SNPs in our AA samples (SH2B3, P= 0.009; TBX3-TBX5, P= 0.03; and CSK-ULK3, P= 0.0004). These genetic loci represent the best evidence of genetic influences on SBP and DBP in AAs to date. More broadly, this work supports that notion that blood pressure among AAs is a trait with genetic underpinnings but also with significant complexity.
Keywords: Adult; African Americans; Aged; Blood Pressure; Cohort Studies; Diastole; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Hypertension; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Systole

Association of genomic loci from a cardiovascular gene SNP array with fibrinogen levels in European Americans and African-Americans from six cohort studies: the Candidate Gene Association Resource (CARe). - Wassel, Christina L; Lange, Leslie A; Keating, Brendan J; Taylor, Kira C; Johnson, Andrew D; Palmer, Cameron; Ho, Lindsey A; Smith, Nicholas L; Lange, Ethan M; Li, Yun; Yang, Qiong; Delaney, Joseph A; et al. (Blood, 2011)
Several common genomic loci, involving various immunity- and metabolism-related genes, have been associated with plasma fibrinogen in European Americans (EAs). The genetic determinants of fibrinogen in African Americans (AAs) are poorly characterized. Using a vascular gene-centric array in 23,634 EA and 6657 AA participants from 6 studies comprising the Candidate Gene Association Resource project, we examined the association of 47,539 common and lower frequency variants with fibrinogen concentration. We identified a rare Pro265Leu variant in FGB (rs6054) associated with lower fibrinogen. Common fibrinogen gene single nucleotide polymorphisms (FGB rs1800787 and FGG rs2066861) significantly associated with fibrinogen in EAs were prevalent in AAs and showed consistent associations. Several fibrinogen locus single nucleotide polymorphism associated with lower fibrinogen were exclusive to AAs; these include a newly reported association with FGA rs10050257. For IL6R, IL1RN, and NLRP3 inflammatory gene loci, associations with fibrinogen were concordant between EAs and AAs, but not at other loci (CPS1, PCCB, and SCL22A5-IRF1). The association of FGG rs2066861 with fibrinogen differed according to assay type used to measure fibrinogen. Further characterization of common and lower-frequency genetic variants that contribute to interpopulation differences in fibrinogen phenotype may help refine our understanding of the contribution of hemostasis and inflammation to atherothrombotic risk.
Keywords: Adult; African Americans; Aged; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Fibrinogen; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

Association of HSP70 and its co-chaperones with Alzheimer's disease. - Broer, Linda; Ikram, Mohammad Arfan; Schuur, Maaike; DeStefano, Anita L; Bis, Joshua C; Liu, Fan; Rivadeneira, Fernando; Uitterlinden, André G; Beiser, Alexa S; Longstreth, William T; Hofman, Albert; Aulchenko, Yurii; et al. (J Alzheimers Dis, 2011)
The heat shock protein (HSP) 70 family has been implicated in the pathology of Alzheimer's disease (AD). In this study, we examined common genetic variations in the 80 genes encoding HSP70 and its co-chaperones. We conducted a study in a series of 462 patients and 5238 unaffected participants derived from the Rotterdam Study, a population-based study including 7983 persons aged 55 years and older. We genotyped a total of 12,053 Single Nucleotide Polymorphisms (SNPs) using the HumanHap550K Genotyping BeadChip from Illumina. Replication was performed in two independent cohort studies, the Framingham Heart study (FHS; n = 806) and Cardiovascular Health Study (CHS; n = 2150). When adjusting for multiple testing, we found a small but consistent, though not significant effect of rs12118313 located 32 kb from PFDN2, with an OR of 1.19 (p-value from meta-analysis = 0.003). However this SNP was in the intron of another gene, suggesting it is unlikely this SNP reflects the effect of PFDN2. In a formal pathway analysis we found nominally significant evidence for an association of BAG, DNAJA and prefoldin with AD. These findings corroborate with those of a study of 2032 AD patients and 5328 controls, in which several members of the prefoldin family showed evidence for association to AD. Our study did not reveal evidence for a genetic variant if the HSP70 family with a major effect on AD. However, our findings of the single SNP analysis and pathway analysis suggest that multiple genetic variants in prefoldin are associated with AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Genetic Association Studies; Genetic Variation; HSP70 Heat-Shock Proteins; Humans; Middle Aged; Molecular Chaperones; Polymorphism, Single Nucleotide

Association of hypertension drug target genes with blood pressure and hypertension in 86,588 individuals. - Johnson, Andrew D; Newton-Cheh, Christopher; Chasman, Daniel I; Ehret, Georg B; Johnson, Toby; Rose, Lynda; Rice, Kenneth; Verwoert, Germaine C; Launer, Lenore J; Gudnason, Vilmundur; Larson, Martin G; Chakravarti, Aravinda; et al. (Hypertension, 2011)
We previously conducted genome-wide association meta-analysis of systolic blood pressure, diastolic blood pressure, and hypertension in 29,136 people from 6 cohort studies in the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. Here we examine associations of these traits with 30 gene regions encoding known antihypertensive drug targets. We find nominal evidence of association of ADRB1, ADRB2, AGT, CACNA1A, CACNA1C, and SLC12A3 polymorphisms with 1 or more BP traits in the Cohorts for Heart and Aging Research in Genomic Epidemiology genome-wide association meta-analysis. We attempted replication of the top meta-analysis single nucleotide polymorphisms for these genes in the Global BPgen Consortium (n=34,433) and the Women's Genome Health Study (n=23,019) and found significant results for rs1801253 in ADRB1 (Arg389Gly), with the Gly allele associated with a lower mean systolic blood pressure (β: 0.57 mm Hg; SE: 0.09 mm Hg; meta-analysis: P=4.7×10(-10)), diastolic blood pressure (β: 0.36 mm Hg; SE: 0.06 mm Hg; meta-analysis: P=9.5×10(-10)), and prevalence of hypertension (β: 0.06 mm Hg; SE: 0.02 mm Hg; meta-analysis: P=3.3×10(-4)). Variation in AGT (rs2004776) was associated with systolic blood pressure (β: 0.42 mm Hg; SE: 0.09 mm Hg; meta-analysis: P=3.8×10(-6)), as well as diastolic blood pressure (P=5.0×10(-8)) and hypertension (P=3.7×10(-7)). A polymorphism in ACE (rs4305) showed modest replication of association with increased hypertension (β: 0.06 mm Hg; SE: 0.01 mm Hg; meta-analysis: P=3.0×10(-5)). Two loci, ADRB1 and AGT, contain single nucleotide polymorphisms that reached a genome-wide significance threshold in meta-analysis for the first time. Our findings suggest that these genes warrant further studies of their genetic effects on blood pressure, including pharmacogenetic interactions.
Keywords: Alleles; Angiotensinogen; Antihypertensive Agents; Blood Pressure; Female; Genetic Predisposition to Disease; Genotype; Humans; Hypertension; Male; Pharmacogenetics; Polymorphism, Single Nucleotide; Receptors, Adrenergic, beta-1

Association of polymorphisms in the hepatocyte growth factor gene promoter with keratoconus. - Burdon, Kathryn P; Macgregor, Stuart; Bykhovskaya, Yelena; Javadiyan, Sharhbanou; Li, Xiaohui; Laurie, Kate J; Muszynska, Dorota; Lindsay, Richard; Lechner, Judith; Haritunians, Talin; Henders, Anjali K; Dash, Durga; et al. (Invest Ophthalmol Vis Sci, 2011)
PURPOSE: Keratoconus is a progressive disorder of the cornea that can lead to severe visual impairment or blindness. Although several genomic regions have been linked to rare familial forms of keratoconus, no genes have yet been definitively identified for common forms of the disease. METHODS: Two genome-wide association scans were undertaken in parallel. The first used pooled DNA from an Australian cohort, followed by typing of top-ranked single-nucleotide polymorphisms (SNPs) in individual DNA samples. The second was conducted in individually genotyped patients, and controls from the USA. Tag SNPs around the hepatocyte growth factor (HGF) gene were typed in three additional replication cohorts. Serum levels of HGF protein in normal individuals were assessed with ELISA and correlated with genotype. RESULTS: The only SNP observed to be associated in both the pooled discovery and primary replication cohort was rs1014091, located upstream of the HGF gene. The nearby SNP rs3735520 was found to be associated in the individually typed discovery cohort (P = 6.1 × 10(-7)). Genotyping of tag SNPs around HGF revealed association at rs3735520 and rs17501108/rs1014091 in four of the five cohorts. Meta-analysis of all five datasets together yielded suggestive P values for rs3735520 (P = 9.9 × 10(-7)) and rs17501108 (P = 9.9 × 10(-5)). In addition, SNP rs3735520 was found to be associated with serum HGF level in normal individuals (P = 0.036). CONCLUSIONS: Taken together, these results implicate genetic variation at the HGF locus with keratoconus susceptibility.
Keywords: Adult; Aged; Chromosomes, Human, Pair 7; Corneal Topography; Enzyme-Linked Immunosorbent Assay; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Hepatocyte Growth Factor; Humans; Keratoconus; Middle Aged; Nucleic Acid Hybridization; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Sequence Tagged Sites

A bivariate genome-wide approach to metabolic syndrome: STAMPEED consortium. - Kraja, Aldi T; Vaidya, Dhananjay; Pankow, James S; Goodarzi, Mark O; Assimes, Themistocles L; Kullo, Iftikhar J; Sovio, Ulla; Mathias, Rasika A; Sun, Yan V; Franceschini, Nora; Absher, Devin; Li, Guo; et al. (Diabetes, 2011)
OBJECTIVE The metabolic syndrome (MetS) is defined as concomitant disorders of lipid and glucose metabolism, central obesity, and high blood pressure, with an increased risk of type 2 diabetes and cardiovascular disease. This study tests whether common genetic variants with pleiotropic effects account for some of the correlated architecture among five metabolic phenotypes that define MetS. RESEARCH DESIGN AND METHODS Seven studies of the STAMPEED consortium, comprising 22,161 participants of European ancestry, underwent genome-wide association analyses of metabolic traits using a panel of ∼2.5 million imputed single nucleotide polymorphisms (SNPs). Phenotypes were defined by the National Cholesterol Education Program (NCEP) criteria for MetS in pairwise combinations. Individuals exceeding the NCEP thresholds for both traits of a pair were considered affected. RESULTS Twenty-nine common variants were associated with MetS or a pair of traits. Variants in the genes LPL, CETP, APOA5 (and its cluster), GCKR (and its cluster), LIPC, TRIB1, LOC100128354/MTNR1B, ABCB11, and LOC100129150 were further tested for their association with individual qualitative and quantitative traits. None of the 16 top SNPs (one per gene) associated simultaneously with more than two individual traits. Of them 11 variants showed nominal associations with MetS per se. The effects of 16 top SNPs on the quantitative traits were relatively small, together explaining from ∼9% of the variance in triglycerides, 5.8% of high-density lipoprotein cholesterol, 3.6% of fasting glucose, and 1.4% of systolic blood pressure. CONCLUSIONS Qualitative and quantitative pleiotropic tests on pairs of traits indicate that a small portion of the covariation in these traits can be explained by the reported common genetic variants.
Keywords: Adult; Aged; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Meta-Analysis as Topic; Metabolic Syndrome; Middle Aged; Phenotype; Polymorphism, Single Nucleotide

Candidate gene association study for diabetic retinopathy in persons with type 2 diabetes: the Candidate gene Association Resource (CARe). - Sobrin, Lucia; Green, Todd; Sim, Xueling; Jensen, Richard A; Tai, E Shyong; Tay, Wan Ting; Wang, Jie Jin; Mitchell, Paul; Sandholm, Niina; Liu, Yiyuan; Hietala, Kustaa; Iyengar, Sudha K; et al. (Invest Ophthalmol Vis Sci, 2011)
PURPOSE: To investigate whether variants in cardiovascular candidate genes, some of which have been previously associated with type 2 diabetes (T2D), diabetic retinopathy (DR), and diabetic nephropathy (DN), are associated with DR in the Candidate gene Association Resource (CARe). METHODS: Persons with T2D who were enrolled in the study (n = 2691) had fundus photography and genotyping of single nucleotide polymorphisms (SNPs) in 2000 candidate genes. Two case definitions were investigated: Early Treatment Diabetic Retinopathy Study (ETDRS) grades ≥ 14 and ≥ 30. The χ² analyses for each CARe cohort were combined by Cochran-Mantel-Haenszel (CMH) pooling of odds ratios (ORs) and corrected for multiple hypothesis testing. Logistic regression was performed with adjustment for other DR risk factors. Results from replication in independent cohorts were analyzed with CMH meta-analysis methods. RESULTS: Among 39 genes previously associated with DR, DN, or T2D, three SNPs in P-selectin (SELP) were associated with DR. The strongest association was to rs6128 (OR = 0.43, P = 0.0001, after Bonferroni correction). These associations remained significant after adjustment for DR risk factors. Among other genes examined, several variants were associated with DR with significant P values, including rs6856425 tagging α-l-iduronidase (IDUA) (P = 2.1 × 10(-5), after Bonferroni correction). However, replication in independent cohorts did not reveal study-wide significant effects. The P values after replication were 0.55 and 0.10 for rs6128 and rs6856425, respectively. CONCLUSIONS: Genes associated with DN, T2D, and vascular diseases do not appear to be consistently associated with DR. A few genetic variants associated with DR, particularly those in SELP and near IDUA, should be investigated in additional DR cohorts.
Keywords: Cardiovascular Diseases; Diabetes Mellitus, Type 2; Diabetic Nephropathies; Diabetic Retinopathy; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Iduronidase; Odds Ratio; P-Selectin; Polymorphism, Single Nucleotide; Risk Factors

Cerivastatin, genetic variants, and the risk of rhabdomyolysis. - Marciante, Kristin D; Durda, Jon P; Heckbert, Susan R; Lumley, Thomas; Rice, Ken; McKnight, Barbara; Totah, Rheem A; Tamraz, Bani; Kroetz, Deanna L; Fukushima, Hisayo; Kaspera, Rüdiger; Bis, Joshua C; et al. (Pharmacogenet Genomics, 2011)
OBJECTIVE: The withdrawal of cerivastatin involved an uncommon but serious adverse reaction, rhabdomyolysis. The bimodal response, rhabdomyolysis in a small proportion of users, points to genetic factors as a potential cause. We conducted a case-control study to evaluate genetic markers for cerivastatin-associated rhabdomyolysis. METHODS: This study had two components: a candidate gene study to evaluate variants in CYP2C8, UGT1A1, UGT1A3, and SLCO1B1; and a genome-wide association study to identify risk factors in other regions of the genome. A total of 185 rhabdomyolysis cases were frequency matched to statin-using controls from the Cardiovascular Health Study (n=374) and the Heart and Vascular Health Study (n=358). Validation relied on functional studies. RESULTS: Permutation test results suggested an association between cerivastatin-associated rhabdomyolysis and variants in SLCO1B1 (P=0.002), but not variants in CYP2C8 (P=0.073) or UGTs (P=0.523). An additional copy of the minor allele of SLCO1B1 rs4149056 (p.Val174Ala) was associated with the risk of rhabdomyolysis (odds ratio: 1.89; 95% confidence interval: 1.40-2.56). In transfected cells, this variant reduced cerivastatin transport by 40% compared with the reference transporter (P<0.001). The genome-wide association study identified an intronic variant (rs2819742) in the ryanodine receptor 2 gene (RYR2) as significant (P=1.74E-07). An additional copy of the minor allele of the RYR2 variant was associated with a reduced risk of rhabdomyolysis (odds ratio: 0.48; 95% confidence interval: 0.36-0.63). CONCLUSION: We identified modest genetic risk factors for an extreme response to cerivastatin. Disabling genetic variants in the candidate genes were not responsible for the bimodal response to cerivastatin.
Keywords: Adult; Aged; Aged, 80 and over; Aryl Hydrocarbon Hydroxylases; Case-Control Studies; Cytochrome P-450 CYP2C8; Female; Genetic Variation; Genome-Wide Association Study; Glucuronosyltransferase; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Organic Anion Transporters; Polymorphism, Single Nucleotide; Pyridines; Rhabdomyolysis; Risk; Ryanodine Receptor Calcium Release Channel; Solute Carrier Organic Anion Transporter Family Member 1b1

Enhanced statistical tests for GWAS in admixed populations: assessment using African Americans from CARe and a Breast Cancer Consortium. - Pasaniuc, Bogdan; Zaitlen, Noah; Lettre, Guillaume; Chen, Gary K; Tandon, Arti; Kao, W H Linda; Ruczinski, Ingo; Fornage, Myriam; Siscovick, David S; Zhu, Xiaofeng; Larkin, Emma; Lange, Leslie A; et al. (PLoS Genet, 2011)
While genome-wide association studies (GWAS) have primarily examined populations of European ancestry, more recent studies often involve additional populations, including admixed populations such as African Americans and Latinos. In admixed populations, linkage disequilibrium (LD) exists both at a fine scale in ancestral populations and at a coarse scale (admixture-LD) due to chromosomal segments of distinct ancestry. Disease association statistics in admixed populations have previously considered SNP association (LD mapping) or admixture association (mapping by admixture-LD), but not both. Here, we introduce a new statistical framework for combining SNP and admixture association in case-control studies, as well as methods for local ancestry-aware imputation. We illustrate the gain in statistical power achieved by these methods by analyzing data of 6,209 unrelated African Americans from the CARe project genotyped on the Affymetrix 6.0 chip, in conjunction with both simulated and real phenotypes, as well as by analyzing the FGFR2 locus using breast cancer GWAS data from 5,761 African-American women. We show that, at typed SNPs, our method yields an 8% increase in statistical power for finding disease risk loci compared to the power achieved by standard methods in case-control studies. At imputed SNPs, we observe an 11% increase in statistical power for mapping disease loci when our local ancestry-aware imputation framework and the new scoring statistic are jointly employed. Finally, we show that our method increases statistical power in regions harboring the causal SNP in the case when the causal SNP is untyped and cannot be imputed. Our methods and our publicly available software are broadly applicable to GWAS in admixed populations.
Keywords: African Americans; Algorithms; Breast Neoplasms; Chromosome Mapping; Coronary Disease; Diabetes Mellitus, Type 2; Female; Gene Frequency; Genetic Variation; Genetics, Population; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Male; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Principal Component Analysis; Receptor, Fibroblast Growth Factor, Type 2; Software

A gene-centric association scan for Coagulation Factor VII levels in European and African Americans: the Candidate Gene Association Resource (CARe) Consortium. - Taylor, Kira C; Lange, Leslie A; Zabaneh, Delilah; Lange, Ethan; Keating, Brendan J; Tang, Weihong; Smith, Nicholas L; Delaney, Joseph A; Kumari, Meena; Hingorani, Aroon; North, Kari E; Kivimaki, Mika; et al. (Hum Mol Genet, 2011)
Polymorphisms in several distinct genomic regions, including the F7 gene, were recently associated with factor VII (FVII) levels in European Americans (EAs). The genetic determinants of FVII in African Americans (AAs) are unknown. We used a 50,000 single nucleotide polymorphism (SNP) gene-centric array having dense coverage of over 2,000 candidate genes for cardiovascular disease (CVD) pathways in a community-based sample of 16,324 EA and 3898 AA participants from the Candidate Gene Association Resource (CARe) consortium. Our aim was the discovery of new genomic loci and more detailed characterization of existing loci associated with FVII levels. In EAs, we identified three new loci associated with FVII, of which APOA5 on chromosome 11q23 and HNF4A on chromosome 20q12-13 were replicated in a sample of 4289 participants from the Whitehall II study. We confirmed four previously reported FVII-associated loci (GCKR, MS4A6A, F7 and PROCR) in CARe EA samples. In AAs, the F7 and PROCR regions were significantly associated with FVII. Several of the FVII-associated regions are known to be associated with lipids and other cardiovascular-related traits. At the F7 locus, there was evidence of at least five independently associated SNPs in EAs and three independent signals in AAs. Though the variance in FVII explained by the existing loci is substantial (20% in EA and 10% in AA), larger sample sizes and investigation of lower frequency variants may be required to identify additional FVII-associated loci in EAs and AAs and further clarify the relationship between FVII and other CVD risk factors.
Keywords: Adult; African Americans; Aged; Cardiovascular Diseases; European Continental Ancestry Group; Factor VII; Female; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Genetic association for renal traits among participants of African ancestry reveals new loci for renal function. - Liu, Ching-Ti; Garnaas, Maija K; Tin, Adrienne; Köttgen, Anna; Franceschini, Nora; Peralta, Carmen A; de Boer, Ian H; Lu, Xiaoning; Atkinson, Elizabeth; Ding, Jingzhong; Nalls, Michael; Shriner, Daniel; et al. (PLoS Genet, 2011)
Chronic kidney disease (CKD) is an increasing global public health concern, particularly among populations of African ancestry. We performed an interrogation of known renal loci, genome-wide association (GWA), and IBC candidate-gene SNP association analyses in African Americans from the CARe Renal Consortium. In up to 8,110 participants, we performed meta-analyses of GWA and IBC array data for estimated glomerular filtration rate (eGFR), CKD (eGFR <60 mL/min/1.73 m(2)), urinary albumin-to-creatinine ratio (UACR), and microalbuminuria (UACR >30 mg/g) and interrogated the 250 kb flanking region around 24 SNPs previously identified in European Ancestry renal GWAS analyses. Findings were replicated in up to 4,358 African Americans. To assess function, individually identified genes were knocked down in zebrafish embryos by morpholino antisense oligonucleotides. Expression of kidney-specific genes was assessed by in situ hybridization, and glomerular filtration was evaluated by dextran clearance. Overall, 23 of 24 previously identified SNPs had direction-consistent associations with eGFR in African Americans, 2 of which achieved nominal significance (UMOD, PIP5K1B). Interrogation of the flanking regions uncovered 24 new index SNPs in African Americans, 12 of which were replicated (UMOD, ANXA9, GCKR, TFDP2, DAB2, VEGFA, ATXN2, GATM, SLC22A2, TMEM60, SLC6A13, and BCAS3). In addition, we identified 3 suggestive loci at DOK6 (p-value = 5.3×10(-7)) and FNDC1 (p-value = 3.0×10(-7)) for UACR, and KCNQ1 with eGFR (p = 3.6×10(-6)). Morpholino knockdown of kcnq1 in the zebrafish resulted in abnormal kidney development and filtration capacity. We identified several SNPs in association with eGFR in African Ancestry individuals, as well as 3 suggestive loci for UACR and eGFR. Functional genetic studies support a role for kcnq1 in glomerular development in zebrafish.
Keywords: Adaptor Proteins, Vesicular Transport; Adult; African Continental Ancestry Group; Aged; Animals; Female; Gene Knockdown Techniques; Genetic Association Studies; Genetic Loci; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; KCNQ1 Potassium Channel; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Neoplasm Proteins; Phenotype; Polymorphism, Single Nucleotide; Zebrafish

Genetic determinants of lipid traits in diverse populations from the population architecture using genomics and epidemiology (PAGE) study. - Dumitrescu, Logan; Carty, Cara L; Taylor, Kira; Schumacher, Fredrick R; Hindorff, Lucia A; Ambite, José L; Anderson, Garnet; Best, Lyle G; Brown-Gentry, Kristin; Bůzková, Petra; Carlson, Christopher S; Cochran, Barbara; et al. (PLoS Genet, 2011)
For the past five years, genome-wide association studies (GWAS) have identified hundreds of common variants associated with human diseases and traits, including high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) levels. Approximately 95 loci associated with lipid levels have been identified primarily among populations of European ancestry. The Population Architecture using Genomics and Epidemiology (PAGE) study was established in 2008 to characterize GWAS-identified variants in diverse population-based studies. We genotyped 49 GWAS-identified SNPs associated with one or more lipid traits in at least two PAGE studies and across six racial/ethnic groups. We performed a meta-analysis testing for SNP associations with fasting HDL-C, LDL-C, and ln(TG) levels in self-identified European American (~20,000), African American (~9,000), American Indian (~6,000), Mexican American/Hispanic (~2,500), Japanese/East Asian (~690), and Pacific Islander/Native Hawaiian (~175) adults, regardless of lipid-lowering medication use. We replicated 55 of 60 (92%) SNP associations tested in European Americans at p<0.05. Despite sufficient power, we were unable to replicate ABCA1 rs4149268 and rs1883025, CETP rs1864163, and TTC39B rs471364 previously associated with HDL-C and MAFB rs6102059 previously associated with LDL-C. Based on significance (p<0.05) and consistent direction of effect, a majority of replicated genotype-phentoype associations for HDL-C, LDL-C, and ln(TG) in European Americans generalized to African Americans (48%, 61%, and 57%), American Indians (45%, 64%, and 77%), and Mexican Americans/Hispanics (57%, 56%, and 86%). Overall, 16 associations generalized across all three populations. For the associations that did not generalize, differences in effect sizes, allele frequencies, and linkage disequilibrium offer clues to the next generation of association studies for these traits.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Continental Population Groups; Female; Gene Frequency; Genetics, Population; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Lipid Metabolism; Lipoproteins, HDL; Lipoproteins, LDL; Male; Middle Aged; Molecular Epidemiology; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors; Triglycerides; Young Adult

Genetic loci associated with plasma phospholipid n-3 fatty acids: a meta-analysis of genome-wide association studies from the CHARGE Consortium. - Lemaitre, Rozenn N; Tanaka, Toshiko; Tang, Weihong; Manichaikul, Ani; Foy, Millennia; Kabagambe, Edmond K; Nettleton, Jennifer A; King, Irena B; Weng, Lu-Chen; Bhattacharya, Sayanti; Bandinelli, Stefania; Bis, Joshua C; et al. (PLoS Genet, 2011)
Long-chain n-3 polyunsaturated fatty acids (PUFAs) can derive from diet or from α-linolenic acid (ALA) by elongation and desaturation. We investigated the association of common genetic variation with plasma phospholipid levels of the four major n-3 PUFAs by performing genome-wide association studies in five population-based cohorts comprising 8,866 subjects of European ancestry. Minor alleles of SNPs in FADS1 and FADS2 (desaturases) were associated with higher levels of ALA (p = 3 x 10⁻⁶⁴) and lower levels of eicosapentaenoic acid (EPA, p = 5 x 10⁻⁵⁸) and docosapentaenoic acid (DPA, p = 4 x 10⁻¹⁵⁴). Minor alleles of SNPs in ELOVL2 (elongase) were associated with higher EPA (p = 2 x 10⁻¹²) and DPA (p = 1 x 10⁻⁴³) and lower docosahexaenoic acid (DHA, p = 1 x 10⁻¹⁵). In addition to genes in the n-3 pathway, we identified a novel association of DPA with several SNPs in GCKR (glucokinase regulator, p = 1 x 10⁻⁸). We observed a weaker association between ALA and EPA among carriers of the minor allele of a representative SNP in FADS2 (rs1535), suggesting a lower rate of ALA-to-EPA conversion in these subjects. In samples of African, Chinese, and Hispanic ancestry, associations of n-3 PUFAs were similar with a representative SNP in FADS1 but less consistent with a representative SNP in ELOVL2. Our findings show that common variation in n-3 metabolic pathway genes and in GCKR influences plasma phospholipid levels of n-3 PUFAs in populations of European ancestry and, for FADS1, in other ancestries.
Keywords: Alleles; Continental Population Groups; Fatty Acids, Omega-3; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide

Genetic variants in novel pathways influence blood pressure and cardiovascular disease risk. - Ehret, Georg B; Munroe, Patricia B; Rice, Kenneth M; Bochud, Murielle; Johnson, Andrew D; Chasman, Daniel I; Smith, Albert V; Tobin, Martin D; Verwoert, Germaine C; Hwang, Shih-Jen; Pihur, Vasyl; Vollenweider, Peter; et al. (Nature, 2011)
Blood pressure is a heritable trait influenced by several biological pathways and responsive to environmental stimuli. Over one billion people worldwide have hypertension (≥140 mm Hg systolic blood pressure or  ≥90 mm Hg diastolic blood pressure). Even small increments in blood pressure are associated with an increased risk of cardiovascular events. This genome-wide association study of systolic and diastolic blood pressure, which used a multi-stage design in 200,000 individuals of European descent, identified sixteen novel loci: six of these loci contain genes previously known or suspected to regulate blood pressure (GUCY1A3-GUCY1B3, NPR3-C5orf23, ADM, FURIN-FES, GOSR2, GNAS-EDN3); the other ten provide new clues to blood pressure physiology. A genetic risk score based on 29 genome-wide significant variants was associated with hypertension, left ventricular wall thickness, stroke and coronary artery disease, but not kidney disease or kidney function. We also observed associations with blood pressure in East Asian, South Asian and African ancestry individuals. Our findings provide new insights into the genetics and biology of blood pressure, and suggest potential novel therapeutic pathways for cardiovascular disease prevention.
Keywords: Africa; Asia; Blood Pressure; Cardiovascular Diseases; Coronary Artery Disease; Europe; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Kidney Diseases; Polymorphism, Single Nucleotide; Stroke

Genetic variation near IRS1 associates with reduced adiposity and an impaired metabolic profile. - Kilpeläinen, Tuomas O; Zillikens, M Carola; Stančáková, Alena; Finucane, Francis M; Ried, Janina S; Langenberg, Claudia; Zhang, Weihua; Beckmann, Jacques S; Luan, Jian'an; Vandenput, Liesbeth; Styrkarsdottir, Unnur; Zhou, Yanhua; et al. (Nat Genet, 2011)
Genome-wide association studies have identified 32 loci influencing body mass index, but this measure does not distinguish lean from fat mass. To identify adiposity loci, we meta-analyzed associations between ∼2.5 million SNPs and body fat percentage from 36,626 individuals and followed up the 14 most significant (P < 10(-6)) independent loci in 39,576 individuals. We confirmed a previously established adiposity locus in FTO (P = 3 × 10(-26)) and identified two new loci associated with body fat percentage, one near IRS1 (P = 4 × 10(-11)) and one near SPRY2 (P = 3 × 10(-8)). Both loci contain genes with potential links to adipocyte physiology. Notably, the body-fat-decreasing allele near IRS1 is associated with decreased IRS1 expression and with an impaired metabolic profile, including an increased visceral to subcutaneous fat ratio, insulin resistance, dyslipidemia, risk of diabetes and coronary artery disease and decreased adiponectin levels. Our findings provide new insights into adiposity and insulin resistance.
Keywords: Adiponectin; Adiposity; Alleles; Body Fat Distribution; Body Mass Index; Body Weight; Female; Genetic Variation; Genome-Wide Association Study; Humans; Insulin Receptor Substrate Proteins; Intracellular Signaling Peptides and Proteins; Male; Membrane Proteins; Meta-Analysis as Topic; Metabolome; Obesity; Polymorphism, Single Nucleotide; Subcutaneous Fat

Genome-wide association analysis of soluble ICAM-1 concentration reveals novel associations at the NFKBIK, PNPLA3, RELA, and SH2B3 loci. - Paré, Guillaume; Ridker, Paul M; Rose, Lynda; Barbalic, Maja; Dupuis, Josée; Dehghan, Abbas; Bis, Joshua C; Benjamin, Emelia J; Shiffman, Dov; Parker, Alexander N; Chasman, Daniel I (PLoS Genet, 2011)
Soluble ICAM-1 (sICAM-1) is an endothelium-derived inflammatory marker that has been associated with diverse conditions such as myocardial infarction, diabetes, stroke, and malaria. Despite evidence for a heritable component to sICAM-1 levels, few genetic loci have been identified so far. To comprehensively address this issue, we performed a genome-wide association analysis of sICAM-1 concentration in 22,435 apparently healthy women from the Women's Genome Health Study. While our results confirm the previously reported associations at the ABO and ICAM1 loci, four novel associations were identified in the vicinity of NFKBIK (rs3136642, P = 5.4 × 10(-9)), PNPLA3 (rs738409, P  =  5.8 × 10(-9)), RELA (rs1049728, P =  2.7 × 10(-16)), and SH2B3 (rs3184504, P =  2.9 × 10(-17)). Two loci, NFKBIB and RELA, are involved in NFKB signaling pathway; PNPLA3 is known for its association with fatty liver disease; and SH3B2 has been associated with a multitude of traits and disease including myocardial infarction. These associations provide insights into the genetic regulation of sICAM-1 levels and implicate these loci in the regulation of endothelial function.
Keywords: ABO Blood-Group System; Cohort Studies; Female; Gene Frequency; Genetic Loci; Genome, Human; Genome-Wide Association Study; Genotype; Humans; I-kappa B Kinase; Intercellular Adhesion Molecule-1; Lipase; Membrane Proteins; Models, Genetic; Multifactorial Inheritance; Polymorphism, Single Nucleotide; Proteins; Transcription Factor RelA

Genome-wide association studies of cerebral white matter lesion burden: the CHARGE consortium. - Fornage, Myriam; Debette, Stephanie; Bis, Joshua C; Schmidt, Helena; Ikram, M Arfan; Dufouil, Carole; Sigurdsson, Sigurdur; Lumley, Thomas; DeStefano, Anita L; Fazekas, Franz; Vrooman, Henri A; Shibata, Dean K; et al. (Ann Neurol, 2011)
OBJECTIVE: White matter hyperintensities (WMHs) detectable by magnetic resonance imaging are part of the spectrum of vascular injury associated with aging of the brain and are thought to reflect ischemic damage to the small deep cerebral vessels. WMHs are associated with an increased risk of cognitive and motor dysfunction, dementia, depression, and stroke. Despite a significant heritability, few genetic loci influencing WMH burden have been identified. METHODS: We performed a meta-analysis of genome-wide association studies (GWASs) for WMH burden in 9,361 stroke-free individuals of European descent from 7 community-based cohorts. Significant findings were tested for replication in 3,024 individuals from 2 additional cohorts. RESULTS: We identified 6 novel risk-associated single nucleotide polymorphisms (SNPs) in 1 locus on chromosome 17q25 encompassing 6 known genes including WBP2, TRIM65, TRIM47, MRPL38, FBF1, and ACOX1. The most significant association was for rs3744028 (p(discovery) = 4.0 × 10(-9) ; p(replication) = 1.3 × 10(-7) ; p(combined) = 4.0 × 10(-15) ). Other SNPs in this region also reaching genome-wide significance were rs9894383 (p = 5.3 × 10(-9) ), rs11869977 (p = 5.7 × 10(-9) ), rs936393 (p = 6.8 × 10(-9) ), rs3744017 (p = 7.3 × 10(-9) ), and rs1055129 (p = 4.1 × 10(-8) ). Variant alleles at these loci conferred a small increase in WMH burden (4-8% of the overall mean WMH burden in the sample). INTERPRETATION: This large GWAS of WMH burden in community-based cohorts of individuals of European descent identifies a novel locus on chromosome 17. Further characterization of this locus may provide novel insights into the pathogenesis of cerebral WMH.
Keywords: Aged; Aged, 80 and over; Cerebral Cortex; Chromosomes, Human, Pair 17; Cognition Disorders; Cohort Studies; European Continental Ancestry Group; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Middle Aged; Movement Disorders; Nerve Fibers, Myelinated; Polymorphism, Single Nucleotide; Residence Characteristics; RNA, Messenger

Genome-wide association study for serum urate concentrations and gout among African Americans identifies genomic risk loci and a novel URAT1 loss-of-function allele. - Tin, Adrienne; Woodward, Owen M; Kao, Wen Hong Linda; Liu, Ching-Ti; Lu, Xiaoning; Nalls, Michael A; Shriner, Daniel; Semmo, Mariam; Akylbekova, Ermeg L; Wyatt, Sharon B; Hwang, Shih-Jen; Yang, Qiong; et al. (Hum Mol Genet, 2011)
Serum urate concentrations are highly heritable and elevated serum urate is a key risk factor for gout. Genome-wide association studies (GWAS) of serum urate in African American (AA) populations are lacking. We conducted a meta-analysis of GWAS of serum urate levels and gout among 5820 AA and a large candidate gene study among 6890 AA and 21 708 participants of European ancestry (EA) within the Candidate Gene Association Resource Consortium. Findings were tested for replication among 1996 independent AA individuals, and evaluated for their association among 28 283 EA participants of the CHARGE Consortium. Functional studies were conducted using (14)C-urate transport assays in mammalian Chinese hamster ovary cells. In the discovery GWAS of serum urate, three loci achieved genome-wide significance (P< 5.0 × 10(-8)): a novel locus near SGK1/SLC2A12 on chromosome 6 (rs9321453, P= 1.0 × 10(-9)), and two loci previously identified in EA participants, SLC2A9 (P= 3.8 × 10(-32)) and SLC22A12 (P= 2.1 × 10(-10)). A novel rare non-synonymous variant of large effect size in SLC22A12, rs12800450 (minor allele frequency 0.01, G65W), was identified and replicated (beta -1.19 mg/dl, P= 2.7 × 10(-16)). (14)C-urate transport assays showed reduced urate transport for the G65W URAT1 mutant. Finally, in analyses of 11 loci previously associated with serum urate in EA individuals, 10 of 11 lead single-nucleotide polymorphisms showed direction-consistent association with urate among AA. In summary, we identified and replicated one novel locus in association with serum urate levels and experimentally characterize the novel G65W variant in URAT1 as a functional allele. Our data support the importance of multi-ethnic GWAS in the identification of novel risk loci as well as functional variants.
Keywords: Adult; African Americans; Aged; Animals; CHO Cells; Cricetinae; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Gout; Humans; Loss of Heterozygosity; Male; Middle Aged; Organic Anion Transporters; Organic Cation Transport Proteins; Polymorphism, Single Nucleotide; Uric Acid; Young Adult

A genome-wide association study identifies novel loci associated with circulating IGF-I and IGFBP-3. - Kaplan, Robert C; Petersen, Ann-Kristin; Chen, Ming-Huei; Teumer, Alexander; Glazer, Nicole L; Döring, Angela; Lam, Carolyn S P; Friedrich, Nele; Newman, Anne; Müller, Martina; Yang, Qiong; Homuth, Georg; et al. (Hum Mol Genet, 2011)
Insulin-like growth factor-I (IGF-I) and insulin-like growth factor-binding protein-3 (IGFBP-3) are involved in cell replication, proliferation, differentiation, protein synthesis, carbohydrate homeostasis and bone metabolism. Circulating IGF-I and IGFBP-3 concentrations predict anthropometric traits and risk of cancer and cardiovascular disease. In a genome-wide association study of 10 280 middle-aged and older men and women from four community-based cohort studies, we confirmed a known association of single nucleotide polymorphisms in the IGFBP3 gene region on chromosome 7p12.3 with IGFBP-3 concentrations using a significance threshold of P < 5 × 10(-8) (P = 3.3 × 10(-101)). Furthermore, the same IGFBP3 gene locus (e.g. rs11977526) that was associated with IGFBP-3 concentrations was also associated with the opposite direction of effect, with IGF-I concentration after adjustment for IGFBP-3 concentration (P = 1.9 × 10(-26)). A novel and independent locus on chromosome 7p12.3 (rs700752) had genome-wide significant associations with higher IGFBP-3 (P = 4.4 × 10(-21)) and higher IGF-I (P = 4.9 × 10(-9)) concentrations; when the two measurements were adjusted for one another, the IGF-I association was attenuated but the IGFBP-3 association was not. Two additional loci demonstrated genome-wide significant associations with IGFBP-3 concentration (rs1065656, chromosome 16p13.3, P = 1.2 × 10(-11), IGFALS, a confirmatory finding; and rs4234798, chromosome 4p16.1, P = 4.5 × 10(-10), SORCS2, a novel finding). Together, the four genome-wide significant loci explained 6.5% of the population variation in IGFBP-3 concentration. Furthermore, we observed a borderline statistically significant association between IGF-I concentration and FOXO3 (rs2153960, chromosome 6q21, P = 5.1 × 10(-7)), a locus associated with longevity. These genetic loci deserve further investigation to elucidate the biological basis for the observed associations and clarify their possible role in IGF-mediated regulation of cell growth and metabolism.
Keywords: Aged; Chromosomes, Human, Pair 7; Cohort Studies; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Male; Polymorphism, Single Nucleotide

Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure. - Wain, Louise V; Verwoert, Germaine C; O'Reilly, Paul F; Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Henneman, Peter; Smith, Albert V; Ehret, Georg B; Amin, Najaf; et al. (Nat Genet, 2011)
Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans. We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery (N = 74,064) and follow-up studies (N = 48,607), we identified at genome-wide significance (P = 2.7 × 10(-8) to P = 2.3 × 10(-13)) four new PP loci (at 4q12 near CHIC2, 7q22.3 near PIK3CG, 8q24.12 in NOV and 11q24.3 near ADAMTS8), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1) and one locus associated with both of these traits (2q24.3 near FIGN) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.
Keywords: Arteries; Blood Pressure; Case-Control Studies; Follow-Up Studies; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Linkage Disequilibrium; Polymorphism, Single Nucleotide

Identification of a sudden cardiac death susceptibility locus at 2q24.2 through genome-wide association in European ancestry individuals. - Arking, Dan E; Junttila, M Juhani; Goyette, Philippe; Huertas-Vazquez, Adriana; Eijgelsheim, Mark; Blom, Marieke T; Newton-Cheh, Christopher; Reinier, Kyndaron; Teodorescu, Carmen; Uy-Evanado, Audrey; Carter-Monroe, Naima; Kaikkonen, Kari S; et al. (PLoS Genet, 2011)
Sudden cardiac death (SCD) continues to be one of the leading causes of mortality worldwide, with an annual incidence estimated at 250,000-300,000 in the United States and with the vast majority occurring in the setting of coronary disease. We performed a genome-wide association meta-analysis in 1,283 SCD cases and >20,000 control individuals of European ancestry from 5 studies, with follow-up genotyping in up to 3,119 SCD cases and 11,146 controls from 11 European ancestry studies, and identify the BAZ2B locus as associated with SCD (P = 1.8×10(-10)). The risk allele, while ancestral, has a frequency of ~1.4%, suggesting strong negative selection and increases risk for SCD by 1.92-fold per allele (95% CI 1.57-2.34). We also tested the role of 49 SNPs previously implicated in modulating electrocardiographic traits (QRS, QT, and RR intervals). Consistent with epidemiological studies showing increased risk of SCD with prolonged QRS/QT intervals, the interval-prolonging alleles are in aggregate associated with increased risk for SCD (P = 0.006).
Keywords: Adult; Aged; Alleles; Chromosomes, Human, Pair 2; Death, Sudden, Cardiac; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Myocardial Contraction; Polymorphism, Single Nucleotide

Large-scale candidate gene analysis in whites and African Americans identifies IL6R polymorphism in relation to atrial fibrillation: the National Heart, Lung, and Blood Institute's Candidate Gene Association Resource (CARe) project. - Schnabel, Renate B; Kerr, Kathleen F; Lubitz, Steven A; Alkylbekova, Ermeg L; Marcus, Gregory M; Sinner, Moritz F; Magnani, Jared W; Wolf, Philip A; Deo, Rajat; Lloyd-Jones, Donald M; Lunetta, Kathryn L; Mehra, Reena; et al. (Circ Cardiovasc Genet, 2011)
BACKGROUND: The genetic background of atrial fibrillation (AF) in whites and African Americans is largely unknown. Genes in cardiovascular pathways have not been systematically investigated. METHODS AND RESULTS: We examined a panel of approximately 50,000 common single-nucleotide polymorphisms (SNPs) in 2095 cardiovascular candidate genes and AF in 3 cohorts with participants of European (n=18,524; 2260 cases) or African American descent (n=3662; 263 cases) in the National Heart, Lung, and Blood Institute's Candidate Gene Association Resource. Results in whites were followed up in the German Competence Network for AF (n=906, 468 cases). The top result was assessed in relation to incident ischemic stroke in the Cohorts for Heart and Aging Research in Genomic Epidemiology Stroke Consortium (n=19,602 whites, 1544 incident strokes). SNP rs4845625 in the IL6R gene was associated with AF (relative risk [RR] C allele, 0.90; 95% confidence interval [CI], 0.85-0.95; P=0.0005) in whites but did not reach statistical significance in African Americans (RR, 0.86; 95% CI, 0.72-1.03; P=0.09). The results were comparable in the German AF Network replication, (RR, 0.71; 95% CI, 0.57-0.89; P=0.003). No association between rs4845625 and stroke was observed in whites. The known chromosome 4 locus near PITX2 in whites also was associated with AF in African Americans (rs4611994; hazard ratio, 1.40; 95% CI, 1.16-1.69; P=0.0005). CONCLUSIONS: In a community-based cohort meta-analysis, we identified genetic association in IL6R with AF in whites. Additionally, we demonstrated that the chromosome 4 locus known from recent genome-wide association studies in whites is associated with AF in African Americans.
Keywords: African Americans; Aged; Alleles; Atrial Fibrillation; Chromosomes, Human, Pair 4; Cohort Studies; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Polymorphism, Single Nucleotide; Receptors, Interleukin-6; Risk Factors; Stroke; United States

Meta-analysis of gene-environment interaction: joint estimation of SNP and SNP × environment regression coefficients. - Manning, Alisa K; LaValley, Michael; Liu, Ching-Ti; Rice, Kenneth; An, Ping; Liu, Yongmei; Miljkovic, Iva; Rasmussen-Torvik, Laura; Harris, Tamara B; Province, Michael A; Borecki, Ingrid B; Florez, Jose C; et al. (Genet Epidemiol, 2011)
INTRODUCTION: Genetic discoveries are validated through the meta-analysis of genome-wide association scans in large international consortia. Because environmental variables may interact with genetic factors, investigation of differing genetic effects for distinct levels of an environmental exposure in these large consortia may yield additional susceptibility loci undetected by main effects analysis. We describe a method of joint meta-analysis (JMA) of SNP and SNP by Environment (SNP × E) regression coefficients for use in gene-environment interaction studies. METHODS: In testing SNP × E interactions, one approach uses a two degree of freedom test to identify genetic variants that influence the trait of interest. This approach detects both main and interaction effects between the trait and the SNP. We propose a method to jointly meta-analyze the SNP and SNP × E coefficients using multivariate generalized least squares. This approach provides confidence intervals of the two estimates, a joint significance test for SNP and SNP × E terms, and a test of homogeneity across samples. RESULTS: We present a simulation study comparing this method to four other methods of meta-analysis and demonstrate that the JMA performs better than the others when both main and interaction effects are present. Additionally, we implemented our methods in a meta-analysis of the association between SNPs from the type 2 diabetes-associated gene PPARG and log-transformed fasting insulin levels and interaction by body mass index in a combined sample of 19,466 individuals from five cohorts.
Keywords: Adult; Aged; Body Mass Index; Confidence Intervals; Diabetes Mellitus, Type 2; Environment; Fasting; Female; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Insulin; Least-Squares Analysis; Male; Mathematical Computing; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; PPAR gamma

Meta-analysis of genome-wide association studies from the CHARGE consortium identifies common variants associated with carotid intima media thickness and plaque. - Bis, Joshua C; Kavousi, Maryam; Franceschini, Nora; Isaacs, Aaron; Abecasis, Goncalo R; Schminke, Ulf; Post, Wendy S; Smith, Albert V; Cupples, L Adrienne; Markus, Hugh S; Schmidt, Reinhold; Huffman, Jennifer E; et al. (Nat Genet, 2011)
Carotid intima media thickness (cIMT) and plaque determined by ultrasonography are established measures of subclinical atherosclerosis that each predicts future cardiovascular disease events. We conducted a meta-analysis of genome-wide association data in 31,211 participants of European ancestry from nine large studies in the setting of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. We then sought additional evidence to support our findings among 11,273 individuals using data from seven additional studies. In the combined meta-analysis, we identified three genomic regions associated with common carotid intima media thickness and two different regions associated with the presence of carotid plaque (P < 5 × 10(-8)). The associated SNPs mapped in or near genes related to cellular signaling, lipid metabolism and blood pressure homeostasis, and two of the regions were associated with coronary artery disease (P < 0.006) in the Coronary Artery Disease Genome-Wide Replication and Meta-Analysis (CARDIoGRAM) consortium. Our findings may provide new insight into pathways leading to subclinical atherosclerosis and subsequent cardiovascular events.
Keywords: Adult; Aged; Aging; Atherosclerosis; Carotid Intima-Media Thickness; Cohort Studies; Coronary Artery Disease; European Continental Ancestry Group; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genotype; Heart; Humans; Middle Aged; Phenotype; Plaque, Atherosclerotic; Polymorphism, Single Nucleotide; Risk Factors

A phenomics-based strategy identifies loci on APOC1, BRAP, and PLCG1 associated with metabolic syndrome phenotype domains. - Avery, Christy L; He, Qianchuan; North, Kari E; Ambite, José L; Boerwinkle, Eric; Fornage, Myriam; Hindorff, Lucia A; Kooperberg, Charles; Meigs, James B; Pankow, James S; Pendergrass, Sarah A; Psaty, Bruce M; et al. (PLoS Genet, 2011)
Despite evidence of the clustering of metabolic syndrome components, current approaches for identifying unifying genetic mechanisms typically evaluate clinical categories that do not provide adequate etiological information. Here, we used data from 19,486 European American and 6,287 African American Candidate Gene Association Resource Consortium participants to identify loci associated with the clustering of metabolic phenotypes. Six phenotype domains (atherogenic dyslipidemia, vascular dysfunction, vascular inflammation, pro-thrombotic state, central obesity, and elevated plasma glucose) encompassing 19 quantitative traits were examined. Principal components analysis was used to reduce the dimension of each domain such that >55% of the trait variance was represented within each domain. We then applied a statistically efficient and computational feasible multivariate approach that related eight principal components from the six domains to 250,000 imputed SNPs using an additive genetic model and including demographic covariates. In European Americans, we identified 606 genome-wide significant SNPs representing 19 loci. Many of these loci were associated with only one trait domain, were consistent with results in African Americans, and overlapped with published findings, for instance central obesity and FTO. However, our approach, which is applicable to any set of interval scale traits that is heritable and exhibits evidence of phenotypic clustering, identified three new loci in or near APOC1, BRAP, and PLCG1, which were associated with multiple phenotype domains. These pleiotropic loci may help characterize metabolic dysregulation and identify targets for intervention.
Keywords: African Americans; Apolipoprotein C-I; Blood Glucose; Dyslipidemias; European Continental Ancestry Group; Genetic Association Studies; Genetic Predisposition to Disease; Genome, Human; Humans; Metabolic Syndrome; Obesity, Abdominal; Phenotype; Phospholipase C gamma; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable; Ubiquitin-Protein Ligases; Vascular Diseases

Total zinc intake may modify the glucose-raising effect of a zinc transporter (SLC30A8) variant: a 14-cohort meta-analysis. - Kanoni, Stavroula; Nettleton, Jennifer A; Hivert, Marie-France; Ye, Zheng; van Rooij, Frank J A; Shungin, Dmitry; Sonestedt, Emily; Ngwa, Julius S; Wojczynski, Mary K; Lemaitre, Rozenn N; Gustafsson, Stefan; Anderson, Jennifer S; et al. (Diabetes, 2011)
OBJECTIVE: Many genetic variants have been associated with glucose homeostasis and type 2 diabetes in genome-wide association studies. Zinc is an essential micronutrient that is important for β-cell function and glucose homeostasis. We tested the hypothesis that zinc intake could influence the glucose-raising effect of specific variants. RESEARCH DESIGN AND METHODS: We conducted a 14-cohort meta-analysis to assess the interaction of 20 genetic variants known to be related to glycemic traits and zinc metabolism with dietary zinc intake (food sources) and a 5-cohort meta-analysis to assess the interaction with total zinc intake (food sources and supplements) on fasting glucose levels among individuals of European ancestry without diabetes. RESULTS: We observed a significant association of total zinc intake with lower fasting glucose levels (β-coefficient ± SE per 1 mg/day of zinc intake: -0.0012 ± 0.0003 mmol/L, summary P value = 0.0003), while the association of dietary zinc intake was not significant. We identified a nominally significant interaction between total zinc intake and the SLC30A8 rs11558471 variant on fasting glucose levels (β-coefficient ± SE per A allele for 1 mg/day of greater total zinc intake: -0.0017 ± 0.0006 mmol/L, summary interaction P value = 0.005); this result suggests a stronger inverse association between total zinc intake and fasting glucose in individuals carrying the glucose-raising A allele compared with individuals who do not carry it. None of the other interaction tests were statistically significant. CONCLUSIONS: Our results suggest that higher total zinc intake may attenuate the glucose-raising effect of the rs11558471 SLC30A8 (zinc transporter) variant. Our findings also support evidence for the association of higher total zinc intake with lower fasting glucose levels.
Keywords: Blood Glucose; Cation Transport Proteins; Cohort Studies; Humans; Polymorphism, Single Nucleotide; Zinc; Zinc Transporter 8

Assessment of gene-by-sex interaction effect on bone mineral density. - Liu, Ching-Ti; Estrada, Karol; Yerges-Armstrong, Laura M; Amin, Najaf; Evangelou, Evangelos; Li, Guo; Minster, Ryan L; Carless, Melanie A; Kammerer, Candace M; Oei, Ling; Zhou, Yanhua; Alonso, Nerea; et al. (J Bone Miner Res, 2012)
Sexual dimorphism in various bone phenotypes, including bone mineral density (BMD), is widely observed; however, the extent to which genes explain these sex differences is unclear. To identify variants with different effects by sex, we examined gene-by-sex autosomal interactions genome-wide, and performed expression quantitative trait loci (eQTL) analysis and bioinformatics network analysis. We conducted an autosomal genome-wide meta-analysis of gene-by-sex interaction on lumbar spine (LS) and femoral neck (FN) BMD in 25,353 individuals from 8 cohorts. In a second stage, we followed up the 12 top single-nucleotide polymorphisms (SNPs; p < 1 × 10(-5) ) in an additional set of 24,763 individuals. Gene-by-sex interaction and sex-specific effects were examined in these 12 SNPs. We detected one novel genome-wide significant interaction associated with LS-BMD at the Chr3p26.1-p25.1 locus, near the GRM7 gene (male effect = 0.02 and p = 3.0 × 10(-5) ; female effect = -0.007 and p = 3.3 × 10(-2) ), and 11 suggestive loci associated with either FN- or LS-BMD in discovery cohorts. However, there was no evidence for genome-wide significant (p < 5 × 10(-8) ) gene-by-sex interaction in the joint analysis of discovery and replication cohorts. Despite the large collaborative effort, no genome-wide significant evidence for gene-by-sex interaction was found to influence BMD variation in this screen of autosomal markers. If they exist, gene-by-sex interactions for BMD probably have weak effects, accounting for less than 0.08% of the variation in these traits per implicated SNP. © 2012 American Society for Bone and Mineral Research.
Keywords: Bone Density; Cohort Studies; Female; Genes; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Sex Characteristics

Association between chromosome 9p21 variants and the ankle-brachial index identified by a meta-analysis of 21 genome-wide association studies. - Murabito, Joanne M; White, Charles C; Kavousi, Maryam; Sun, Yan V; Feitosa, Mary F; Nambi, Vijay; Lamina, Claudia; Schillert, Arne; Coassin, Stefan; Bis, Joshua C; Broer, Linda; Crawford, Dana C; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: Genetic determinants of peripheral arterial disease (PAD) remain largely unknown. To identify genetic variants associated with the ankle-brachial index (ABI), a noninvasive measure of PAD, we conducted a meta-analysis of genome-wide association study data from 21 population-based cohorts. METHODS AND RESULTS: Continuous ABI and PAD (ABI ≤0.9) phenotypes adjusted for age and sex were examined. Each study conducted genotyping and imputed data to the ≈2.5 million single nucleotide polymorphisms (SNPs) in HapMap. Linear and logistic regression models were used to test each SNP for association with ABI and PAD using additive genetic models. Study-specific data were combined using fixed effects inverse variance weighted meta-analyses. There were a total of 41 692 participants of European ancestry (≈60% women, mean ABI 1.02 to 1.19), including 3409 participants with PAD and with genome-wide association study data available. In the discovery meta-analysis, rs10757269 on chromosome 9 near CDKN2B had the strongest association with ABI (β=-0.006, P=2.46×10(-8)). We sought replication of the 6 strongest SNP associations in 5 population-based studies and 3 clinical samples (n=16 717). The association for rs10757269 strengthened in the combined discovery and replication analysis (P=2.65×10(-9)). No other SNP associations for ABI or PAD achieved genome-wide significance. However, 2 previously reported candidate genes for PAD and 1 SNP associated with coronary artery disease were associated with ABI: DAB21P (rs13290547, P=3.6×10(-5)), CYBA (rs3794624, P=6.3×10(-5)), and rs1122608 (LDLR, P=0.0026). CONCLUSIONS: Genome-wide association studies in more than 40 000 individuals identified 1 genome wide significant association on chromosome 9p21 with ABI. Two candidate genes for PAD and 1 SNP for coronary artery disease are associated with ABI.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Alleles; Ankle Brachial Index; Chromosomes, Human, Pair 9; Cohort Studies; Cyclin-Dependent Kinase Inhibitor p15; Female; Genome-Wide Association Study; Genotype; HapMap Project; Humans; Logistic Models; Male; Middle Aged; Peripheral Vascular Diseases; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; Sex Factors

Association of genetic loci with sleep apnea in European Americans and African-Americans: the Candidate Gene Association Resource (CARe). - Patel, Sanjay R; Goodloe, Robert; De, Gourab; Kowgier, Matthew; Weng, Jia; Buxbaum, Sarah G; Cade, Brian; Fulop, Tibor; Gharib, Sina A; Gottlieb, Daniel J; Hillman, David; Larkin, Emma K; et al. (PLoS One, 2012)
Although obstructive sleep apnea (OSA) is known to have a strong familial basis, no genetic polymorphisms influencing apnea risk have been identified in cross-cohort analyses. We utilized the National Heart, Lung, and Blood Institute (NHLBI) Candidate Gene Association Resource (CARe) to identify sleep apnea susceptibility loci. Using a panel of 46,449 polymorphisms from roughly 2,100 candidate genes on a customized Illumina iSelect chip, we tested for association with the apnea hypopnea index (AHI) as well as moderate to severe OSA (AHI≥15) in 3,551 participants of the Cleveland Family Study and two cohorts participating in the Sleep Heart Health Study.Among 647 African-Americans, rs11126184 in the pleckstrin (PLEK) gene was associated with OSA while rs7030789 in the lysophosphatidic acid receptor 1 (LPAR1) gene was associated with AHI using a chip-wide significance threshold of p-value<2×10(-6). Among 2,904 individuals of European ancestry, rs1409986 in the prostaglandin E2 receptor (PTGER3) gene was significantly associated with OSA. Consistency of effects between rs7030789 and rs1409986 in LPAR1 and PTGER3 and apnea phenotypes were observed in independent clinic-based cohorts.Novel genetic loci for apnea phenotypes were identified through the use of customized gene chips and meta-analyses of cohort data with replication in clinic-based samples. The identified SNPs all lie in genes associated with inflammation suggesting inflammation may play a role in OSA pathogenesis.
Keywords: Adult; African Americans; Aged; Alleles; European Continental Ancestry Group; Female; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genotype; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Polysomnography; Sleep Apnea, Obstructive

Associations between incident ischemic stroke events and stroke and cardiovascular disease-related genome-wide association studies single nucleotide polymorphisms in the Population Architecture Using Genomics and Epidemiology study. - Carty, Cara L; Bůzková, Petra; Fornage, Myriam; Franceschini, Nora; Cole, Shelley; Heiss, Gerardo; Hindorff, Lucia A; Howard, Barbara V; Mann, Sue; Martin, Lisa W; Zhang, Ying; Matise, Tara C; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: Genome-wide association studies (GWAS) have identified loci associated with ischemic stroke (IS) and cardiovascular disease (CVD) in European-descent individuals, but their replication in different populations has been largely unexplored. METHODS AND RESULTS: Nine single nucleotide polymorphisms (SNPs) selected from GWAS and meta-analyses of stroke, and 86 SNPs previously associated with myocardial infarction and CVD risk factors, including blood lipids (high density lipoprotein [HDL], low density lipoprotein [LDL], and triglycerides), type 2 diabetes, and body mass index (BMI), were investigated for associations with incident IS in European Americans (EA) N=26 276, African-Americans (AA) N=8970, and American Indians (AI) N=3570 from the Population Architecture using Genomics and Epidemiology Study. Ancestry-specific fixed effects meta-analysis with inverse variance weighting was used to combine study-specific log hazard ratios from Cox proportional hazards models. Two of 9 stroke SNPs (rs783396 and rs1804689) were significantly associated with [corrected] IS hazard in AA; none were significant in this large EA cohort. Of 73 CVD risk factor SNPs tested in EA, 2 (HDL and triglycerides SNPs) were associated with IS. In AA, SNPs associated with LDL, HDL, and BMI were significantly associated with IS (3 of 86 SNPs tested). Out of 58 SNPs tested in AI, 1 LDL SNP was significantly associated with IS. CONCLUSIONS: Our analyses showing lack of replication in spite of reasonable power for many stroke SNPs and differing results by ancestry highlight the need to follow up on GWAS findings and conduct genetic association studies in diverse populations. We found modest IS associations with BMI and lipids SNPs, though these findings require confirmation.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cholesterol, HDL; Cholesterol, LDL; European Continental Ancestry Group; Female; Genetics, Population; Genome-Wide Association Study; Genomics; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Stroke; Triglycerides

Circulating and dietary α-linolenic acid and incidence of congestive heart failure in older adults: the Cardiovascular Health Study. - Lemaitre, Rozenn N; Sitlani, Colleen; Song, Xiaoling; King, Irena B; McKnight, Barbara; Spiegelman, Donna; Sacks, Frank M; Djoussé, Luc; Rimm, Eric B; Siscovick, David S; Mozaffarian, Dariush (Am J Clin Nutr, 2012)
BACKGROUND: Few studies have evaluated the association between the n-3 fatty acid α-linolenic acid (ALA) and the incidence of congestive heart failure (CHF). OBJECTIVE: We investigated whether plasma phospholipid concentrations and estimated dietary consumption of ALA are associated with incident CHF. DESIGN: We used data from the Cardiovascular Health Study, a prospective cohort study of cardiovascular diseases among adults aged ≥65 y, from 4 US communities. A total of 2957 participants free of prevalent heart disease and with available fatty acid measurements were included in biomarker analyses (30,722 person-years and 686 incident CHF events). A total of 4432 participants free of prevalent heart disease were included in dietary analyses (52,609 person-years and 1072 events). We investigated the association of ALA with incident CHF by using Cox regression. RESULTS: After adjustment for age, sex, race, education, smoking status, BMI, waist circumference, and alcohol consumption, plasma phospholipid ALA was not associated with incident CHF (HR for the highest compared with the lowest quartile: 0.97; 95% CI: 0.79, 1.21; P-trend = 0.85). Likewise, dietary ALA was not associated with incident CHF (adjusted HR for the highest compared with the lowest quartile: 0.96; 95% CI: 0.82, 1.20; P-trend = 0.97). We observed no association of biomarker or dietary ALA with nonvalvular CHF subtype. We also found little evidence of an association between ALA and CHF in subgroups based on age, sex, diabetes, fish consumption, BMI, or FADS2 genotype (rs1535). CONCLUSION: ALA intake is not associated with incident CHF in older adults. This trial was registered at clinicaltrials.gov as NCT00005133.
Keywords: Aged; Alcohol Drinking; alpha-Linolenic Acid; Biomarkers; Body Mass Index; Cardiovascular Diseases; Diet; Fatty Acid Desaturases; Female; Follow-Up Studies; Heart Failure; Humans; Incidence; Male; Polymorphism, Single Nucleotide; Prevalence; Prospective Studies; Risk Factors; Smoking; Surveys and Questionnaires; United States

Common genetic variants differentially influence the transition from clinically defined states of fasting glucose metabolism. - Walford, G A; Green, T; Neale, B; Isakova, T; Rotter, J I; Grant, S F A; Fox, C S; Pankow, J S; Wilson, J G; Meigs, J B; Siscovick, D S; Bowden, D W; et al. (Diabetologia, 2012)
AIMS/HYPOTHESIS: Common genetic variants have been associated with type 2 diabetes. We hypothesised that a subset of these variants may have different effects on the transition from normal fasting glucose (NFG) to impaired fasting glucose (IFG) than on that from IFG to diabetes. METHODS: We identified 16 type 2 diabetes risk variants from the Illumina Broad Candidate-gene Association Resource (CARe) array genotyped in 26,576 CARe participants. Participants were categorised at baseline as NFG, IFG or type 2 diabetic (n = 16,465, 8,017 or 2,291, respectively). Using Cox proportional hazards and likelihood ratio tests (LRTs), we compared rates of progression by genotype for 4,909 (NFG to IFG) and 1,518 (IFG to type 2 diabetes) individuals, respectively. We then performed multinomial regression analyses at baseline, comparing the risk of assignment to the NFG, IFG or diabetes groups by genotype. RESULTS: The rate of progression from NFG to IFG was significantly greater in participants carrying the risk allele at MTNR1B (p = 1 × 10(-4)), nominally greater at GCK and SLC30A8 (p < 0.05) and nominally smaller at IGF2BP2 (p = 0.01) than the rate of progression from IFG to diabetes by the LRT. Results of the baseline, multinomial regression model were consistent with these findings. CONCLUSIONS/INTERPRETATION: Common genetic risk variants at GCK, SLC30A8, IGF2BP2 and MTNR1B influence to different extents the development of IFG and the transition from IFG to type 2 diabetes. Our findings may have implications for understanding the genetic contribution of these variants to the development of IFG and type 2 diabetes.
Keywords: Adult; Aged; Blood Glucose; Cohort Studies; Diabetes Mellitus, Type 2; Disease Progression; Fasting; Female; Genetic Variation; Genotype; Humans; Male; Middle Aged; Models, Genetic; Polymorphism, Single Nucleotide; Proportional Hazards Models; Regression Analysis; Risk

Effect of Alzheimer's disease risk genes on trajectories of cognitive function in the Cardiovascular Health Study. - Sweet, Robert A; Seltman, Howard; Emanuel, James E; Lopez, Oscar L; Becker, James T; Bis, Joshua C; Weamer, Elise A; Demichele-Sweet, Mary Ann A; Kuller, Lewis H (Am J Psychiatry, 2012)
OBJECTIVE: The trajectory of cognitive decline in patients with late-onset Alzheimer's disease varies widely. Genetic variations in CLU, PICALM, and CR1 are associated with Alzheimer's disease, but it is unknown whether they exert their effects by altering cognitive trajectory in elderly individuals at risk for the disease. METHOD: The authors developed a Bayesian model to fit cognitive trajectories in a cohort of elderly subjects and test for genetic effects. They first validated the model's ability to detect the previously established effects of APOE ε4 alleles on age at cognitive decline and of psychosis on the rate of cognitive decline in 802 subjects from the Cardiovascular Health Cognition Study who did not have dementia at study entry and developed incident dementia during follow-up. The authors then evaluated the effects of CLU, PICALM, and CR1 on age and rate of decline in 1,831 subjects who did not have dementia at study entry and then did or did not develop incident dementia by study's end. RESULTS: The model generated robust fits to the observed cognitive trajectory data, and validation analysis supported the model's utility. CLU and CR1 were associated with more rapid cognitive decline. PICALM was associated with an earlier age at midpoint of cognitive decline. Associations remained after accounting for the effects of APOE and demographic factors. CONCLUSIONS: Evaluation of cognitive trajectories provides a powerful approach to dissecting genetic effects on the processes leading to cognitive deterioration and Alzheimer's disease.
Keywords: Age of Onset; Aged; Alleles; Alzheimer Disease; Apolipoprotein E4; Bayes Theorem; Clusterin; Cohort Studies; Dementia; Disease Progression; Female; Genetic Predisposition to Disease; Humans; Male; Models, Psychological; Monomeric Clathrin Assembly Proteins; Polymorphism, Single Nucleotide; Receptors, Complement 3b; Risk Factors

Eight genetic loci associated with variation in lipoprotein-associated phospholipase A2 mass and activity and coronary heart disease: meta-analysis of genome-wide association studies from five community-based studies. - Grallert, Harald; Dupuis, Josée; Bis, Joshua C; Dehghan, Abbas; Barbalic, Maja; Baumert, Jens; Lu, Chen; Smith, Nicholas L; Uitterlinden, André G; Roberts, Robert; Khuseyinova, Natalie; Schnabel, Renate B; et al. (Eur Heart J, 2012)
AIMS: Lipoprotein-associated phospholipase A2 (Lp-PLA2) generates proinflammatory and proatherogenic compounds in the arterial vascular wall and is a potential therapeutic target in coronary heart disease (CHD). We searched for genetic loci related to Lp-PLA2 mass or activity by a genome-wide association study as part of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. METHODS AND RESULTS: In meta-analyses of findings from five population-based studies, comprising 13 664 subjects, variants at two loci (PLA2G7, CETP) were associated with Lp-PLA2 mass. The strongest signal was at rs1805017 in PLA2G7 [P = 2.4 × 10(-23), log Lp-PLA2 difference per allele (beta): 0.043]. Variants at six loci were associated with Lp-PLA2 activity (PLA2G7, APOC1, CELSR2, LDL, ZNF259, SCARB1), among which the strongest signals were at rs4420638, near the APOE-APOC1-APOC4-APOC2 cluster [P = 4.9 × 10(-30); log Lp-PLA2 difference per allele (beta): -0.054]. There were no significant gene-environment interactions between these eight polymorphisms associated with Lp-PLA2 mass or activity and age, sex, body mass index, or smoking status. Four of the polymorphisms (in APOC1, CELSR2, SCARB1, ZNF259), but not PLA2G7, were significantly associated with CHD in a second study. CONCLUSION: Levels of Lp-PLA2 mass and activity were associated with PLA2G7, the gene coding for this protein. Lipoprotein-associated phospholipase A2 activity was also strongly associated with genetic variants related to low-density lipoprotein cholesterol levels.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Coronary Artery Disease; Coronary Disease; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Middle Aged; Phospholipases A2; Polymorphism, Single Nucleotide

Evaluation of the metabochip genotyping array in African Americans and implications for fine mapping of GWAS-identified loci: the PAGE study. - Buyske, Steven; Wu, Ying; Carty, Cara L; Cheng, Iona; Assimes, Themistocles L; Dumitrescu, Logan; Hindorff, Lucia A; Mitchell, Sabrina; Ambite, Jose Luis; Boerwinkle, Eric; Bůzková, Petra; Carlson, Chris S; et al. (PLoS One, 2012)
The Metabochip is a custom genotyping array designed for replication and fine mapping of metabolic, cardiovascular, and anthropometric trait loci and includes low frequency variation content identified from the 1000 Genomes Project. It has 196,725 SNPs concentrated in 257 genomic regions. We evaluated the Metabochip in 5,863 African Americans; 89% of all SNPs passed rigorous quality control with a call rate of 99.9%. Two examples illustrate the value of fine mapping with the Metabochip in African-ancestry populations. At CELSR2/PSRC1/SORT1, we found the strongest associated SNP for LDL-C to be rs12740374 (p = 3.5 × 10(-11)), a SNP indistinguishable from multiple SNPs in European ancestry samples due to high correlation. Its distinct signal supports functional studies elsewhere suggesting a causal role in LDL-C. At CETP we found rs17231520, with risk allele frequency 0.07 in African Americans, to be associated with HDL-C (p = 7.2 × 10(-36)). This variant is very rare in Europeans and not tagged in common GWAS arrays, but was identified as associated with HDL-C in African Americans in a single-gene study. Our results, one narrowing the risk interval and the other revealing an associated variant not found in Europeans, demonstrate the advantages of high-density genotyping of common and rare variation for fine mapping of trait loci in African American samples.
Keywords: African Americans; Cardiovascular Diseases; Cholesterol Ester Transfer Proteins; Cholesterol, HDL; Cholesterol, LDL; Chromosomes, Human; Cohort Studies; Gene Frequency; Genome-Wide Association Study; Genotype; Humans; Metabolic Diseases; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Evolution and functional impact of rare coding variation from deep sequencing of human exomes. - Tennessen, Jacob A; Bigham, Abigail W; O'Connor, Timothy D; Fu, Wenqing; Kenny, Eimear E; Gravel, Simon; McGee, Sean; Do, Ron; Liu, Xiaoming; Jun, Goo; Kang, Hyun Min; Jordan, Daniel; et al. (Science, 2012)
As a first step toward understanding how rare variants contribute to risk for complex diseases, we sequenced 15,585 human protein-coding genes to an average median depth of 111× in 2440 individuals of European (n = 1351) and African (n = 1088) ancestry. We identified over 500,000 single-nucleotide variants (SNVs), the majority of which were rare (86% with a minor allele frequency less than 0.5%), previously unknown (82%), and population-specific (82%). On average, 2.3% of the 13,595 SNVs each person carried were predicted to affect protein function of ~313 genes per genome, and ~95.7% of SNVs predicted to be functionally important were rare. This excess of rare functional variants is due to the combined effects of explosive, recent accelerated population growth and weak purifying selection. Furthermore, we show that large sample sizes will be required to associate rare variants with complex traits.
Keywords: African Americans; Disease; European Continental Ancestry Group; Evolution, Molecular; Exome; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Male; Polymorphism, Single Nucleotide; Population Growth; Selection, Genetic

Fine-mapping and initial characterization of QT interval loci in African Americans. - Avery, Christy L; Sethupathy, Praveen; Buyske, Steven; He, Qianchuan; Lin, Dan-Yu; Arking, Dan E; Carty, Cara L; Duggan, David; Fesinmeyer, Megan D; Hindorff, Lucia A; Jeff, Janina M; Klein, Liviu; et al. (PLoS Genet, 2012)
The QT interval (QT) is heritable and its prolongation is a risk factor for ventricular tachyarrhythmias and sudden death. Most genetic studies of QT have examined European ancestral populations; however, the increased genetic diversity in African Americans provides opportunities to narrow association signals and identify population-specific variants. We therefore evaluated 6,670 SNPs spanning eleven previously identified QT loci in 8,644 African American participants from two Population Architecture using Genomics and Epidemiology (PAGE) studies: the Atherosclerosis Risk in Communities study and Women's Health Initiative Clinical Trial. Of the fifteen known independent QT variants at the eleven previously identified loci, six were significantly associated with QT in African American populations (P≤1.20×10(-4)): ATP1B1, PLN1, KCNQ1, NDRG4, and two NOS1AP independent signals. We also identified three population-specific signals significantly associated with QT in African Americans (P≤1.37×10(-5)): one at NOS1AP and two at ATP1B1. Linkage disequilibrium (LD) patterns in African Americans assisted in narrowing the region likely to contain the functional variants for several loci. For example, African American LD patterns showed that 0 SNPs were in LD with NOS1AP signal rs12143842, compared with European LD patterns that indicated 87 SNPs, which spanned 114.2 Kb, were in LD with rs12143842. Finally, bioinformatic-based characterization of the nine African American signals pointed to functional candidates located exclusively within non-coding regions, including predicted binding sites for transcription factors such as TBX5, which has been implicated in cardiac structure and conductance. In this detailed evaluation of QT loci, we identified several African Americans SNPs that better define the association with QT and successfully narrowed intervals surrounding established loci. These results demonstrate that the same loci influence variation in QT across multiple populations, that novel signals exist in African Americans, and that the SNPs identified as strong candidates for functional evaluation implicate gene regulatory dysfunction in QT prolongation.
Keywords: African Americans; Aged; Computational Biology; Electrocardiography; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Metagenomics; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Risk Factors; Tachycardia; United States

FTO genotype is associated with phenotypic variability of body mass index. - Yang, Jian; Loos, Ruth J F; Powell, Joseph E; Medland, Sarah E; Speliotes, Elizabeth K; Chasman, Daniel I; Rose, Lynda M; Thorleifsson, Gudmar; Steinthorsdottir, Valgerdur; Mägi, Reedik; Waite, Lindsay; Smith, Albert Vernon; et al. (Nature, 2012)
There is evidence across several species for genetic control of phenotypic variation of complex traits, such that the variance among phenotypes is genotype dependent. Understanding genetic control of variability is important in evolutionary biology, agricultural selection programmes and human medicine, yet for complex traits, no individual genetic variants associated with variance, as opposed to the mean, have been identified. Here we perform a meta-analysis of genome-wide association studies of phenotypic variation using ∼170,000 samples on height and body mass index (BMI) in human populations. We report evidence that the single nucleotide polymorphism (SNP) rs7202116 at the FTO gene locus, which is known to be associated with obesity (as measured by mean BMI for each rs7202116 genotype), is also associated with phenotypic variability. We show that the results are not due to scale effects or other artefacts, and find no other experiment-wise significant evidence for effects on variability, either at loci other than FTO for BMI or at any locus for height. The difference in variance for BMI among individuals with opposite homozygous genotypes at the FTO locus is approximately 7%, corresponding to a difference of ∼0.5 kilograms in the standard deviation of weight. Our results indicate that genetic variants can be discovered that are associated with variability, and that between-person variability in obesity can partly be explained by the genotype at the FTO locus. The results are consistent with reported FTO by environment interactions for BMI, possibly mediated by DNA methylation. Our BMI results for other SNPs and our height results for all SNPs suggest that most genetic variants, including those that influence mean height or mean BMI, are not associated with phenotypic variance, or that their effects on variability are too small to detect even with samples sizes greater than 100,000.
Keywords: Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Body Height; Body Mass Index; Co-Repressor Proteins; Female; Genetic Variation; Genome-Wide Association Study; Humans; Male; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; Proteins; Repressor Proteins

Genetic determinants of the ankle-brachial index: a meta-analysis of a cardiovascular candidate gene 50K SNP panel in the candidate gene association resource (CARe) consortium. - Wassel, Christina L; Lamina, Claudia; Nambi, Vijay; Coassin, Stefan; Mukamal, Kenneth J; Ganesh, Santhi K; Jacobs, David R; Franceschini, Nora; Papanicolaou, George J; Gibson, Quince; Yanek, Lisa R; van der Harst, Pim; et al. (Atherosclerosis, 2012)
BACKGROUND: Candidate gene association studies for peripheral artery disease (PAD), including subclinical disease assessed with the ankle-brachial index (ABI), have been limited by the modest number of genes examined. We conducted a two stage meta-analysis of ∼50,000 SNPs across ∼2100 candidate genes to identify genetic variants for ABI. METHODS AND RESULTS: We studied subjects of European ancestry from 8 studies (n=21,547, 55% women, mean age 44-73 years) and African American ancestry from 5 studies (n=7267, 60% women, mean age 41-73 years) involved in the candidate gene association resource (CARe) consortium. In each ethnic group, additive genetic models were used (with each additional copy of the minor allele corresponding to the given beta) to test each SNP for association with continuous ABI (excluding ABI>1.40) and PAD (defined as ABI<0.90) using linear or logistic regression with adjustment for known PAD risk factors and population stratification. We then conducted a fixed-effects inverse-variance weighted meta-analyses considering a p<2×10(-6) to denote statistical significance. RESULTS: In the European ancestry discovery meta-analyses, rs2171209 in SYTL3 (β=-0.007, p=6.02×10(-7)) and rs290481 in TCF7L2 (β=-0.008, p=7.01×10(-7)) were significantly associated with ABI. None of the SNP associations for PAD were significant, though a SNP in CYP2B6 (p=4.99×10(-5)) was among the strongest associations. These 3 genes are linked to key PAD risk factors (lipoprotein(a), type 2 diabetes, and smoking behavior, respectively). We sought replication in 6 population-based and 3 clinical samples (n=15,440) for rs290481 and rs2171209. However, in the replication stage (rs2171209, p=0.75; rs290481, p=0.19) and in the combined discovery and replication analysis the SNP-ABI associations were no longer significant (rs2171209, p=1.14×10(-3); rs290481, p=8.88×10(-5)). In African Americans, none of the SNP associations for ABI or PAD achieved an experiment-wide level of significance. CONCLUSIONS: Genetic determinants of ABI and PAD remain elusive. Follow-up of these preliminary findings may uncover important biology given the known gene-risk factor associations. New and more powerful approaches to PAD gene discovery are warranted.
Keywords: Adult; African Americans; Aged; Ankle Brachial Index; Aryl Hydrocarbon Hydroxylases; Cytochrome P-450 CYP2B6; European Continental Ancestry Group; Female; Humans; Male; Middle Aged; Oxidoreductases, N-Demethylating; Peripheral Arterial Disease; Polymorphism, Single Nucleotide; Risk Factors; Transcription Factor 7-Like 2 Protein

Genetic variants and associations of 25-hydroxyvitamin D concentrations with major clinical outcomes. - Levin, Gregory P; Robinson-Cohen, Cassianne; de Boer, Ian H; Houston, Denise K; Lohman, Kurt; Liu, Yongmei; Kritchevsky, Stephen B; Cauley, Jane A; Tanaka, Toshiko; Ferrucci, Luigi; Bandinelli, Stefania; Patel, Kushang V; et al. (JAMA, 2012)
CONTEXT: Lower serum 25-hydroxyvitamin D concentrations are associated with greater risks of many chronic diseases across large, prospective community-based studies. Substrate 25-hydroxyvitamin D must be converted to 1,25-dihydroxyvitamin D for full biological activity, and complex metabolic pathways suggest that interindividual variability in vitamin D metabolism may alter the clinical consequences of measured serum 25-hydroxyvitamin D. OBJECTIVE: To investigate whether common variation within genes encoding the vitamin D-binding protein, megalin, cubilin, CYP27B1, CYP24A1, and the vitamin D receptor (VDR) modify associations of low 25-hydroxyvitamin D with major clinical outcomes. DESIGN, SETTING, AND PARTICIPANTS: Examination of 141 single-nucleotide polymorphisms in a discovery cohort of 1514 white participants (who were recruited from 4 US regions) from the community-based Cardiovascular Health Study. Participants had serum 25-hydroxyvitamin D measurements in 1992-1993 and were followed up for a median of 11 years (through 2006). Replication meta-analyses were conducted across the independent, community-based US Health, Aging, and Body Composition (n = 922; follow-up: 1998-1999 through 2005), Italian Invecchiare in Chianti (n = 835; follow-up: 1998-2000 through 2006), and Swedish Uppsala Longitudinal Study of Adult Men (n = 970; follow-up: 1991-1995 through 2008) cohort studies. MAIN OUTCOME MEASURE: Composite outcome of incident hip facture, myocardial infarction, cancer, and mortality over long-term follow-up. RESULTS: Interactions between 5 single-nucleotide polymorphisms and low 25-hydroxyvitamin D concentration were identified in the discovery phase and 1 involving a variant in the VDR gene replicated in independent meta-analysis. Among Cardiovascular Health Study participants, low 25-hydroxyvitamin D concentration was associated with hazard ratios for risk of the composite outcome of 1.40 (95% CI, 1.12-1.74) for those who had 1 minor allele at rs7968585 and 1.82 (95% CI, 1.31-2.54) for those with 2 minor alleles at rs7968585. In contrast, there was no evidence of an association (estimated hazard ratio, 0.93 [95% CI, 0.70-1.24]) among participants who had 0 minor alleles at this single-nucleotide polymorphism. CONCLUSION: Known associations of low 25-hydroxyvitamin D with major health outcomes may vary according to common genetic differences in the vitamin D receptor.
Keywords: 25-Hydroxyvitamin D3 1-alpha-Hydroxylase; Aged; Chronic Disease; Cohort Studies; Female; Genetic Variation; Genotype; Hip Fractures; Humans; Low Density Lipoprotein Receptor-Related Protein-2; Male; Meta-Analysis as Topic; Myocardial Infarction; Neoplasms; Polymorphism, Single Nucleotide; Receptors, Calcitriol; Receptors, Cell Surface; Risk; Steroid Hydroxylases; Vitamin D; Vitamin D3 24-Hydroxylase

Genetic variants in Arhgef11 are associated with kidney injury in the Dahl salt-sensitive rat. - Williams, Jan M; Johnson, Ashley C; Stelloh, Cary; Dreisbach, Albert W; Franceschini, Nora; Regner, Kevin R; Townsend, Raymond R; Roman, Richard J; Garrett, Michael R (Hypertension, 2012)
A previous genetic analysis comparing the Dahl salt-sensitive (S) rat with the spontaneously hypertensive rat identified a major locus on chromosome 2 that influences proteinuria in the S rat. In the present study, blood pressure, proteinuria, and renal hemodynamics were evaluated in congenic strains with small segments of the protective spontaneously hypertensive rat genome on the S background. Proteinuria and renal function were significantly improved in the congenic strains compared with the S. The causative locus interval was narrowed to <375 kb on the basis of congenic strains, haplotype data, comparative mapping, and concordance with human genetic studies. Sequencing of the coding region of genes in this region identified 36 single nucleotide polymorphisms (13 nonsynonymous and 23 synonymous). Gene expression profiling indicated that only a few genes exhibited differential expression. Arhgef11, Pear1, and Sh2d2 were identified as important candidate genes that may be linked to kidney injury in the S rat. In particular, Arhgef11 plays an important role in the activation of the Rho-ROCK signaling pathway. Inhibition of this pathway using fasudil resulted in a significant reduction of proteinuria in treated S rats (compared with untreated S). However, no difference was observed between treated or untreated spontaneously hypertensive rat or congenic strains. The homologous region in humans was found to be associated with estimated glomerular filtration rate in the Candidate Gene Association Resource population. In summary, these findings demonstrate that allelic variants in Arhgef11, acting through the Rho-ROCK pathway, could influence kidney injury in the S as well as provide insight into human kidney disease.
Keywords: 1-(5-Isoquinolinesulfonyl)-2-Methylpiperazine; Animals; Animals, Congenic; Blood Pressure; Blotting, Western; Chromosome Mapping; Gene Expression Profiling; Genetic Predisposition to Disease; Guanine Nucleotide Exchange Factors; Humans; Kidney; Kidney Diseases; Male; Polymorphism, Single Nucleotide; Protein Kinase Inhibitors; Proteinuria; Quantitative Trait Loci; Rats; Rats, Inbred Dahl; Rats, Inbred SHR; Renal Circulation; Reverse Transcriptase Polymerase Chain Reaction; rho-Associated Kinases; rhoA GTP-Binding Protein; Signal Transduction

Genome-wide association studies identify CHRNA5/3 and HTR4 in the development of airflow obstruction. - Wilk, Jemma B; Shrine, Nick R G; Loehr, Laura R; Zhao, Jing Hua; Manichaikul, Ani; Lopez, Lorna M; Smith, Albert Vernon; Heckbert, Susan R; Smolonska, Joanna; Tang, Wenbo; Loth, Daan W; Curjuric, Ivan; et al. (Am J Respir Crit Care Med, 2012)
RATIONALE: Genome-wide association studies (GWAS) have identified loci influencing lung function, but fewer genes influencing chronic obstructive pulmonary disease (COPD) are known. OBJECTIVES: Perform meta-analyses of GWAS for airflow obstruction, a key pathophysiologic characteristic of COPD assessed by spirometry, in population-based cohorts examining all participants, ever smokers, never smokers, asthma-free participants, and more severe cases. METHODS: Fifteen cohorts were studied for discovery (3,368 affected; 29,507 unaffected), and a population-based family study and a meta-analysis of case-control studies were used for replication and regional follow-up (3,837 cases; 4,479 control subjects). Airflow obstruction was defined as FEV(1) and its ratio to FVC (FEV(1)/FVC) both less than their respective lower limits of normal as determined by published reference equations. MEASUREMENTS AND MAIN RESULTS: The discovery meta-analyses identified one region on chromosome 15q25.1 meeting genome-wide significance in ever smokers that includes AGPHD1, IREB2, and CHRNA5/CHRNA3 genes. The region was also modestly associated among never smokers. Gene expression studies confirmed the presence of CHRNA5/3 in lung, airway smooth muscle, and bronchial epithelial cells. A single-nucleotide polymorphism in HTR4, a gene previously related to FEV(1)/FVC, achieved genome-wide statistical significance in combined meta-analysis. Top single-nucleotide polymorphisms in ADAM19, RARB, PPAP2B, and ADAMTS19 were nominally replicated in the COPD meta-analysis. CONCLUSIONS: These results suggest an important role for the CHRNA5/3 region as a genetic risk factor for airflow obstruction that may be independent of smoking and implicate the HTR4 gene in the etiology of airflow obstruction.
Keywords: Aged; Female; Forced Expiratory Volume; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Pulmonary Disease, Chronic Obstructive; Receptors, Nicotinic; Receptors, Serotonin, 5-HT4; Smoking; Vital Capacity

Genome-wide association study for circulating levels of PAI-1 provides novel insights into its regulation. - Huang, Jie; Sabater-Lleal, Maria; Asselbergs, Folkert W; Tregouet, David; Shin, So-Youn; Ding, Jingzhong; Baumert, Jens; Oudot-Mellakh, Tiphaine; Folkersen, Lasse; Johnson, Andrew D; Smith, Nicholas L; Williams, Scott M; et al. (Blood, 2012)
We conducted a genome-wide association study to identify novel associations between genetic variants and circulating plasminogen activator inhibitor-1 (PAI-1) concentration, and examined functional implications of variants and genes that were discovered. A discovery meta-analysis was performed in 19 599 subjects, followed by replication analysis of genome-wide significant (P < 5 × 10(-8)) single nucleotide polymorphisms (SNPs) in 10 796 independent samples. We further examined associations with type 2 diabetes and coronary artery disease, assessed the functional significance of the SNPs for gene expression in human tissues, and conducted RNA-silencing experiments for one novel association. We confirmed the association of the 4G/5G proxy SNP rs2227631 in the promoter region of SERPINE1 (7q22.1) and discovered genome-wide significant associations at 3 additional loci: chromosome 7q22.1 close to SERPINE1 (rs6976053, discovery P = 3.4 × 10(-10)); chromosome 11p15.2 within ARNTL (rs6486122, discovery P = 3.0 × 10(-8)); and chromosome 3p25.2 within PPARG (rs11128603, discovery P = 2.9 × 10(-8)). Replication was achieved for the 7q22.1 and 11p15.2 loci. There was nominal association with type 2 diabetes and coronary artery disease at ARNTL (P < .05). Functional studies identified MUC3 as a candidate gene for the second association signal on 7q22.1. In summary, SNPs in SERPINE1 and ARNTL and an SNP associated with the expression of MUC3 were robustly associated with circulating levels of PAI-1.
Keywords: Adaptor Proteins, Signal Transducing; ARNTL Transcription Factors; ATPases Associated with Diverse Cellular Activities; Cell Line; Cell Line, Tumor; Cohort Studies; Coronary Artery Disease; Diabetes Mellitus, Type 2; Gene Expression Profiling; Gene Expression Regulation; Gene Frequency; Genome-Wide Association Study; Genotype; Humans; LIM Domain Proteins; Meta-Analysis as Topic; Monocytes; Mucin-3; Plasminogen Activator Inhibitor 1; Polymorphism, Single Nucleotide; PPAR gamma; Proteasome Endopeptidase Complex; RNA Interference; Transcription Factors

A genome-wide association study identifies a potential novel gene locus for keratoconus, one of the commonest causes for corneal transplantation in developed countries. - Li, Xiaohui; Bykhovskaya, Yelena; Haritunians, Talin; Siscovick, David; Aldave, Anthony; Szczotka-Flynn, Loretta; Iyengar, Sudha K; Rotter, Jerome I; Taylor, Kent D; Rabinowitz, Yaron S (Hum Mol Genet, 2012)
Keratoconus is a condition in which the cornea progressively thins over time, and is a major cause for cornea transplantation. To identify keratoconus susceptibility regions, we performed a comprehensive genome-wide association study (GWAS) using a discovery and replication design. A discovery panel of 222 keratoconus Caucasian patients and 3324 Caucasian controls was genotyped using Illumina 370K beadchips. Further associated and fine-mapping single nucleotide polymorphisms (SNPs) (n= 4905) were genotyped in an independent replication case-control panel of 304 cases and 518 controls and a family panel of 307 subjects in 70 families. Logistic regression models implemented in PLINK were performed to test associations in case-control samples with and without principal component (PC) adjustments. Generalized estimation equation models accounting for familial correlations implemented in GWAF were used for association testing in families. No genome-wide associations were identified in the discovery GWAS panel. From the initial testing without adjustments for PCs, the top three SNPs located at 3p26 (rs6442925), 2q21.3 (rs4954218) and 19q13.3 (rs1428642) were identified with unadjusted P-values of 6.5 × 10(-8), 2.4 × 10(-7) and 3.1 × 10(-7), respectively. After adjustments for PCs, rs1428642 became the most significant through the genome with a P-value of 1.4 × 10(-6), while rs6442925 and rs4954218 were less significant (P= 1.9 × 10(-5) and 2.6 × 10(-4)). SNP rs4954218 was confirmed in two independent replication panels with P-values of 0.004 and 0.009, respectively. Meta-analysis revealed a highest association at rs4954218 with adjusted P= 1.6 × 10(-7) (unadjusted P= 1.2 × 10(-9)). These findings suggest SNP rs4954218, located near the RAB3GAP1 gene, previously reported to be associated with corneal malformation, is a potential susceptibility locus for keratoconus.
Keywords: Case-Control Studies; Chromosomes, Human, Pair 2; Cohort Studies; Corneal Transplantation; Developed Countries; Genome-Wide Association Study; Humans; Keratoconus; Polymorphism, Single Nucleotide

Genome-wide joint meta-analysis of SNP and SNP-by-smoking interaction identifies novel loci for pulmonary function. - Hancock, Dana B; Soler Artigas, Maria; Gharib, Sina A; Henry, Amanda; Manichaikul, Ani; Ramasamy, Adaikalavan; Loth, Daan W; Imboden, Medea; Koch, Beate; McArdle, Wendy L; Smith, Albert V; Smolonska, Joanna; et al. (PLoS Genet, 2012)
Genome-wide association studies have identified numerous genetic loci for spirometic measures of pulmonary function, forced expiratory volume in one second (FEV(1)), and its ratio to forced vital capacity (FEV(1)/FVC). Given that cigarette smoking adversely affects pulmonary function, we conducted genome-wide joint meta-analyses (JMA) of single nucleotide polymorphism (SNP) and SNP-by-smoking (ever-smoking or pack-years) associations on FEV(1) and FEV(1)/FVC across 19 studies (total N = 50,047). We identified three novel loci not previously associated with pulmonary function. SNPs in or near DNER (smallest P(JMA = )5.00×10(-11)), HLA-DQB1 and HLA-DQA2 (smallest P(JMA = )4.35×10(-9)), and KCNJ2 and SOX9 (smallest P(JMA = )1.28×10(-8)) were associated with FEV(1)/FVC or FEV(1) in meta-analysis models including SNP main effects, smoking main effects, and SNP-by-smoking (ever-smoking or pack-years) interaction. The HLA region has been widely implicated for autoimmune and lung phenotypes, unlike the other novel loci, which have not been widely implicated. We evaluated DNER, KCNJ2, and SOX9 and found them to be expressed in human lung tissue. DNER and SOX9 further showed evidence of differential expression in human airway epithelium in smokers compared to non-smokers. Our findings demonstrated that joint testing of SNP and SNP-by-environment interaction identified novel loci associated with complex traits that are missed when considering only the genetic main effects.
Keywords: Forced Expiratory Volume; Gene Expression; Genome, Human; Genome-Wide Association Study; HLA-DQ Antigens; HLA-DQ beta-Chains; Humans; Lung; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Potassium Channels, Inwardly Rectifying; Pulmonary Disease, Chronic Obstructive; Receptors, Cell Surface; Smoking; SOX9 Transcription Factor; Vital Capacity

Genome-wide meta-analyses of smoking behaviors in African Americans. - David, S P; Hamidovic, A; Chen, G K; Bergen, A W; Wessel, J; Kasberger, J L; Brown, W M; Petruzella, S; Thacker, E L; Kim, Y; Nalls, M A; Tranah, G J; et al. (Transl Psychiatry, 2012)
The identification and exploration of genetic loci that influence smoking behaviors have been conducted primarily in populations of the European ancestry. Here we report results of the first genome-wide association study meta-analysis of smoking behavior in African Americans in the Study of Tobacco in Minority Populations Genetics Consortium (n = 32,389). We identified one non-coding single-nucleotide polymorphism (SNP; rs2036527[A]) on chromosome 15q25.1 associated with smoking quantity (cigarettes per day), which exceeded genome-wide significance (β = 0.040, s.e. = 0.007, P = 1.84 × 10(-8)). This variant is present in the 5'-distal enhancer region of the CHRNA5 gene and defines the primary index signal reported in studies of the European ancestry. No other SNP reached genome-wide significance for smoking initiation (SI, ever vs never smoking), age of SI, or smoking cessation (SC, former vs current smoking). Informative associations that approached genome-wide significance included three modestly correlated variants, at 15q25.1 within PSMA4, CHRNA5 and CHRNA3 for smoking quantity, which are associated with a second signal previously reported in studies in European ancestry populations, and a signal represented by three SNPs in the SPOCK2 gene on chr10q22.1. The association at 15q25.1 confirms this region as an important susceptibility locus for smoking quantity in men and women of African ancestry. Larger studies will be needed to validate the suggestive loci that did not reach genome-wide significance and further elucidate the contribution of genetic variation to disparities in cigarette consumption, SC and smoking-attributable disease between African Americans and European Americans.
Keywords: Adult; African Americans; Aged; Chromosomes, Human, Pair 10; Chromosomes, Human, Pair 15; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; Proteoglycans; Receptors, Nicotinic; Smoking; Statistics as Topic

Genome-wide meta-analysis identifies 56 bone mineral density loci and reveals 14 loci associated with risk of fracture. - Estrada, Karol; Styrkarsdottir, Unnur; Evangelou, Evangelos; Hsu, Yi-Hsiang; Duncan, Emma L; Ntzani, Evangelia E; Oei, Ling; Albagha, Omar M E; Amin, Najaf; Kemp, John P; Koller, Daniel L; Li, Guo; et al. (Nat Genet, 2012)
Bone mineral density (BMD) is the most widely used predictor of fracture risk. We performed the largest meta-analysis to date on lumbar spine and femoral neck BMD, including 17 genome-wide association studies and 32,961 individuals of European and east Asian ancestry. We tested the top BMD-associated markers for replication in 50,933 independent subjects and for association with risk of low-trauma fracture in 31,016 individuals with a history of fracture (cases) and 102,444 controls. We identified 56 loci (32 new) associated with BMD at genome-wide significance (P < 5 × 10(-8)). Several of these factors cluster within the RANK-RANKL-OPG, mesenchymal stem cell differentiation, endochondral ossification and Wnt signaling pathways. However, we also discovered loci that were localized to genes not known to have a role in bone biology. Fourteen BMD-associated loci were also associated with fracture risk (P < 5 × 10(-4), Bonferroni corrected), of which six reached P < 5 × 10(-8), including at 18p11.21 (FAM210A), 7q21.3 (SLC25A13), 11q13.2 (LRP5), 4q22.1 (MEPE), 2p16.2 (SPTBN1) and 10q21.1 (DKK1). These findings shed light on the genetic architecture and pathophysiological mechanisms underlying BMD variation and fracture susceptibility.
Keywords: Bone Density; Computational Biology; European Continental Ancestry Group; Extracellular Matrix Proteins; Female; Femur Neck; Fractures, Bone; Gene Expression Profiling; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Glycoproteins; Humans; Intercellular Signaling Peptides and Proteins; Low Density Lipoprotein Receptor-Related Protein-5; Lumbar Vertebrae; Male; Mitochondrial Membrane Transport Proteins; Osteoporosis; Phosphoproteins; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors; Spectrin

Impact of ancestry and common genetic variants on QT interval in African Americans. - Smith, J Gustav; Avery, Christy L; Evans, Daniel S; Nalls, Michael A; Meng, Yan A; Smith, Erin N; Palmer, Cameron; Tanaka, Toshiko; Mehra, Reena; Butler, Anne M; Young, Taylor; Buxbaum, Sarah G; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: Ethnic differences in cardiac arrhythmia incidence have been reported, with a particularly high incidence of sudden cardiac death and low incidence of atrial fibrillation in individuals of African ancestry. We tested the hypotheses that African ancestry and common genetic variants are associated with prolonged duration of cardiac repolarization, a central pathophysiological determinant of arrhythmia, as measured by the electrocardiographic QT interval. METHODS AND RESULTS: First, individual estimates of African and European ancestry were inferred from genome-wide single-nucleotide polymorphism (SNP) data in 7 population-based cohorts of African Americans (n=12,097) and regressed on measured QT interval from ECGs. Second, imputation was performed for 2.8 million SNPs, and a genome-wide association study of QT interval was performed in 10 cohorts (n=13,105). There was no evidence of association between genetic ancestry and QT interval (P=0.94). Genome-wide significant associations (P<2.5 × 10(-8)) were identified with SNPs at 2 loci, upstream of the genes NOS1AP (rs12143842, P=2 × 10(-15)) and ATP1B1 (rs1320976, P=2 × 10(-10)). The most significant SNP in NOS1AP was the same as the strongest SNP previously associated with QT interval in individuals of European ancestry. Low probability values (P<10(-5)) were observed for SNPs at several other loci previously identified in genome-wide association studies in individuals of European ancestry, including KCNQ1, KCNH2, LITAF, and PLN. CONCLUSIONS: We observed no difference in duration of cardiac repolarization with global genetic indices of African American ancestry. In addition, our genome-wide association study extends the association of polymorphisms at several loci associated with repolarization in individuals of European ancestry to include individuals of African ancestry.
Keywords: Adult; African Americans; Aged; Electrocardiography; European Continental Ancestry Group; Female; Genealogy and Heraldry; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Meta-analyses identify 13 loci associated with age at menopause and highlight DNA repair and immune pathways. - Stolk, Lisette; Perry, John R B; Chasman, Daniel I; He, Chunyan; Mangino, Massimo; Sulem, Patrick; Barbalic, Maja; Broer, Linda; Byrne, Enda M; Ernst, Florian; Esko, Tõnu; Franceschini, Nora; et al. (Nat Genet, 2012)
To newly identify loci for age at natural menopause, we carried out a meta-analysis of 22 genome-wide association studies (GWAS) in 38,968 women of European descent, with replication in up to 14,435 women. In addition to four known loci, we identified 13 loci newly associated with age at natural menopause (at P < 5 × 10(-8)). Candidate genes located at these newly associated loci include genes implicated in DNA repair (EXO1, HELQ, UIMC1, FAM175A, FANCI, TLK1, POLG and PRIM1) and immune function (IL11, NLRP11 and PRRC2A (also known as BAT2)). Gene-set enrichment pathway analyses using the full GWAS data set identified exoDNase, NF-κB signaling and mitochondrial dysfunction as biological processes related to timing of menopause.
Keywords: Age Factors; DNA Helicases; DNA Polymerase gamma; DNA Primase; DNA Repair; DNA Repair Enzymes; DNA-Directed DNA Polymerase; European Continental Ancestry Group; Exodeoxyribonucleases; Female; Genetic Loci; Genome-Wide Association Study; Humans; Immunity; Menopause; Polymorphism, Single Nucleotide; Proteins

Meta-analysis identifies six new susceptibility loci for atrial fibrillation. - Ellinor, Patrick T; Lunetta, Kathryn L; Albert, Christine M; Glazer, Nicole L; Ritchie, Marylyn D; Smith, Albert V; Arking, Dan E; Müller-Nurasyid, Martina; Krijthe, Bouwe P; Lubitz, Steven A; Bis, Joshua C; Chung, Mina K; et al. (Nat Genet, 2012)
Atrial fibrillation is a highly prevalent arrhythmia and a major risk factor for stroke, heart failure and death. We conducted a genome-wide association study (GWAS) in individuals of European ancestry, including 6,707 with and 52,426 without atrial fibrillation. Six new atrial fibrillation susceptibility loci were identified and replicated in an additional sample of individuals of European ancestry, including 5,381 subjects with and 10,030 subjects without atrial fibrillation (P < 5 × 10(-8)). Four of the loci identified in Europeans were further replicated in silico in a GWAS of Japanese individuals, including 843 individuals with and 3,350 individuals without atrial fibrillation. The identified loci implicate candidate genes that encode transcription factors related to cardiopulmonary development, cardiac-expressed ion channels and cell signaling molecules.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Atrial Fibrillation; Child; Child, Preschool; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Infant; Infant, Newborn; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Young Adult

Multi-ethnic analysis of lipid-associated loci: the NHLBI CARe project. - Musunuru, Kiran; Romaine, Simon P R; Lettre, Guillaume; Wilson, James G; Volcik, Kelly A; Tsai, Michael Y; Taylor, Herman A; Schreiner, Pamela J; Rotter, Jerome I; Rich, Stephen S; Redline, Susan; Psaty, Bruce M; et al. (PLoS One, 2012)
BACKGROUND: Whereas it is well established that plasma lipid levels have substantial heritability within populations, it remains unclear how many of the genetic determinants reported in previous studies (largely performed in European American cohorts) are relevant in different ethnicities. METHODOLOGY/PRINCIPAL FINDINGS: We tested a set of ∼50,000 polymorphisms from ∼2,000 candidate genes and genetic loci from genome-wide association studies (GWAS) for association with low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglycerides (TG) in 25,000 European Americans and 9,000 African Americans in the National Heart, Lung, and Blood Institute (NHLBI) Candidate Gene Association Resource (CARe). We replicated associations for a number of genes in one or both ethnicities and identified a novel lipid-associated variant in a locus harboring ICAM1. We compared the architecture of genetic loci associated with lipids in both African Americans and European Americans and found that the same genes were relevant across ethnic groups but the specific associated variants at each gene often differed. CONCLUSIONS/SIGNIFICANCE: We identify or provide further evidence for a number of genetic determinants of plasma lipid levels through population association studies. In many loci the determinants appear to differ substantially between African Americans and European Americans.
Keywords: African Americans; Cholesterol, HDL; Cholesterol, LDL; European Continental Ancestry Group; Genetic Association Studies; Genetic Loci; Humans; Polymorphism, Single Nucleotide; Triglycerides

Novel loci associated with PR interval in a genome-wide association study of 10 African American cohorts. - Butler, Anne M; Yin, Xiaoyan; Evans, Daniel S; Nalls, Michael A; Smith, Erin N; Tanaka, Toshiko; Li, Guo; Buxbaum, Sarah G; Whitsel, Eric A; Alonso, Alvaro; Arking, Dan E; Benjamin, Emelia J; et al. (Circ Cardiovasc Genet, 2012)
BACKGROUND: The PR interval, as measured by the resting, standard 12-lead ECG, reflects the duration of atrial/atrioventricular nodal depolarization. Substantial evidence exists for a genetic contribution to PR, including genome-wide association studies that have identified common genetic variants at 9 loci influencing PR in populations of European and Asian descent. However, few studies have examined loci associated with PR in African Americans. METHODS AND RESULTS: We present results from the largest genome-wide association study to date of PR in 13 415 adults of African descent from 10 cohorts. We tested for association between PR (ms) and ≈2.8 million genotyped and imputed single-nucleotide polymorphisms. Imputation was performed using HapMap 2 YRI and CEU panels. Study-specific results, adjusted for global ancestry and clinical correlates of PR, were meta-analyzed using the inverse variance method. Variation in genome-wide test statistic distributions was noted within studies (λ range: 0.9-1.1), although not after genomic control correction was applied to the overall meta-analysis (λ: 1.008). In addition to generalizing previously reported associations with MEIS1, SCN5A, ARHGAP24, CAV1, and TBX5 to African American populations at the genome-wide significance level (P<5.0 × 10(-8)), we also identified a novel locus: ITGA9, located in a region previously implicated in SCN5A expression. The 3p21 region harboring SCN5A also contained 2 additional independent secondary signals influencing PR (P<5.0 × 10(-8)). CONCLUSIONS: This study demonstrates the ability to map novel loci in African Americans as well as the generalizability of loci associated with PR across populations of African, European, and Asian descent.
Keywords: Adult; African Americans; Cohort Studies; Electrocardiography; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide

Novel loci for adiponectin levels and their influence on type 2 diabetes and metabolic traits: a multi-ethnic meta-analysis of 45,891 individuals. - Dastani, Zari; Hivert, Marie-France; Timpson, Nicholas; Perry, John R B; Yuan, Xin; Scott, Robert A; Henneman, Peter; Heid, Iris M; Kizer, Jorge R; Lyytikäinen, Leo-Pekka; Fuchsberger, Christian; Tanaka, Toshiko; et al. (PLoS Genet, 2012)
Circulating levels of adiponectin, a hormone produced predominantly by adipocytes, are highly heritable and are inversely associated with type 2 diabetes mellitus (T2D) and other metabolic traits. We conducted a meta-analysis of genome-wide association studies in 39,883 individuals of European ancestry to identify genes associated with metabolic disease. We identified 8 novel loci associated with adiponectin levels and confirmed 2 previously reported loci (P = 4.5×10(-8)-1.2×10(-43)). Using a novel method to combine data across ethnicities (N = 4,232 African Americans, N = 1,776 Asians, and N = 29,347 Europeans), we identified two additional novel loci. Expression analyses of 436 human adipocyte samples revealed that mRNA levels of 18 genes at candidate regions were associated with adiponectin concentrations after accounting for multiple testing (p<3×10(-4)). We next developed a multi-SNP genotypic risk score to test the association of adiponectin decreasing risk alleles on metabolic traits and diseases using consortia-level meta-analytic data. This risk score was associated with increased risk of T2D (p = 4.3×10(-3), n = 22,044), increased triglycerides (p = 2.6×10(-14), n = 93,440), increased waist-to-hip ratio (p = 1.8×10(-5), n = 77,167), increased glucose two hours post oral glucose tolerance testing (p = 4.4×10(-3), n = 15,234), increased fasting insulin (p = 0.015, n = 48,238), but with lower in HDL-cholesterol concentrations (p = 4.5×10(-13), n = 96,748) and decreased BMI (p = 1.4×10(-4), n = 121,335). These findings identify novel genetic determinants of adiponectin levels, which, taken together, influence risk of T2D and markers of insulin resistance.
Keywords: Adiponectin; African Americans; Asian Continental Ancestry Group; Cholesterol, HDL; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose Tolerance Test; Humans; Insulin Resistance; Male; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide; Waist-Hip Ratio

Telomere-associated polymorphisms correlate with cardiovascular disease mortality in Caucasian women: the Cardiovascular Health Study. - Burnett-Hartman, Andrea N; Fitzpatrick, Annette L; Kronmal, Richard A; Psaty, Bruce M; Jenny, Nancy S; Bis, Josh C; Tracy, Russ P; Kimura, Masayuki; Aviv, Abraham (Mech Ageing Dev, 2012)
Leukocyte telomere length (LTL) is linked to cardiovascular disease (CVD); however, it is unclear if LTL has an etiologic role in CVD. To gain insight into the LTL and CVD relationship, a cohort study of CVD mortality and single nucleotide polymorphisms (SNPs) in OBFC1 and TERC, genes related to LTL, was conducted among 3271 Caucasian participants ages ≥65 years enrolled 1989-1990 in the Cardiovascular Health Study. Leukocyte DNA was genotyped for SNPs in OBFC1 (rs4387287 and rs9419958) and TERC (rs3772190) that were previously associated with LTL through genome-wide association studies. Cox regression was used to estimate adjusted hazard ratios (HRs) and 95% confidence intervals (CIs). The OBFC1 SNPs were in linkage disequilibrium (r(2)=0.99), and both SNPs were similarly associated with CVD mortality in women. For women, there was a decreased risk of CVD death associated with the minor allele (rs4387287), HR=0.7; 95% CI: 0.5-0.9 (CC vs. AC) and HR=0.5; 95% CI: 0.20-1.4 (CC vs. AA) (P-trend <0.01). For men there was no association, HR=1.0; 95% CI: 0.7-1.3 (CC vs. AC) and HR=1.7; 95% CI: 0.8-3.6 (CC vs. AA) (P-trend=0.64). These findings support the hypothesis that telomere biology and associated genes may play a role in CVD-related death, particularly among women.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Female; Humans; Leukocytes; Male; Polymorphism, Genetic; Polymorphism, Single Nucleotide; Risk; RNA; Sex Factors; Telomerase; Telomere

Ultraconserved elements in the human genome: association and transmission analyses of highly constrained single-nucleotide polymorphisms. - Chiang, Charleston W K; Liu, Ching-Ti; Lettre, Guillaume; Lange, Leslie A; Jorgensen, Neal W; Keating, Brendan J; Vedantam, Sailaja; Nock, Nora L; Franceschini, Nora; Reiner, Alex P; Demerath, Ellen W; Boerwinkle, Eric; et al. (Genetics, 2012)
Ultraconserved elements in the human genome likely harbor important biological functions as they are dosage sensitive and are able to direct tissue-specific expression. Because they are under purifying selection, variants in these elements may have a lower frequency in the population but a higher likelihood of association with complex traits. We tested a set of highly constrained SNPs (hcSNPs) distributed genome-wide among ultraconserved and nearly ultraconserved elements for association with seven traits related to reproductive (age at natural menopause, number of children, age at first child, and age at last child) and overall [longevity, body mass index (BMI), and height] fitness. Using up to 24,047 European-American samples from the National Heart, Lung, and Blood Institute Candidate Gene Association Resource (CARe), we observed an excess of associations with BMI and height. In an independent replication panel the most strongly associated SNPs showed an 8.4-fold enrichment of associations at the nominal level, including three variants in previously identified loci and one in a locus (DENND1A) previously shown to be associated with polycystic ovary syndrome. Finally, using 1430 family trios, we showed that the transmissions from heterozygous parents to offspring of the derived alleles of rare (frequency ≤ 0.5%) hcSNPs are not biased, particularly after adjusting for the rates of genotype missingness and error in the data. The lack of transmission bias ruled out an immediately and strongly deleterious effect due to the rare derived alleles, consistent with the observation that mice homozygous for the deletion of ultraconserved elements showed no overt phenotype. Our study also illustrated the importance of carefully modeling potential technical confounders when analyzing genotype data of rare variants.
Keywords: Alleles; Animals; Body Height; Body Mass Index; Child; Conserved Sequence; Dogs; Evolution, Molecular; Female; Genetic Fitness; Genetic Variation; Genome, Human; Genotype; Humans; Inheritance Patterns; Male; Mice; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Rats; Reproduction; Young Adult

Association of genome-wide variation with highly sensitive cardiac troponin-T levels in European Americans and Blacks: a meta-analysis from atherosclerosis risk in communities and cardiovascular health studies. - Yu, Bing; Barbalic, Maja; Brautbar, Ariel; Nambi, Vijay; Hoogeveen, Ron C; Tang, Weihong; Mosley, Thomas H; Rotter, Jerome I; deFilippi, Christopher R; O'Donnell, Christopher J; Kathiresan, Sekar; Rice, Ken; et al. (Circ Cardiovasc Genet, 2013)
BACKGROUND: High levels of cardiac troponin T, measured by a highly sensitive assay (hs-cTnT), are strongly associated with incident coronary heart disease and heart failure. To date, no large-scale genome-wide association study of hs-cTnT has been reported. We sought to identify novel genetic variants that are associated with hs-cTnT levels. METHODS AND RESULTS: We performed a genome-wide association in 9491 European Americans and 2053 blacks free of coronary heart disease and heart failure from 2 prospective cohorts: the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study. Genome-wide association studies were conducted in each study and race stratum. Fixed-effect meta-analyses combined the results of linear regression from 2 cohorts within each race stratum and then across race strata to produce overall estimates and probability values. The meta-analysis identified a significant association at chromosome 8q13 (rs10091374; P=9.06×10(-9)) near the nuclear receptor coactivator 2 (NCOA2) gene. Overexpression of NCOA2 can be detected in myoblasts. An additional analysis using logistic regression and the clinically motivated 99th percentile cut point detected a significant association at 1q32 (rs12564445; P=4.73×10(-8)) in the gene TNNT2, which encodes the cardiac troponin T protein itself. The hs-cTnT-associated single-nucleotide polymorphisms were not associated with coronary heart disease in a large case-control study, but rs12564445 was significantly associated with incident heart failure in Atherosclerosis Risk in Communities Study European Americans (hazard ratio=1.16; P=0.004). CONCLUSIONS: We identified 2 loci, near NCOA2 and in the TNNT2 gene, at which variation was significantly associated with hs-cTnT levels. Further use of the new assay should enable replication of these results.
Keywords: African Continental Ancestry Group; Atherosclerosis; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Nuclear Receptor Coactivator 2; Polymorphism, Single Nucleotide; Prospective Studies; Residence Characteristics; Risk Factors; Troponin T

Best practices and joint calling of the HumanExome BeadChip: the CHARGE Consortium. - Grove, Megan L; Yu, Bing; Cochran, Barbara J; Haritunians, Talin; Bis, Joshua C; Taylor, Kent D; Hansen, Mark; Borecki, Ingrid B; Cupples, L Adrienne; Fornage, Myriam; Gudnason, Vilmundur; Harris, Tamara B; et al. (PLoS One, 2013)
Genotyping arrays are a cost effective approach when typing previously-identified genetic polymorphisms in large numbers of samples. One limitation of genotyping arrays with rare variants (e.g., minor allele frequency [MAF] <0.01) is the difficulty that automated clustering algorithms have to accurately detect and assign genotype calls. Combining intensity data from large numbers of samples may increase the ability to accurately call the genotypes of rare variants. Approximately 62,000 ethnically diverse samples from eleven Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium cohorts were genotyped with the Illumina HumanExome BeadChip across seven genotyping centers. The raw data files for the samples were assembled into a single project for joint calling. To assess the quality of the joint calling, concordance of genotypes in a subset of individuals having both exome chip and exome sequence data was analyzed. After exclusion of low performing SNPs on the exome chip and non-overlap of SNPs derived from sequence data, genotypes of 185,119 variants (11,356 were monomorphic) were compared in 530 individuals that had whole exome sequence data. A total of 98,113,070 pairs of genotypes were tested and 99.77% were concordant, 0.14% had missing data, and 0.09% were discordant. We report that joint calling allows the ability to accurately genotype rare variation using array technology when large sample sizes are available and best practices are followed. The cluster file from this experiment is available at www.chargeconsortium.com/main/exomechip.
Keywords: Aging; Alleles; Cluster Analysis; Cohort Studies; Continental Population Groups; Exome; Female; Gene Frequency; Genomics; Genotype; Heart; Humans; Male; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Sample Size; Self Report; Sequence Analysis, DNA

Common FABP4 genetic variants and plasma levels of fatty acid binding protein 4 in older adults. - Mukamal, Kenneth J; Wilk, Jemma B; Biggs, Mary L; Jensen, Majken K; Ix, Joachim H; Kizer, Jorge R; Tracy, Russell P; Zieman, Susan J; Mozaffarian, Dariush; Psaty, Bruce M; Siscovick, David S; Djoussé, Luc (Lipids, 2013)
We examined common variants in the fatty acid binding protein 4 gene (FABP4) and plasma levels of FABP4 in adults aged 65 and older from the Cardiovascular Health Study. We genotyped rs16909187, rs1054135, rs16909192, rs10808846, rs7018409, rs2290201, and rs6992708 and measured circulating FABP4 levels among 3190 European Americans and 660 African Americans. Among European Americans, the minor alleles of six single nucleotide polymorphisms (SNP) were associated with lower FABP4 levels (all p ≤ 0.01). Among African Americans, the SNP with the lowest minor allele frequency was associated with lower FABP4 levels (p = 0.015). The C-A haplotype of rs16909192 and rs2290201 was associated with lower FABP4 levels in both European Americans (frequency = 16 %; p = 0.001) and African Americans (frequency = 8 %; p = 0.04). The haplotype combined a SNP in the first intron with one in the 3'untranslated region. However, the alleles associated with lower FABP4 levels were associated with higher fasting glucose in meta-analyses from the MAGIC consortium. These results demonstrate associations of common SNP and haplotypes in the FABP4 gene with lower plasma FABP4 but higher fasting glucose levels.
Keywords: African Americans; Aged; Aged, 80 and over; Blood Glucose; Body Mass Index; Cohort Studies; European Continental Ancestry Group; Fatty Acid-Binding Proteins; Female; Gene Frequency; Genetic Association Studies; Haplotypes; Humans; Insulin; Linkage Disequilibrium; Male; Polymorphism, Single Nucleotide

Common genetic variation near the connexin-43 gene is associated with resting heart rate in African Americans: a genome-wide association study of 13,372 participants. - Deo, R; Nalls, M A; Avery, C L; Smith, J G; Evans, D S; Keller, M F; Butler, A M; Buxbaum, S G; Li, G; Miguel Quibrera, P; Smith, E N; Tanaka, T; et al. (Heart Rhythm, 2013)
BACKGROUND: Genome-wide association studies have identified several genetic loci associated with variation in resting heart rate in European and Asian populations. No study has evaluated genetic variants associated with heart rate in African Americans. OBJECTIVE: To identify novel genetic variants associated with resting heart rate in African Americans. METHODS: Ten cohort studies participating in the Candidate-gene Association Resource and Continental Origins and Genetic Epidemiology Network consortia performed genome-wide genotyping of single nucleotide polymorphisms (SNPs) and imputed 2,954,965 SNPs using HapMap YRI and CEU panels in 13,372 participants of African ancestry. Each study measured the RR interval (ms) from 10-second resting 12-lead electrocardiograms and estimated RR-SNP associations using covariate-adjusted linear regression. Random-effects meta-analysis was used to combine cohort-specific measures of association and identify genome-wide significant loci (P≤2.5×10(-8)). RESULTS: Fourteen SNPs on chromosome 6q22 exceeded the genome-wide significance threshold. The most significant association was for rs9320841 (+13 ms per minor allele; P = 4.98×10(-15)). This SNP was approximately 350 kb downstream of GJA1, a locus previously identified as harboring SNPs associated with heart rate in Europeans. Adjustment for rs9320841 also attenuated the association between the remaining 13 SNPs in this region and heart rate. In addition, SNPs in MYH6, which have been identified in European genome-wide association study, were associated with similar changes in the resting heart rate as this population of African Americans. CONCLUSIONS: An intergenic region downstream of GJA1 (the gene encoding connexin 43, the major protein of the human myocardial gap junction) and an intragenic region within MYH6 are associated with variation in resting heart rate in African Americans as well as in populations of European and Asian origin.
Keywords: Adult; African Americans; Aged; Arrhythmias, Cardiac; Connexin 43; Electrocardiography; Female; Genetic Variation; Genome-Wide Association Study; Genotype; Heart Rate; Humans; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Rest; United States

Common variants associated with plasma triglycerides and risk for coronary artery disease. - Do, Ron; Willer, Cristen J; Schmidt, Ellen M; Sengupta, Sebanti; Gao, Chi; Peloso, Gina M; Gustafsson, Stefan; Kanoni, Stavroula; Ganna, Andrea; Chen, Jin; Buchkovich, Martin L; Mora, Samia; et al. (Nat Genet, 2013)
Triglycerides are transported in plasma by specific triglyceride-rich lipoproteins; in epidemiological studies, increased triglyceride levels correlate with higher risk for coronary artery disease (CAD). However, it is unclear whether this association reflects causal processes. We used 185 common variants recently mapped for plasma lipids (P < 5 × 10(-8) for each) to examine the role of triglycerides in risk for CAD. First, we highlight loci associated with both low-density lipoprotein cholesterol (LDL-C) and triglyceride levels, and we show that the direction and magnitude of the associations with both traits are factors in determining CAD risk. Second, we consider loci with only a strong association with triglycerides and show that these loci are also associated with CAD. Finally, in a model accounting for effects on LDL-C and/or high-density lipoprotein cholesterol (HDL-C) levels, the strength of a polymorphism's effect on triglyceride levels is correlated with the magnitude of its effect on CAD risk. These results suggest that triglyceride-rich lipoproteins causally influence risk for CAD.
Keywords: Biological Transport; Cholesterol, HDL; Cholesterol, LDL; Coronary Artery Disease; Humans; Polymorphism, Single Nucleotide; Risk Factors; Triglycerides

Common variants in Mendelian kidney disease genes and their association with renal function. - Parsa, Afshin; Fuchsberger, Christian; Köttgen, Anna; O'Seaghdha, Conall M; Pattaro, Cristian; de Andrade, Mariza; Chasman, Daniel I; Teumer, Alexander; Endlich, Karlhans; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; et al. (J Am Soc Nephrol, 2013)
Many common genetic variants identified by genome-wide association studies for complex traits map to genes previously linked to rare inherited Mendelian disorders. A systematic analysis of common single-nucleotide polymorphisms (SNPs) in genes responsible for Mendelian diseases with kidney phenotypes has not been performed. We thus developed a comprehensive database of genes for Mendelian kidney conditions and evaluated the association between common genetic variants within these genes and kidney function in the general population. Using the Online Mendelian Inheritance in Man database, we identified 731 unique disease entries related to specific renal search terms and confirmed a kidney phenotype in 218 of these entries, corresponding to mutations in 258 genes. We interrogated common SNPs (minor allele frequency >5%) within these genes for association with the estimated GFR in 74,354 European-ancestry participants from the CKDGen Consortium. However, the top four candidate SNPs (rs6433115 at LRP2, rs1050700 at TSC1, rs249942 at PALB2, and rs9827843 at ROBO2) did not achieve significance in a stage 2 meta-analysis performed in 56,246 additional independent individuals, indicating that these common SNPs are not associated with estimated GFR. The effect of less common or rare variants in these genes on kidney function in the general population and disease-specific cohorts requires further research.
Keywords: Databases, Genetic; European Continental Ancestry Group; Gene Frequency; Genetic Variation; Genome-Wide Association Study; Humans; Kidney; Mendelian Randomization Analysis; Phenotype; Polymorphism, Single Nucleotide; Renal Insufficiency, Chronic

Effects of smoking on the genetic risk of obesity: the population architecture using genomics and epidemiology study. - Fesinmeyer, Megan D; North, Kari E; Lim, Unhee; Bůzková, Petra; Crawford, Dana C; Haessler, Jeffrey; Gross, Myron D; Fowke, Jay H; Goodloe, Robert; Love, Shelley-Ann; Graff, Misa; Carlson, Christopher S; et al. (BMC Med Genet, 2013)
BACKGROUND: Although smoking behavior is known to affect body mass index (BMI), the potential for smoking to influence genetic associations with BMI is largely unexplored. METHODS: As part of the 'Population Architecture using Genomics and Epidemiology (PAGE)' Consortium, we investigated interaction between genetic risk factors associated with BMI and smoking for 10 single nucleotide polymorphisms (SNPs) previously identified in genome-wide association studies. We included 6 studies with a total of 56,466 subjects (16,750 African Americans (AA) and 39,716 European Americans (EA)). We assessed effect modification by testing an interaction term for each SNP and smoking (current vs. former/never) in the linear regression and by stratified analyses. RESULTS: We did not observe strong evidence for interactions and only observed two interactions with p-values <0.1: for rs6548238/TMEM18, the risk allele (C) was associated with BMI only among AA females who were former/never smokers (β = 0.018, p = 0.002), vs. current smokers (β = 0.001, p = 0.95, p(interaction) = 0.10). For rs9939609/FTO, the A allele was more strongly associated with BMI among current smoker EA females (β = 0.017, p = 3.5 x 10(-5)), vs. former/never smokers (β = 0.006, p = 0.05, p(interaction) = 0.08). CONCLUSIONS: These analyses provide limited evidence that smoking status may modify genetic effects of previously identified genetic risk factors for BMI. Larger studies are needed to follow up our results. CLINICAL TRIAL REGISTRATION: NCT00000611.
Keywords: Adolescent; Adult; African Americans; Aged; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Body Mass Index; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Humans; Male; Membrane Proteins; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Proteins; Risk Factors; Smoking; Young Adult

Fine Mapping and Identification of BMI Loci in African Americans. - Gong, Jian; Schumacher, Fredrick; Lim, Unhee; Hindorff, Lucia A; Haessler, Jeff; Buyske, Steven; Carlson, Christopher S; Rosse, Stephanie; Bůzková, Petra; Fornage, Myriam; Gross, Myron; Pankratz, Nathan; et al. (Am J Hum Genet, 2013)
Genome-wide association studies (GWASs) primarily performed in European-ancestry (EA) populations have identified numerous loci associated with body mass index (BMI). However, it is still unclear whether these GWAS loci can be generalized to other ethnic groups, such as African Americans (AAs). Furthermore, the putative functional variant or variants in these loci mostly remain under investigation. The overall lower linkage disequilibrium in AA compared to EA populations provides the opportunity to narrow in or fine-map these BMI-related loci. Therefore, we used the Metabochip to densely genotype and evaluate 21 BMI GWAS loci identified in EA studies in 29,151 AAs from the Population Architecture using Genomics and Epidemiology (PAGE) study. Eight of the 21 loci (SEC16B, TMEM18, ETV5, GNPDA2, TFAP2B, BDNF, FTO, and MC4R) were found to be associated with BMI in AAs at 5.8 × 10(-5). Within seven out of these eight loci, we found that, on average, a substantially smaller number of variants was correlated (r(2) > 0.5) with the most significant SNP in AA than in EA populations (16 versus 55). Conditional analyses revealed GNPDA2 harboring a potential additional independent signal. Moreover, Metabochip-wide discovery analyses revealed two BMI-related loci, BRE (rs116612809, p = 3.6 × 10(-8)) and DHX34 (rs4802349, p = 1.2 × 10(-7)), which were significant when adjustment was made for the total number of SNPs tested across the chip. These results demonstrate that fine mapping in AAs is a powerful approach for both narrowing in on the underlying causal variants in known loci and discovering BMI-related loci.
Keywords: Adult; African Americans; Aged; Aged, 80 and over; Body Mass Index; Female; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Young Adult

Gene-centric meta-analyses of 108 912 individuals confirm known body mass index loci and reveal three novel signals. - Guo, Yiran; Lanktree, Matthew B; Taylor, Kira C; Hakonarson, Hakon; Lange, Leslie A; Keating, Brendan J (Hum Mol Genet, 2013)
Recent genetic association studies have made progress in uncovering components of the genetic architecture of the body mass index (BMI). We used the ITMAT-Broad-Candidate Gene Association Resource (CARe) (IBC) array comprising up to 49 320 single nucleotide polymorphisms (SNPs) across ~2100 metabolic and cardiovascular-related loci to genotype up to 108 912 individuals of European ancestry (EA), African-Americans, Hispanics and East Asians, from 46 studies, to provide additional insight into SNPs underpinning BMI. We used a five-phase study design: Phase I focused on meta-analysis of EA studies providing individual level genotype data; Phase II performed a replication of cohorts providing summary level EA data; Phase III meta-analyzed results from the first two phases; associated SNPs from Phase III were used for replication in Phase IV; finally in Phase V, a multi-ethnic meta-analysis of all samples from four ethnicities was performed. At an array-wide significance (P < 2.40E-06), we identify novel BMI associations in loci translocase of outer mitochondrial membrane 40 homolog (yeast) - apolipoprotein E - apolipoprotein C-I (TOMM40-APOE-APOC1) (rs2075650, P = 2.95E-10), sterol regulatory element binding transcription factor 2 (SREBF2, rs5996074, P = 9.43E-07) and neurotrophic tyrosine kinase, receptor, type 2 [NTRK2, a brain-derived neurotrophic factor (BDNF) receptor gene, rs1211166, P = 1.04E-06] in the Phase IV meta-analysis. Of 10 loci with previous evidence for BMI association represented on the IBC array, eight were replicated, with the remaining two showing nominal significance. Conditional analyses revealed two independent BMI-associated signals in BDNF and melanocortin 4 receptor (MC4R) regions. Of the 11 array-wide significant SNPs, three are associated with gene expression levels in both primary B-cells and monocytes; with rs4788099 in SH2B adaptor protein 1 (SH2B1) notably being associated with the expression of multiple genes in cis. These multi-ethnic meta-analyses expand our knowledge of BMI genetics.
Keywords: Body Mass Index; Cohort Studies; Ethnic Groups; Humans; Polymorphism, Single Nucleotide

Generalization and dilution of association results from European GWAS in populations of non-European ancestry: the PAGE study. - Carlson, Christopher S; Matise, Tara C; North, Kari E; Haiman, Christopher A; Fesinmeyer, Megan D; Buyske, Steven; Schumacher, Fredrick R; Peters, Ulrike; Franceschini, Nora; Ritchie, Marylyn D; Duggan, David J; Spencer, Kylee L; et al. (PLoS Biol, 2013)
The vast majority of genome-wide association study (GWAS) findings reported to date are from populations with European Ancestry (EA), and it is not yet clear how broadly the genetic associations described will generalize to populations of diverse ancestry. The Population Architecture Using Genomics and Epidemiology (PAGE) study is a consortium of multi-ancestry, population-based studies formed with the objective of refining our understanding of the genetic architecture of common traits emerging from GWAS. In the present analysis of five common diseases and traits, including body mass index, type 2 diabetes, and lipid levels, we compare direction and magnitude of effects for GWAS-identified variants in multiple non-EA populations against EA findings. We demonstrate that, in all populations analyzed, a significant majority of GWAS-identified variants have allelic associations in the same direction as in EA, with none showing a statistically significant effect in the opposite direction, after adjustment for multiple testing. However, 25% of tagSNPs identified in EA GWAS have significantly different effect sizes in at least one non-EA population, and these differential effects were most frequent in African Americans where all differential effects were diluted toward the null. We demonstrate that differential LD between tagSNPs and functional variants within populations contributes significantly to dilute effect sizes in this population. Although most variants identified from GWAS in EA populations generalize to all non-EA populations assessed, genetic models derived from GWAS findings in EA may generate spurious results in non-EA populations due to differential effect sizes. Regardless of the origin of the differential effects, caution should be exercised in applying any genetic risk prediction model based on tagSNPs outside of the ancestry group in which it was derived. Models based directly on functional variation may generalize more robustly, but the identification of functional variants remains challenging.
Keywords: African Americans; Asian Americans; Body Mass Index; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Hispanic Americans; Humans; Indians, North American; Lipids; Metagenomics; Oceanic Ancestry Group; Polymorphism, Single Nucleotide

Genetic analysis of a population heavy drinking phenotype identifies risk variants in whites. - Hamidovic, Ajna; Goodloe, Robert J; Young, Taylor R; Styn, Mindi A; Mukamal, Kenneth J; Choquet, Helene; Kasberger, Jay L; Buxbaum, Sarah G; Papanicolaou, George J; White, Wendy; Volcik, Kelly; Spring, Bonnie; et al. (J Clin Psychopharmacol, 2013)
Genetic association studies thus far have used detailed diagnoses of alcoholism to identify loci associated with risk. This proof-of-concept analysis examined whether population data of lifetime heaviest alcohol consumption may be used to identify genetic loci that modulate risk. We conducted a genetic association study in European Americans between variants in approximately 2100 genes and alcohol consumption as part of the Candidate gene Association Resource project. We defined cases as individuals with a history of drinking 5 or more drinks per day almost every day of the week and controls as current light drinkers (1-5 drinks per week). We cross-validated identified single nucleotide polymorphisms in a meta-analysis of 2 cohorts of unrelated individuals--Atherosclerosis Risk in Communities (ARIC) and Cardiovascular Health Study (CHS)--and in a separate cohort of related individuals--Framingham Heart Study (FHS). The most significant variant in the meta-analysis of ARIC and CHS was rs6933598 in methylenetetrahydrofolate dehydrogenase (P = 7.46 × 10(-05)) with a P value in FHS of 0.042. The top variants in FHS were rs12249562 in cubulin (P = 3.03 × 10(-05)) and rs9839267 near cholecystokinin (P = 3.05 × 10(-05)) with a P value of 0.019 for rs9839267 in CHS. We have here shown feasibility in evaluating lifetime incidence of heavy alcohol drinking from population-based studies for the purpose of conducting genetic association analyses.
Keywords: Aged; Alcohol Drinking; Alcoholism; Case-Control Studies; European Continental Ancestry Group; Feasibility Studies; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Humans; Incidence; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Risk

Genetic association of COL5A1 variants in keratoconus patients suggests a complex connection between corneal thinning and keratoconus. - Li, Xiaohui; Bykhovskaya, Yelena; Canedo, Ana Laura Caiado; Haritunians, Talin; Siscovick, David; Aldave, Anthony J; Szczotka-Flynn, Loretta; Iyengar, Sudha K; Rotter, Jerome I; Taylor, Kent D; Rabinowitz, Yaron S (Invest Ophthalmol Vis Sci, 2013)
PURPOSE: Single nucleotide polymorphisms (SNPs) located near or within the COL5A1 gene, at 9q34.2-q34.3 chromosomal region have been reported in association with central corneal thickness (CCT). Using family linkage analysis, we identified a keratoconus susceptibility locus at 9q34. These findings led us to perform an association study between COL5A1 variation and keratoconus susceptibility. METHODS: A Caucasian case-control cohort of 222 keratoconus patients and 3324 controls was selected as the discovery panel. An independent case-control panel of 304 cases and 518 controls and a family panel of 186 subjects were replicated for genotyping and association. Forty-four SNPs (21 for discovery and 23 for fine-mapping) spanning 300 kilobases in and around COL5A1 were genotyped and tested for genetic association. Logistic regression models implemented in PLINK were used to test for association in case controls. Generalized estimating equation models accounting for familial correlations implemented in genome-wide interaction analyses with family data were used for association testing in families. RESULTS: Two CCT associated SNPs (rs1536482 and rs7044529 near and within COL5A1) were identified in the keratoconus discovery cohort (P values of 6.5 × 10(-3) and 7.4 × 10(-3)). SNP rs1536482 was replicated in the second case-control sample (P = 0.02), and SNP rs7044529 was replicated in a keratoconus family panel (P = 0.03). Meta P values of rs1536482 and rs7044529 in the keratoconus cohorts were 1.5 × 10(-4) (odds ratio [OR] = 1.30) and 2.9 × 10(-3) (OR = 1.39). After Bonferroni correction, the association of SNP rs1536482 remained significant (P = 6.5 × 10(-3)). CONCLUSIONS: SNPs in the COL5A1 region, which regulate normal variation in CCT, may play a role in the thinning associated with keratoconus.
Keywords: Adult; Aged; Collagen Type V; Cornea; Corneal Topography; DNA; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Keratoconus; Male; Microscopy, Acoustic; Middle Aged; Polymorphism, Single Nucleotide; Tomography, Optical Coherence

Genetic risk factors for BMI and obesity in an ethnically diverse population: results from the population architecture using genomics and epidemiology (PAGE) study. - Fesinmeyer, Megan D; North, Kari E; Ritchie, Marylyn D; Lim, Unhee; Franceschini, Nora; Wilkens, Lynne R; Gross, Myron D; Bůzková, Petra; Glenn, Kimberly; Quibrera, P Miguel; Fernandez-Rhodes, Lindsay; Li, Qiong; et al. (Obesity (Silver Spring), 2013)
OBJECTIVE: Several genome-wide association studies (GWAS) have demonstrated that common genetic variants contribute to obesity. However, studies of this complex trait have focused on ancestrally European populations, despite the high prevalence of obesity in some minority groups. DESIGN AND METHODS: As part of the "Population Architecture using Genomics and Epidemiology (PAGE)" Consortium, we investigated the association between 13 GWAS-identified single-nucleotide polymorphisms (SNPs) and BMI and obesity in 69,775 subjects, including 6,149 American Indians, 15,415 African-Americans, 2,438 East Asians, 7,346 Hispanics, 604 Pacific Islanders, and 37,823 European Americans. For the BMI-increasing allele of each SNP, we calculated β coefficients using linear regression (for BMI) and risk estimates using logistic regression (for obesity defined as BMI ≥ 30) followed by fixed-effects meta-analysis to combine results across PAGE sites. Analyses stratified by racial/ethnic group assumed an additive genetic model and were adjusted for age, sex, and current smoking. We defined "replicating SNPs" (in European Americans) and "generalizing SNPs" (in other racial/ethnic groups) as those associated with an allele frequency-specific increase in BMI. RESULTS: By this definition, we replicated 9/13 SNP associations (5 out of 8 loci) in European Americans. We also generalized 8/13 SNP associations (5/8 loci) in East Asians, 7/13 (5/8 loci) in African Americans, 6/13 (4/8 loci) in Hispanics, 5/8 in Pacific Islanders (5/8 loci), and 5/9 (4/8 loci) in American Indians. CONCLUSION: Linkage disequilibrium patterns suggest that tagSNPs selected for European Americans may not adequately tag causal variants in other ancestry groups. Accordingly, fine-mapping in large samples is needed to comprehensively explore these loci in diverse populations.
Keywords: Alleles; Body Mass Index; Ethnic Groups; Gene Frequency; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Metagenomics; Obesity; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

Genetic variants associated with fasting glucose and insulin concentrations in an ethnically diverse population: results from the Population Architecture using Genomics and Epidemiology (PAGE) study. - Fesinmeyer, Megan D; Meigs, James B; North, Kari E; Schumacher, Fredrick R; Bůzková, Petra; Franceschini, Nora; Haessler, Jeffrey; Goodloe, Robert; Spencer, Kylee L; Voruganti, Venkata Saroja; Howard, Barbara V; Jackson, Rebecca; et al. (BMC Med Genet, 2013)
BACKGROUND: Multiple genome-wide association studies (GWAS) within European populations have implicated common genetic variants associated with insulin and glucose concentrations. In contrast, few studies have been conducted within minority groups, which carry the highest burden of impaired glucose homeostasis and type 2 diabetes in the U.S. METHODS: As part of the 'Population Architecture using Genomics and Epidemiology (PAGE) Consortium, we investigated the association of up to 10 GWAS-identified single nucleotide polymorphisms (SNPs) in 8 genetic regions with glucose or insulin concentrations in up to 36,579 non-diabetic subjects including 23,323 European Americans (EA) and 7,526 African Americans (AA), 3,140 Hispanics, 1,779 American Indians (AI), and 811 Asians. We estimated the association between each SNP and fasting glucose or log-transformed fasting insulin, followed by meta-analysis to combine results across PAGE sites. RESULTS: Overall, our results show that 9/9 GWAS SNPs are associated with glucose in EA (p = 0.04 to 9 × 10-15), versus 3/9 in AA (p= 0.03 to 6 × 10-5), 3/4 SNPs in Hispanics, 2/4 SNPs in AI, and 1/2 SNPs in Asians. For insulin we observed a significant association with rs780094/GCKR in EA, Hispanics and AI only. CONCLUSIONS: Generalization of results across multiple racial/ethnic groups helps confirm the relevance of some of these loci for glucose and insulin metabolism. Lack of association in non-EA groups may be due to insufficient power, or to unique patterns of linkage disequilibrium.
Keywords: Adaptor Proteins, Signal Transducing; Adult; African Americans; Aged; Alleles; Asian Continental Ancestry Group; Blood Glucose; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Genomics; Hispanic Americans; Humans; Indians, North American; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide; Transcription Factor 7-Like 2 Protein

Genetically elevated fetuin-A levels, fasting glucose levels, and risk of type 2 diabetes: the cardiovascular health study. - Jensen, Majken K; Bartz, Traci M; Djoussé, Luc; Kizer, Jorge R; Zieman, Susan J; Rimm, Eric B; Siscovick, David S; Psaty, Bruce M; Ix, Joachim H; Mukamal, Kenneth J (Diabetes Care, 2013)
OBJECTIVE: Fetuin-A levels are associated with higher risk of type 2 diabetes, but it is unknown if the association is causal. We investigated common (>5%) genetic variants in the fetuin-A gene (AHSG) fetuin-A levels, fasting glucose, and risk of type 2 diabetes. RESEARCH DESIGN AND METHODS: Genetic variation, fetuin-A levels, and fasting glucose were assessed in 2,893 Caucasian and 542 African American community-living individuals 65 years of age or older in 1992-1993. RESULTS: Common AHSG variants (rs4917 and rs2248690) were strongly associated with fetuin-A concentrations (P<0.0001). In analyses of 259 incident cases of type 2 diabetes, the single nucleotide polymorphisms (SNPs) were not associated with diabetes risk during follow-up and similar null associations were observed when 579 prevalent cases were included. As expected, higher fetuin-A levels were associated with higher fasting glucose concentrations (1.9 mg/dL [95% CI, 1.2-2.7] higher per SD in Caucasians), but Mendelian randomization analyses using both SNPs as unbiased proxies for measured fetuin-A did not support an association between genetically predicted fetuin-A levels and fasting glucose (-0.3 mg/dL [95% CI, -1.9 to 1.3] lower per SD in Caucasians). The difference between the associations of fasting glucose with actual and genetically predicted fetuin-A level was statistically significant (P=0.001). Results among the smaller sample of African Americans trended in similar directions but were statistically insignificant. CONCLUSIONS: Common variants in the AHSG gene are strongly associated with plasma fetuin-A concentrations, but not with risk of type 2 diabetes or glucose concentrations, raising the possibility that the association between fetuin-A and type 2 diabetes may not be causal.
Keywords: alpha-2-HS-Glycoprotein; Blood Glucose; Diabetes Mellitus, Type 2; Fasting; Female; Genotype; Humans; Male; Polymorphism, Single Nucleotide

Genome-wide and gene-centric analyses of circulating myeloperoxidase levels in the charge and care consortia. - Reiner, Alexander P; Hartiala, Jaana; Zeller, Tanja; Bis, Joshua C; Dupuis, Josée; Fornage, Myriam; Baumert, Jens; Kleber, Marcus E; Wild, Philipp S; Baldus, Stephan; Bielinski, Suzette J; Fontes, João D; et al. (Hum Mol Genet, 2013)
Increased systemic levels of myeloperoxidase (MPO) are associated with the risk of coronary artery disease (CAD). To identify the genetic factors that are associated with circulating MPO levels, we carried out a genome-wide association study (GWAS) and a gene-centric analysis in subjects of European ancestry and African Americans (AAs). A locus on chromosome 1q31.1 containing the complement factor H (CFH) gene was strongly associated with serum MPO levels in 9305 subjects of European ancestry (lead SNP rs800292; P = 4.89 × 10(-41)) and in 1690 AA subjects (rs505102; P = 1.05 × 10(-8)). Gene-centric analyses in 8335 subjects of European ancestry additionally identified two rare MPO coding sequence variants that were associated with serum MPO levels (rs28730837, P = 5.21 × 10(-12); rs35897051, P = 3.32 × 10(-8)). A GWAS for plasma MPO levels in 9260 European ancestry subjects identified a chromosome 17q22 region near MPO that was significantly associated (lead SNP rs6503905; P = 2.94 × 10(-12)), but the CFH locus did not exhibit evidence of association with plasma MPO levels. Functional analyses revealed that rs800292 was associated with levels of complement proteins in serum. Variants at chromosome 17q22 also had pleiotropic cis effects on gene expression. In a case-control analysis of ∼80 000 subjects from CARDIoGRAM, none of the identified single-nucleotide polymorphisms (SNPs) were associated with CAD. These results suggest that distinct genetic factors regulate serum and plasma MPO levels, which may have relevance for various acute and chronic inflammatory disorders. The clinical implications for CAD and a better understanding of the functional basis for the association of CFH and MPO variants with circulating MPO levels require further study.
Keywords: Adult; African Americans; Aged; Case-Control Studies; Complement Factor H; Coronary Artery Disease; European Continental Ancestry Group; Female; Gene Expression Regulation, Enzymologic; Genetic Association Studies; Genetic Variation; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Peroxidase; Polymorphism, Single Nucleotide; Young Adult

Genome-wide association analyses identify 18 new loci associated with serum urate concentrations. - Köttgen, Anna; Albrecht, Eva; Teumer, Alexander; Vitart, Veronique; Krumsiek, Jan; Hundertmark, Claudia; Pistis, Giorgio; Ruggiero, Daniela; O'Seaghdha, Conall M; Haller, Toomas; Yang, Qiong; Tanaka, Toshiko; et al. (Nat Genet, 2013)
Elevated serum urate concentrations can cause gout, a prevalent and painful inflammatory arthritis. By combining data from >140,000 individuals of European ancestry within the Global Urate Genetics Consortium (GUGC), we identified and replicated 28 genome-wide significant loci in association with serum urate concentrations (18 new regions in or near TRIM46, INHBB, SFMBT1, TMEM171, VEGFA, BAZ1B, PRKAG2, STC1, HNF4G, A1CF, ATXN2, UBE2Q2, IGF1R, NFAT5, MAF, HLF, ACVR1B-ACVRL1 and B3GNT4). Associations for many of the loci were of similar magnitude in individuals of non-European ancestry. We further characterized these loci for associations with gout, transcript expression and the fractional excretion of urate. Network analyses implicate the inhibins-activins signaling pathways and glucose metabolism in systemic urate control. New candidate genes for serum urate concentration highlight the importance of metabolic control of urate production and excretion, which may have implications for the treatment and prevention of gout.
Keywords: Analysis of Variance; European Continental Ancestry Group; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Glucose; Gout; Humans; Inhibins; Polymorphism, Single Nucleotide; Signal Transduction; Uric Acid

Genome-wide association of body fat distribution in African ancestry populations suggests new loci. - Liu, Ching-Ti; Monda, Keri L; Taylor, Kira C; Lange, Leslie; Demerath, Ellen W; Palmas, Walter; Wojczynski, Mary K; Ellis, Jaclyn C; Vitolins, Mara Z; Liu, Simin; Papanicolaou, George J; Irvin, Marguerite R; et al. (PLoS Genet, 2013)
Central obesity, measured by waist circumference (WC) or waist-hip ratio (WHR), is a marker of body fat distribution. Although obesity disproportionately affects minority populations, few studies have conducted genome-wide association study (GWAS) of fat distribution among those of predominantly African ancestry (AA). We performed GWAS of WC and WHR, adjusted and unadjusted for BMI, in up to 33,591 and 27,350 AA individuals, respectively. We identified loci associated with fat distribution in AA individuals using meta-analyses of GWA results for WC and WHR (stage 1). Overall, 25 SNPs with single genomic control (GC)-corrected p-values<5.0 × 10(-6) were followed-up (stage 2) in AA with WC and with WHR. Additionally, we interrogated genomic regions of previously identified European ancestry (EA) WHR loci among AA. In joint analysis of association results including both Stage 1 and 2 cohorts, 2 SNPs demonstrated association, rs2075064 at LHX2, p = 2.24×10(-8) for WC-adjusted-for-BMI, and rs6931262 at RREB1, p = 2.48×10(-8) for WHR-adjusted-for-BMI. However, neither signal was genome-wide significant after double GC-correction (LHX2: p = 6.5 × 10(-8); RREB1: p = 5.7 × 10(-8)). Six of fourteen previously reported loci for waist in EA populations were significant (p<0.05 divided by the number of independent SNPs within the region) in AA studied here (TBX15-WARS2, GRB14, ADAMTS9, LY86, RSPO3, ITPR2-SSPN). Further, we observed associations with metabolic traits: rs13389219 at GRB14 associated with HDL-cholesterol, triglycerides, and fasting insulin, and rs13060013 at ADAMTS9 with HDL-cholesterol and fasting insulin. Finally, we observed nominal evidence for sexual dimorphism, with stronger results in AA women at the GRB14 locus (p for interaction = 0.02). In conclusion, we identified two suggestive loci associated with fat distribution in AA populations in addition to confirming 6 loci previously identified in populations of EA. These findings reinforce the concept that there are fat distribution loci that are independent of generalized adiposity.
Keywords: Adiposity; African Continental Ancestry Group; Body Fat Distribution; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Obesity; Polymorphism, Single Nucleotide; Waist-Hip Ratio

A genome-wide association study for venous thromboembolism: the extended cohorts for heart and aging research in genomic epidemiology (CHARGE) consortium. - Tang, Weihong; Teichert, Martina; Chasman, Daniel I; Heit, John A; Morange, Pierre-Emmanuel; Li, Guo; Pankratz, Nathan; Leebeek, Frank W; Paré, Guillaume; de Andrade, Mariza; Tzourio, Christophe; Psaty, Bruce M; et al. (Genet Epidemiol, 2013)
Venous thromboembolism (VTE) is a common, heritable disease resulting in high rates of hospitalization and mortality. Yet few associations between VTE and genetic variants, all in the coagulation pathway, have been established. To identify additional genetic determinants of VTE, we conducted a two-stage genome-wide association study (GWAS) among individuals of European ancestry in the extended cohorts for heart and aging research in genomic epidemiology (CHARGE) VTE consortium. The discovery GWAS comprised 1,618 incident VTE cases out of 44,499 participants from six community-based studies. Genotypes for genome-wide single-nucleotide polymorphisms (SNPs) were imputed to approximately 2.5 million SNPs in HapMap and association with VTE assessed using study-design appropriate regression methods. Meta-analysis of these results identified two known loci, in F5 and ABO. Top 1,047 tag SNPs (P ≤ 0.0016) from the discovery GWAS were tested for association in an additional 3,231 cases and 3,536 controls from three case-control studies. In the combined data from these two stages, additional genome-wide significant associations were observed on 4q35 at F11 (top SNP rs4253399, intronic to F11) and on 4q28 at FGG (rs6536024, 9.7 kb from FGG; P < 5.0 × 10(-13) for both). The associations at the FGG locus were not completely explained by previously reported variants. Loci at or near SUSD1 and OTUD7A showed borderline yet novel associations (P < 5.0 × 10(-6) ) and constitute new candidate genes. In conclusion, this large GWAS replicated key genetic associations in F5 and ABO, and confirmed the importance of F11 and FGG loci for VTE. Future studies are warranted to better characterize the associations with F11 and FGG and to replicate the new candidate associations.
Keywords: Aged; Aging; Case-Control Studies; Cohort Studies; Female; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Risk Factors; Venous Thromboembolism

Genome-wide association study identifies novel loci associated with concentrations of four plasma phospholipid fatty acids in the de novo lipogenesis pathway: results from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortiu - Wu, Jason H Y; Lemaitre, Rozenn N; Manichaikul, Ani; Guan, Weihua; Tanaka, Toshiko; Foy, Millennia; Kabagambe, Edmond K; Djoussé, Luc; Siscovick, David; Fretts, Amanda M; Johnson, Catherine; King, Irena B; et al. (Circ Cardiovasc Genet, 2013)
BACKGROUND- Palmitic acid (16:0), stearic acid (18:0), palmitoleic acid (16:1n-7), and oleic acid (18:1n-9) are major saturated and monounsaturated fatty acids that affect cellular signaling and metabolic pathways. They are synthesized via de novo lipogenesis and are the main saturated and monounsaturated fatty acids in the diet. Levels of these fatty acids have been linked to diseases including type 2 diabetes mellitus and coronary heart disease. METHODS AND RESULTS- Genome-wide association studies were conducted in 5 population-based cohorts comprising 8961 participants of European ancestry to investigate the association of common genetic variation with plasma levels of these 4 fatty acids. We identified polymorphisms in 7 novel loci associated with circulating levels of ≥1 of these fatty acids. ALG14 (asparagine-linked glycosylation 14 homolog) polymorphisms were associated with higher 16:0 (P=2.7×10(-11)) and lower 18:0 (P=2.2×10(-18)). FADS1 and FADS2 (desaturases) polymorphisms were associated with higher 16:1n-7 (P=6.6×10(-13)) and 18:1n-9 (P=2.2×10(-32)) and lower 18:0 (P=1.3×10(-20)). LPGAT1 (lysophosphatidylglycerol acyltransferase) polymorphisms were associated with lower 18:0 (P=2.8×10(-9)). GCKR (glucokinase regulator; P=9.8×10(-10)) and HIF1AN (factor inhibiting hypoxia-inducible factor-1; P=5.7×10(-9)) polymorphisms were associated with higher 16:1n-7, whereas PKD2L1 (polycystic kidney disease 2-like 1; P=5.7×10(-15)) and a locus on chromosome 2 (not near known genes) were associated with lower 16:1n-7 (P=4.1×10(-8)). CONCLUSIONS- Our findings provide novel evidence that common variations in genes with diverse functions, including protein-glycosylation, polyunsaturated fatty acid metabolism, phospholipid modeling, and glucose- and oxygen-sensing pathways, are associated with circulating levels of 4 fatty acids in the de novo lipogenesis pathway. These results expand our knowledge of genetic factors relevant to de novo lipogenesis and fatty acid biology.
Keywords: Adult; Aged; Chromosomes, Human, Pair 2; Cohort Studies; Coronary Disease; Diabetes Mellitus, Type 2; Fatty Acids, Monounsaturated; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Linkage Disequilibrium; Lipogenesis; Male; Middle Aged; Oleic Acid; Palmitic Acid; Polymorphism, Single Nucleotide; Stearic Acids

Genome-wide association study of cardiac structure and systolic function in African Americans: the Candidate Gene Association Resource (CARe) study. - Fox, Ervin R; Musani, Solomon K; Barbalic, Maja; Lin, Honghuang; Yu, Bing; Ogunyankin, Kofo O; Smith, Nicholas L; Kutlar, Abdullah; Glazer, Nicole L; Post, Wendy S; Paltoo, Dina N; Dries, Daniel L; et al. (Circ Cardiovasc Genet, 2013)
BACKGROUND: Using data from 4 community-based cohorts of African Americans, we tested the association between genome-wide markers (single-nucleotide polymorphisms) and cardiac phenotypes in the Candidate-gene Association Resource study. METHODS AND RESULTS: Among 6765 African Americans, we related age, sex, height, and weight-adjusted residuals for 9 cardiac phenotypes (assessed by echocardiogram or magnetic resonance imaging) to 2.5 million single-nucleotide polymorphisms genotyped using Genome-wide Affymetrix Human SNP Array 6.0 (Affy6.0) and the remainder imputed. Within the cohort, genome-wide association analysis was conducted, followed by meta-analysis across cohorts using inverse variance weights (genome-wide significance threshold=4.0 ×10(-7)). Supplementary pathway analysis was performed. We attempted replication in 3 smaller cohorts of African ancestry and tested lookups in 1 consortium of European ancestry (EchoGEN). Across the 9 phenotypes, variants in 4 genetic loci reached genome-wide significance: rs4552931 in UBE2V2 (P=1.43×10(-7)) for left ventricular mass, rs7213314 in WIPI1 (P=1.68×10(-7)) for left ventricular internal diastolic diameter, rs1571099 in PPAPDC1A (P=2.57×10(-8)) for interventricular septal wall thickness, and rs9530176 in KLF5 (P=4.02×10(-7)) for ejection fraction. Associated variants were enriched in 3 signaling pathways involved in cardiac remodeling. None of the 4 loci replicated in cohorts of African ancestry was confirmed in lookups in EchoGEN. CONCLUSIONS: In the largest genome-wide association study of cardiac structure and function to date in African Americans, we identified 4 genetic loci related to left ventricular mass, interventricular septal wall thickness, left ventricular internal diastolic diameter, and ejection fraction, which reached genome-wide significance. Replication results suggest that these loci may be unique to individuals of African ancestry. Additional large-scale studies are warranted for these complex phenotypes.
Keywords: African Americans; Aged; Cohort Studies; Diastole; Echocardiography; European Continental Ancestry Group; Female; Genome-Wide Association Study; Genotype; Heart; Humans; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Systole

A genome-wide association study of depressive symptoms. - Hek, Karin; Demirkan, Ayse; Lahti, Jari; Terracciano, Antonio; Teumer, Alexander; Cornelis, Marilyn C; Amin, Najaf; Bakshis, Erin; Baumert, Jens; Ding, Jingzhong; Liu, Yongmei; Marciante, Kristin; et al. (Biol Psychiatry, 2013)
BACKGROUND: Depression is a heritable trait that exists on a continuum of varying severity and duration. Yet, the search for genetic variants associated with depression has had few successes. We exploit the entire continuum of depression to find common variants for depressive symptoms. METHODS: In this genome-wide association study, we combined the results of 17 population-based studies assessing depressive symptoms with the Center for Epidemiological Studies Depression Scale. Replication of the independent top hits (p<1×10(-5)) was performed in five studies assessing depressive symptoms with other instruments. In addition, we performed a combined meta-analysis of all 22 discovery and replication studies. RESULTS: The discovery sample comprised 34,549 individuals (mean age of 66.5) and no loci reached genome-wide significance (lowest p = 1.05×10(-7)). Seven independent single nucleotide polymorphisms were considered for replication. In the replication set (n = 16,709), we found suggestive association of one single nucleotide polymorphism with depressive symptoms (rs161645, 5q21, p = 9.19×10(-3)). This 5q21 region reached genome-wide significance (p = 4.78×10(-8)) in the overall meta-analysis combining discovery and replication studies (n = 51,258). CONCLUSIONS: The results suggest that only a large sample comprising more than 50,000 subjects may be sufficiently powered to detect genes for depressive symptoms.
Keywords: Aged; Aged, 80 and over; Chromosomes, Human, Pair 5; Depression; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

A genome-wide association study of early menopause and the combined impact of identified variants. - Perry, John R B; Corre, Tanguy; Esko, Tõnu; Chasman, Daniel I; Fischer, Krista; Franceschini, Nora; He, Chunyan; Kutalik, Zoltán; Mangino, Massimo; Rose, Lynda M; Vernon Smith, Albert; Stolk, Lisette; et al. (Hum Mol Genet, 2013)
Early menopause (EM) affects up to 10% of the female population, reducing reproductive lifespan considerably. Currently, it constitutes the leading cause of infertility in the western world, affecting mainly those women who postpone their first pregnancy beyond the age of 30 years. The genetic aetiology of EM is largely unknown in the majority of cases. We have undertaken a meta-analysis of genome-wide association studies (GWASs) in 3493 EM cases and 13 598 controls from 10 independent studies. No novel genetic variants were discovered, but the 17 variants previously associated with normal age at natural menopause as a quantitative trait (QT) were also associated with EM and primary ovarian insufficiency (POI). Thus, EM has a genetic aetiology which overlaps variation in normal age at menopause and is at least partly explained by the additive effects of the same polygenic variants. The combined effect of the common variants captured by the single nucleotide polymorphism arrays was estimated to account for ∼30% of the variance in EM. The association between the combined 17 variants and the risk of EM was greater than the best validated non-genetic risk factor, smoking.
Keywords: Case-Control Studies; Female; Gene Frequency; Genome-Wide Association Study; Humans; Menopause, Premature; Polymorphism, Single Nucleotide; Primary Ovarian Insufficiency; Quantitative Trait Loci; Risk

Genome-wide association study of retinopathy in individuals without diabetes. - Jensen, Richard A; Sim, Xueling; Li, Xiaohui; Cotch, Mary Frances; Ikram, M Kamran; Holliday, Elizabeth G; Eiriksdottir, Gudny; Harris, Tamara B; Jonasson, Fridbert; Klein, Barbara E K; Launer, Lenore J; Smith, Albert Vernon; et al. (PLoS One, 2013)
BACKGROUND: Mild retinopathy (microaneurysms or dot-blot hemorrhages) is observed in persons without diabetes or hypertension and may reflect microvascular disease in other organs. We conducted a genome-wide association study (GWAS) of mild retinopathy in persons without diabetes. METHODS: A working group agreed on phenotype harmonization, covariate selection and analytic plans for within-cohort GWAS. An inverse-variance weighted fixed effects meta-analysis was performed with GWAS results from six cohorts of 19,411 Caucasians. The primary analysis included individuals without diabetes and secondary analyses were stratified by hypertension status. We also singled out the results from single nucleotide polymorphisms (SNPs) previously shown to be associated with diabetes and hypertension, the two most common causes of retinopathy. RESULTS: No SNPs reached genome-wide significance in the primary analysis or the secondary analysis of participants with hypertension. SNP, rs12155400, in the histone deacetylase 9 gene (HDAC9) on chromosome 7, was associated with retinopathy in analysis of participants without hypertension, -1.3±0.23 (beta ± standard error), p = 6.6×10(-9). Evidence suggests this was a false positive finding. The minor allele frequency was low (∼2%), the quality of the imputation was moderate (r(2) ∼0.7), and no other common variants in the HDAC9 gene were associated with the outcome. SNPs found to be associated with diabetes and hypertension in other GWAS were not associated with retinopathy in persons without diabetes or in subgroups with or without hypertension. CONCLUSIONS: This GWAS of retinopathy in individuals without diabetes showed little evidence of genetic associations. Further studies are needed to identify genes associated with these signs in order to help unravel novel pathways and determinants of microvascular diseases.
Keywords: Aged; Aged, 80 and over; Female; Genome-Wide Association Study; Genotype; Histone Deacetylases; Humans; Hypertension; Male; Polymorphism, Single Nucleotide; Repressor Proteins; Retinal Diseases

Genome-wide meta-analysis identifies 11 new loci for anthropometric traits and provides insights into genetic architecture. - Berndt, Sonja I; Gustafsson, Stefan; Mägi, Reedik; Ganna, Andrea; Wheeler, Eleanor; Feitosa, Mary F; Justice, Anne E; Monda, Keri L; Croteau-Chonka, Damien C; Day, Felix R; Esko, Tõnu; Fall, Tove; et al. (Nat Genet, 2013)
Approaches exploiting trait distribution extremes may be used to identify loci associated with common traits, but it is unknown whether these loci are generalizable to the broader population. In a genome-wide search for loci associated with the upper versus the lower 5th percentiles of body mass index, height and waist-to-hip ratio, as well as clinical classes of obesity, including up to 263,407 individuals of European ancestry, we identified 4 new loci (IGFBP4, H6PD, RSRC1 and PPP2R2A) influencing height detected in the distribution tails and 7 new loci (HNF4G, RPTOR, GNAT2, MRPS33P4, ADCY9, HS6ST3 and ZZZ3) for clinical classes of obesity. Further, we find a large overlap in genetic structure and the distribution of variants between traits based on extremes and the general population and little etiological heterogeneity between obesity subgroups.
Keywords: Anthropometry; Body Height; Body Mass Index; Case-Control Studies; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Meta-Analysis as Topic; Obesity; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Waist-Hip Ratio

Genome-wide meta-analysis of observational studies shows common genetic variants associated with macronutrient intake. - Tanaka, Toshiko; Ngwa, Julius S; van Rooij, Frank J A; Zillikens, M Carola; Wojczynski, Mary K; Frazier-Wood, Alexis C; Houston, Denise K; Kanoni, Stavroula; Lemaitre, Rozenn N; Luan, Jian'an; Mikkilä, Vera; Renstrom, Frida; et al. (Am J Clin Nutr, 2013)
BACKGROUND: Macronutrient intake varies substantially between individuals, and there is evidence that this variation is partly accounted for by genetic variants. OBJECTIVE: The objective of the study was to identify common genetic variants that are associated with macronutrient intake. DESIGN: We performed 2-stage genome-wide association (GWA) meta-analysis of macronutrient intake in populations of European descent. Macronutrients were assessed by using food-frequency questionnaires and analyzed as percentages of total energy consumption from total fat, protein, and carbohydrate. From the discovery GWA (n = 38,360), 35 independent loci associated with macronutrient intake at P < 5 × 10(-6) were identified and taken forward to replication in 3 additional cohorts (n = 33,533) from the DietGen Consortium. For one locus, fat mass obesity-associated protein (FTO), cohorts with Illumina MetaboChip genotype data (n = 7724) provided additional replication data. RESULTS: A variant in the chromosome 19 locus (rs838145) was associated with higher carbohydrate (β ± SE: 0.25 ± 0.04%; P = 1.68 × 10(-8)) and lower fat (β ± SE: -0.21 ± 0.04%; P = 1.57 × 10(-9)) consumption. A candidate gene in this region, fibroblast growth factor 21 (FGF21), encodes a fibroblast growth factor involved in glucose and lipid metabolism. The variants in this locus were associated with circulating FGF21 protein concentrations (P < 0.05) but not mRNA concentrations in blood or brain. The body mass index (BMI)-increasing allele of the FTO variant (rs1421085) was associated with higher protein intake (β ± SE: 0.10 ± 0.02%; P = 9.96 × 10(-10)), independent of BMI (after adjustment for BMI, β ± SE: 0.08 ± 0.02%; P = 3.15 × 10(-7)). CONCLUSION: Our results indicate that variants in genes involved in nutrient metabolism and obesity are associated with macronutrient consumption in humans. Trials related to this study were registered at clinicaltrials.gov as NCT00005131 (Atherosclerosis Risk in Communities), NCT00005133 (Cardiovascular Health Study), NCT00005136 (Family Heart Study), NCT00005121 (Framingham Heart Study), NCT00083369 (Genetic and Environmental Determinants of Triglycerides), NCT01331512 (InCHIANTI Study), and NCT00005487 (Multi-Ethnic Study of Atherosclerosis).
Keywords: Alleles; Atherosclerosis; Body Mass Index; Dietary Carbohydrates; Dietary Fats; Dietary Proteins; Energy Intake; European Continental Ancestry Group; Fibroblast Growth Factors; Follow-Up Studies; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Life Style; Obesity; Polymorphism, Single Nucleotide; Prospective Studies; Quantitative Trait Loci; Surveys and Questionnaires

Genome-wide study identifies two loci associated with lung function decline in mild to moderate COPD. - Hansel, Nadia N; Ruczinski, Ingo; Rafaels, Nicholas; Sin, Don D; Daley, Denise; Malinina, Alla; Huang, Lili; Sandford, Andrew; Murray, Tanda; Kim, Yoonhee; Vergara, Candelaria; Heckbert, Susan R; et al. (Hum Genet, 2013)
Accelerated lung function decline is a key COPD phenotype; however, its genetic control remains largely unknown. We performed a genome-wide association study using the Illumina Human660W-Quad v.1_A BeadChip. Generalized estimation equations were used to assess genetic contributions to lung function decline over a 5-year period in 4,048 European American Lung Health Study participants with largely mild COPD. Genotype imputation was performed using reference HapMap II data. To validate regions meeting genome-wide significance, replication of top SNPs was attempted in independent cohorts. Three genes (TMEM26, ANK3 and FOXA1) within the regions of interest were selected for tissue expression studies using immunohistochemistry. Two intergenic SNPs (rs10761570, rs7911302) on chromosome 10 and one SNP on chromosome 14 (rs177852) met genome-wide significance after Bonferroni. Further support for the chromosome 10 region was obtained by imputation, the most significantly associated imputed SNPs (rs10761571, rs7896712) being flanked by observed markers rs10761570 and rs7911302. Results were not replicated in four general population cohorts or a smaller cohort of subjects with moderate to severe COPD; however, we show novel expression of genes near regions of significantly associated SNPS, including TMEM26 and FOXA1 in airway epithelium and lung parenchyma, and ANK3 in alveolar macrophages. Levels of expression were associated with lung function and COPD status. We identified two novel regions associated with lung function decline in mild COPD. Genes within these regions were expressed in relevant lung cells and their expression related to airflow limitation suggesting they may represent novel candidate genes for COPD susceptibility.
Keywords: Adult; Ankyrins; Chromosomes, Human, Pair 10; Chromosomes, Human, Pair 14; Cohort Studies; Female; Genome-Wide Association Study; Hepatocyte Nuclear Factor 3-alpha; Humans; Linkage Disequilibrium; Lung; Male; Membrane Proteins; Middle Aged; Polymorphism, Single Nucleotide; Pulmonary Disease, Chronic Obstructive

Higher magnesium intake is associated with lower fasting glucose and insulin, with no evidence of interaction with select genetic loci, in a meta-analysis of 15 CHARGE Consortium Studies. - Hruby, Adela; Ngwa, Julius S; Renstrom, Frida; Wojczynski, Mary K; Ganna, Andrea; Hallmans, Göran; Houston, Denise K; Jacques, Paul F; Kanoni, Stavroula; Lehtimäki, Terho; Lemaitre, Rozenn N; Manichaikul, Ani; et al. (J Nutr, 2013)
Favorable associations between magnesium intake and glycemic traits, such as fasting glucose and insulin, are observed in observational and clinical studies, but whether genetic variation affects these associations is largely unknown. We hypothesized that single nucleotide polymorphisms (SNPs) associated with either glycemic traits or magnesium metabolism affect the association between magnesium intake and fasting glucose and insulin. Fifteen studies from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium provided data from up to 52,684 participants of European descent without known diabetes. In fixed-effects meta-analyses, we quantified 1) cross-sectional associations of dietary magnesium intake with fasting glucose (mmol/L) and insulin (ln-pmol/L) and 2) interactions between magnesium intake and SNPs related to fasting glucose (16 SNPs), insulin (2 SNPs), or magnesium (8 SNPs) on fasting glucose and insulin. After adjustment for age, sex, energy intake, BMI, and behavioral risk factors, magnesium (per 50-mg/d increment) was inversely associated with fasting glucose [β = -0.009 mmol/L (95% CI: -0.013, -0.005), P < 0.0001] and insulin [-0.020 ln-pmol/L (95% CI: -0.024, -0.017), P < 0.0001]. No magnesium-related SNP or interaction between any SNP and magnesium reached significance after correction for multiple testing. However, rs2274924 in magnesium transporter-encoding TRPM6 showed a nominal association (uncorrected P = 0.03) with glucose, and rs11558471 in SLC30A8 and rs3740393 near CNNM2 showed a nominal interaction (uncorrected, both P = 0.02) with magnesium on glucose. Consistent with other studies, a higher magnesium intake was associated with lower fasting glucose and insulin. Nominal evidence of TRPM6 influence and magnesium interaction with select loci suggests that further investigation is warranted.
Keywords: Blood Glucose; Female; Genetic Loci; Humans; Insulin; Magnesium; Male; Polymorphism, Single Nucleotide; Trace Elements; TRPM Cation Channels

Identification of heart rate-associated loci and their effects on cardiac conduction and rhythm disorders. - den Hoed, Marcel; Eijgelsheim, Mark; Esko, Tõnu; Brundel, Bianca J J M; Peal, David S; Evans, David M; Nolte, Ilja M; Segrè, Ayellet V; Holm, Hilma; Handsaker, Robert E; Westra, Harm-Jan; Johnson, Toby; et al. (Nat Genet, 2013)
Elevated resting heart rate is associated with greater risk of cardiovascular disease and mortality. In a 2-stage meta-analysis of genome-wide association studies in up to 181,171 individuals, we identified 14 new loci associated with heart rate and confirmed associations with all 7 previously established loci. Experimental downregulation of gene expression in Drosophila melanogaster and Danio rerio identified 20 genes at 11 loci that are relevant for heart rate regulation and highlight a role for genes involved in signal transmission, embryonic cardiac development and the pathophysiology of dilated cardiomyopathy, congenital heart failure and/or sudden cardiac death. In addition, genetic susceptibility to increased heart rate is associated with altered cardiac conduction and reduced risk of sick sinus syndrome, and both heart rate-increasing and heart rate-decreasing variants associate with risk of atrial fibrillation. Our findings provide fresh insights into the mechanisms regulating heart rate and identify new therapeutic targets.
Keywords: Animals; Arrhythmias, Cardiac; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Heart Rate; Humans; Metabolic Networks and Pathways; Polymorphism, Single Nucleotide; Quantitative Trait Loci

The influence of obesity-related single nucleotide polymorphisms on BMI across the life course: the PAGE study. - Graff, Mariaelisa; Gordon-Larsen, Penny; Lim, Unhee; Fowke, Jay H; Love, Shelly-Ann; Fesinmeyer, Megan; Wilkens, Lynne R; Vertilus, Shawyntee; Ritchie, Marilyn D; Prentice, Ross L; Pankow, Jim; Monroe, Kristine; et al. (Diabetes, 2013)
Evidence is limited as to whether heritable risk of obesity varies throughout adulthood. Among >34,000 European Americans, aged 18-100 years, from multiple U.S. studies in the Population Architecture using Genomics and Epidemiology (PAGE) Consortium, we examined evidence for heterogeneity in the associations of five established obesity risk variants (near FTO, GNPDA2, MTCH2, TMEM18, and NEGR1) with BMI across four distinct epochs of adulthood: 1) young adulthood (ages 18-25 years), adulthood (ages 26-49 years), middle-age adulthood (ages 50-69 years), and older adulthood (ages ≥70 years); or 2) by menopausal status in women and stratification by age 50 years in men. Summary-effect estimates from each meta-analysis were compared for heterogeneity across the life epochs. We found heterogeneity in the association of the FTO (rs8050136) variant with BMI across the four adulthood epochs (P = 0.0006), with larger effects in young adults relative to older adults (β [SE] = 1.17 [0.45] vs. 0.09 [0.09] kg/m², respectively, per A allele) and smaller intermediate effects. We found no evidence for heterogeneity in the association of GNPDA2, MTCH2, TMEM18, and NEGR1 with BMI across adulthood. Genetic predisposition to obesity may have greater effects on body weight in young compared with older adulthood for FTO, suggesting changes by age, generation, or secular trends. Future research should compare and contrast our findings with results using longitudinal data.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Aging; Body Mass Index; Cohort Studies; Cross-Sectional Studies; European Continental Ancestry Group; Female; Genetic Association Studies; Health Surveys; Humans; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Proteins; United States; Young Adult

Insights into the genetic architecture of early stage age-related macular degeneration: a genome-wide association study meta-analysis. - Holliday, Elizabeth G; Smith, Albert V; Cornes, Belinda K; Buitendijk, Gabriëlle H S; Jensen, Richard A; Sim, Xueling; Aspelund, Thor; Aung, Tin; Baird, Paul N; Boerwinkle, Eric; Cheng, Ching Yu; van Duijn, Cornelia M; et al. (PLoS One, 2013)
Genetic factors explain a majority of risk variance for age-related macular degeneration (AMD). While genome-wide association studies (GWAS) for late AMD implicate genes in complement, inflammatory and lipid pathways, the genetic architecture of early AMD has been relatively under studied. We conducted a GWAS meta-analysis of early AMD, including 4,089 individuals with prevalent signs of early AMD (soft drusen and/or retinal pigment epithelial changes) and 20,453 individuals without these signs. For various published late AMD risk loci, we also compared effect sizes between early and late AMD using an additional 484 individuals with prevalent late AMD. GWAS meta-analysis confirmed previously reported association of variants at the complement factor H (CFH) (peak P = 1.5×10(-31)) and age-related maculopathy susceptibility 2 (ARMS2) (P = 4.3×10(-24)) loci, and suggested Apolipoprotein E (ApoE) polymorphisms (rs2075650; P = 1.1×10(-6)) associated with early AMD. Other possible loci that did not reach GWAS significance included variants in the zinc finger protein gene GLI3 (rs2049622; P = 8.9×10(-6)) and upstream of GLI2 (rs6721654; P = 6.5×10(-6)), encoding retinal Sonic hedgehog signalling regulators, and in the tyrosinase (TYR) gene (rs621313; P = 3.5×10(-6)), involved in melanin biosynthesis. For a range of published, late AMD risk loci, estimated effect sizes were significantly lower for early than late AMD. This study confirms the involvement of multiple established AMD risk variants in early AMD, but suggests weaker genetic effects on the risk of early AMD relative to late AMD. Several biological processes were suggested to be potentially specific for early AMD, including pathways regulating RPE cell melanin content and signalling pathways potentially involved in retinal regeneration, generating hypotheses for further investigation.
Keywords: Apolipoproteins E; Complement Factor H; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Kruppel-Like Transcription Factors; Macular Degeneration; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Proteins; Risk Factors; Zinc Finger Protein Gli3

Investigation of gene-by-sex interactions for lipid traits in diverse populations from the population architecture using genomics and epidemiology study. - Taylor, Kira C; Carty, Cara L; Dumitrescu, Logan; Bůzková, Petra; Cole, Shelley A; Hindorff, Lucia; Schumacher, Fred R; Wilkens, Lynne R; Shohet, Ralph V; Quibrera, P Miguel; Johnson, Karen C; Henderson, Brian E; et al. (BMC Genet, 2013)
BACKGROUND: High-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) levels are influenced by both genes and the environment. Genome-wide association studies (GWAS) have identified ~100 common genetic variants associated with HDL-C, LDL-C, and/or TG levels, mostly in populations of European descent, but little is known about the modifiers of these associations. Here, we investigated whether GWAS-identified SNPs for lipid traits exhibited heterogeneity by sex in the Population Architecture using Genomics and Epidemiology (PAGE) study. RESULTS: A sex-stratified meta-analysis was performed for 49 GWAS-identified SNPs for fasting HDL-C, LDL-C, and ln(TG) levels among adults self-identified as European American (25,013). Heterogeneity by sex was established when phet < 0.001. There was evidence for heterogeneity by sex for two SNPs for ln(TG) in the APOA1/C3/A4/A5/BUD13 gene cluster: rs28927680 (p(het) = 7.4 x 10(-7)) and rs3135506 (p(het) = 4.3 x 10(-4)one SNP in PLTP for HDL levels (rs7679; p(het) = 9.9 x 10(-4)), and one in HMGCR for LDL levels (rs12654264; p(het) = 3.1 x 10(-5)). We replicated heterogeneity by sex in five of seventeen loci previously reported by genome-wide studies (binomial p = 0.0009). We also present results for other racial/ethnic groups in the supplementary materials, to provide a resource for future meta-analyses. CONCLUSIONS: We provide further evidence for sex-specific effects of SNPs in the APOA1/C3/A4/A5/BUD13 gene cluster, PLTP, and HMGCR on fasting triglyceride levels in European Americans from the PAGE study. Our findings emphasize the need for considering context-specific effects when interpreting genetic associations emerging from GWAS, and also highlight the difficulties in replicating interaction effects across studies and across racial/ethnic groups.
Keywords: Female; Genetic Heterogeneity; Genome, Human; Genome-Wide Association Study; Humans; Lipids; Male; Polymorphism, Single Nucleotide; Population Groups

Ischemic stroke is associated with the ABO locus: the EuroCLOT study. - Williams, Frances M K; Carter, Angela M; Hysi, Pirro G; Surdulescu, Gabriela; Hodgkiss, Dylan; Soranzo, Nicole; Traylor, Matthew; Bevan, Steve; Dichgans, Martin; Rothwell, Peter M W; Sudlow, Cathie; Farrall, Martin; et al. (Ann Neurol, 2013)
OBJECTIVE: End-stage coagulation and the structure/function of fibrin are implicated in the pathogenesis of ischemic stroke. We explored whether genetic variants associated with end-stage coagulation in healthy volunteers account for the genetic predisposition to ischemic stroke and examined their influence on stroke subtype. METHODS: Common genetic variants identified through genome-wide association studies of coagulation factors and fibrin structure/function in healthy twins (n = 2,100, Stage 1) were examined in ischemic stroke (n = 4,200 cases) using 2 independent samples of European ancestry (Stage 2). A third clinical collection having stroke subtyping (total 8,900 cases, 55,000 controls) was used for replication (Stage 3). RESULTS: Stage 1 identified 524 single nucleotide polymorphisms (SNPs) from 23 linkage disequilibrium blocks having significant association (p < 5 × 10(-8)) with 1 or more coagulation/fibrin phenotypes. The most striking associations included SNP rs5985 with factor XIII activity (p = 2.6 × 10(-186)), rs10665 with FVII (p = 2.4 × 10(-47)), and rs505922 in the ABO gene with both von Willebrand factor (p = 4.7 × 10(-57)) and factor VIII (p = 1.2 × 10(-36)). In Stage 2, the 23 independent SNPs were examined in stroke cases/noncases using MOnica Risk, Genetics, Archiving and Monograph (MORGAM) and Wellcome Trust Case Control Consortium 2 collections. SNP rs505922 was nominally associated with ischemic stroke (odds ratio = 0.94, 95% confidence interval = 0.88-0.99, p = 0.023). Independent replication in Meta-Stroke confirmed the rs505922 association with stroke, beta (standard error, SE) = 0.066 (0.02), p = 0.001, a finding specific to large-vessel and cardioembolic stroke (p = 0.001 and p = < 0.001, respectively) but not seen with small-vessel stroke (p = 0.811). INTERPRETATION: ABO gene variants are associated with large-vessel and cardioembolic stroke but not small-vessel disease. This work sheds light on the different pathogenic mechanisms underpinning stroke subtype.
Keywords: ABO Blood-Group System; Adolescent; Adult; Aged; Aged, 80 and over; Blood Coagulation; Brain Ischemia; Cohort Studies; Europe; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Stroke; Young Adult

Lack of associations of ten candidate coronary heart disease risk genetic variants and subclinical atherosclerosis in four US populations: the Population Architecture using Genomics and Epidemiology (PAGE) study. - Zhang, Lili; Bůzková, Petra; Wassel, Christina L; Roman, Mary J; North, Kari E; Crawford, Dana C; Boston, Jonathan; Brown-Gentry, Kristin D; Cole, Shelley A; Deelman, Ewa; Goodloe, Robert; Wilson, Sarah; et al. (Atherosclerosis, 2013)
BACKGROUND: A number of genetic variants have been discovered by recent genome-wide association studies for their associations with clinical coronary heart disease (CHD). However, it is unclear whether these variants are also associated with the development of CHD as measured by subclinical atherosclerosis phenotypes, ankle brachial index (ABI), carotid artery intima-media thickness (cIMT) and carotid plaque. METHODS: Ten CHD risk single nucleotide polymorphisms (SNPs) were genotyped in individuals of European American (EA), African American (AA), American Indian (AI), and Mexican American (MA) ancestry in the Population Architecture using Genomics and Epidemiology (PAGE) study. In each individual study, we performed linear or logistic regression to examine population-specific associations between SNPs and ABI, common and internal cIMT, and plaque. The results from individual studies were meta-analyzed using a fixed effect inverse variance weighted model. RESULTS: None of the ten SNPs was significantly associated with ABI and common or internal cIMT, after Bonferroni correction. In the sample of 13,337 EA, 3809 AA, and 5353 AI individuals with carotid plaque measurement, the GCKR SNP rs780094 was significantly associated with the presence of plaque in AI only (OR = 1.32, 95% confidence interval: 1.17, 1.49, P = 1.08 × 10(-5)), but not in the other populations (P = 0.90 in EA and P = 0.99 in AA). A 9p21 region SNP, rs1333049, was nominally associated with plaque in EA (OR = 1.07, P = 0.02) and in AI (OR = 1.10, P = 0.05). CONCLUSIONS: We identified a significant association between rs780094 and plaque in AI populations, which needs to be replicated in future studies. There was little evidence that the index CHD risk variants identified through genome-wide association studies in EA influence the development of CHD through subclinical atherosclerosis as assessed by cIMT and ABI across ancestries.
Keywords: African Americans; Aged; Ankle Brachial Index; Asymptomatic Diseases; Carotid Artery Diseases; Carotid Intima-Media Thickness; Coronary Disease; European Continental Ancestry Group; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Indians, North American; Linear Models; Logistic Models; Male; Mexican Americans; Middle Aged; Odds Ratio; Phenotype; Polymorphism, Single Nucleotide; Predictive Value of Tests; Risk Assessment; Risk Factors; United States

Lipoprotein receptor-related protein 1 variants and dietary fatty acids: meta-analysis of European origin and African American studies. - Smith, C E; Ngwa, J; Tanaka, T; Qi, Q; Wojczynski, M K; Lemaitre, R N; Anderson, J S; Manichaikul, A; Mikkilä, V; van Rooij, F J A; Ye, Z; Bandinelli, S; et al. (Int J Obes (Lond), 2013)
OBJECTIVE: Low-density lipoprotein-related receptor protein 1 (LRP1) is a multi-functional endocytic receptor and signaling molecule that is expressed in adipose and the hypothalamus. Evidence for a role of LRP1 in adiposity is accumulating from animal and in vitro models, but data from human studies are limited. The study objectives were to evaluate (i) relationships between LRP1 genotype and anthropometric traits, and (ii) whether these relationships were modified by dietary fatty acids. DESIGN AND METHODS: We conducted race/ethnic-specific meta-analyses using data from 14 studies of US and European whites and 4 of African Americans to evaluate associations of dietary fatty acids and LRP1 genotypes with body mass index (BMI), waist circumference and hip circumference, as well as interactions between dietary fatty acids and LRP1 genotypes. Seven single-nucleotide polymorphisms (SNPs) of LRP1 were evaluated in whites (N up to 42 000) and twelve SNPs in African Americans (N up to 5800). RESULTS: After adjustment for age, sex and population substructure if relevant, for each one unit greater intake of percentage of energy from saturated fat (SFA), BMI was 0.104 kg m(-2) greater, waist was 0.305 cm larger and hip was 0.168 cm larger (all P<0.0001). Other fatty acids were not associated with outcomes. The association of SFA with outcomes varied by genotype at rs2306692 (genotyped in four studies of whites), where the magnitude of the association of SFA intake with each outcome was greater per additional copy of the T allele: 0.107 kg m(-2) greater for BMI (interaction P=0.0001), 0.267 cm for waist (interaction P=0.001) and 0.21 cm for hip (interaction P=0.001). No other significant interactions were observed. CONCLUSION: Dietary SFA and LRP1 genotype may interactively influence anthropometric traits. Further exploration of this, and other diet x genotype interactions, may improve understanding of interindividual variability in the relationships of dietary factors with anthropometric traits.
Keywords: Adipose Tissue; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Body Mass Index; Europe; European Continental Ancestry Group; Fatty Acids; Female; Gene Frequency; Gene-Environment Interaction; Genetic Predisposition to Disease; Genotype; Humans; Low Density Lipoprotein Receptor-Related Protein-1; Male; Middle Aged; Obesity; Phenotype; Polymorphism, Single Nucleotide; Prevalence; United States

A meta-analysis identifies new loci associated with body mass index in individuals of African ancestry. - Monda, Keri L; Chen, Gary K; Taylor, Kira C; Palmer, Cameron; Edwards, Todd L; Lange, Leslie A; Ng, Maggie C Y; Adeyemo, Adebowale A; Allison, Matthew A; Bielak, Lawrence F; Chen, Guanjie; Graff, Mariaelisa; et al. (Nat Genet, 2013)
Genome-wide association studies (GWAS) have identified 36 loci associated with body mass index (BMI), predominantly in populations of European ancestry. We conducted a meta-analysis to examine the association of >3.2 million SNPs with BMI in 39,144 men and women of African ancestry and followed up the most significant associations in an additional 32,268 individuals of African ancestry. We identified one new locus at 5q33 (GALNT10, rs7708584, P = 3.4 × 10(-11)) and another at 7p15 when we included data from the GIANT consortium (MIR148A-NFE2L3, rs10261878, P = 1.2 × 10(-10)). We also found suggestive evidence of an association at a third locus at 6q16 in the African-ancestry sample (KLHL32, rs974417, P = 6.9 × 10(-8)). Thirty-two of the 36 previously established BMI variants showed directionally consistent effect estimates in our GWAS (binomial P = 9.7 × 10(-7)), five of which reached genome-wide significance. These findings provide strong support for shared BMI loci across populations, as well as for the utility of studying ancestrally diverse populations.
Keywords: African Americans; Body Mass Index; Case-Control Studies; Gene Frequency; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Obesity; Polymorphism, Single Nucleotide

Meta-analysis of 74,046 individuals identifies 11 new susceptibility loci for Alzheimer's disease. - Lambert, J C; Ibrahim-Verbaas, C A; Harold, D; Naj, A C; Sims, R; Bellenguez, C; DeStafano, A L; Bis, J C; Beecham, G W; Grenier-Boley, B; Russo, G; Thorton-Wells, T A; et al. (Nat Genet, 2013)
Eleven susceptibility loci for late-onset Alzheimer's disease (LOAD) were identified by previous studies; however, a large portion of the genetic risk for this disease remains unexplained. We conducted a large, two-stage meta-analysis of genome-wide association studies (GWAS) in individuals of European ancestry. In stage 1, we used genotyped and imputed data (7,055,881 SNPs) to perform meta-analysis on 4 previously published GWAS data sets consisting of 17,008 Alzheimer's disease cases and 37,154 controls. In stage 2, 11,632 SNPs were genotyped and tested for association in an independent set of 8,572 Alzheimer's disease cases and 11,312 controls. In addition to the APOE locus (encoding apolipoprotein E), 19 loci reached genome-wide significance (P < 5 × 10(-8)) in the combined stage 1 and stage 2 analysis, of which 11 are newly associated with Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cohort Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Meta-analysis of genome-wide association studies identifies six new Loci for serum calcium concentrations. - O'Seaghdha, Conall M; Wu, Hongsheng; Yang, Qiong; Kapur, Karen; Guessous, Idris; Zuber, Annie Mercier; Köttgen, Anna; Stoudmann, Candice; Teumer, Alexander; Kutalik, Zoltán; Mangino, Massimo; Dehghan, Abbas; et al. (PLoS Genet, 2013)
Calcium is vital to the normal functioning of multiple organ systems and its serum concentration is tightly regulated. Apart from CASR, the genes associated with serum calcium are largely unknown. We conducted a genome-wide association meta-analysis of 39,400 individuals from 17 population-based cohorts and investigated the 14 most strongly associated loci in ≤ 21,679 additional individuals. Seven loci (six new regions) in association with serum calcium were identified and replicated. Rs1570669 near CYP24A1 (P = 9.1E-12), rs10491003 upstream of GATA3 (P = 4.8E-09) and rs7481584 in CARS (P = 1.2E-10) implicate regions involved in Mendelian calcemic disorders: Rs1550532 in DGKD (P = 8.2E-11), also associated with bone density, and rs7336933 near DGKH/KIAA0564 (P = 9.1E-10) are near genes that encode distinct isoforms of diacylglycerol kinase. Rs780094 is in GCKR. We characterized the expression of these genes in gut, kidney, and bone, and demonstrate modulation of gene expression in bone in response to dietary calcium in mice. Our results shed new light on the genetics of calcium homeostasis.
Keywords: Animals; Bone and Bones; Bone Density; Calcium; European Continental Ancestry Group; Gene Expression Regulation; Genome-Wide Association Study; Homeostasis; Humans; Kidney; Mice; Polymorphism, Single Nucleotide

A meta-analysis of thyroid-related traits reveals novel loci and gender-specific differences in the regulation of thyroid function. - Porcu, Eleonora; Medici, Marco; Pistis, Giorgio; Volpato, Claudia B; Wilson, Scott G; Cappola, Anne R; Bos, Steffan D; Deelen, Joris; den Heijer, Martin; Freathy, Rachel M; Lahti, Jari; Liu, Chunyu; et al. (PLoS Genet, 2013)
Thyroid hormone is essential for normal metabolism and development, and overt abnormalities in thyroid function lead to common endocrine disorders affecting approximately 10% of individuals over their life span. In addition, even mild alterations in thyroid function are associated with weight changes, atrial fibrillation, osteoporosis, and psychiatric disorders. To identify novel variants underlying thyroid function, we performed a large meta-analysis of genome-wide association studies for serum levels of the highly heritable thyroid function markers TSH and FT4, in up to 26,420 and 17,520 euthyroid subjects, respectively. Here we report 26 independent associations, including several novel loci for TSH (PDE10A, VEGFA, IGFBP5, NFIA, SOX9, PRDM11, FGF7, INSR, ABO, MIR1179, NRG1, MBIP, ITPK1, SASH1, GLIS3) and FT4 (LHX3, FOXE1, AADAT, NETO1/FBXO15, LPCAT2/CAPNS2). Notably, only limited overlap was detected between TSH and FT4 associated signals, in spite of the feedback regulation of their circulating levels by the hypothalamic-pituitary-thyroid axis. Five of the reported loci (PDE8B, PDE10A, MAF/LOC440389, NETO1/FBXO15, and LPCAT2/CAPNS2) show strong gender-specific differences, which offer clues for the known sexual dimorphism in thyroid function and related pathologies. Importantly, the TSH-associated loci contribute not only to variation within the normal range, but also to TSH values outside the reference range, suggesting that they may be involved in thyroid dysfunction. Overall, our findings explain, respectively, 5.64% and 2.30% of total TSH and FT4 trait variance, and they improve the current knowledge of the regulation of hypothalamic-pituitary-thyroid axis function and the consequences of genetic variation for hypo- or hyperthyroidism.
Keywords: Female; Genome-Wide Association Study; Humans; Hyperthyroidism; Hypothyroidism; Male; Phenotype; Polymorphism, Genetic; Polymorphism, Single Nucleotide; Sex Characteristics; Signal Transduction; Thyroid Gland; Thyrotropin; Thyroxine

Multiethnic meta-analysis of genome-wide association studies in >100 000 subjects identifies 23 fibrinogen-associated Loci but no strong evidence of a causal association between circulating fibrinogen and cardiovascular disease. - Sabater-Lleal, Maria; Huang, Jie; Chasman, Daniel; Naitza, Silvia; Dehghan, Abbas; Johnson, Andrew D; Teumer, Alexander; Reiner, Alex P; Folkersen, Lasse; Basu, Saonli; Rudnicka, Alicja R; Trompet, Stella; et al. (Circulation, 2013)
BACKGROUND: Estimates of the heritability of plasma fibrinogen concentration, an established predictor of cardiovascular disease, range from 34% to 50%. Genetic variants so far identified by genome-wide association studies explain only a small proportion (<2%) of its variation. METHODS AND RESULTS: We conducted a meta-analysis of 28 genome-wide association studies including >90 000 subjects of European ancestry, the first genome-wide association meta-analysis of fibrinogen levels in 7 studies in blacks totaling 8289 samples, and a genome-wide association study in Hispanics totaling 1366 samples. Evaluation for association of single-nucleotide polymorphisms with clinical outcomes included a total of 40 695 cases and 85 582 controls for coronary artery disease, 4752 cases and 24 030 controls for stroke, and 3208 cases and 46 167 controls for venous thromboembolism. Overall, we identified 24 genome-wide significant (P<5×10(-8)) independent signals in 23 loci, including 15 novel associations, together accounting for 3.7% of plasma fibrinogen variation. Gene-set enrichment analysis highlighted key roles in fibrinogen regulation for the 3 structural fibrinogen genes and pathways related to inflammation, adipocytokines, and thyrotrophin-releasing hormone signaling. Whereas lead single-nucleotide polymorphisms in a few loci were significantly associated with coronary artery disease, the combined effect of all 24 fibrinogen-associated lead single-nucleotide polymorphisms was not significant for coronary artery disease, stroke, or venous thromboembolism. CONCLUSIONS: We identify 23 robustly associated fibrinogen loci, 15 of which are new. Clinical outcome analysis of these loci does not support a causal relationship between circulating levels of fibrinogen and coronary artery disease, stroke, or venous thromboembolism.
Keywords: Adolescent; Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Cardiovascular Diseases; Coronary Artery Disease; European Continental Ancestry Group; Female; Fibrinogen; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Hispanic Americans; Humans; Male; Middle Aged; Myocardial Infarction; Polymorphism, Single Nucleotide; Risk Factors; Stroke; Venous Thromboembolism; Young Adult

No evidence of interaction between known lipid-associated genetic variants and smoking in the multi-ethnic PAGE population. - Dumitrescu, Logan; Carty, Cara L; Franceschini, Nora; Hindorff, Lucia A; Cole, Shelley A; Bůzková, Petra; Schumacher, Fredrick R; Eaton, Charles B; Goodloe, Robert J; Duggan, David J; Haessler, Jeff; Cochran, Barbara; et al. (Hum Genet, 2013)
Genome-wide association studies (GWAS) have identified many variants that influence high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and/or triglycerides. However, environmental modifiers, such as smoking, of these known genotype-phenotype associations are just recently emerging in the literature. We have tested for interactions between smoking and 49 GWAS-identified variants in over 41,000 racially/ethnically diverse samples with lipid levels from the Population Architecture Using Genomics and Epidemiology (PAGE) study. Despite their biological plausibility, we were unable to detect significant SNP × smoking interactions.
Keywords: Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Ethnic Groups; Female; Gene Frequency; Gene-Environment Interaction; Genetics, Population; Genome-Wide Association Study; Humans; Lipid Metabolism; Male; Polymorphism, Single Nucleotide; Prevalence; Smoking; Triglycerides; Young Adult

Post-genome-wide association study challenges for lipid traits: describing age as a modifier of gene-lipid associations in the Population Architecture using Genomics and Epidemiology (PAGE) study. - Dumitrescu, Logan; Carty, Cara L; Franceschini, Nora; Hindorff, Lucia A; Cole, Shelley A; Bůzková, Petra; Schumacher, Fredrick R; Eaton, Charles B; Goodloe, Robert J; Duggan, David J; Haessler, Jeff; Cochran, Barbara; et al. (Ann Hum Genet, 2013)
Numerous common genetic variants that influence plasma high-density lipoprotein cholesterol, low-density lipoprotein cholesterol (LDL-C), and triglyceride distributions have been identified via genome-wide association studies (GWAS). However, whether or not these associations are age-dependent has largely been overlooked. We conducted an association study and meta-analysis in more than 22,000 European Americans between 49 previously identified GWAS variants and the three lipid traits, stratified by age (males: <50 or ≥50 years of age; females: pre- or postmenopausal). For each variant, a test of heterogeneity was performed between the two age strata and significant Phet values were used as evidence of age-specific genetic effects. We identified seven associations in females and eight in males that displayed suggestive heterogeneity by age (Phet < 0.05). The association between rs174547 (FADS1) and LDL-C in males displayed the most evidence for heterogeneity between age groups (Phet = 1.74E-03, I(2) = 89.8), with a significant association in older males (P = 1.39E-06) but not younger males (P = 0.99). However, none of the suggestive modifying effects survived adjustment for multiple testing, highlighting the challenges of identifying modifiers of modest SNP-trait associations despite large sample sizes.
Keywords: Adult; Aged; European Continental Ancestry Group; Female; Genetic Association Studies; Genome-Wide Association Study; Humans; Lipids; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Risk Factors

Replication of genetic loci for ages at menarche and menopause in the multi-ethnic Population Architecture using Genomics and Epidemiology (PAGE) study. - Carty, C L; Spencer, K L; Setiawan, V W; Fernandez-Rhodes, L; Malinowski, J; Buyske, S; Young, A; Jorgensen, N W; Cheng, I; Carlson, C S; Brown-Gentry, K; Goodloe, R; et al. (Hum Reprod, 2013)
STUDY QUESTION: Do genetic associations identified in genome-wide association studies (GWAS) of age at menarche (AM) and age at natural menopause (ANM) replicate in women of diverse race/ancestry from the Population Architecture using Genomics and Epidemiology (PAGE) Study? SUMMARY ANSWER: We replicated GWAS reproductive trait single nucleotide polymorphisms (SNPs) in our European descent population and found that many SNPs were also associated with AM and ANM in populations of diverse ancestry. WHAT IS KNOWN ALREADY: Menarche and menopause mark the reproductive lifespan in women and are important risk factors for chronic diseases including obesity, cardiovascular disease and cancer. Both events are believed to be influenced by environmental and genetic factors, and vary in populations differing by genetic ancestry and geography. Most genetic variants associated with these traits have been identified in GWAS of European-descent populations. STUDY DESIGN, SIZE, DURATION: A total of 42 251 women of diverse ancestry from PAGE were included in cross-sectional analyses of AM and ANM. MATERIALS, SETTING, METHODS: SNPs previously associated with ANM (n = 5 SNPs) and AM (n = 3 SNPs) in GWAS were genotyped in American Indians, African Americans, Asians, European Americans, Hispanics and Native Hawaiians. To test SNP associations with ANM or AM, we used linear regression models stratified by race/ethnicity and PAGE sub-study. Results were then combined in race-specific fixed effect meta-analyses for each outcome. For replication and generalization analyses, significance was defined at P < 0.01 for ANM analyses and P < 0.017 for AM analyses. MAIN RESULTS AND THE ROLE OF CHANCE: We replicated findings for AM SNPs in the LIN28B locus and an intergenic region on 9q31 in European Americans. The LIN28B SNPs (rs314277 and rs314280) were also significantly associated with AM in Asians, but not in other race/ethnicity groups. Linkage disequilibrium (LD) patterns at this locus varied widely among the ancestral groups. With the exception of an intergenic SNP at 13q34, all ANM SNPs replicated in European Americans. Three were significantly associated with ANM in other race/ethnicity populations: rs2153157 (6p24.2/SYCP2L), rs365132 (5q35/UIMC1) and rs16991615 (20p12.3/MCM8). While rs1172822 (19q13/BRSK1) was not significant in the populations of non-European descent, effect sizes showed similar trends. LIMITATIONS, REASONS FOR CAUTION: Lack of association for the GWAS SNPs in the non-European American groups may be due to differences in locus LD patterns between these groups and the European-descent populations included in the GWAS discovery studies; and in some cases, lower power may also contribute to non-significant findings. WIDER IMPLICATIONS OF THE FINDINGS: The discovery of genetic variants associated with the reproductive traits provides an important opportunity to elucidate the biological mechanisms involved with normal variation and disorders of menarche and menopause. In this study we replicated most, but not all reported SNPs in European descent populations and examined the epidemiologic architecture of these early reported variants, describing their generalizability and effect size across differing ancestral populations. Such data will be increasingly important for prioritizing GWAS SNPs for follow-up in fine-mapping and resequencing studies, as well as in translational research.
Keywords: Age Factors; Cross-Sectional Studies; Female; Genome-Wide Association Study; Genotype; Humans; Menarche; Menopause; Polymorphism, Single Nucleotide

Resequencing and clinical associations of the 9p21.3 region: a comprehensive investigation in the Framingham heart study. - Johnson, Andrew D; Hwang, Shih-Jen; Voorman, Arend; Morrison, Alanna; Peloso, Gina M; Hsu, Yi-Hsiang; Thanassoulis, George; Newton-Cheh, Christopher; Rogers, Ian S; Hoffmann, Udo; Freedman, Jane E; Fox, Caroline S; et al. (Circulation, 2013)
BACKGROUND: 9p21.3 is among the most strongly replicated regions for cardiovascular disease. There are few reports of sequencing the associated 9p21.3 interval. We set out to sequence the 9p21.3 region followed by a comprehensive study of genetic associations with clinical and subclinical cardiovascular disease and its risk factors, as well as with copy number variation and gene expression, in the Framingham Heart Study (FHS). METHODS AND RESULTS: We sequenced 281 individuals (94 with myocardial infarction, 94 with high coronary artery calcium levels, and 93 control subjects free of elevated coronary artery calcium or myocardial infarction), followed by genotyping and association in >7000 additional FHS individuals. We assessed genetic associations with clinical and subclinical cardiovascular disease, risk factor phenotypes, and gene expression levels of the protein-coding genes CDKN2A and CDKN2B and the noncoding gene ANRIL in freshly harvested leukocytes and platelets. Within this large sample, we found strong associations of 9p21.3 variants with increased risk for myocardial infarction, higher coronary artery calcium levels, and larger abdominal aorta diameters and no evidence for association with traditional cardiovascular disease risk factors. No common protein-coding variation, variants in splice donor or acceptor sites, or copy number variation events were observed. By contrast, strong associations were observed between genetic variants and gene expression, particularly for a short isoform of ANRIL and for CDKN2B. CONCLUSIONS: Our thorough genomic characterization of 9p21.3 suggests common variants likely account for observed disease associations and provides further support for the hypothesis that complex regulatory variation affecting ANRIL and CDKN2B gene expression may contribute to increased risk for clinically apparent and subclinical coronary artery disease and aortic disease.
Keywords: Calcinosis; Chromosomes, Human, Pair 9; Coronary Artery Disease; Cyclin-Dependent Kinase Inhibitor p15; Cyclin-Dependent Kinase Inhibitor p16; DNA Copy Number Variations; Female; Follow-Up Studies; Genetic Predisposition to Disease; Genotype; Humans; Longitudinal Studies; Male; Massachusetts; Middle Aged; Myocardial Infarction; Phenotype; Polymorphism, Single Nucleotide; Risk Factors; RNA, Long Noncoding; Sequence Analysis, DNA

Sex-stratified genome-wide association studies including 270,000 individuals show sexual dimorphism in genetic loci for anthropometric traits. - Randall, Joshua C; Winkler, Thomas W; Kutalik, Zoltán; Berndt, Sonja I; Jackson, Anne U; Monda, Keri L; Kilpeläinen, Tuomas O; Esko, Tõnu; Mägi, Reedik; Li, Shengxu; Workalemahu, Tsegaselassie; Feitosa, Mary F; et al. (PLoS Genet, 2013)
Given the anthropometric differences between men and women and previous evidence of sex-difference in genetic effects, we conducted a genome-wide search for sexually dimorphic associations with height, weight, body mass index, waist circumference, hip circumference, and waist-to-hip-ratio (133,723 individuals) and took forward 348 SNPs into follow-up (additional 137,052 individuals) in a total of 94 studies. Seven loci displayed significant sex-difference (FDR<5%), including four previously established (near GRB14/COBLL1, LYPLAL1/SLC30A10, VEGFA, ADAMTS9) and three novel anthropometric trait loci (near MAP3K1, HSD17B4, PPARG), all of which were genome-wide significant in women (P<5×10(-8)), but not in men. Sex-differences were apparent only for waist phenotypes, not for height, weight, BMI, or hip circumference. Moreover, we found no evidence for genetic effects with opposite directions in men versus women. The PPARG locus is of specific interest due to its role in diabetes genetics and therapy. Our results demonstrate the value of sex-specific GWAS to unravel the sexually dimorphic genetic underpinning of complex traits.
Keywords: Anthropometry; Body Height; Body Mass Index; Body Weight; Body Weights and Measures; Female; Genetic Loci; Genome, Human; Genome-Wide Association Study; Humans; Male; Polymorphism, Single Nucleotide; Sex Characteristics; Waist Circumference; Waist-Hip Ratio

Soluble CD14: genomewide association analysis and relationship to cardiovascular risk and mortality in older adults. - Reiner, Alex P; Lange, Ethan M; Jenny, Nancy S; Chaves, Paulo H M; Ellis, Jaclyn; Li, Jin; Walston, Jeremy; Lange, Leslie A; Cushman, Mary; Tracy, Russell P (Arterioscler Thromb Vasc Biol, 2013)
OBJECTIVE: CD14 is a glycosylphosphotidylinositol-anchored membrane glycoprotein expressed on neutrophils and monocytes/macrophages that also circulates as a soluble form (sCD14). Despite the well-recognized role of CD14 in inflammation, relatively little is known about the genetic determinants of sCD14 or the relationship of sCD14 to vascular- and aging-related phenotypes. METHODS AND RESULTS: We measured baseline levels of sCD14 in >5000 European-American and black adults aged 65 years and older from the Cardiovascular Health Study, who were well characterized at baseline for atherosclerotic risk factors and subclinical cardiovascular disease, and who have been followed for clinical cardiovascular disease and mortality outcomes up to 20 years. At baseline, sCD14 generally showed strong positive correlations with traditional cardio-metabolic risk factors and with subclinical measures of vascular disease such as carotid wall thickness and ankle-brachial index (independently of traditional cardiovascular disease risk factors), and was also inversely correlated with body mass index. In genomewide association analyses of sCD14, we (1) confirmed the importance of the CD14 locus on chromosome 5q21 in European-American; (2) identified a novel African ancestry-specific allele of CD14 associated with lower sCD14 in blacks; and (3) identified a putative novel association in European-American of a nonsynonymous variant of PIGC, which encodes an enzyme required for the first step in glycosylphosphotidylinositol anchor biosynthesis. Finally, we show that, like other acute phase inflammatory biomarkers, sCD14 predicts incident cardiovascular disease, and strongly and independently predicts all-cause mortality in older adults. CONCLUSIONS: CD14 independently predicts risk mortality in older adults.
Keywords: African Americans; Age Factors; Aged; Biomarkers; Cardiovascular Diseases; Chromosomes, Human, Pair 5; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Haplotypes; Hexosyltransferases; Humans; Incidence; Inflammation Mediators; Linear Models; Lipopolysaccharide Receptors; Logistic Models; Male; Membrane Proteins; Multivariate Analysis; Phenotype; Polymorphism, Single Nucleotide; Principal Component Analysis; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States

Strategy to control type I error increases power to identify genetic variation using the full biological trajectory. - Benke, K S; Wu, Y; Fallin, D M; Maher, B; Palmer, L J (Genet Epidemiol, 2013)
Genome-wide association studies have been successful in identifying loci that underlie continuous traits measured at a single time point. To additionally consider continuous traits longitudinally, it is desirable to look at SNP effects at baseline and over time using linear-mixed effects models. Estimation and interpretation of two coefficients in the same model raises concern regarding the optimal control of type I error. To investigate this issue, we calculate type I error and power under an alternative for joint tests, including the two degree of freedom likelihood ratio test, and compare this to single degree of freedom tests for each effect separately at varying alpha levels. We show which joint tests are the optimal way to control the type I error and also illustrate that information can be gained by joint testing in situations where either or both SNP effects are underpowered. We also show that closed form power calculations can approximate simulated power for the case of balanced data, provide reasonable approximations for imbalanced data, but overestimate power for complicated residual error structures. We conclude that a two degree of freedom test is an attractive strategy in a hypothesis-free genome-wide setting and recommend its use for genome-wide studies employing linear-mixed effects models.
Keywords: Cohort Studies; Computer Simulation; Genetic Variation; Genome-Wide Association Study; Humans; Linear Models; Models, Genetic; Polymorphism, Single Nucleotide

ADAM19 and HTR4 variants and pulmonary function: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - London, Stephanie J; Gao, Wei; Gharib, Sina A; Hancock, Dana B; Wilk, Jemma B; House, John S; Gibbs, Richard A; Muzny, Donna M; Lumley, Thomas; Franceschini, Nora; North, Kari E; Psaty, Bruce M; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: The pulmonary function measures of forced expiratory volume in 1 second (FEV1) and its ratio to forced vital capacity (FVC) are used in the diagnosis and monitoring of lung diseases and predict cardiovascular mortality in the general population. Genome-wide association studies (GWASs) have identified numerous loci associated with FEV1 and FEV1/FVC, but the causal variants remain uncertain. We hypothesized that novel or rare variants poorly tagged by GWASs may explain the significant associations between FEV1/FVC and 2 genes: ADAM19 and HTR4. METHODS AND RESULTS: We sequenced ADAM19 and its promoter region along with the ≈21-kb portion of HTR4 harboring GWAS single-nucleotide polymorphisms for pulmonary function and analyzed associations with FEV1/FVC among 3983 participants of European ancestry from Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Meta-analysis of common variants in each region identified statistically significant associations (316 tests; P<1.58×10(-4)) with FEV1/FVC for 14 ADAM19 single-nucleotide polymorphisms and 24 HTR4 single-nucleotide polymorphisms. After conditioning on the sentinel GWASs hit in each gene (ADAM19 rs1422795, minor allele frequency=0.33 and HTR4 rs11168048, minor allele frequency=0.40], 1 single-nucleotide polymorphism remained statistically significant (ADAM19 rs13155908, minor allele frequency=0.12; P=1.56×10(-4)). Analysis of rare variants (minor allele frequency <1%) using sequence kernel association test did not identify associations with either region. CONCLUSIONS: Sequencing identified 1 common variant associated with FEV1/FVC independent of the sentinel ADAM19 GWAS hit and supports the original HTR4 GWAS findings. Rare variants do not seem to underlie GWAS associations with pulmonary function for common variants in ADAM19 and HTR4.
Keywords: ADAM Proteins; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Lung; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Association between alcohol and cardiovascular disease: Mendelian randomisation analysis based on individual participant data. - Holmes, Michael V; Dale, Caroline E; Zuccolo, Luisa; Silverwood, Richard J; Guo, Yiran; Ye, Zheng; Prieto-Merino, David; Dehghan, Abbas; Trompet, Stella; Wong, Andrew; Cavadino, Alana; Drogan, Dagmar; et al. (BMJ, 2014)
OBJECTIVE: To use the rs1229984 variant in the alcohol dehydrogenase 1B gene (ADH1B) as an instrument to investigate the causal role of alcohol in cardiovascular disease. DESIGN: Mendelian randomisation meta-analysis of 56 epidemiological studies. PARTICIPANTS: 261 991 individuals of European descent, including 20 259 coronary heart disease cases and 10 164 stroke events. Data were available on ADH1B rs1229984 variant, alcohol phenotypes, and cardiovascular biomarkers. MAIN OUTCOME MEASURES: Odds ratio for coronary heart disease and stroke associated with the ADH1B variant in all individuals and by categories of alcohol consumption. RESULTS: Carriers of the A-allele of ADH1B rs1229984 consumed 17.2% fewer units of alcohol per week (95% confidence interval 15.6% to 18.9%), had a lower prevalence of binge drinking (odds ratio 0.78 (95% CI 0.73 to 0.84)), and had higher abstention (odds ratio 1.27 (1.21 to 1.34)) than non-carriers. Rs1229984 A-allele carriers had lower systolic blood pressure (-0.88 (-1.19 to -0.56) mm Hg), interleukin-6 levels (-5.2% (-7.8 to -2.4%)), waist circumference (-0.3 (-0.6 to -0.1) cm), and body mass index (-0.17 (-0.24 to -0.10) kg/m(2)). Rs1229984 A-allele carriers had lower odds of coronary heart disease (odds ratio 0.90 (0.84 to 0.96)). The protective association of the ADH1B rs1229984 A-allele variant remained the same across all categories of alcohol consumption (P=0.83 for heterogeneity). Although no association of rs1229984 was identified with the combined subtypes of stroke, carriers of the A-allele had lower odds of ischaemic stroke (odds ratio 0.83 (0.72 to 0.95)). CONCLUSIONS: Individuals with a genetic variant associated with non-drinking and lower alcohol consumption had a more favourable cardiovascular profile and a reduced risk of coronary heart disease than those without the genetic variant. This suggests that reduction of alcohol consumption, even for light to moderate drinkers, is beneficial for cardiovascular health.
Keywords: Adult; Aged; Alcohol Dehydrogenase; Alcohol Drinking; Biomarkers; Coronary Disease; Female; Genetic Markers; Genotype; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Models, Statistical; Polymorphism, Single Nucleotide; Stroke

Association of a cystatin C gene variant with cystatin C levels, CKD, and risk of incident cardiovascular disease and mortality. - O'Seaghdha, Conall M; Tin, Adrienne; Yang, Qiong; Katz, Ronit; Liu, Yongmei; Harris, Tamara; Astor, Brad; Coresh, Josef; Fox, Caroline S; Kao, W H Linda; Shlipak, Michael G (Am J Kidney Dis, 2014)
BACKGROUND: Carriers of the T allele of the single-nucleotide polymorphism rs13038305 tend to have lower cystatin C levels and higher cystatin C-based estimated glomerular filtration rate (eGFRcys). Adjusting for this genetic effect on cystatin C concentrations may improve GFR estimation, reclassify cases of chronic kidney disease (CKD), and strengthen risk estimates for cardiovascular disease (CVD) and mortality. STUDY DESIGN: Observational. SETTING & POPULATION: 4 population-based cohorts: Atherosclerosis Risk in Communities (ARIC), Cardiovascular Health (CHS), Framingham Heart (FHS), and Health, Aging, and Body Composition (Health ABC) studies. PREDICTORS: We estimated the association of rs13038305 with eGFRcys and serum creatinine-based eGFR (eGFRcr) and performed longitudinal analyses of the associations of eGFRcys with mortality and cardiovascular events following adjustment for rs13038305. OUTCOMES: We assessed reclassification by genotype-adjusted eGFRcys across CKD categories: <45, 45-59, 60-89, and ≥ 90 mL/min/1.73 m(2). We compared mortality and CVD outcomes in those reclassified to a worse eGFRcys category with those unaffected. Results were combined using fixed-effect inverse-variance meta-analysis. RESULTS: In 14,645 participants, each copy of the T allele of rs13038305 (frequency, 21%) was associated with a 6.4% lower cystatin C concentration, 5.5-mL/min/1.73 m(2) higher eGFRcys, and 36% [95% CI, 29%-41%] lower odds of CKD. Associations with CVD (HR, 1.17; 95% CI, 1.14-1.20) and mortality (HR, 1.22; 95% CI, 1.19-1.24) per 10-mL/min/1.73 m(2) lower eGFRcys were similar with or without rs13038305 adjustment. 1,134 (7.7%) participants were reclassified to a worse CKD category following rs13038305 adjustment, and rates of CVD and mortality were higher in individuals who were reclassified. However, the overall net reclassification index was not significant for either outcome, at 0.009 (95% CI, -0.003 to 0.022) for mortality and 0.014 (95% CI, 0.0 to 0.028) for CVD. LIMITATIONS: rs13038305 explains only a small proportion of cystatin C variation. CONCLUSIONS: Statistical adjustment can correct a genetic bias in GFR estimates based on cystatin C in carriers of the T allele of rs13038305 and result in changes in disease classification. However, on a population level, the effects on overall reclassification of CKD status are modest.
Keywords: Aged; Bias; Biomarkers; Cardiovascular Diseases; Creatinine; Cystatin C; Female; Genetic Variation; Glomerular Filtration Rate; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Renal Insufficiency, Chronic; Risk Assessment; Risk Factors; Severity of Illness Index; Statistics as Topic; Survival Rate

Association of levels of fasting glucose and insulin with rare variants at the chromosome 11p11.2-MADD locus: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Cornes, Belinda K; Brody, Jennifer A; Nikpoor, Naghmeh; Morrison, Alanna C; Chu, Huan; Ahn, Byung Soo; Wang, Shuai; Dauriz, Marco; Barzilay, Joshua I; Dupuis, Josée; Florez, Jose C; Coresh, Josef; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Common variation at the 11p11.2 locus, encompassing MADD, ACP2, NR1H3, MYBPC3, and SPI1, has been associated in genome-wide association studies with fasting glucose and insulin (FI). In the Cohorts for Heart and Aging Research in Genomic Epidemiology Targeted Sequencing Study, we sequenced 5 gene regions at 11p11.2 to identify rare, potentially functional variants influencing fasting glucose or FI levels. METHODS AND RESULTS: Sequencing (mean depth, 38×) across 16.1 kb in 3566 individuals without diabetes mellitus identified 653 variants, 79.9% of which were rare (minor allele frequency <1%) and novel. We analyzed rare variants in 5 gene regions with FI or fasting glucose using the sequence kernel association test. At NR1H3, 53 rare variants were jointly associated with FI (P=2.73×10(-3)); of these, 7 were predicted to have regulatory function and showed association with FI (P=1.28×10(-3)). Conditioning on 2 previously associated variants at MADD (rs7944584, rs10838687) did not attenuate this association, suggesting that there are >2 independent signals at 11p11.2. One predicted regulatory variant, chr11:47227430 (hg18; minor allele frequency=0.00068), contributed 20.6% to the overall sequence kernel association test score at NR1H3, lies in intron 2 of NR1H3, and is a predicted binding site for forkhead box A1 (FOXA1), a transcription factor associated with insulin regulation. In human HepG2 hepatoma cells, the rare chr11:47227430 A allele disrupted FOXA1 binding and reduced FOXA1-dependent transcriptional activity. CONCLUSIONS: Sequencing at 11p11.2-NR1H3 identified rare variation associated with FI. One variant, chr11:47227430, seems to be functional, with the rare A allele reducing transcription factor FOXA1 binding and FOXA1-dependent transcriptional activity.
Keywords: Aged; Aged, 80 and over; Aging; Blood Glucose; Chromosomes, Human, Pair 11; Cohort Studies; Death Domain Receptor Signaling Adaptor Proteins; Diabetes Mellitus, Type 2; Fasting; Female; Gene Frequency; Genetic Variation; Genome-Wide Association Study; Genomics; Guanine Nucleotide Exchange Factors; Heart Diseases; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Associations of NINJ2 sequence variants with incident ischemic stroke in the Cohorts for Heart and Aging in Genomic Epidemiology (CHARGE) consortium. - Bis, Joshua C; DeStefano, Anita; Liu, Xiaoming; Brody, Jennifer A; Choi, Seung Hoan; Verhaaren, Benjamin F J; Debette, Stephanie; Ikram, M Arfan; Shahar, Eyal; Butler, Kenneth R; Gottesman, Rebecca F; Muzny, Donna; et al. (PLoS One, 2014)
BACKGROUND: Stroke, the leading neurologic cause of death and disability, has a substantial genetic component. We previously conducted a genome-wide association study (GWAS) in four prospective studies from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and demonstrated that sequence variants near the NINJ2 gene are associated with incident ischemic stroke. Here, we sought to fine-map functional variants in the region and evaluate the contribution of rare variants to ischemic stroke risk. METHODS AND RESULTS: We sequenced 196 kb around NINJ2 on chromosome 12p13 among 3,986 European ancestry participants, including 475 ischemic stroke cases, from the Atherosclerosis Risk in Communities Study, Cardiovascular Health Study, and Framingham Heart Study. Meta-analyses of single-variant tests for 425 common variants (minor allele frequency [MAF] ≥ 1%) confirmed the original GWAS results and identified an independent intronic variant, rs34166160 (MAF = 0.012), most significantly associated with incident ischemic stroke (HR = 1.80, p = 0.0003). Aggregating 278 putatively-functional variants with MAF≤ 1% using count statistics, we observed a nominally statistically significant association, with the burden of rare NINJ2 variants contributing to decreased ischemic stroke incidence (HR = 0.81; p = 0.026). CONCLUSION: Common and rare variants in the NINJ2 region were nominally associated with incident ischemic stroke among a subset of CHARGE participants. Allelic heterogeneity at this locus, caused by multiple rare, low frequency, and common variants with disparate effects on risk, may explain the difficulties in replicating the original GWAS results. Additional studies that take into account the complex allelic architecture at this locus are needed to confirm these findings.
Keywords: Cell Adhesion Molecules, Neuronal; European Continental Ancestry Group; Female; Genetic Association Studies; Genetic Heterogeneity; Humans; Introns; Ischemia; Male; Myocardial Infarction; Polymorphism, Single Nucleotide; Prospective Studies; Sequence Analysis, DNA

The challenges of genome-wide interaction studies: lessons to learn from the analysis of HDL blood levels. - van Leeuwen, Elisabeth M; Smouter, Françoise A S; Kam-Thong, Tony; Karbalai, Nazanin; Smith, Albert V; Harris, Tamara B; Launer, Lenore J; Sitlani, Colleen M; Li, Guo; Brody, Jennifer A; Bis, Joshua C; White, Charles C; et al. (PLoS One, 2014)
Genome-wide association studies (GWAS) have revealed 74 single nucleotide polymorphisms (SNPs) associated with high-density lipoprotein cholesterol (HDL) blood levels. This study is, to our knowledge, the first genome-wide interaction study (GWIS) to identify SNP×SNP interactions associated with HDL levels. We performed a GWIS in the Rotterdam Study (RS) cohort I (RS-I) using the GLIDE tool which leverages the massively parallel computing power of Graphics Processing Units (GPUs) to perform linear regression on all genome-wide pairs of SNPs. By performing a meta-analysis together with Rotterdam Study cohorts II and III (RS-II and RS-III), we were able to filter 181 interaction terms with a p-value<1 · 10-8 that replicated in the two independent cohorts. We were not able to replicate any of these interaction term in the AGES, ARIC, CHS, ERF, FHS and NFBC-66 cohorts (Ntotal = 30,011) when adjusting for multiple testing. Our GWIS resulted in the consistent finding of a possible interaction between rs774801 in ARMC8 (ENSG00000114098) and rs12442098 in SPATA8 (ENSG00000185594) being associated with HDL levels. However, p-values do not reach the preset Bonferroni correction of the p-values. Our study suggest that even for highly genetically determined traits such as HDL the sample sizes needed to detect SNP×SNP interactions are large and the 2-step filtering approaches do not yield a solution. Here we present our analysis plan and our reservations concerning GWIS.
Keywords: Cholesterol, HDL; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Common variation in fatty acid metabolic genes and risk of incident sudden cardiac arrest. - Lemaitre, Rozenn N; Johnson, Catherine O; Hesselson, Stephanie; Sotoodehnia, Nona; Sotoodhenia, Nona; McKnight, Barbara; Sitlani, Colleen M; Rea, Thomas D; King, Irena B; Kwok, Pui-Yan; Mak, Angel; Li, Guo; et al. (Heart Rhythm, 2014)
BACKGROUND: There is limited information on genetic factors associated with sudden cardiac arrest (SCA). OBJECTIVE: To assess the association of common variation in genes in fatty acid pathways with SCA risk. METHODS: We selected 85 candidate genes and 1155 single nucleotide polymorphisms (SNPs) tagging common variation in each gene. We investigated the SNP associations with SCA in a population-based case-control study. Cases (n = 2160) were from a repository of SCA in the greater Seattle area. Controls (n = 2615), frequency-matched on age and sex, were from the same area. We used linear logistic regression to examine SNP associations with SCA. We performed permutation-based p-min tests to account for multiple comparisons within each gene. The SNP associations with a corrected P value of <.05 were then examined in a meta-analysis of these SNP associations in 9 replication studies totaling 2129 SCA cases and 23,833 noncases. RESULTS: Eight SNPs in or near 8 genes were associated with SCA risk in the discovery study, one of which was nominally significant in the replication phase (rs7737692, minor allele frequency 36%, near the LPCAT1 gene). For each copy of the minor allele, rs7737692 was associated with 13% lower SCA risk (95% confidence interval -21% to -5%) in the discovery phase and 9% lower SCA risk (95% confidence interval -16% to -1%) in the replication phase. CONCLUSIONS: While none of the associations reached significance with Bonferroni correction, a common genetic variant near LPCAT1, a gene involved in the remodeling of phospholipids, was nominally associated with incident SCA risk. Further study is needed to validate this observation.
Keywords: 1-Acylglycerophosphocholine O-Acyltransferase; Aged; Algorithms; Alleles; Case-Control Studies; Death, Sudden, Cardiac; Fatty Acids; Female; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Male; Polymorphism, Single Nucleotide; Risk Factors

Drug-gene interactions and the search for missing heritability: a cross-sectional pharmacogenomics study of the QT interval. - Avery, C L; Sitlani, C M; Arking, D E; Arnett, D K; Bis, J C; Boerwinkle, E; Buckley, B M; Ida Chen, Y-D; de Craen, A J M; Eijgelsheim, M; Enquobahrie, D; Evans, D S; et al. (Pharmacogenomics J, 2014)
Variability in response to drug use is common and heritable, suggesting that genome-wide pharmacogenomics studies may help explain the 'missing heritability' of complex traits. Here, we describe four independent analyses in 33 781 participants of European ancestry from 10 cohorts that were designed to identify genetic variants modifying the effects of drugs on QT interval duration (QT). Each analysis cross-sectionally examined four therapeutic classes: thiazide diuretics (prevalence of use=13.0%), tri/tetracyclic antidepressants (2.6%), sulfonylurea hypoglycemic agents (2.9%) and QT-prolonging drugs as classified by the University of Arizona Center for Education and Research on Therapeutics (4.4%). Drug-gene interactions were estimated using covariable-adjusted linear regression and results were combined with fixed-effects meta-analysis. Although drug-single-nucleotide polymorphism (SNP) interactions were biologically plausible and variables were well-measured, findings from the four cross-sectional meta-analyses were null (Pinteraction>5.0 × 10(-8)). Simulations suggested that additional efforts, including longitudinal modeling to increase statistical power, are likely needed to identify potentially important pharmacogenomic effects.
Keywords: Computer Simulation; Cross-Sectional Studies; Drug-Related Side Effects and Adverse Reactions; Electrocardiography; European Continental Ancestry Group; Gene-Environment Interaction; Genome-Wide Association Study; Humans; Linear Models; Long QT Syndrome; Markov Chains; Pharmacogenetics; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

Effect of genetic variants associated with plasma homocysteine levels on stroke risk. - Cotlarciuc, Ioana; Malik, Rainer; Holliday, Elizabeth G; Ahmadi, Kourosh R; Paré, Guillaume; Psaty, Bruce M; Fornage, Myriam; Hasan, Nazeeha; Rinne, Paul E; Ikram, M Arfan; Markus, Hugh S; Rosand, Jonathan; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Elevated total plasma homocysteine (tHcy) levels are known to be associated with increased risk of ischemic stroke (IS). Given that both tHcy and IS are heritable traits, we investigated a potential genetic relationship between homocysteine levels and stroke risk by assessing 18 polymorphisms previously associated with tHcy levels for their association with IS and its subtypes. METHODS: Previous meta-analysis results from an international stroke collaborative network, METASTROKE, were used to assess association of the 18 tHcy-associated single-nucleotide polymorphisms (SNPs) in 12 389 IS cases and 62 004 controls. We also investigated the associations in regions located within 50 kb from the 18 tHcy-related SNPs and the association of a genetic risk score, including the 18 SNPs. RESULTS: One SNP located in the RASIP1 gene and a cluster of 3 SNPs located at and near SLC17A3 were significantly associated with IS (P<0.0003) after correcting for multiple testing. For stroke subtypes, the sentinel SNP located upstream of MUT was significantly associated with small-vessel disease (P=0.0022), whereas 1 SNP located in MTHFR was significantly associated with large-vessel disease (P=0.00019). A genetic risk score, including the 18 SNPs, did not show significant association with IS or its subtypes. CONCLUSIONS: This study found several potential associations with IS and its subtypes: an association of an MUT variant with small-vessel disease, an MTHFR variant with large-vessel disease, and associations of RASIP1 and SLC17A3 variants with overall IS.
Keywords: Brain Ischemia; Cohort Studies; Europe; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Genome; Homocysteine; Humans; Polymorphism, Single Nucleotide; Risk; Stroke

Effects of long-term averaging of quantitative blood pressure traits on the detection of genetic associations. - Ganesh, Santhi K; Chasman, Daniel I; Larson, Martin G; Guo, Xiuqing; Verwoert, Germain; Bis, Joshua C; Gu, Xiangjun; Smith, Albert V; Yang, Min-Lee; Zhang, Yan; Ehret, Georg; Rose, Lynda M; et al. (Am J Hum Genet, 2014)
Blood pressure (BP) is a heritable, quantitative trait with intraindividual variability and susceptibility to measurement error. Genetic studies of BP generally use single-visit measurements and thus cannot remove variability occurring over months or years. We leveraged the idea that averaging BP measured across time would improve phenotypic accuracy and thereby increase statistical power to detect genetic associations. We studied systolic BP (SBP), diastolic BP (DBP), mean arterial pressure (MAP), and pulse pressure (PP) averaged over multiple years in 46,629 individuals of European ancestry. We identified 39 trait-variant associations across 19 independent loci (p < 5 × 10(-8)); five associations (in four loci) uniquely identified by our LTA analyses included those of SBP and MAP at 2p23 (rs1275988, near KCNK3), DBP at 2q11.2 (rs7599598, in FER1L5), and PP at 6p21 (rs10948071, near CRIP3) and 7p13 (rs2949837, near IGFBP3). Replication analyses conducted in cohorts with single-visit BP data showed positive replication of associations and a nominal association (p < 0.05). We estimated a 20% gain in statistical power with long-term average (LTA) as compared to single-visit BP association studies. Using LTA analysis, we identified genetic loci influencing BP. LTA might be one way of increasing the power of genetic associations for continuous traits in extant samples for other phenotypes that are measured serially over time.
Keywords: Blood Pressure; Genome-Wide Association Study; Humans; Longitudinal Studies; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Evidence of heterogeneity by race/ethnicity in genetic determinants of QT interval. - Seyerle, Amanda A; Young, Alicia M; Jeff, Janina M; Melton, Phillip E; Jorgensen, Neal W; Lin, Yi; Carty, Cara L; Deelman, Ewa; Heckbert, Susan R; Hindorff, Lucia A; Jackson, Rebecca D; Martin, Lisa W; et al. (Epidemiology, 2014)
BACKGROUND: QT interval (QT) prolongation is an established risk factor for ventricular tachyarrhythmia and sudden cardiac death. Previous genome-wide association studies in populations of the European descent have identified multiple genetic loci that influence QT, but few have examined these loci in ethnically diverse populations. METHODS: Here, we examine the direction, magnitude, and precision of effect sizes for 21 previously reported SNPs from 12 QT loci, in populations of European (n = 16,398), African (n = 5,437), American Indian (n = 5,032), Hispanic (n = 1,143), and Asian (n = 932) descent as part of the Population Architecture using Genomics and Epidemiology (PAGE) study. Estimates obtained from linear regression models stratified by race/ethnicity were combined using inverse-variance weighted meta-analysis. Heterogeneity was evaluated using Cochran's Q test. RESULTS: Of 21 SNPs, 7 showed consistent direction of effect across all 5 populations, and an additional 9 had estimated effects that were consistent across 4 populations. Despite consistent direction of effect, 9 of 16 SNPs had evidence (P < 0.05) of heterogeneity by race/ethnicity. For these 9 SNPs, linkage disequilibrium plots often indicated substantial variation in linkage disequilibrium patterns among the various racial/ethnic groups, as well as possible allelic heterogeneity. CONCLUSIONS: These results emphasize the importance of analyzing racial/ethnic groups separately in genetic studies. Furthermore, they underscore the possible utility of trans-ethnic studies to pinpoint underlying casual variants influencing heritable traits such as QT.
Keywords: Aged; Continental Population Groups; Electrocardiography; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Long QT Syndrome; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Risk Factors

FTO genetic variants, dietary intake and body mass index: insights from 177,330 individuals. - Qi, Qibin; Kilpeläinen, Tuomas O; Downer, Mary K; Tanaka, Toshiko; Smith, Caren E; Sluijs, Ivonne; Sonestedt, Emily; Chu, Audrey Y; Renstrom, Frida; Lin, Xiaochen; Ängquist, Lars H; Huang, Jinyan; et al. (Hum Mol Genet, 2014)
FTO is the strongest known genetic susceptibility locus for obesity. Experimental studies in animals suggest the potential roles of FTO in regulating food intake. The interactive relation among FTO variants, dietary intake and body mass index (BMI) is complex and results from previous often small-scale studies in humans are highly inconsistent. We performed large-scale analyses based on data from 177,330 adults (154 439 Whites, 5776 African Americans and 17 115 Asians) from 40 studies to examine: (i) the association between the FTO-rs9939609 variant (or a proxy single-nucleotide polymorphism) and total energy and macronutrient intake and (ii) the interaction between the FTO variant and dietary intake on BMI. The minor allele (A-allele) of the FTO-rs9939609 variant was associated with higher BMI in Whites (effect per allele = 0.34 [0.31, 0.37] kg/m(2), P = 1.9 × 10(-105)), and all participants (0.30 [0.30, 0.35] kg/m(2), P = 3.6 × 10(-107)). The BMI-increasing allele of the FTO variant showed a significant association with higher dietary protein intake (effect per allele = 0.08 [0.06, 0.10] %, P = 2.4 × 10(-16)), and relative weak associations with lower total energy intake (-6.4 [-10.1, -2.6] kcal/day, P = 0.001) and lower dietary carbohydrate intake (-0.07 [-0.11, -0.02] %, P = 0.004). The associations with protein (P = 7.5 × 10(-9)) and total energy (P = 0.002) were attenuated but remained significant after adjustment for BMI. We did not find significant interactions between the FTO variant and dietary intake of total energy, protein, carbohydrate or fat on BMI. Our findings suggest a positive association between the BMI-increasing allele of FTO variant and higher dietary protein intake and offer insight into potential link between FTO, dietary protein intake and adiposity.
Keywords: Adult; African Americans; Aged; Alleles; Asian Continental Ancestry Group; Body Mass Index; Dietary Carbohydrates; Dietary Fats; Dietary Proteins; Energy Intake; European Continental Ancestry Group; Female; Gene Frequency; Humans; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Proteins

A genetic association study of D-dimer levels with 50K SNPs from a candidate gene chip in four ethnic groups. - Weng, Lu-Chen; Tang, Weihong; Rich, Stephen S; Smith, Nicholas L; Redline, Susan; O'Donnell, Christopher J; Basu, Saonli; Reiner, Alexander P; Delaney, Joseph A; Tracy, Russell P; Palmer, Cameron D; Young, Taylor; et al. (Thromb Res, 2014)
INTRODUCTION: D-dimer, a fibrin degradation product, is related to risk of cardiovascular disease and venous thromboembolism. Genetic determinants of D-dimer are not well characterized; notably, few data have been reported for African American (AA), Asian, and Hispanic populations. MATERIALS AND METHODS: We conducted a large-scale candidate gene association study to identify variants in genes associated with D-dimer levels in multi-ethnic populations. Four cohorts, comprising 6,848 European Americans (EAs), 2,192 AAs, 670 Asians, and 1,286 Hispanics in the National Heart, Lung, and Blood Institute Candidate Gene Association Resource consortium, were assembled. Approximately 50,000 genotyped single nucleotide polymorphisms (SNPs) in 2,000 cardiovascular disease gene loci were analyzed by linear regression, adjusting for age, sex, study site, and principal components in each cohort and ethnic group. Results across studies were combined within each ethnic group by meta-analysis. RESULTS: Twelve SNPs in coagulation factor V (F5) and 3 SNPs in the fibrinogen alpha chain (FGA) were significantly associated with D-dimer level in EAs with p<2.0×10(-6). The signal for the most associated SNP in F5 (rs6025, factor V Leiden) was replicated in Hispanics (p=0.023), while that for the top functional SNP in FGA (rs6050) was replicated in AAs (p=0.006). No additional SNPs were significantly associated with D-dimer. CONCLUSIONS: Our study replicated previously reported associations of D-dimer with SNPs in F5 and FGA in EAs; we demonstrated replication of the association of D-dimer with FGA rs6050 in AAs and the factor V Leiden variant in Hispanics.
Keywords: Adult; Aged; Cardiovascular Diseases; Ethnic Groups; Factor V; Female; Fibrin Fibrinogen Degradation Products; Fibrinogen; Genetic Association Studies; Genotype; Humans; Male; Middle Aged; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Young Adult

Genetic association study of QT interval highlights role for calcium signaling pathways in myocardial repolarization. - Arking, Dan E; Pulit, Sara L; Crotti, Lia; van der Harst, Pim; Munroe, Patricia B; Koopmann, Tamara T; Sotoodehnia, Nona; Rossin, Elizabeth J; Morley, Michael; Wang, Xinchen; Johnson, Andrew D; Lundby, Alicia; et al. (Nat Genet, 2014)
The QT interval, an electrocardiographic measure reflecting myocardial repolarization, is a heritable trait. QT prolongation is a risk factor for ventricular arrhythmias and sudden cardiac death (SCD) and could indicate the presence of the potentially lethal mendelian long-QT syndrome (LQTS). Using a genome-wide association and replication study in up to 100,000 individuals, we identified 35 common variant loci associated with QT interval that collectively explain ∼8-10% of QT-interval variation and highlight the importance of calcium regulation in myocardial repolarization. Rare variant analysis of 6 new QT interval-associated loci in 298 unrelated probands with LQTS identified coding variants not found in controls but of uncertain causality and therefore requiring validation. Several newly identified loci encode proteins that physically interact with other recognized repolarization proteins. Our integration of common variant association, expression and orthogonal protein-protein interaction screens provides new insights into cardiac electrophysiology and identifies new candidate genes for ventricular arrhythmias, LQTS and SCD.
Keywords: Adult; Aged; Arrhythmias, Cardiac; Calcium Signaling; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Ventricles; Humans; Long QT Syndrome; Male; Middle Aged; Myocardium; Polymorphism, Single Nucleotide

Genetic determinants of age-related macular degeneration in diverse populations from the PAGE study. - Restrepo, Nicole A; Spencer, Kylee L; Goodloe, Robert; Garrett, Tiana A; Heiss, Gerardo; Bůzková, Petra; Jorgensen, Neal; Jensen, Richard A; Matise, Tara C; Hindorff, Lucia A; Klein, Barbara E K; Klein, Ronald; et al. (Invest Ophthalmol Vis Sci, 2014)
PURPOSE: Substantial progress has been made in identifying susceptibility variants for AMD in European populations; however, few studies have been conducted to understand the role these variants play in AMD risk in diverse populations. The present study aims to examine AMD risk across diverse populations in known and suspected AMD complement factor and lipid-related loci. METHODS: Targeted genotyping was performed across study sites for AMD and lipid trait-associated single nucleotide polymorphism (SNPs). Genetic association tests were performed at individual sites and then meta-analyzed using logistic regression assuming an additive genetic model stratified by self-described race/ethnicity. Participants included cases with early or late AMD and controls with no signs of AMD as determined by fundus photography. Populations included in this study were European Americans, African Americans, Mexican Americans, and Singaporeans from the Population Architecture using Genomics and Epidemiology (PAGE) study. RESULTS: Index variants of AMD, rs1061170 (CFH) and rs10490924 (ARMS2), were associated with AMD at P=3.05×10(-8) and P=6.36×10(-6), respectively, in European Americans. In general, none of the major AMD index variants generalized to our non-European populations with the exception of rs10490924 in Mexican Americans at an uncorrected P value<0.05. Four lipid-associated SNPS (LPL rs328, TRIB1 rs6987702, CETP rs1800775, and KCTD10/MVK rs2338104) were associated with AMD in African Americans and Mexican Americans (P<0.05), but these associations did not survive strict corrections for multiple testing. CONCLUSIONS: While most associations did not generalize in the non-European populations, variants within lipid-related genes were found to be associated with AMD. This study highlights the need for larger well-powered studies in non-European populations.
Keywords: Adult; Aged; Aged, 80 and over; Complement Factor H; DNA; Ethnic Groups; Female; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Macular Degeneration; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Prevalence; Prospective Studies; Proteins; Risk Factors; United States

Genetic diversity is a predictor of mortality in humans. - Bihlmeyer, Nathan A; Brody, Jennifer A; Smith, Albert Vernon; Lunetta, Kathryn L; Nalls, Mike; Smith, Jennifer A; Tanaka, Toshiko; Davies, Gail; Yu, Lei; Mirza, Saira Saeed; Teumer, Alexander; Coresh, Josef; et al. (BMC Genet, 2014)
BACKGROUND: It has been well-established, both by population genetics theory and direct observation in many organisms, that increased genetic diversity provides a survival advantage. However, given the limitations of both sample size and genome-wide metrics, this hypothesis has not been comprehensively tested in human populations. Moreover, the presence of numerous segregating small effect alleles that influence traits that directly impact health directly raises the question as to whether global measures of genomic variation are themselves associated with human health and disease. RESULTS: We performed a meta-analysis of 17 cohorts followed prospectively, with a combined sample size of 46,716 individuals, including a total of 15,234 deaths. We find a significant association between increased heterozygosity and survival (P = 0.03). We estimate that within a single population, every standard deviation of heterozygosity an individual has over the mean decreases that person's risk of death by 1.57%. CONCLUSIONS: This effect was consistent between European and African ancestry cohorts, men and women, and major causes of death (cancer and cardiovascular disease), demonstrating the broad positive impact of genomic diversity on human survival.
Keywords: Genome-Wide Association Study; Heterozygote; Humans; Mortality; Polymorphism, Single Nucleotide; Proportional Hazards Models

Genetic variants related to height and risk of atrial fibrillation: the cardiovascular health study. - Rosenberg, Michael A; Kaplan, Robert C; Siscovick, David S; Psaty, Bruce M; Heckbert, Susan R; Newton-Cheh, Christopher; Mukamal, Kenneth J (Am J Epidemiol, 2014)
Increased height is a known independent risk factor for atrial fibrillation (AF). However, whether genetic determinants of height influence risk is uncertain. In this candidate gene study, we examined the association of 209 height-associated single-nucleotide polymorphisms (SNPs) with incident AF in 3,309 persons of European descent from the Cardiovascular Health Study, a prospective cohort study of older adults (aged ≥ 65 years) enrolled in 1989-1990. After a median follow-up period of 13.2 years, 879 participants developed incident AF. The height-associated SNPs together explained approximately 10% of the variation in height (P = 6.0 × 10(-8)). Using an unweighted genetic height score, we found a nonsignificant association with risk of AF (per allele, hazard ratio = 1.01, 95% confidence interval: 1.00, 1.02; P = 0.06). In weighted analyses, we found that genetically predicted height was strongly associated with AF risk (per 10 cm, hazard ratio = 1.30, 95% confidence interval: 1.03, 1.64; P = 0.03). Importantly, for all models, the inclusion of actual height completely attenuated the genetic height effect. Finally, we identified 1 nonsynonymous SNP (rs1046934) that was independently associated with AF and may warrant future study. In conclusion, we found that genetic determinants of height appear to increase the risk of AF, primarily via height itself. This approach of examining SNPs associated with an intermediate phenotype should be considered as a method for identifying novel genetic targets.
Keywords: African Americans; Aged; Atrial Fibrillation; Body Height; Endonucleases; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Humans; Longitudinal Studies; Male; Polymorphism, Single Nucleotide; Proportional Hazards Models; Risk Factors

Gene-wide analysis detects two new susceptibility genes for Alzheimer's disease. - Escott-Price, Valentina; Bellenguez, Céline; Wang, Li-San; Choi, Seung-Hoan; Harold, Denise; Jones, Lesley; Holmans, Peter; Gerrish, Amy; Vedernikov, Alexey; Richards, Alexander; DeStefano, Anita L; Lambert, Jean-Charles; et al. (PLoS One, 2014)
BACKGROUND: Alzheimer's disease is a common debilitating dementia with known heritability, for which 20 late onset susceptibility loci have been identified, but more remain to be discovered. This study sought to identify new susceptibility genes, using an alternative gene-wide analytical approach which tests for patterns of association within genes, in the powerful genome-wide association dataset of the International Genomics of Alzheimer's Project Consortium, comprising over 7 m genotypes from 25,580 Alzheimer's cases and 48,466 controls. PRINCIPAL FINDINGS: In addition to earlier reported genes, we detected genome-wide significant loci on chromosomes 8 (TP53INP1, p = 1.4×10-6) and 14 (IGHV1-67 p = 7.9×10-8) which indexed novel susceptibility loci. SIGNIFICANCE: The additional genes identified in this study, have an array of functions previously implicated in Alzheimer's disease, including aspects of energy metabolism, protein degradation and the immune system and add further weight to these pathways as potential therapeutic targets in Alzheimer's disease.
Keywords: Alzheimer Disease; Carrier Proteins; Case-Control Studies; Genome-Wide Association Study; Heat-Shock Proteins; Humans; Polymorphism, Single Nucleotide; Receptors, Antigen, B-Cell

Genome-wide association analysis identifies six new loci associated with forced vital capacity. - Loth, Daan W; Soler Artigas, Maria; Gharib, Sina A; Wain, Louise V; Franceschini, Nora; Koch, Beate; Pottinger, Tess D; Smith, Albert Vernon; Duan, Qing; Oldmeadow, Chris; Lee, Mi Kyeong; Strachan, David P; et al. (Nat Genet, 2014)
Forced vital capacity (FVC), a spirometric measure of pulmonary function, reflects lung volume and is used to diagnose and monitor lung diseases. We performed genome-wide association study meta-analysis of FVC in 52,253 individuals from 26 studies and followed up the top associations in 32,917 additional individuals of European ancestry. We found six new regions associated at genome-wide significance (P < 5 × 10(-8)) with FVC in or near EFEMP1, BMP6, MIR129-2-HSD17B12, PRDM11, WWOX and KCNJ2. Two loci previously associated with spirometric measures (GSTCD and PTCH1) were related to FVC. Newly implicated regions were followed up in samples from African-American, Korean, Chinese and Hispanic individuals. We detected transcripts for all six newly implicated genes in human lung tissue. The new loci may inform mechanisms involved in lung development and the pathogenesis of restrictive lung disease.
Keywords: Cohort Studies; Databases, Genetic; Follow-Up Studies; Forced Expiratory Volume; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Lung Diseases; Meta-Analysis as Topic; Polymorphism, Single Nucleotide; Prognosis; Quantitative Trait Loci; Respiratory Function Tests; Spirometry; Vital Capacity

Genome-wide association study for circulating tissue plasminogen activator levels and functional follow-up implicates endothelial STXBP5 and STX2. - Huang, Jie; Huffman, Jennifer E; Yamakuchi, Munekazu; Yamkauchi, Munekazu; Trompet, Stella; Asselbergs, Folkert W; Sabater-Lleal, Maria; Trégouët, David-Alexandre; Chen, Wei-Min; Smith, Nicholas L; Kleber, Marcus E; Shin, So-Youn; et al. (Arterioscler Thromb Vasc Biol, 2014)
OBJECTIVE: Tissue plasminogen activator (tPA), a serine protease, catalyzes the conversion of plasminogen to plasmin, the major enzyme responsible for endogenous fibrinolysis. In some populations, elevated plasma levels of tPA have been associated with myocardial infarction and other cardiovascular diseases. We conducted a meta-analysis of genome-wide association studies to identify novel correlates of circulating levels of tPA. APPROACH AND RESULTS: Fourteen cohort studies with tPA measures (N=26 929) contributed to the meta-analysis. Three loci were significantly associated with circulating tPA levels (P<5.0×10(-8)). The first locus is on 6q24.3, with the lead single nucleotide polymorphism (SNP; rs9399599; P=2.9×10(-14)) within STXBP5. The second locus is on 8p11.21. The lead SNP (rs3136739; P=1.3×10(-9)) is intronic to POLB and <200 kb away from the tPA encoding the gene PLAT. We identified a nonsynonymous SNP (rs2020921) in modest linkage disequilibrium with rs3136739 (r(2)=0.50) within exon 5 of PLAT (P=2.0×10(-8)). The third locus is on 12q24.33, with the lead SNP (rs7301826; P=1.0×10(-9)) within intron 7 of STX2. We further found evidence for the association of lead SNPs in STXBP5 and STX2 with expression levels of the respective transcripts. In in vitro cell studies, silencing STXBP5 decreased the release of tPA from vascular endothelial cells, whereas silencing STX2 increased the tPA release. Through an in silico lookup, we found no associations of the 3 lead SNPs with coronary artery disease or stroke. CONCLUSIONS: We identified 3 loci associated with circulating tPA levels, the PLAT region, STXBP5, and STX2. Our functional studies implicate a novel role for STXBP5 and STX2 in regulating tPA release.
Keywords: Aged; Cells, Cultured; Coronary Artery Disease; Endothelial Cells; Europe; Female; Gene Expression Regulation; Gene Silencing; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Nerve Tissue Proteins; Phenotype; Polymorphism, Single Nucleotide; R-SNARE Proteins; Risk Factors; Stroke; Syntaxin 1; Tissue Plasminogen Activator; Transfection; United States; Up-Regulation

Genome-wide association study of L-arginine and dimethylarginines reveals novel metabolic pathway for symmetric dimethylarginine. - Lüneburg, Nicole; Lieb, Wolfgang; Zeller, Tanja; Chen, Ming-Huei; Maas, Renke; Carter, Angela M; Xanthakis, Vanessa; Glazer, Nicole L; Schwedhelm, Edzard; Seshadri, Sudha; Ikram, Mohammad Arfan; Longstreth, William T; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Dimethylarginines (DMA) interfere with nitric oxide formation by inhibiting nitric oxide synthase (asymmetrical DMA [ADMA]) and l-arginine uptake into the cell (ADMA and symmetrical DMA [SDMA]). In prospective clinical studies, ADMA has been characterized as a cardiovascular risk marker, whereas SDMA is a novel marker for renal function and associated with all-cause mortality after ischemic stroke. The aim of the current study was to characterize the environmental and genetic contributions to interindividual variability of these biomarkers. METHODS AND RESULTS: This study comprised a genome-wide association analysis of 3 well-characterized population-based cohorts (Framingham Heart Study [FHS; n=2992], Gutenberg Health Study [GHS; n=4354], and Multinational Monitoring of Trends and Determinants in Cardiovascular Disease Study [MONICA]/Cooperative Health Research in the Augsburg Area, Augsburg, Bavaria, Germany [KORA] F3 [n=581]) and identified replicated loci (DDAH1, MED23, Arg1, and AGXT2) associated with the interindividual variability in ADMA, l-arginine, and SDMA. Experimental in silico and in vitro studies confirmed functional significance of the identified AGXT2 variants. Clinical outcome analysis in 384 patients of the Leeds stroke study demonstrated an association between increased plasma levels of SDMA, AGXT2 variants, and various cardiometabolic risk factors. AGXT2 variants were not associated with poststroke survival in the Leeds study or were they associated with incident stroke in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium. CONCLUSIONS: These genome-wide association study support the importance of DDAH1 and MED23/Arg1 in regulating ADMA and l-arginine metabolism, respectively, and identify a novel regulatory renal pathway for SDMA by AGXT2. AGXT2 variants might explain part of the pathogenic link between SDMA, renal function, and outcome. An association between AGXT2 variants and stroke is unclear and warrants further investigation.
Keywords: Adult; Aged; Amidohydrolases; Arginine; Binding Sites; Cohort Studies; Female; Genetic Loci; Genome-Wide Association Study; Genotype; HEK293 Cells; Humans; Male; Mediator Complex; Middle Aged; Polymorphism, Single Nucleotide; Protein Structure, Tertiary; Risk Factors; Stroke; Substrate Specificity; Transaminases

Genome-wide association study of plasma N6 polyunsaturated fatty acids within the cohorts for heart and aging research in genomic epidemiology consortium. - Guan, Weihua; Steffen, Brian T; Lemaitre, Rozenn N; Wu, Jason H Y; Tanaka, Toshiko; Manichaikul, Ani; Foy, Millennia; Rich, Stephen S; Wang, Lu; Nettleton, Jennifer A; Tang, Weihong; Gu, Xiangjun; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Omega6 (n6) polyunsaturated fatty acids (PUFAs) and their metabolites are involved in cell signaling, inflammation, clot formation, and other crucial biological processes. Genetic components, such as variants of fatty acid desaturase (FADS) genes, determine the composition of n6 PUFAs. METHODS AND RESULTS: To elucidate undiscovered biological pathways that may influence n6 PUFA composition, we conducted genome-wide association studies and meta-analyses of associations of common genetic variants with 6 plasma n6 PUFAs in 8631 white adults (55% women) across 5 prospective studies. Plasma phospholipid or total plasma fatty acids were analyzed by similar gas chromatography techniques. The n6 fatty acids linoleic acid (LA), γ-linolenic acid (GLA), dihomo-GLA, arachidonic acid, and adrenic acid were expressed as percentage of total fatty acids. We performed linear regression with robust SEs to test for single-nucleotide polymorphism-fatty acid associations, with pooling using inverse-variance-weighted meta-analysis. Novel regions were identified on chromosome 10 associated with LA (rs10740118; P=8.1×10(-9); near NRBF2), on chromosome 16 with LA, GLA, dihomo-GLA, and arachidonic acid (rs16966952; P=1.2×10(-15), 5.0×10(-11), 7.6×10(-65), and 2.4×10(-10), respectively; NTAN1), and on chromosome 6 with adrenic acid after adjustment for arachidonic acid (rs3134950; P=2.1×10(-10); AGPAT1). We confirmed previous findings of the FADS cluster on chromosome 11 with LA and arachidonic acid, and further observed novel genome-wide significant association of this cluster with GLA, dihomo-GLA, and adrenic acid (P=2.3×10(-72), 2.6×10(-151), and 6.3×10(-140), respectively). CONCLUSIONS: Our findings suggest that along with the FADS gene cluster, additional genes may influence n6 PUFA composition.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Chromosomes, Human, Pair 10; Chromosomes, Human, Pair 16; Chromosomes, Human, Pair 6; Fatty Acid Desaturases; Fatty Acids, Omega-6; Female; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies; Sequence Analysis, DNA

Large multiethnic Candidate Gene Study for C-reactive protein levels: identification of a novel association at CD36 in African Americans. - Ellis, Jaclyn; Lange, Ethan M; Li, Jin; Dupuis, Josée; Baumert, Jens; Walston, Jeremy D; Keating, Brendan J; Durda, Peter; Fox, Ervin R; Palmer, Cameron D; Meng, Yan A; Young, Taylor; et al. (Hum Genet, 2014)
C-reactive protein (CRP) is a heritable biomarker of systemic inflammation and a predictor of cardiovascular disease (CVD). Large-scale genetic association studies for CRP have largely focused on individuals of European descent. We sought to uncover novel genetic variants for CRP in a multiethnic sample using the ITMAT Broad-CARe (IBC) array, a custom 50,000 SNP gene-centric array having dense coverage of over 2,000 candidate CVD genes. We performed analyses on 7,570 African Americans (AA) from the Candidate gene Association Resource (CARe) study and race-combined meta-analyses that included 29,939 additional individuals of European descent from CARe, the Women's Health Initiative (WHI) and KORA studies. We observed array-wide significance (p < 2.2 × 10(-6)) for four loci in AA, three of which have been reported previously in individuals of European descent (IL6R, p = 2.0 × 10(-6); CRP, p = 4.2 × 10(-71); APOE, p = 1.6 × 10(-6)). The fourth significant locus, CD36 (p = 1.6 × 10(-6)), was observed at a functional variant (rs3211938) that is extremely rare in individuals of European descent. We replicated the CD36 finding (p = 1.8 × 10(-5)) in an independent sample of 8,041 AA women from WHI; a meta-analysis combining the CARe and WHI AA results at rs3211938 reached genome-wide significance (p = 1.5 × 10(-10)). In the race-combined meta-analyses, 13 loci reached significance, including ten (CRP, TOMM40/APOE/APOC1, HNF1A, LEPR, GCKR, IL6R, IL1RN, NLRP3, HNF4A and BAZ1B/BCL7B) previously associated with CRP, and one (ARNTL) previously reported to be nominally associated with CRP. Two novel loci were also detected (RPS6KB1, p = 2.0 × 10(-6); CD36, p = 1.4 × 10(-6)). These results highlight both shared and unique genetic risk factors for CRP in AA compared to populations of European descent.
Keywords: Adult; African Americans; Aged; Biomarkers; C-Reactive Protein; Cardiovascular Diseases; CD36 Antigens; Female; Genetic Loci; Genetic Predisposition to Disease; Genetics, Population; Genome-Wide Association Study; Humans; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Large-scale meta-analysis of genome-wide association data identifies six new risk loci for Parkinson's disease. - Nalls, Mike A; Pankratz, Nathan; Lill, Christina M; Do, Chuong B; Hernandez, Dena G; Saad, Mohamad; DeStefano, Anita L; Kara, Eleanna; Bras, Jose; Sharma, Manu; Schulte, Claudia; Keller, Margaux F; et al. (Nat Genet, 2014)
We conducted a meta-analysis of Parkinson's disease genome-wide association studies using a common set of 7,893,274 variants across 13,708 cases and 95,282 controls. Twenty-six loci were identified as having genome-wide significant association; these and 6 additional previously reported loci were then tested in an independent set of 5,353 cases and 5,551 controls. Of the 32 tested SNPs, 24 replicated, including 6 newly identified loci. Conditional analyses within loci showed that four loci, including GBA, GAK-DGKQ, SNCA and the HLA region, contain a secondary independent risk variant. In total, we identified and replicated 28 independent risk variants for Parkinson's disease across 24 loci. Although the effect of each individual locus was small, risk profile analysis showed substantial cumulative risk in a comparison of the highest and lowest quintiles of genetic risk (odds ratio (OR) = 3.31, 95% confidence interval (CI) = 2.55-4.30; P = 2 × 10(-16)). We also show six risk loci associated with proximal gene expression or DNA methylation.
Keywords: Case-Control Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Parkinson Disease; Polymorphism, Single Nucleotide; Risk Factors

A low-frequency variant in MAPK14 provides mechanistic evidence of a link with myeloperoxidase: a prognostic cardiovascular risk marker. - Waterworth, Dawn M; Li, Li; Scott, Robert; Warren, Liling; Gillson, Christopher; Aponte, Jennifer; Sarov-Blat, Lea; Sprecher, Dennis; Dupuis, Josée; Reiner, Alex; Psaty, Bruce M; Tracy, Russell P; et al. (J Am Heart Assoc, 2014)
BACKGROUND: Genetics can be used to predict drug effects and generate hypotheses around alternative indications. To support Losmapimod, a p38 mitogen-activated protein kinase inhibitor in development for acute coronary syndrome, we characterized gene variation in MAPK11/14 genes by exome sequencing and follow-up genotyping or imputation in participants well-phenotyped for cardiovascular and metabolic traits. METHODS AND RESULTS: Investigation of genetic variation in MAPK11 and MAPK14 genes using additive genetic models in linear or logistic regression with cardiovascular, metabolic, and biomarker phenotypes highlighted an association of RS2859144 in MAPK14 with myeloperoxidase in a dyslipidemic population (Genetic Epidemiology of Metabolic Syndrome Study), P=2.3×10(-6)). This variant (or proxy) was consistently associated with myeloperoxidase in the Framingham Heart Study and Cardiovascular Health Study studies (replication meta-P=0.003), leading to a meta-P value of 9.96×10(-7) in the 3 dyslipidemic groups. The variant or its proxy was then profiled in additional population-based cohorts (up to a total of 58 930 subjects) including Cohorte Lausannoise, Ely, Fenland, European Prospective Investigation of Cancer, London Life Sciences Prospective Population Study, and the Genetics of Obesity Associations study obesity case-control for up to 40 cardiovascular and metabolic traits. Overall analysis identified the same single nucleotide polymorphisms to be nominally associated consistently with glomerular filtration rate (P=0.002) and risk of obesity (body mass index ≥30 kg/m(2), P=0.004). CONCLUSIONS: As myeloperoxidase is a prognostic marker of coronary events, the MAPK14 variant may provide a mechanistic link between p38 map kinase and these events, providing information consistent with current indication of Losmapimod for acute coronary syndrome. If replicated, the association with glomerular filtration rate, along with previous biological findings, also provides support for kidney diseases as alternative indications.
Keywords: Adult; Aged; Cardiovascular Diseases; Dyslipidemias; Exome; Female; Genotype; Humans; Linear Models; Logistic Models; Male; Metabolic Syndrome X; Middle Aged; Mitogen-Activated Protein Kinase 11; Mitogen-Activated Protein Kinase 14; Obesity; Peroxidase; Polymorphism, Single Nucleotide; Prognosis; Risk Factors; Sequence Analysis, DNA

Meta-analysis in more than 17,900 cases of ischemic stroke reveals a novel association at 12q24.12. - Kilarski, Laura L; Achterberg, Sefanja; Devan, William J; Traylor, Matthew; Malik, Rainer; Lindgren, Arne; Pare, Guillame; Sharma, Pankaj; Slowik, Agniesczka; Thijs, Vincent; Walters, Matthew; Worrall, Bradford B; et al. (Neurology, 2014)
OBJECTIVES: To perform a genome-wide association study (GWAS) using the Immunochip array in 3,420 cases of ischemic stroke and 6,821 controls, followed by a meta-analysis with data from more than 14,000 additional ischemic stroke cases. METHODS: Using the Immunochip, we genotyped 3,420 ischemic stroke cases and 6,821 controls. After imputation we meta-analyzed the results with imputed GWAS data from 3,548 cases and 5,972 controls recruited from the ischemic stroke WTCCC2 study, and with summary statistics from a further 8,480 cases and 56,032 controls in the METASTROKE consortium. A final in silico "look-up" of 2 single nucleotide polymorphisms in 2,522 cases and 1,899 controls was performed. Associations were also examined in 1,088 cases with intracerebral hemorrhage and 1,102 controls. RESULTS: In an overall analysis of 17,970 cases of ischemic stroke and 70,764 controls, we identified a novel association on chromosome 12q24 (rs10744777, odds ratio [OR] 1.10 [1.07-1.13], p = 7.12 × 10(-11)) with ischemic stroke. The association was with all ischemic stroke rather than an individual stroke subtype, with similar effect sizes seen in different stroke subtypes. There was no association with intracerebral hemorrhage (OR 1.03 [0.90-1.17], p = 0.695). CONCLUSION: Our results show, for the first time, a genetic risk locus associated with ischemic stroke as a whole, rather than in a subtype-specific manner. This finding was not associated with intracerebral hemorrhage.
Keywords: Brain Ischemia; Cerebral Hemorrhage; Chromosomes, Human, Pair 12; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Polymorphism, Single Nucleotide; Risk; Stroke

Meta-analysis of genome-wide association studies in African Americans provides insights into the genetic architecture of type 2 diabetes. - Ng, Maggie C Y; Shriner, Daniel; Chen, Brian H; Li, Jiang; Chen, Wei-Min; Guo, Xiuqing; Liu, Jiankang; Bielinski, Suzette J; Yanek, Lisa R; Nalls, Michael A; Comeau, Mary E; Rasmussen-Torvik, Laura J; et al. (PLoS Genet, 2014)
Type 2 diabetes (T2D) is more prevalent in African Americans than in Europeans. However, little is known about the genetic risk in African Americans despite the recent identification of more than 70 T2D loci primarily by genome-wide association studies (GWAS) in individuals of European ancestry. In order to investigate the genetic architecture of T2D in African Americans, the MEta-analysis of type 2 DIabetes in African Americans (MEDIA) Consortium examined 17 GWAS on T2D comprising 8,284 cases and 15,543 controls in African Americans in stage 1 analysis. Single nucleotide polymorphisms (SNPs) association analysis was conducted in each study under the additive model after adjustment for age, sex, study site, and principal components. Meta-analysis of approximately 2.6 million genotyped and imputed SNPs in all studies was conducted using an inverse variance-weighted fixed effect model. Replications were performed to follow up 21 loci in up to 6,061 cases and 5,483 controls in African Americans, and 8,130 cases and 38,987 controls of European ancestry. We identified three known loci (TCF7L2, HMGA2 and KCNQ1) and two novel loci (HLA-B and INS-IGF2) at genome-wide significance (4.15 × 10(-94)<P<5 × 10(-8), odds ratio (OR)  = 1.09 to 1.36). Fine-mapping revealed that 88 of 158 previously identified T2D or glucose homeostasis loci demonstrated nominal to highly significant association (2.2 × 10(-23) < locus-wide P<0.05). These novel and previously identified loci yielded a sibling relative risk of 1.19, explaining 17.5% of the phenotypic variance of T2D on the liability scale in African Americans. Overall, this study identified two novel susceptibility loci for T2D in African Americans. A substantial number of previously reported loci are transferable to African Americans after accounting for linkage disequilibrium, enabling fine mapping of causal variants in trans-ethnic meta-analysis studies.
Keywords: African Americans; Diabetes Mellitus, Type 2; Genome-Wide Association Study; HLA-B27 Antigen; HMGA2 Protein; Humans; KCNQ1 Potassium Channel; Mutant Chimeric Proteins; Polymorphism, Single Nucleotide; Transcription Factor 7-Like 2 Protein

Multiancestral analysis of inflammation-related genetic variants and C-reactive protein in the population architecture using genomics and epidemiology study. - Kocarnik, Jonathan M; Pendergrass, Sarah A; Carty, Cara L; Pankow, James S; Schumacher, Fredrick R; Cheng, Iona; Durda, Peter; Ambite, Jose Luis; Deelman, Ewa; Cook, Nancy R; Liu, Simin; Wactawski-Wende, Jean; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: C-reactive protein (CRP) is a biomarker of inflammation. Genome-wide association studies (GWAS) have identified single-nucleotide polymorphisms (SNPs) associated with CRP concentrations and inflammation-related traits such as cardiovascular disease, type 2 diabetes mellitus, and obesity. We aimed to replicate previous CRP-SNP associations, assess whether these associations generalize to additional race/ethnicity groups, and evaluate inflammation-related SNPs for a potentially pleiotropic association with CRP. METHODS AND RESULTS: We selected and analyzed 16 CRP-associated and 250 inflammation-related GWAS SNPs among 40 473 African American, American Indian, Asian/Pacific Islander, European American, and Hispanic participants from 7 studies collaborating in the Population Architecture using Genomics and Epidemiology (PAGE) study. Fixed-effect meta-analyses combined study-specific race/ethnicity-stratified linear regression estimates to evaluate the association between each SNP and high-sensitivity CRP. Overall, 18 SNPs in 8 loci were significantly associated with CRP (Bonferroni-corrected P<3.1×10(-3) for replication, P<2.0×10(-4) for pleiotropy): Seven of these were specific to European Americans, while 9 additionally generalized to African Americans (1), Hispanics (5), or both (3); 1 SNP was seen only in African Americans and Hispanics. Two SNPs in the CELSR2/PSRC1/SORT1 locus showed a potentially novel association with CRP: rs599839 (P=2.0×10(-6)) and rs646776 (P=3.1×10(-5)). CONCLUSIONS: We replicated 16 SNP-CRP associations, 10 of which generalized to African Americans and/or Hispanics. We also identified potentially novel pleiotropic associations with CRP for two SNPs previously associated with coronary artery disease and/or low-density lipoprotein-cholesterol. These findings demonstrate the benefit of evaluating genotype-phenotype associations in multiple race/ethnicity groups and looking for pleiotropic relationships among SNPs previously associated with related phenotypes.
Keywords: Adult; African Continental Ancestry Group; Aged; Asian Continental Ancestry Group; C-Reactive Protein; Female; Genetic Variation; Genome-Wide Association Study; Hispanic Americans; Humans; Indians, North American; Inflammation; Male; Middle Aged; Polymorphism, Single Nucleotide; United States; Young Adult

Multilocus genetic risk score associates with ischemic stroke in case-control and prospective cohort studies. - Malik, Rainer; Bevan, Steve; Nalls, Michael A; Holliday, Elizabeth G; Devan, William J; Cheng, Yu-Ching; Ibrahim-Verbaas, Carla A; Verhaaren, Benjamin F J; Bis, Joshua C; Joon, Aron Y; de Stefano, Anita L; Fornage, Myriam; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Genome-wide association studies have revealed multiple common variants associated with known risk factors for ischemic stroke (IS). However, their aggregate effect on risk is uncertain. We aimed to generate a multilocus genetic risk score (GRS) for IS based on genome-wide association studies data from clinical-based samples and to establish its external validity in prospective population-based cohorts. METHODS: Three thousand five hundred forty-eight clinic-based IS cases and 6399 controls from the Wellcome Trust Case Control Consortium 2 were used for derivation of the GRS. Subjects from the METASTROKE consortium served as a replication sample. The validation sample consisted of 22 751 participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. We selected variants that had reached genome-wide significance in previous association studies on established risk factors for IS. RESULTS: A combined GRS for atrial fibrillation, coronary artery disease, hypertension, and systolic blood pressure significantly associated with IS both in the case-control samples and in the prospective population-based studies. Subjects in the top quintile of the combined GRS had >2-fold increased risk of IS compared with subjects in the lowest quintile. Addition of the combined GRS to a simple model based on sex significantly improved the prediction of IS in the combined clinic-based samples but not in the population-based studies, and there was no significant improvement in net reclassification. CONCLUSIONS: A multilocus GRS based on common variants for established cardiovascular risk factors was significantly associated with IS both in clinic-based samples and in the general population. However, the improvement in clinical risk prediction was found to be small.
Keywords: Adult; Aged; Aged, 80 and over; Atrial Fibrillation; Blood Pressure; Brain Ischemia; Case-Control Studies; Cohort Studies; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Multilocus Sequence Typing; Polymorphism, Single Nucleotide; Population; Prospective Studies; Reproducibility of Results; Risk Assessment; Risk Factors; Sex Factors; Stroke

Novel gene variants predict serum levels of the cytokines IL-18 and IL-1ra in older adults. - Matteini, A M; Li, J; Lange, E M; Tanaka, T; Lange, L A; Tracy, R P; Wang, Y; Biggs, M L; Arking, D E; Fallin, M D; Chakravarti, A; Psaty, B M; et al. (Cytokine, 2014)
Activation of inflammatory pathways measured by serum inflammatory markers such as interleukin-18 (IL-18) and interleukin-1 receptor antagonist (IL-1ra) is strongly associated with the progression of chronic disease states in older adults. Given that these serum cytokine levels are in part a heritable trait, genetic variation may predict increased serum levels. Using the Cardiovascular Health Study and InCHIANTI cohorts, a genome-wide association study was performed to identify genetic variants that influence IL-18 and IL-1ra serum levels among older adults. Multiple linear regression models characterized the association between each SNP and log-transformed cytokine values. Tests for multiple independent signals within statistically significant loci were performed using haplotype analysis and regression models conditional on lead SNP in each region. Multiple SNPs were associated with these cytokines with genome-wide significance, including SNPs in the IL-18-BCO gene region of chromosome 2 for IL-18 (top SNP rs2250417, P=1.9×10(-32)) and in the IL-1 gene family region of chromosome 2 for IL-1ra (rs6743376, P=2.3×10(-26)). Haplotype tests and conditional linear regression models showed evidence of multiple independent signals in these regions. Serum IL-18 levels were also associated with a region on chromosome 2 containing the NLRC4 gene (rs12989936, P=2.7×10(-19)). These data characterize multiple robust genetic signals that influence IL-18 and IL-1ra cytokine production. In particular, the signal for serum IL-18 located on chromosome two is novel and potentially important in inflammasome triggered chronic activation of inflammation in older adults. Replication in independent cohorts is an important next step, as well as molecular studies to better understand the role of NLRC4.
Keywords: Aged; Aged, 80 and over; Calcium-Binding Proteins; CARD Signaling Adaptor Proteins; Chromosomes, Human, Pair 2; Female; Genetic Variation; Genome-Wide Association Study; Genotype; Haplotypes; Humans; Inflammation; Interleukin 1 Receptor Antagonist Protein; Interleukin-18; Male; Polymorphism, Single Nucleotide

Novel genetic markers associate with atrial fibrillation risk in Europeans and Japanese. - Lubitz, Steven A; Lunetta, Kathryn L; Lin, Honghuang; Arking, Dan E; Trompet, Stella; Li, Guo; Krijthe, Bouwe P; Chasman, Daniel I; Barnard, John; Kleber, Marcus E; Dörr, Marcus; Ozaki, Kouichi; et al. (J Am Coll Cardiol, 2014)
OBJECTIVES: This study sought to identify nonredundant atrial fibrillation (AF) genetic susceptibility signals and examine their cumulative relations with AF risk. BACKGROUND: AF-associated loci span broad genomic regions that may contain multiple susceptibility signals. Whether multiple signals exist at AF loci has not been systematically explored. METHODS: We performed association testing conditioned on the most significant, independently associated genetic markers at 9 established AF loci using 2 complementary techniques in 64,683 individuals of European ancestry (3,869 incident and 3,302 prevalent AF cases). Genetic risk scores were created and tested for association with AF in Europeans and an independent sample of 11,309 individuals of Japanese ancestry (7,916 prevalent AF cases). RESULTS: We observed at least 4 distinct AF susceptibility signals on chromosome 4q25 upstream of PITX2, but not at the remaining 8 AF loci. A multilocus score comprised 12 genetic markers demonstrated an estimated 5-fold gradient in AF risk. We observed a similar spectrum of risk associated with these markers in Japanese. Regions containing AF signals on chromosome 4q25 displayed a greater degree of evolutionary conservation than the remainder of the locus, suggesting that they may tag regulatory elements. CONCLUSIONS: The chromosome 4q25 AF locus is architecturally complex and harbors at least 4 AF susceptibility signals in individuals of European ancestry. Similar polygenic AF susceptibility exists between Europeans and Japanese. Future work is necessary to identify causal variants, determine mechanisms by which associated loci predispose to AF, and explore whether AF susceptibility signals classify individuals at risk for AF and related morbidity.
Keywords: Adult; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Atrial Fibrillation; Chromosome Mapping; Chromosomes, Human, Pair 4; Europe; European Continental Ancestry Group; Female; Genetic Markers; Genetic Predisposition to Disease; Homeodomain Proteins; Humans; Japan; Male; Middle Aged; Polymorphism, Single Nucleotide; Transcription Factors

Pharmacogenetic meta-analysis of genome-wide association studies of LDL cholesterol response to statins. - Postmus, Iris; Trompet, Stella; Deshmukh, Harshal A; Barnes, Michael R; Li, Xiaohui; Warren, Helen R; Chasman, Daniel I; Zhou, Kaixin; Arsenault, Benoit J; Donnelly, Louise A; Wiggins, Kerri L; Avery, Christy L; et al. (Nat Commun, 2014)
Statins effectively lower LDL cholesterol levels in large studies and the observed interindividual response variability may be partially explained by genetic variation. Here we perform a pharmacogenetic meta-analysis of genome-wide association studies (GWAS) in studies addressing the LDL cholesterol response to statins, including up to 18,596 statin-treated subjects. We validate the most promising signals in a further 22,318 statin recipients and identify two loci, SORT1/CELSR2/PSRC1 and SLCO1B1, not previously identified in GWAS. Moreover, we confirm the previously described associations with APOE and LPA. Our findings advance the understanding of the pharmacogenetic architecture of statin response.
Keywords: Cholesterol, LDL; Genome-Wide Association Study; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Pharmacogenetics; Polymorphism, Single Nucleotide

Predicting stroke through genetic risk functions: the CHARGE Risk Score Project. - Ibrahim-Verbaas, Carla A; Fornage, Myriam; Bis, Joshua C; Choi, Seung Hoan; Psaty, Bruce M; Meigs, James B; Rao, Madhu; Nalls, Mike; Fontes, João D; O'Donnell, Christopher J; Kathiresan, Sekar; Ehret, Georg B; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Beyond the Framingham Stroke Risk Score, prediction of future stroke may improve with a genetic risk score (GRS) based on single-nucleotide polymorphisms associated with stroke and its risk factors. METHODS: The study includes 4 population-based cohorts with 2047 first incident strokes from 22,720 initially stroke-free European origin participants aged ≥55 years, who were followed for up to 20 years. GRSs were constructed with 324 single-nucleotide polymorphisms implicated in stroke and 9 risk factors. The association of the GRS to first incident stroke was tested using Cox regression; the GRS predictive properties were assessed with area under the curve statistics comparing the GRS with age and sex, Framingham Stroke Risk Score models, and reclassification statistics. These analyses were performed per cohort and in a meta-analysis of pooled data. Replication was sought in a case-control study of ischemic stroke. RESULTS: In the meta-analysis, adding the GRS to the Framingham Stroke Risk Score, age and sex model resulted in a significant improvement in discrimination (all stroke: Δjoint area under the curve=0.016, P=2.3×10(-6); ischemic stroke: Δjoint area under the curve=0.021, P=3.7×10(-7)), although the overall area under the curve remained low. In all the studies, there was a highly significantly improved net reclassification index (P<10(-4)). CONCLUSIONS: The single-nucleotide polymorphisms associated with stroke and its risk factors result only in a small improvement in prediction of future stroke compared with the classical epidemiological risk factors for stroke.
Keywords: Age Factors; Aged; Aged, 80 and over; Area Under Curve; Case-Control Studies; Cohort Studies; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Risk Factors; ROC Curve; Sex Factors; Stroke

A robust method for genome-wide association meta-analysis with the application to circulating insulin-like growth factor I concentrations. - Wang, Tao; Zhou, Baiyu; Guo, Tingwei; Bidlingmaier, Martin; Wallaschofski, Henri; Teumer, Alexander; Vasan, Ramachandran S; Kaplan, Robert C (Genet Epidemiol, 2014)
Genome-wide association studies (GWAS) offer an excellent opportunity to identify the genetic variants underlying complex human diseases. Successful utilization of this approach requires a large sample size to identify single nucleotide polymorphisms (SNPs) with subtle effects. Meta-analysis is a cost-efficient means to achieve large sample size by combining data from multiple independent GWAS; however, results from studies performed on different populations can be variable due to various reasons, including varied linkage equilibrium structures as well as gene-gene and gene-environment interactions. Nevertheless, one should expect effects of the SNP are more similar between similar populations than those between populations with quite different genetic and environmental backgrounds. Prior information on populations of GWAS is often not considered in current meta-analysis methods, rendering such analyses less optimal for the detecting association. This article describes a test that improves meta-analysis to incorporate variable heterogeneity among populations. The proposed method is remarkably simple in computation and hence can be performed in a rapid fashion in the setting of GWAS. Simulation results demonstrate the validity and higher power of the proposed method over conventional methods in the presence of heterogeneity. As a demonstration, we applied the test to real GWAS data to identify SNPs associated with circulating insulin-like growth factor I concentrations.
Keywords: Computer Simulation; Genetic Linkage; Genome; Genome-Wide Association Study; Humans; Insulin-Like Growth Factor I; Meta-Analysis as Topic; Models, Genetic; Polymorphism, Single Nucleotide; Sample Size

Sequence variation in TMEM18 in association with body mass index: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Liu, Ching-Ti; Young, Kristin L; Brody, Jennifer A; Olden, Matthias; Wojczynski, Mary K; Heard-Costa, Nancy; Li, Guo; Morrison, Alanna C; Muzny, Donna; Gibbs, Richard A; Reid, Jeffrey G; Shao, Yaming; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Genome-wide association studies for body mass index (BMI) previously identified a locus near TMEM18. We conducted targeted sequencing of this region to investigate the role of common, low-frequency, and rare variants influencing BMI. METHODS AND RESULTS: We sequenced TMEM18 and regions downstream of TMEM18 on chromosome 2 in 3976 individuals of European ancestry from 3 community-based cohorts (Atherosclerosis Risk in Communities, Cardiovascular Health Study, and Framingham Heart Study), including 200 adults selected for high BMI. We examined the association between BMI and variants identified in the region from nucleotide position 586 432 to 677 539 (hg18). Rare variants (minor allele frequency, <1%) were analyzed using a burden test and the sequence kernel association test. Results from the 3 cohort studies were meta-analyzed. We estimate that mean BMI is 0.43 kg/m(2) higher for each copy of the G allele of single-nucleotide polymorphism rs7596758 (minor allele frequency, 29%; P=3.46×10(-4)) using a Bonferroni threshold of P<4.6×10(-4). Analyses conditional on previous genome-wide association study single-nucleotide polymorphisms associated with BMI in the region led to attenuation of this signal and uncovered another independent (r(2)<0.2), statistically significant association, rs186019316 (P=2.11×10(-4)). Both rs186019316 and rs7596758 or proxies are located in transcription factor binding regions. No significant association with rare variants was found in either the exons of TMEM18 or the 3' genome-wide association study region. CONCLUSIONS: Targeted sequencing around TMEM18 identified 2 novel BMI variants with possible regulatory function.
Keywords: Adult; Aged; Aging; Body Mass Index; Cohort Studies; Female; Genetic Association Studies; Genetic Variation; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Male; Membrane Proteins; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Young Adult

Sequencing of 2 subclinical atherosclerosis candidate regions in 3669 individuals: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Bis, Joshua C; White, Charles C; Franceschini, Nora; Brody, Jennifer; Zhang, Xiaoling; Muzny, Donna; Santibanez, Jireh; Gibbs, Richard; Liu, Xiaoming; Lin, Honghuang; Boerwinkle, Eric; Psaty, Bruce M; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Atherosclerosis, the precursor to coronary heart disease and stroke, is characterized by an accumulation of fatty cells in the arterial intimal-medial layers. Common carotid intima media thickness (cIMT) and plaque are subclinical atherosclerosis measures that predict cardiovascular disease events. Previously, genome-wide association studies demonstrated evidence for association with cIMT (SLC17A4) and plaque (PIK3CG). METHODS AND RESULTS: We sequenced 120 kb around SLC17A4 (6p22.2) and 251 kb around PIK3CG (7q22.3) among 3669 European ancestry participants from the Atherosclerosis Risk in Communities (ARIC) study, Cardiovascular Health Study (CHS), and Framingham Heart Study (FHS) in Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Primary analyses focused on 438 common variants (minor allele frequency ≥1%), which were independently meta-analyzed. A 3' untranslated region CCDC71L variant (rs2286149), upstream from PIK3CG, was the most significant finding in cIMT (P=0.00033) and plaque (P=0.0004) analyses. A SLC17A4 intronic variant was also associated with cIMT (P=0.008). Both were in low linkage disequilibrium with the genome-wide association study single nucleotide polymorphisms. Gene-based tests including T1 count and sequence kernel association test for rare variants (minor allele frequency <1%) did not yield statistically significant associations. However, we observed nominal associations for rare variants in CCDC71L and SLC17A3 with cIMT and of the entire 7q22 region with plaque (P=0.05). CONCLUSIONS: Common and rare variants in PIK3CG and SLC17A4 regions demonstrated modest association with subclinical atherosclerosis traits. Although not conclusive, these findings may help to understand the genetic architecture of regions previously implicated by genome-wide association studies and identify variants within these regions for further investigation in larger samples.
Keywords: Aged; Aged, 80 and over; Aging; Atherosclerosis; Class Ib Phosphatidylinositol 3-Kinase; Cohort Studies; European Continental Ancestry Group; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Sodium-Phosphate Cotransporter Proteins, Type I

Sequencing of SCN5A identifies rare and common variants associated with cardiac conduction: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. - Magnani, Jared W; Brody, Jennifer A; Prins, Bram P; Arking, Dan E; Lin, Honghuang; Yin, Xiaoyan; Liu, Ching-Ti; Morrison, Alanna C; Zhang, Feng; Spector, Tim D; Alonso, Alvaro; Bis, Joshua C; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: The cardiac sodium channel SCN5A regulates atrioventricular and ventricular conduction. Genetic variants in this gene are associated with PR and QRS intervals. We sought to characterize further the contribution of rare and common coding variation in SCN5A to cardiac conduction. METHODS AND RESULTS: In Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study, we performed targeted exonic sequencing of SCN5A (n=3699, European ancestry individuals) and identified 4 common (minor allele frequency >1%) and 157 rare variants. Common and rare SCN5A coding variants were examined for association with PR and QRS intervals through meta-analysis of European ancestry participants from CHARGE, National Heart, Lung, and Blood Institute's Exome Sequencing Project (n=607), and the UK10K (n=1275) and by examining Exome Sequencing Project African ancestry participants (n=972). Rare coding SCN5A variants in aggregate were associated with PR interval in European and African ancestry participants (P=1.3×10(-3)). Three common variants were associated with PR and QRS interval duration among European ancestry participants and one among African ancestry participants. These included 2 well-known missense variants: rs1805124 (H558R) was associated with PR and QRS shortening in European ancestry participants (P=6.25×10(-4) and P=5.2×10(-3), respectively) and rs7626962 (S1102Y) was associated with PR shortening in those of African ancestry (P=2.82×10(-3)). Among European ancestry participants, 2 novel synonymous variants, rs1805126 and rs6599230, were associated with cardiac conduction. Our top signal, rs1805126 was associated with PR and QRS lengthening (P=3.35×10(-7) and P=2.69×10(-4), respectively) and rs6599230 was associated with PR shortening (P=2.67×10(-5)). CONCLUSIONS: By sequencing SCN5A, we identified novel common and rare coding variants associated with cardiac conduction.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Heart Conduction System; Heart Diseases; Humans; Male; Middle Aged; NAV1.5 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Shared genetic susceptibility to ischemic stroke and coronary artery disease: a genome-wide analysis of common variants. - Dichgans, Martin; Malik, Rainer; König, Inke R; Rosand, Jonathan; Clarke, Robert; Gretarsdottir, Solveig; Thorleifsson, Gudmar; Mitchell, Braxton D; Assimes, Themistocles L; Levi, Christopher; O'Donnell, Christopher J; Fornage, Myriam; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Ischemic stroke (IS) and coronary artery disease (CAD) share several risk factors and each has a substantial heritability. We conducted a genome-wide analysis to evaluate the extent of shared genetic determination of the two diseases. METHODS: Genome-wide association data were obtained from the METASTROKE, Coronary Artery Disease Genome-wide Replication and Meta-analysis (CARDIoGRAM), and Coronary Artery Disease (C4D) Genetics consortia. We first analyzed common variants reaching a nominal threshold of significance (P<0.01) for CAD for their association with IS and vice versa. We then examined specific overlap across phenotypes for variants that reached a high threshold of significance. Finally, we conducted a joint meta-analysis on the combined phenotype of IS or CAD. Corresponding analyses were performed restricted to the 2167 individuals with the ischemic large artery stroke (LAS) subtype. RESULTS: Common variants associated with CAD at P<0.01 were associated with a significant excess risk for IS and for LAS and vice versa. Among the 42 known genome-wide significant loci for CAD, 3 and 5 loci were significantly associated with IS and LAS, respectively. In the joint meta-analyses, 15 loci passed genome-wide significance (P<5×10(-8)) for the combined phenotype of IS or CAD and 17 loci passed genome-wide significance for LAS or CAD. Because these loci had prior evidence for genome-wide significance for CAD, we specifically analyzed the respective signals for IS and LAS and found evidence for association at chr12q24/SH2B3 (PIS=1.62×10(-7)) and ABO (PIS=2.6×10(-4)), as well as at HDAC9 (PLAS=2.32×10(-12)), 9p21 (PLAS=3.70×10(-6)), RAI1-PEMT-RASD1 (PLAS=2.69×10(-5)), EDNRA (PLAS=7.29×10(-4)), and CYP17A1-CNNM2-NT5C2 (PLAS=4.9×10(-4)). CONCLUSIONS: Our results demonstrate substantial overlap in the genetic risk of IS and particularly the LAS subtype with CAD.
Keywords: Brain Ischemia; Coronary Artery Disease; Data Interpretation, Statistical; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Phenotype; Polymorphism, Single Nucleotide; Reproducibility of Results; Risk Factors; Stroke

Sleep duration does not mediate or modify association of common genetic variants with type 2 diabetes. - Tare, Archana; Lane, Jacqueline M; Cade, Brian E; Grant, Struan F A; Chen, Ting-Hsu; Punjabi, Naresh M; Lauderdale, Diane S; Zee, Phyllis C; Gharib, Sina A; Gottlieb, Daniel J; Scheer, Frank A J L; Redline, Susan; et al. (Diabetologia, 2014)
AIMS/HYPOTHESIS: Short and long sleep duration are associated with increased risk of type 2 diabetes. We aimed to investigate whether genetic variants for fasting glucose or type 2 diabetes associate with short or long sleep duration and whether sleep duration modifies the association of genetic variants with these traits. METHODS: We examined the cross-sectional relationship between self-reported habitual sleep duration and prevalence of type 2 diabetes in individuals of European descent participating in five studies included in the Candidate Gene Association Resource (CARe), totalling 1,474 cases and 8,323 controls. We tested for association of 16 fasting glucose-associated variants, 27 type 2 diabetes-associated variants and aggregate genetic risk scores with continuous and dichotomised (≤5 h or ≥9 h) sleep duration using regression models adjusted for age, sex and BMI. Finally, we tested whether a gene × behaviour interaction of variants with sleep duration had an impact on fasting glucose or type 2 diabetes risk. RESULTS: Short sleep duration was significantly associated with type 2 diabetes in CARe (OR 1.32; 95% CI 1.08, 1.61; p = 0.008). Variants previously associated with fasting glucose or type 2 diabetes and genetic risk scores were not associated with sleep duration. Furthermore, no study-wide significant interaction was observed between sleep duration and these variants on glycaemic traits. Nominal interactions were observed for sleep duration and PPARG rs1801282, CRY2 rs7943320 and HNF1B rs4430796 in influencing risk of type 2 diabetes (p < 0.05). CONCLUSIONS/INTERPRETATION: Our findings suggest that differences in habitual sleep duration do not mediate or modify the relationship between common variants underlying glycaemic traits (including in circadian rhythm genes) and diabetes.
Keywords: Blood Glucose; Body Composition; Body Mass Index; Cross-Sectional Studies; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Fasting; Female; Genetic Predisposition to Disease; Genetic Variation; Genotype; Glucose Intolerance; Glycated Hemoglobin A; Humans; Insulin Resistance; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Sleep; Surveys and Questionnaires; Time Factors; United States

Strategies to design and analyze targeted sequencing data: cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Lin, Honghuang; Wang, Min; Brody, Jennifer A; Bis, Joshua C; Dupuis, Josée; Lumley, Thomas; McKnight, Barbara; Rice, Kenneth M; Sitlani, Colleen M; Reid, Jeffrey G; Bressler, Jan; Liu, Xiaoming; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Genome-wide association studies have identified thousands of genetic variants that influence a variety of diseases and health-related quantitative traits. However, the causal variants underlying the majority of genetic associations remain unknown. Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study aims to follow up genome-wide association study signals and identify novel associations of the allelic spectrum of identified variants with cardiovascular-related traits. METHODS AND RESULTS: The study included 4231 participants from 3 CHARGE cohorts: the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, and the Framingham Heart Study. We used a case-cohort design in which we selected both a random sample of participants and participants with extreme phenotypes for each of 14 traits. We sequenced and analyzed 77 genomic loci, which had previously been associated with ≥1 of 14 phenotypes. A total of 52 736 variants were characterized by sequencing and passed our stringent quality control criteria. For common variants (minor allele frequency ≥1%), we performed unweighted regression analyses to obtain P values for associations and weighted regression analyses to obtain effect estimates that accounted for the sampling design. For rare variants, we applied 2 approaches: collapsed aggregate statistics and joint analysis of variants using the sequence kernel association test. CONCLUSIONS: We sequenced 77 genomic loci in participants from 3 cohorts. We established a set of filters to identify high-quality variants and implemented statistical and bioinformatics strategies to analyze the sequence data and identify potentially functional variants within genome-wide association study loci.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Genetic Variation; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Research Design; Sequence Analysis, DNA

Targeted sequencing in candidate genes for atrial fibrillation: the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Targeted Sequencing Study. - Lin, Honghuang; Sinner, Moritz F; Brody, Jennifer A; Arking, Dan E; Lunetta, Kathryn L; Rienstra, Michiel; Lubitz, Steven A; Magnani, Jared W; Sotoodehnia, Nona; McKnight, Barbara; McManus, David D; Boerwinkle, Eric; et al. (Heart Rhythm, 2014)
BACKGROUND: Genome-wide association studies (GWAS) have identified common genetic variants that predispose to atrial fibrillation (AF). It is unclear whether rare and low-frequency variants in genes implicated by such GWAS confer additional risk of AF. OBJECTIVE: To study the association of genetic variants with AF at GWAS top loci. METHODS: In the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Targeted Sequencing Study, we selected and sequenced 77 target gene regions from GWAS loci of complex diseases or traits, including 4 genes hypothesized to be related to AF (PRRX1, CAV1, CAV2, and ZFHX3). Sequencing was performed in participants with (n = 948) and without (n = 3330) AF from the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Massachusetts General Hospital. RESULTS: One common variant (rs11265611; P = 1.70 × 10(-6)) intronic to IL6R (interleukin-6 receptor gene) was significantly associated with AF after Bonferroni correction (odds ratio 0.70; 95% confidence interval 0.58-0.85). The variant was not genotyped or imputed by prior GWAS, but it is in linkage disequilibrium (r(2) = .69) with the single-nucleotide polymorphism, with the strongest association with AF so far at this locus (rs4845625). In the rare variant joint analysis, damaging variants within the PRRX1 region showed significant association with AF after Bonferroni correction (P = .01). CONCLUSIONS: We identified 1 common single-nucleotide polymorphism and 1 gene region that were significantly associated with AF. Future sequencing efforts with larger sample sizes and more comprehensive genome coverage are anticipated to identify additional AF-related variants.
Keywords: Aged; Atrial Fibrillation; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Homeodomain Proteins; Humans; Linkage Disequilibrium; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Interleukin-6

Telomere length and the risk of atrial fibrillation: insights into the role of biological versus chronological aging. - Roberts, Jason D; Dewland, Thomas A; Longoria, James; Fitzpatrick, Annette L; Ziv, Elad; Hu, Donglei; Lin, Jue; Glidden, David V; Psaty, Bruce M; Burchard, Esteban G; Blackburn, Elizabeth H; Olgin, Jeffrey E; et al. (Circ Arrhythm Electrophysiol, 2014)
BACKGROUND: Advanced age is the most important risk factor for atrial fibrillation (AF); however, the mechanism remains unknown. Telomeres, regions of DNA that shorten with cell division, are considered reliable markers of biological aging. We sought to examine the association between leukocyte telomere length (LTL) and incident AF in a large population-based cohort using direct LTL measurements and genetic data. To further explore our findings, we compared atrial cell telomere length and LTL in cardiac surgery patients. METHODS AND RESULTS: Mean LTL and the TERT rs2736100 single nucleotide polymorphism were assessed as predictors of incident AF in the Cardiovascular Health Study (CHS). Among the surgical patients, within subject comparison of atrial cell telomere length versus LTL was assessed. Among 1639 CHS participants, we observed no relationship between mean LTL and incident AF before and after adjustment for potential confounders (adjusted hazard ratio, 1.09; 95% confidence interval: 0.92-1.29; P=0.299); chronologic age remained strongly associated with AF in the same model. No association was observed between the TERT rs2736100 single nucleotide polymorphism and incident AF (adjusted hazard ratio: 0.95; 95% confidence interval: 0.88-1.04; P=0.265). In 35 cardiac surgery patients (26 with AF), atrial cell telomere length was longer than LTL (1.19 ± 0.20 versus 1.02 ± 0.25 [T/S ratio], P<0.001), a finding that remained consistent within the AF subgroup. CONCLUSIONS: Our study revealed no evidence of an association between LTL and incident AF and no evidence of relative atrial cell telomere shortening in AF. Chronological aging independent of biological markers of aging is the primary risk factor for AF.
Keywords: Age Factors; Aged; Aging; Atrial Fibrillation; California; Cardiac Surgical Procedures; Cellular Senescence; Cross-Sectional Studies; Female; Genetic Predisposition to Disease; Humans; Incidence; Leukocytes; Male; Phenotype; Polymorphism, Single Nucleotide; Prospective Studies; Risk Assessment; Risk Factors; Telomerase; Telomere; Time Factors

Trans-ethnic meta-analysis of white blood cell phenotypes. - Keller, Margaux F; Reiner, Alexander P; Okada, Yukinori; van Rooij, Frank J A; Johnson, Andrew D; Chen, Ming-Huei; Smith, Albert V; Morris, Andrew P; Tanaka, Toshiko; Ferrucci, Luigi; Zonderman, Alan B; Lettre, Guillaume; et al. (Hum Mol Genet, 2014)
White blood cell (WBC) count is a common clinical measure used as a predictor of certain aspects of human health, including immunity and infection status. WBC count is also a complex trait that varies among individuals and ancestry groups. Differences in linkage disequilibrium structure and heterogeneity in allelic effects are expected to play a role in the associations observed between populations. Prior genome-wide association study (GWAS) meta-analyses have identified genomic loci associated with WBC and its subtypes, but much of the heritability of these phenotypes remains unexplained. Using GWAS summary statistics for over 50 000 individuals from three diverse populations (Japanese, African-American and European ancestry), a Bayesian model methodology was employed to account for heterogeneity between ancestry groups. This approach was used to perform a trans-ethnic meta-analysis of total WBC, neutrophil and monocyte counts. Ten previously known associations were replicated and six new loci were identified, including several regions harboring genes related to inflammation and immune cell function. Ninety-five percent credible interval regions were calculated to narrow the association signals and fine-map the putatively causal variants within loci. Finally, a conditional analysis was performed on the most significant SNPs identified by the trans-ethnic meta-analysis (MA), and nine secondary signals within loci previously associated with WBC or its subtypes were identified. This work illustrates the potential of trans-ethnic analysis and ascribes a critical role to multi-ethnic cohorts and consortia in exploring complex phenotypes with respect to variants that lie outside the European-biased GWAS pool.
Keywords: African Americans; Asian Continental Ancestry Group; Bayes Theorem; European Continental Ancestry Group; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Leukocyte Count; Leukocytes; Linkage Disequilibrium; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Whole-exome sequencing identifies rare and low-frequency coding variants associated with LDL cholesterol. - Lange, Leslie A; Hu, Youna; Zhang, He; Xue, Chenyi; Schmidt, Ellen M; Tang, Zheng-Zheng; Bizon, Chris; Lange, Ethan M; Smith, Joshua D; Turner, Emily H; Jun, Goo; Kang, Hyun Min; et al. (Am J Hum Genet, 2014)
Elevated low-density lipoprotein cholesterol (LDL-C) is a treatable, heritable risk factor for cardiovascular disease. Genome-wide association studies (GWASs) have identified 157 variants associated with lipid levels but are not well suited to assess the impact of rare and low-frequency variants. To determine whether rare or low-frequency coding variants are associated with LDL-C, we exome sequenced 2,005 individuals, including 554 individuals selected for extreme LDL-C (>98(th) or <2(nd) percentile). Follow-up analyses included sequencing of 1,302 additional individuals and genotype-based analysis of 52,221 individuals. We observed significant evidence of association between LDL-C and the burden of rare or low-frequency variants in PNPLA5, encoding a phospholipase-domain-containing protein, and both known and previously unidentified variants in PCSK9, LDLR and APOB, three known lipid-related genes. The effect sizes for the burden of rare variants for each associated gene were substantially higher than those observed for individual SNPs identified from GWASs. We replicated the PNPLA5 signal in an independent large-scale sequencing study of 2,084 individuals. In conclusion, this large whole-exome-sequencing study for LDL-C identified a gene not known to be implicated in LDL-C and provides unique insight into the design and analysis of similar experiments.
Keywords: Adult; Aged; Apolipoproteins E; Cholesterol, LDL; Cohort Studies; Dyslipidemias; Exome; Female; Follow-Up Studies; Gene Frequency; Genetic Code; Genome-Wide Association Study; Genotype; Humans; Lipase; Male; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Proprotein Convertase 9; Proprotein Convertases; Receptors, LDL; Sequence Analysis, DNA; Serine Endopeptidases

Association of 25-Hydroxyvitamin D status and genetic variation in the vitamin D metabolic pathway with FEV1 in the Framingham Heart Study. - Hansen, J G; Gao, W; Dupuis, J; O'Connor, G T; Tang, W; Kowgier, M; Sood, A; Gharib, S A; Palmer, L J; Fornage, M; Heckbert, S R; Psaty, B M; et al. (Respir Res, 2015)
BACKGROUND: Vitamin D is associated with lung function in cross-sectional studies, and vitamin D inadequacy is hypothesized to play a role in the pathogenesis of chronic obstructive pulmonary disease. Further data are needed to clarify the relation between vitamin D status, genetic variation in vitamin D metabolic genes, and cross-sectional and longitudinal changes in lung function in healthy adults. METHODS: We estimated the association between serum 25-hydroxyvitamin D [25(OH)D] and cross-sectional forced expiratory volume in the first second (FEV1) in Framingham Heart Study (FHS) Offspring and Third Generation participants and the association between serum 25(OH)D and longitudinal change in FEV1 in Third Generation participants using linear mixed-effects models. Using a gene-based approach, we investigated the association between 241 SNPs in 6 select vitamin D metabolic genes in relation to longitudinal change in FEV1 in Offspring participants and pursued replication of these findings in a meta-analyzed set of 4 independent cohorts. RESULTS: We found a positive cross-sectional association between 25(OH)D and FEV1 in FHS Offspring and Third Generation participants (P=0.004). There was little or no association between 25(OH)D and longitudinal change in FEV1 in Third Generation participants (P=0.97). In Offspring participants, the CYP2R1 gene, hypothesized to influence usual serum 25(OH)D status, was associated with longitudinal change in FEV1 (gene-based P<0.05). The most significantly associated SNP from CYP2R1 had a consistent direction of association with FEV1 in the meta-analyzed set of replication cohorts, but the association did not reach statistical significance thresholds (P=0.09). CONCLUSIONS: Serum 25(OH)D status was associated with cross-sectional FEV1, but not longitudinal change in FEV1. The inconsistent associations may be driven by differences in the groups studied. CYP2R1 demonstrated a gene-based association with longitudinal change in FEV1 and is a promising candidate gene for further studies.
Keywords: Adult; Aged; Cohort Studies; Cross-Sectional Studies; DNA-Binding Proteins; Female; Genetic Variation; Humans; Longitudinal Studies; Male; Massachusetts; Metabolic Networks and Pathways; Middle Aged; Nuclear Proteins; Polymorphism, Single Nucleotide; Vitamin D

Association of Alzheimer's disease GWAS loci with MRI markers of brain aging. - Chauhan, Ganesh; Adams, Hieab H H; Bis, Joshua C; Weinstein, Galit; Yu, Lei; Töglhofer, Anna Maria; Smith, Albert Vernon; van der Lee, Sven J; Gottesman, Rebecca F; Thomson, Russell; Wang, Jing; Yang, Qiong; et al. (Neurobiol Aging, 2015)
Whether novel risk variants of Alzheimer's disease (AD) identified through genome-wide association studies also influence magnetic resonance imaging-based intermediate phenotypes of AD in the general population is unclear. We studied association of 24 AD risk loci with intracranial volume, total brain volume, hippocampal volume (HV), white matter hyperintensity burden, and brain infarcts in a meta-analysis of genetic association studies from large population-based samples (N = 8175-11,550). In single-SNP based tests, AD risk allele of APOE (rs2075650) was associated with smaller HV (p = 0.0054) and CD33 (rs3865444) with smaller intracranial volume (p = 0.0058). In gene-based tests, there was associations of HLA-DRB1 with total brain volume (p = 0.0006) and BIN1 with HV (p = 0.00089). A weighted AD genetic risk score was associated with smaller HV (beta ± SE = -0.047 ± 0.013, p = 0.00041), even after excluding the APOE locus (p = 0.029). However, only association of AD genetic risk score with HV, including APOE, was significant after multiple testing correction (including number of independent phenotypes tested). These results suggest that novel AD genetic risk variants may contribute to structural brain aging in nondemented older community persons.
Keywords: Aging; Alleles; Alzheimer Disease; Apolipoproteins E; Brain; Female; Genome-Wide Association Study; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Organ Size; Polymorphism, Single Nucleotide; Risk; Sialic Acid Binding Ig-like Lectin 3

Association of exome sequences with plasma C-reactive protein levels in >9000 participants. - Schick, Ursula M; Auer, Paul L; Bis, Joshua C; Lin, Honghuang; Wei, Peng; Pankratz, Nathan; Lange, Leslie A; Brody, Jennifer; Stitziel, Nathan O; Kim, Daniel S; Carlson, Christopher S; Fornage, Myriam; et al. (Hum Mol Genet, 2015)
C-reactive protein (CRP) concentration is a heritable systemic marker of inflammation that is associated with cardiovascular disease risk. Genome-wide association studies have identified CRP-associated common variants associated in ∼25 genes. Our aims were to apply exome sequencing to (1) assess whether the candidate loci contain rare coding variants associated with CRP levels and (2) perform an exome-wide search for rare variants in novel genes associated with CRP levels. We exome-sequenced 6050 European-Americans (EAs) and 3109 African-Americans (AAs) from the NHLBI-ESP and the CHARGE consortia, and performed association tests of sequence data with measured CRP levels. In single-variant tests across candidate loci, a novel rare (minor allele frequency = 0.16%) CRP-coding variant (rs77832441-A; p.Thr59Met) was associated with 53% lower mean CRP levels (P = 2.9 × 10(-6)). We replicated the association of rs77832441 in an exome array analysis of 11 414 EAs (P = 3.0 × 10(-15)). Despite a strong effect on CRP levels, rs77832441 was not associated with inflammation-related phenotypes including coronary heart disease. We also found evidence for an AA-specific association of APOE-ε2 rs7214 with higher CRP levels. At the exome-wide significance level (P < 5.0 × 10(-8)), we confirmed associations for reported common variants of HNF1A, CRP, IL6R and TOMM40-APOE. In gene-based tests, a burden of rare/lower frequency variation in CRP in EAs (P ≤ 6.8 × 10(-4)) and in retinoic acid receptor-related orphan receptor α (RORA) in AAs (P = 1.7 × 10(-3)) were associated with CRP levels at the candidate gene level (P < 2.0 × 10(-3)). This inquiry did not elucidate novel genes, but instead demonstrated that variants distributed across the allele frequency spectrum within candidate genes contribute to CRP levels.
Keywords: Adult; African Americans; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; European Continental Ancestry Group; Exome; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Hepatocyte Nuclear Factor 1-alpha; Humans; Male; Plasma; Polymorphism, Single Nucleotide; Receptors, Interleukin-6; Risk Factors

Coagulation factor XII genetic variation, ex vivo thrombin generation, and stroke risk in the elderly: results from the Cardiovascular Health Study. - Olson, N C; Butenas, S; Lange, L A; Lange, E M; Cushman, M; Jenny, N S; Walston, J; Souto, J C; Soria, J M; Chauhan, G; Debette, S; Longstreth, W T; et al. (J Thromb Haemost, 2015)
BACKGROUND: The relationships of thrombin generation (TG) with cardiovascular disease risk are underevaluated in population-based cohorts. OBJECTIVES: To evaluate the relationships of TG influenced by the contact and tissue factor coagulation pathways ex vivo with common single-nucleotide polymorphisms (SNPs) and incident cardiovascular disease and stroke. PATIENTS/METHODS: We measured peak TG (pTG) in baseline plasma samples of Cardiovascular Health Study participants (n = 5411), both with and without inhibitory anti-factor XIa antibody (pTG/FXIa(-) ). We evaluated their associations with ~ 50 000 SNPs by using the IBCv2 genotyping array, and with incident cardiovascular disease and stroke events over a median follow-up of 13.2 years. RESULTS: The minor allele for an SNP in the FXII gene (F12), rs1801020, was associated with lower pTG in European-Americans (β = - 34.2 ± 3.5 nm; P = 3.3 × 10(-22) ; minor allele frequency [MAF] = 0.23) and African-Americans (β = - 31.1 ± 7.9 nm; P = 9.0 × 10(-5) ; MAF = 0.42). Lower FXIa-independent pTG (pTG/FXIa(-) ) was associated with the F12 rs1801020 minor allele, and higher pTG/FXIa(-) was associated with the ABO SNP rs657152 minor allele (β = 16.3 nm; P = 4.3 × 10(-9) ; MAF = 0.37). The risk factor-adjusted ischemic stroke hazard ratios were 1.09 (95% confidence interval CI 1.01-1.17; P = 0.03) for pTG, 1.06 (95% CI 0.98-1.15; P = 0.17) for pTG/FXIa(-) , and 1.11 (95% CI 1.02-1.21; P = 0.02) for FXIa-dependent pTG (pTG/FXIa(+) ), per one standard deviation increment (n = 834 ischemic strokes). In a multicohort candidate gene analysis, rs1801020 was not associated with incident ischemic stroke (β = - 0.02; standard error = 0.08; P = 0.81). CONCLUSIONS: These results support the importance of contact activation pathway-dependent TG as a risk factor for ischemic stroke, and indicate the importance of F12 SNPs for TG ex vivo and in vivo.
Keywords: African Americans; Age Factors; Aged; Blood Coagulation; Brain Ischemia; European Continental Ancestry Group; Factor XII; Female; Gene Frequency; Genetic Predisposition to Disease; Humans; Incidence; Male; Phenotype; Polymorphism, Single Nucleotide; Prospective Studies; Risk Assessment; Risk Factors; Stroke; Thrombin; Time Factors; United States

Common variation in COL4A1/COL4A2 is associated with sporadic cerebral small vessel disease. - Rannikmae, Kristiina; Davies, Gail; Thomson, Pippa A; Bevan, Steve; Devan, William J; Falcone, Guido J; Traylor, Matthew; Anderson, Christopher D; Battey, Thomas W K; Radmanesh, Farid; Deka, Ranjan; Woo, Jessica G; et al. (Neurology, 2015)
OBJECTIVES: We hypothesized that common variants in the collagen genes COL4A1/COL4A2 are associated with sporadic forms of cerebral small vessel disease. METHODS: We conducted meta-analyses of existing genotype data among individuals of European ancestry to determine associations of 1,070 common single nucleotide polymorphisms (SNPs) in the COL4A1/COL4A2 genomic region with the following: intracerebral hemorrhage and its subtypes (deep, lobar) (1,545 cases, 1,485 controls); ischemic stroke and its subtypes (cardioembolic, large vessel disease, lacunar) (12,389 cases, 62,004 controls); and white matter hyperintensities (2,733 individuals with ischemic stroke and 9,361 from population-based cohorts with brain MRI data). We calculated a statistical significance threshold that accounted for multiple testing and linkage disequilibrium between SNPs (p < 0.000084). RESULTS: Three intronic SNPs in COL4A2 were significantly associated with deep intracerebral hemorrhage (lead SNP odds ratio [OR] 1.29, 95% confidence interval [CI] 1.14-1.46, p = 0.00003; r(2) > 0.9 between SNPs). Although SNPs associated with deep intracerebral hemorrhage did not reach our significance threshold for association with lacunar ischemic stroke (lead SNP OR 1.10, 95% CI 1.03-1.18, p = 0.0073), and with white matter hyperintensity volume in symptomatic ischemic stroke patients (lead SNP OR 1.07, 95% CI 1.01-1.13, p = 0.016), the direction of association was the same. There was no convincing evidence of association with white matter hyperintensities in population-based studies or with non-small vessel disease cerebrovascular phenotypes. CONCLUSIONS: Our results indicate an association between common variation in the COL4A2 gene and symptomatic small vessel disease, particularly deep intracerebral hemorrhage. These findings merit replication studies, including in ethnic groups of non-European ancestry.
Keywords: Cerebral Small Vessel Diseases; Collagen Type IV; Genetic Association Studies; Genetic Variation; Humans; Polymorphism, Single Nucleotide

Consumption of meat is associated with higher fasting glucose and insulin concentrations regardless of glucose and insulin genetic risk scores: a meta-analysis of 50,345 Caucasians. - Fretts, Amanda M; Follis, Jack L; Nettleton, Jennifer A; Lemaitre, Rozenn N; Ngwa, Julius S; Wojczynski, Mary K; Kalafati, Ioanna Panagiota; Varga, Tibor V; Frazier-Wood, Alexis C; Houston, Denise K; Lahti, Jari; Ericson, Ulrika; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Recent studies suggest that meat intake is associated with diabetes-related phenotypes. However, whether the associations of meat intake and glucose and insulin homeostasis are modified by genes related to glucose and insulin is unknown. OBJECTIVE: We investigated the associations of meat intake and the interaction of meat with genotype on fasting glucose and insulin concentrations in Caucasians free of diabetes mellitus. DESIGN: Fourteen studies that are part of the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium participated in the analysis. Data were provided for up to 50,345 participants. Using linear regression within studies and a fixed-effects meta-analysis across studies, we examined 1) the associations of processed meat and unprocessed red meat intake with fasting glucose and insulin concentrations; and 2) the interactions of processed meat and unprocessed red meat with genetic risk score related to fasting glucose or insulin resistance on fasting glucose and insulin concentrations. RESULTS: Processed meat was associated with higher fasting glucose, and unprocessed red meat was associated with both higher fasting glucose and fasting insulin concentrations after adjustment for potential confounders [not including body mass index (BMI)]. For every additional 50-g serving of processed meat per day, fasting glucose was 0.021 mmol/L (95% CI: 0.011, 0.030 mmol/L) higher. Every additional 100-g serving of unprocessed red meat per day was associated with a 0.037-mmol/L (95% CI: 0.023, 0.051-mmol/L) higher fasting glucose concentration and a 0.049-ln-pmol/L (95% CI: 0.035, 0.063-ln-pmol/L) higher fasting insulin concentration. After additional adjustment for BMI, observed associations were attenuated and no longer statistically significant. The association of processed meat and fasting insulin did not reach statistical significance after correction for multiple comparisons. Observed associations were not modified by genetic loci known to influence fasting glucose or insulin resistance. CONCLUSION: The association of higher fasting glucose and insulin concentrations with meat consumption was not modified by an index of glucose- and insulin-related single-nucleotide polymorphisms. Six of the participating studies are registered at clinicaltrials.gov as NCT0000513 (Atherosclerosis Risk in Communities), NCT00149435 (Cardiovascular Health Study), NCT00005136 (Family Heart Study), NCT00005121 (Framingham Heart Study), NCT00083369 (Genetics of Lipid Lowering Drugs and Diet Network), and NCT00005487 (Multi-Ethnic Study of Atherosclerosis).
Keywords: Blood Glucose; Cohort Studies; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hyperglycemia; Hyperinsulinism; Insulin; Insulin Resistance; Insulin-Secreting Cells; Meat; Meat Products; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Convergent genetic and expression data implicate immunity in Alzheimer's disease. (Alzheimers Dement, 2015)
BACKGROUND: Late-onset Alzheimer's disease (AD) is heritable with 20 genes showing genome-wide association in the International Genomics of Alzheimer's Project (IGAP). To identify the biology underlying the disease, we extended these genetic data in a pathway analysis. METHODS: The ALIGATOR and GSEA algorithms were used in the IGAP data to identify associated functional pathways and correlated gene expression networks in human brain. RESULTS: ALIGATOR identified an excess of curated biological pathways showing enrichment of association. Enriched areas of biology included the immune response (P = 3.27 × 10(-12) after multiple testing correction for pathways), regulation of endocytosis (P = 1.31 × 10(-11)), cholesterol transport (P = 2.96 × 10(-9)), and proteasome-ubiquitin activity (P = 1.34 × 10(-6)). Correlated gene expression analysis identified four significant network modules, all related to the immune response (corrected P = .002-.05). CONCLUSIONS: The immune response, regulation of endocytosis, cholesterol transport, and protein ubiquitination represent prime targets for AD therapeutics.
Keywords: Algorithms; Alzheimer Disease; Brain; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide

Dietary fatty acids modulate associations between genetic variants and circulating fatty acids in plasma and erythrocyte membranes: Meta-analysis of nine studies in the CHARGE consortium. - Smith, Caren E; Follis, Jack L; Nettleton, Jennifer A; Foy, Millennia; Wu, Jason H Y; Ma, Yiyi; Tanaka, Toshiko; Manichakul, Ani W; Wu, Hongyu; Chu, Audrey Y; Steffen, Lyn M; Fornage, Myriam; et al. (Mol Nutr Food Res, 2015)
SCOPE: Tissue concentrations of omega-3 fatty acids may reduce cardiovascular disease risk, and genetic variants are associated with circulating fatty acids concentrations. Whether dietary fatty acids interact with genetic variants to modify circulating omega-3 fatty acids is unclear. We evaluated interactions between genetic variants and fatty acid intakes for circulating alpha-linoleic acid, eicosapentaenoic acid, docosahexaenoic acid, and docosapentaenoic acid. METHODS AND RESULTS: We conducted meta-analyses (N = 11 668) evaluating interactions between dietary fatty acids and genetic variants (rs174538 and rs174548 in FADS1 (fatty acid desaturase 1), rs7435 in AGPAT3 (1-acyl-sn-glycerol-3-phosphate), rs4985167 in PDXDC1 (pyridoxal-dependent decarboxylase domain-containing 1), rs780094 in GCKR (glucokinase regulatory protein), and rs3734398 in ELOVL2 (fatty acid elongase 2)). Stratification by measurement compartment (plasma versus erthyrocyte) revealed compartment-specific interactions between FADS1 rs174538 and rs174548 and dietary alpha-linolenic acid and linoleic acid for docosahexaenoic acid and docosapentaenoic acid. CONCLUSION: Our findings reinforce earlier reports that genetically based differences in circulating fatty acids may be partially due to differences in the conversion of fatty acid precursors. Further, fatty acids measurement compartment may modify gene-diet relationships, and considering compartment may improve the detection of gene-fatty acids interactions for circulating fatty acid outcomes.
Keywords: Acetyltransferases; Acyltransferases; Adaptor Proteins, Signal Transducing; Carboxy-Lyases; Diet; Docosahexaenoic Acids; Eicosapentaenoic Acid; Erythrocyte Membrane; Fatty Acid Desaturases; Fatty Acids; Fatty Acids, Omega-3; Female; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Drug-Gene Interactions of Antihypertensive Medications and Risk of Incident Cardiovascular Disease: A Pharmacogenomics Study from the CHARGE Consortium. - Bis, Joshua C; Sitlani, Colleen; Irvin, Ryan; Avery, Christy L; Smith, Albert Vernon; Sun, Fangui; Evans, Daniel S; Musani, Solomon K; Li, Xiaohui; Trompet, Stella; Krijthe, Bouwe P; Harris, Tamara B; et al. (PLoS One, 2015)
BACKGROUND: Hypertension is a major risk factor for a spectrum of cardiovascular diseases (CVD), including myocardial infarction, sudden death, and stroke. In the US, over 65 million people have high blood pressure and a large proportion of these individuals are prescribed antihypertensive medications. Although large long-term clinical trials conducted in the last several decades have identified a number of effective antihypertensive treatments that reduce the risk of future clinical complications, responses to therapy and protection from cardiovascular events vary among individuals. METHODS: Using a genome-wide association study among 21,267 participants with pharmaceutically treated hypertension, we explored the hypothesis that genetic variants might influence or modify the effectiveness of common antihypertensive therapies on the risk of major cardiovascular outcomes. The classes of drug treatments included angiotensin-converting enzyme inhibitors, beta-blockers, calcium channel blockers, and diuretics. In the setting of the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, each study performed array-based genome-wide genotyping, imputed to HapMap Phase II reference panels, and used additive genetic models in proportional hazards or logistic regression models to evaluate drug-gene interactions for each of four therapeutic drug classes. We used meta-analysis to combine study-specific interaction estimates for approximately 2 million single nucleotide polymorphisms (SNPs) in a discovery analysis among 15,375 European Ancestry participants (3,527 CVD cases) with targeted follow-up in a case-only study of 1,751 European Ancestry GenHAT participants as well as among 4,141 African-Americans (1,267 CVD cases). RESULTS: Although drug-SNP interactions were biologically plausible, exposures and outcomes were well measured, and power was sufficient to detect modest interactions, we did not identify any statistically significant interactions from the four antihypertensive therapy meta-analyses (Pinteraction > 5.0×10-8). Similarly, findings were null for meta-analyses restricted to 66 SNPs with significant main effects on coronary artery disease or blood pressure from large published genome-wide association studies (Pinteraction ≥ 0.01). Our results suggest that there are no major pharmacogenetic influences of common SNPs on the relationship between blood pressure medications and the risk of incident CVD.
Keywords: African Americans; Aged; Antihypertensive Agents; Cardiovascular Diseases; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Hypertension; Incidence; Male; Middle Aged; Polymorphism, Single Nucleotide; Treatment Outcome

Fetuin-A and risk of coronary heart disease: A Mendelian randomization analysis and a pooled analysis of AHSG genetic variants in 7 prospective studies. - Laugsand, Lars E; Ix, Joachim H; Bartz, Traci M; Djoussé, Luc; Kizer, Jorge R; Tracy, Russell P; Dehghan, Abbas; Rexrode, Kathryn; Lopez, Oscar L; Rimm, Eric B; Siscovick, David S; O'Donnell, Christopher J; et al. (Atherosclerosis, 2015)
BACKGROUND AND AIMS: Fetuin-A has a plausible role in the inhibition of arterial calcification, but its association with risk of coronary heart disease (CHD) in the general population is unclear. We used two common genetic variants in the fetuin-A gene (AHSG) that are strongly associated with circulating fetuin-A levels to investigate the associations with risk of CHD and subclinical cardiovascular measures (intima-media thickness, ankle-arm index, and coronary artery calcification). METHODS: Genetic variation and fetuin-A levels were assessed in 3299 community-living individuals (2733 Caucasians and 566 African Americans) 65 years of age or older, free of previous cardiovascular disease, who participated in the Cardiovascular Health Study (CHS) in 1992-1993. RESULTS: Among Caucasians, both rs2248690 and rs4917 were associated with 12% lower fetuin-A concentrations per minor allele (P < 0.0001). The hazard ratios (HRs) per minor allele for incident CHD were 1.12 (95% CI: 1.00-1.26) for rs2248690 and 1.02 (0.91-1.14) for rs4917. Using both genotypes as an instrumental variable for measured fetuin-A, the HRs for one standard deviation increase in genetically determined fetuin-A levels on CHD risk were 0.84 (95% CI: 0.70-1.00) for rs2248690 and 0.97 (95% CI: 0.82-1.14) for rs4917, respectively. However, in CHS neither of the genotypes were associated with subclinical cardiovascular measures and when CHS data were meta-analyzed with data from six other prospective studies (totaling 26,702 Caucasian participants and 3295 CHD cases), the meta-analyzed HRs for incident CHD were 1.12 (0.93-1.34) and 1.06 (0.93-1.20) for rs2248690 and rs4917, respectively (p heterogeneity 0.005 and 0.0048). CONCLUSION: Common variants in the AHSG gene are strongly associated with fetuin-A levels, but their concurrent association with CHD risk in current prospective studies is inconsistent. Further investigation in studies with measured fetuin-A and AHSG variants is needed to clarify the potential causal association of fetuin-A with CHD risk.
Keywords: Aged; Aged, 80 and over; alpha-2-HS-Glycoprotein; Carotid Intima-Media Thickness; Coronary Vessels; Female; Genetic Variation; Genotype; Heart Diseases; Humans; Insulin Resistance; Longitudinal Studies; Male; Mendelian Randomization Analysis; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Vascular Calcification

Gene × dietary pattern interactions in obesity: analysis of up to 68 317 adults of European ancestry. - Nettleton, Jennifer A; Follis, Jack L; Ngwa, Julius S; Smith, Caren E; Ahmad, Shafqat; Tanaka, Toshiko; Wojczynski, Mary K; Voortman, Trudy; Lemaitre, Rozenn N; Kristiansson, Kati; Nuotio, Marja-Liisa; Houston, Denise K; et al. (Hum Mol Genet, 2015)
Obesity is highly heritable. Genetic variants showing robust associations with obesity traits have been identified through genome-wide association studies. We investigated whether a composite score representing healthy diet modifies associations of these variants with obesity traits. Totally, 32 body mass index (BMI)- and 14 waist-hip ratio (WHR)-associated single nucleotide polymorphisms were genotyped, and genetic risk scores (GRS) were calculated in 18 cohorts of European ancestry (n = 68 317). Diet score was calculated based on self-reported intakes of whole grains, fish, fruits, vegetables, nuts/seeds (favorable) and red/processed meats, sweets, sugar-sweetened beverages and fried potatoes (unfavorable). Multivariable adjusted, linear regression within each cohort followed by inverse variance-weighted, fixed-effects meta-analysis was used to characterize: (a) associations of each GRS with BMI and BMI-adjusted WHR and (b) diet score modification of genetic associations with BMI and BMI-adjusted WHR. Nominally significant interactions (P = 0.006-0.04) were observed between the diet score and WHR-GRS (but not BMI-GRS), two WHR loci (GRB14 rs10195252; LYPLAL1 rs4846567) and two BMI loci (LRRN6C rs10968576; MTIF3 rs4771122), for the respective BMI-adjusted WHR or BMI outcomes. Although the magnitudes of these select interactions were small, our data indicated that associations between genetic predisposition and obesity traits were stronger with a healthier diet. Our findings generate interesting hypotheses; however, experimental and functional studies are needed to determine their clinical relevance.
Keywords: Adult; Body Mass Index; Case-Control Studies; Diet, Western; Epistasis, Genetic; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Obesity; Polymorphism, Single Nucleotide

Gene-centric approach identifies new and known loci for FVIII activity and VWF antigen levels in European Americans and African Americans. - Tang, Weihong; Cushman, Mary; Green, David; Rich, Stephen S; Lange, Leslie A; Yang, Qiong; Tracy, Russell P; Tofler, Geoffrey H; Basu, Saonli; Wilson, James G; Keating, Brendan J; Weng, Lu-Chen; et al. (Am J Hematol, 2015)
Coagulation factor VIII and von Willebrand factor (VWF) are key proteins in procoagulant activation. Higher FVIII coagulant activity (FVIII :C) and VWF antigen (VWF :Ag) are risk factors for cardiovascular disease and venous thromboembolism. Beyond associations with ABO blood group, genetic determinants of FVIII and VWF are not well understood, especially in non European-American populations. We performed a genetic association study of FVIII :C and VWF:Ag that assessed 50,000 gene-centric single nucleotide polymorphisms (SNPs) in 18,556 European Americans (EAs) and 5,047 African Americans (AAs) from five population-based cohorts. Previously unreported associations for FVIII :C were identified in both AAs and EAs with KNG1 (most significantly associated SNP rs710446, Ile581Thr, Ile581Thr, P = 5.10 × 10(-7) in EAs and P = 3.88 × 10(-3) in AAs) and VWF rs7962217 (Gly2705Arg,P = 6.30 × 10(-9) in EAs and P = 2.98 × 10(-2) in AAs. Significant associations for FVIII :C were also observed with F8/TMLHE region SNP rs12557310 in EAs (P = 8.02 × 10(-10) ), with VWF rs1800380 in AAs (P = 5.62 × 10(-11) ), and with MAT1A rs2236568 in AAs (P51.69 × 10(-6) ). We replicated previously reported associations of FVIII :C and VWF :Ag with the ABO blood group, VWF rs1063856(Thr789Ala), rs216321 (Ala852Gln), and VWF rs2229446 (Arg2185Gln). Findings from this study expand our understanding of genetic influences for FVIII :C and VWF :Ag in both EAs and AAs.
Keywords: Adult; African Americans; Aged; European Continental Ancestry Group; Factor VIII; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Methionine Adenosyltransferase; Middle Aged; Polymorphism, Single Nucleotide; Venous Thromboembolism; von Willebrand Factor

Gene-Environment Interactions of Circadian-Related Genes for Cardiometabolic Traits. - Dashti, Hassan S; Follis, Jack L; Smith, Caren E; Tanaka, Toshiko; Garaulet, Marta; Gottlieb, Daniel J; Hruby, Adela; Jacques, Paul F; Kiefte-de Jong, Jessica C; Lamon-Fava, Stefania; Scheer, Frank A J L; Bartz, Traci M; et al. (Diabetes Care, 2015)
OBJECTIVE: Common circadian-related gene variants associate with increased risk for metabolic alterations including type 2 diabetes. However, little is known about whether diet and sleep could modify associations between circadian-related variants (CLOCK-rs1801260, CRY2-rs11605924, MTNR1B-rs1387153, MTNR1B-rs10830963, NR1D1-rs2314339) and cardiometabolic traits (fasting glucose [FG], HOMA-insulin resistance, BMI, waist circumference, and HDL-cholesterol) to facilitate personalized recommendations. RESEARCH DESIGN AND METHODS: We conducted inverse-variance weighted, fixed-effect meta-analyses of results of adjusted associations and interactions between dietary intake/sleep duration and selected variants on cardiometabolic traits from 15 cohort studies including up to 28,190 participants of European descent from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. RESULTS: We observed significant associations between relative macronutrient intakes and glycemic traits and short sleep duration (<7 h) and higher FG and replicated known MTNR1B associations with glycemic traits. No interactions were evident after accounting for multiple comparisons. However, we observed nominally significant interactions (all P < 0.01) between carbohydrate intake and MTNR1B-rs1387153 for FG with a 0.003 mmol/L higher FG with each additional 1% carbohydrate intake in the presence of the T allele, between sleep duration and CRY2-rs11605924 for HDL-cholesterol with a 0.010 mmol/L higher HDL-cholesterol with each additional hour of sleep in the presence of the A allele, and between long sleep duration (≥9 h) and MTNR1B-rs1387153 for BMI with a 0.60 kg/m(2) higher BMI with long sleep duration in the presence of the T allele relative to normal sleep duration (≥7 to <9 h). CONCLUSIONS: Our results suggest that lower carbohydrate intake and normal sleep duration may ameliorate cardiometabolic abnormalities conferred by common circadian-related genetic variants. Until further mechanistic examination of the nominally significant interactions is conducted, recommendations applicable to the general population regarding diet—specifically higher carbohydrate and lower fat composition—and normal sleep duration should continue to be emphasized among individuals with the investigated circadian-related gene variants.
Keywords: Adult; Alleles; Blood Glucose; Circadian Rhythm Signaling Peptides and Proteins; Cohort Studies; Diabetes Mellitus, Type 2; Diet, Fat-Restricted; European Continental Ancestry Group; Fasting; Female; Gene-Environment Interaction; Humans; Insulin Resistance; Male; Middle Aged; Multicenter Studies as Topic; Observational Studies as Topic; Phenotype; Polymorphism, Single Nucleotide; Sleep; Waist Circumference

Genes from a translational analysis support a multifactorial nature of white matter hyperintensities. - Lopez, Lorna M; Hill, W David; Harris, Sarah E; Valdes Hernandez, Maria; Munoz Maniega, Susana; Bastin, Mark E; Bailey, Emma; Smith, Colin; McBride, Martin; McClure, John; Graham, Delyth; Dominiczak, Anna; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: White matter hyperintensities (WMH) of presumed vascular origin increase the risk of stroke and dementia. Despite strong WMH heritability, few gene associations have been identified. Relevant experimental models may be informative. METHODS: We tested the associations between genes that were differentially expressed in brains of young spontaneously hypertensive stroke-prone rats and human WMH (using volume and visual score) in 621 subjects from the Lothian Birth Cohort 1936 (LBC1936). We then attempted replication in 9361 subjects from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE). We also tested the subjects from LBC1936 for previous genome-wide WMH associations found in subjects from CHARGE. RESULTS: Of 126 spontaneously hypertensive stroke-prone rat genes, 10 were nominally associated with WMH volume or score in subjects from LBC1936, of which 5 (AFP, ALB, GNAI1, RBM8a, and MRPL18) were associated with both WMH volume and score (P<0.05); 2 of the 10 (XPNPEP1, P=6.7×10(-5); FARP1, P=0.024) plus another spontaneously hypertensive stroke-prone rat gene (USMG5, P=0.00014), on chromosomes 10, 13, and 10 respectively, were associated with WMH in subjects from CHARGE. Gene set enrichment showed significant associations for downregulated spontaneously hypertensive stroke-prone rat genes with WMH in humans. In subjects from LBC1936, we replicated CHARGE's genome-wide WMH associations on chromosomes 17 (TRIM65 and TRIM47) and, for the first time, 1 (PMF1). CONCLUSIONS: Despite not passing multiple testing thresholds individually, these genes collectively are relevant to known WMH associations, proposed WMH mechanisms, or dementia: associations with Alzheimer's disease, late-life depression, ATP production, osmotic regulation, neurodevelopmental abnormalities, and cognitive impairment. If replicated further, they suggest a multifactorial nature for WMH and argue for more consideration of vascular contributions to dementia.
Keywords: Aged; Alzheimer Disease; Animals; Brain; Causality; Dementia; Female; Genome-Wide Association Study; Humans; Leukoencephalopathies; Male; Polymorphism, Single Nucleotide; Rats; Rats, Inbred SHR; Rats, Wistar; Risk Factors; Translational Medical Research; White Matter

Genetic contributions to variation in general cognitive function: a meta-analysis of genome-wide association studies in the CHARGE consortium (N=53949). - Davies, G; Armstrong, N; Bis, J C; Bressler, J; Chouraki, V; Giddaluru, S; Hofer, E; Ibrahim-Verbaas, C A; Kirin, M; Lahti, J; van der Lee, S J; Le Hellard, S; et al. (Mol Psychiatry, 2015)
General cognitive function is substantially heritable across the human life course from adolescence to old age. We investigated the genetic contribution to variation in this important, health- and well-being-related trait in middle-aged and older adults. We conducted a meta-analysis of genome-wide association studies of 31 cohorts (N=53,949) in which the participants had undertaken multiple, diverse cognitive tests. A general cognitive function phenotype was tested for, and created in each cohort by principal component analysis. We report 13 genome-wide significant single-nucleotide polymorphism (SNP) associations in three genomic regions, 6q16.1, 14q12 and 19q13.32 (best SNP and closest gene, respectively: rs10457441, P=3.93 × 10(-9), MIR2113; rs17522122, P=2.55 × 10(-8), AKAP6; rs10119, P=5.67 × 10(-9), APOE/TOMM40). We report one gene-based significant association with the HMGN1 gene located on chromosome 21 (P=1 × 10(-6)). These genes have previously been associated with neuropsychiatric phenotypes. Meta-analysis results are consistent with a polygenic model of inheritance. To estimate SNP-based heritability, the genome-wide complex trait analysis procedure was applied to two large cohorts, the Atherosclerosis Risk in Communities Study (N=6617) and the Health and Retirement Study (N=5976). The proportion of phenotypic variation accounted for by all genotyped common SNPs was 29% (s.e.=5%) and 28% (s.e.=7%), respectively. Using polygenic prediction analysis, ~1.2% of the variance in general cognitive function was predicted in the Generation Scotland cohort (N=5487; P=1.5 × 10(-17)). In hypothesis-driven tests, there was significant association between general cognitive function and four genes previously associated with Alzheimer's disease: TOMM40, APOE, ABCG1 and MEF2C.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Cognition; Cognition Disorders; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; HMGN1 Protein; Humans; Male; Middle Aged; Neuropsychological Tests; Phenotype; Polymorphism, Single Nucleotide; Scotland

Genetic loci associated with circulating phospholipid trans fatty acids: a meta-analysis of genome-wide association studies from the CHARGE Consortium. - Mozaffarian, Dariush; Kabagambe, Edmond K; Johnson, Catherine O; Lemaitre, Rozenn N; Manichaikul, Ani; Sun, Qi; Foy, Millennia; Wang, Lu; Wiener, Howard; Irvin, Marguerite R; Rich, Stephen S; Wu, Hongyu; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Circulating trans fatty acids (TFAs), which cannot be synthesized by humans, are linked to adverse health outcomes. Although TFAs are obtained from diet, little is known about subsequent influences (e.g., relating to incorporation, metabolism, or intercompetition with other fatty acids) that could alter circulating concentrations and possibly modulate or mediate impacts on health. OBJECTIVE: The objective was to elucidate novel biologic pathways that may influence circulating TFAs by evaluating associations between common genetic variation and TFA biomarkers. DESIGN: We performed meta-analyses using 7 cohorts of European-ancestry participants (n = 8013) having measured genome-wide variation in single-nucleotide polymorphisms (SNPs) and circulating TFA biomarkers (erythrocyte or plasma phospholipids), including trans-16:1n-7, total trans-18:1, trans/cis-18:2, cis/trans-18:2, and trans/trans-18:2. We further evaluated SNPs with genome-wide significant associations among African Americans (n = 1082), Chinese Americans (n = 669), and Hispanic Americans (n = 657) from 2 of these cohorts. RESULTS: Among European-ancestry participants, 31 SNPs in or near the fatty acid desaturase (FADS) 1 and 2 cluster were associated with cis/trans-18:2; a top hit was rs174548 (β = 0.0035, P = 4.90 × 10(-15)), an SNP previously associated with circulating n-3 and n-6 polyunsaturated fatty acid concentrations. No significant association was identified for other TFAs. rs174548 in FADS1/2 was also associated with cis/trans-18:2 in Hispanic Americans (β = 0.0053, P = 1.05 × 10(-6)) and Chinese Americans (β = 0.0028, P = 0.002) but not African Americans (β = 0.0009, P = 0.34); however, in African Americans, fine mapping identified a top hit in FADS2 associated with cis/trans-18:2 (rs174579: β = 0.0118, P = 4.05 × 10(-5)). The association between rs174548 and cis/trans-18:2 remained significant after further adjustment for individual circulating n-3 and n-6 fatty acids, except arachidonic acid. After adjustment for arachidonic acid concentrations, the association between rs174548 and cis/trans-18:2 was nearly eliminated in European-ancestry participants (β-coefficient reduced by 86%), with similar reductions in Hispanic Americans and Chinese Americans. CONCLUSIONS: Our findings provide novel evidence for genetic regulation of cis/trans-18:2 by the FADS1/2 cluster and suggest that this regulation may be influenced/mediated by concentrations of arachidonic acid, an n-6 polyunsaturated fat.
Keywords: African Americans; Arachidonic Acid; Asian Americans; Biomarkers; European Continental Ancestry Group; Fatty Acids, Omega-6; Gene Frequency; Genetic Association Studies; Genetic Loci; Genotyping Techniques; Humans; Phospholipids; Polymorphism, Single Nucleotide; Trans Fatty Acids

Genetic overlap between diagnostic subtypes of ischemic stroke. - Holliday, Elizabeth G; Traylor, Matthew; Malik, Rainer; Bevan, Steve; Falcone, Guido; Hopewell, Jemma C; Cheng, Yu-Ching; Cotlarciuc, Ioana; Bis, Joshua C; Boerwinkle, Eric; Boncoraglio, Giorgio B; Clarke, Robert; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: Despite moderate heritability, the phenotypic heterogeneity of ischemic stroke has hampered gene discovery, motivating analyses of diagnostic subtypes with reduced sample sizes. We assessed evidence for a shared genetic basis among the 3 major subtypes: large artery atherosclerosis (LAA), cardioembolism, and small vessel disease (SVD), to inform potential cross-subtype analyses. METHODS: Analyses used genome-wide summary data for 12 389 ischemic stroke cases (including 2167 LAA, 2405 cardioembolism, and 1854 SVD) and 62 004 controls from the Metastroke consortium. For 4561 cases and 7094 controls, individual-level genotype data were also available. Genetic correlations between subtypes were estimated using linear mixed models and polygenic profile scores. Meta-analysis of a combined LAA-SVD phenotype (4021 cases and 51 976 controls) was performed to identify shared risk alleles. RESULTS: High genetic correlation was identified between LAA and SVD using linear mixed models (rg=0.96, SE=0.47, P=9×10(-4)) and profile scores (rg=0.72; 95% confidence interval, 0.52-0.93). Between LAA and cardioembolism and SVD and cardioembolism, correlation was moderate using linear mixed models but not significantly different from zero for profile scoring. Joint meta-analysis of LAA and SVD identified strong association (P=1×10(-7)) for single nucleotide polymorphisms near the opioid receptor μ1 (OPRM1) gene. CONCLUSIONS: Our results suggest that LAA and SVD, which have been hitherto treated as genetically distinct, may share a substantial genetic component. Combined analyses of LAA and SVD may increase power to identify small-effect alleles influencing shared pathophysiological processes.
Keywords: Alleles; Atherosclerosis; Cerebral Small Vessel Diseases; Cohort Studies; Data Interpretation, Statistical; Embolism; Genome-Wide Association Study; Genotype; Humans; Ischemia; Linear Models; Meta-Analysis as Topic; Phenotype; Polymorphism, Single Nucleotide; Stroke

Genome-Wide Association Study and Linkage Analysis of the Healthy Aging Index. - Minster, Ryan L; Sanders, Jason L; Singh, Jatinder; Kammerer, Candace M; Barmada, M Michael; Matteini, Amy M; Zhang, Qunyuan; Wojczynski, Mary K; Daw, E Warwick; Brody, Jennifer A; Arnold, Alice M; Lunetta, Kathryn L; et al. (J Gerontol A Biol Sci Med Sci, 2015)
BACKGROUND: The Healthy Aging Index (HAI) is a tool for measuring the extent of health and disease across multiple systems. METHODS: We conducted a genome-wide association study and a genome-wide linkage analysis to map quantitative trait loci associated with the HAI and a modified HAI weighted for mortality risk in 3,140 individuals selected for familial longevity from the Long Life Family Study. The genome-wide association study used the Long Life Family Study as the discovery cohort and individuals from the Cardiovascular Health Study and the Framingham Heart Study as replication cohorts. RESULTS: There were no genome-wide significant findings from the genome-wide association study; however, several single-nucleotide polymorphisms near ZNF704 on chromosome 8q21.13 were suggestively associated with the HAI in the Long Life Family Study (p < 10(-) (6)) and nominally replicated in the Cardiovascular Health Study and Framingham Heart Study. Linkage results revealed significant evidence (log-odds score = 3.36) for a quantitative trait locus for mortality-optimized HAI in women on chromosome 9p24-p23. However, results of fine-mapping studies did not implicate any specific candidate genes within this region of interest. CONCLUSIONS: ZNF704 may be a potential candidate gene for studies of the genetic underpinnings of longevity.
Keywords: Aging; Apolipoproteins E; Forkhead Transcription Factors; Genetic Linkage; Genome-Wide Association Study; Humans; Longevity; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Genome-wide meta-analysis identifies six novel loci associated with habitual coffee consumption. - Cornelis, M C; Byrne, E M; Esko, T; Nalls, M A; Ganna, A; Paynter, N; Monda, K L; Amin, N; Fischer, K; Renstrom, F; Ngwa, J S; Huikari, V; et al. (Mol Psychiatry, 2015)
Coffee, a major dietary source of caffeine, is among the most widely consumed beverages in the world and has received considerable attention regarding health risks and benefits. We conducted a genome-wide (GW) meta-analysis of predominately regular-type coffee consumption (cups per day) among up to 91,462 coffee consumers of European ancestry with top single-nucleotide polymorphisms (SNPs) followed-up in ~30 062 and 7964 coffee consumers of European and African-American ancestry, respectively. Studies from both stages were combined in a trans-ethnic meta-analysis. Confirmed loci were examined for putative functional and biological relevance. Eight loci, including six novel loci, met GW significance (log10Bayes factor (BF)>5.64) with per-allele effect sizes of 0.03-0.14 cups per day. Six are located in or near genes potentially involved in pharmacokinetics (ABCG2, AHR, POR and CYP1A2) and pharmacodynamics (BDNF and SLC6A4) of caffeine. Two map to GCKR and MLXIPL genes related to metabolic traits but lacking known roles in coffee consumption. Enhancer and promoter histone marks populate the regions of many confirmed loci and several potential regulatory SNPs are highly correlated with the lead SNP of each. SNP alleles near GCKR, MLXIPL, BDNF and CYP1A2 that were associated with higher coffee consumption have previously been associated with smoking initiation, higher adiposity and fasting insulin and glucose but lower blood pressure and favorable lipid, inflammatory and liver enzyme profiles (P<5 × 10(-8)).Our genetic findings among European and African-American adults reinforce the role of caffeine in mediating habitual coffee consumption and may point to molecular mechanisms underlying inter-individual variability in pharmacological and health effects of coffee.
Keywords: Adaptor Proteins, Signal Transducing; Basic Helix-Loop-Helix Leucine Zipper Transcription Factors; Brain-Derived Neurotrophic Factor; Coffea; Cytochrome P-450 CYP1A2; Food Habits; Genome-Wide Association Study; Humans; Phenotype; Polymorphism, Single Nucleotide

Genome-wide studies of verbal declarative memory in nondemented older people: the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. - Debette, Stephanie; Ibrahim Verbaas, Carla A; Bressler, Jan; Schuur, Maaike; Smith, Albert; Bis, Joshua C; Davies, Gail; Wolf, Christiane; Gudnason, Vilmundur; Chibnik, Lori B; Yang, Qiong; DeStefano, Anita L; et al. (Biol Psychiatry, 2015)
BACKGROUND: Memory performance in older persons can reflect genetic influences on cognitive function and dementing processes. We aimed to identify genetic contributions to verbal declarative memory in a community setting. METHODS: We conducted genome-wide association studies for paragraph or word list delayed recall in 19 cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, comprising 29,076 dementia- and stroke-free individuals of European descent, aged ≥45 years. Replication of suggestive associations (p < 5 × 10(-6)) was sought in 10,617 participants of European descent, 3811 African-Americans, and 1561 young adults. RESULTS: rs4420638, near APOE, was associated with poorer delayed recall performance in discovery (p = 5.57 × 10(-10)) and replication cohorts (p = 5.65 × 10(-8)). This association was stronger for paragraph than word list delayed recall and in the oldest persons. Two associations with specific tests, in subsets of the total sample, reached genome-wide significance in combined analyses of discovery and replication (rs11074779 [HS3ST4], p = 3.11 × 10(-8), and rs6813517 [SPOCK3], p = 2.58 × 10(-8)) near genes involved in immune response. A genetic score combining 58 independent suggestive memory risk variants was associated with increasing Alzheimer disease pathology in 725 autopsy samples. Association of memory risk loci with gene expression in 138 human hippocampus samples showed cis-associations with WDR48 and CLDN5, both related to ubiquitin metabolism. CONCLUSIONS: This largest study to date exploring the genetics of memory function in ~40,000 older individuals revealed genome-wide associations and suggested an involvement of immune and ubiquitin pathways.
Keywords: Aged; Aged, 80 and over; Aging; Apolipoproteins E; Claudin-5; Cohort Studies; Female; Genome-Wide Association Study; Genotype; Humans; Male; Memory Disorders; Middle Aged; Polymorphism, Single Nucleotide; Proteins; Proteoglycans; Regression Analysis; Sulfotransferases; Verbal Learning

GWAS of longevity in CHARGE consortium confirms APOE and FOXO3 candidacy. - Broer, Linda; Buchman, Aron S; Deelen, Joris; Evans, Daniel S; Faul, Jessica D; Lunetta, Kathryn L; Sebastiani, Paola; Smith, Jennifer A; Smith, Albert V; Tanaka, Toshiko; Yu, Lei; Arnold, Alice M; et al. (J Gerontol A Biol Sci Med Sci, 2015)
BACKGROUND: The genetic contribution to longevity in humans has been estimated to range from 15% to 25%. Only two genes, APOE and FOXO3, have shown association with longevity in multiple independent studies. METHODS: We conducted a meta-analysis of genome-wide association studies including 6,036 longevity cases, age ≥90 years, and 3,757 controls that died between ages 55 and 80 years. We additionally attempted to replicate earlier identified single nucleotide polymorphism (SNP) associations with longevity. RESULTS: In our meta-analysis, we found suggestive evidence for the association of SNPs near CADM2 (odds ratio [OR] = 0.81; p value = 9.66 × 10(-7)) and GRIK2 (odds ratio = 1.24; p value = 5.09 × 10(-8)) with longevity. When attempting to replicate findings earlier identified in genome-wide association studies, only the APOE locus consistently replicated. In an additional look-up of the candidate gene FOXO3, we found that an earlier identified variant shows a highly significant association with longevity when including published data with our meta-analysis (odds ratio = 1.17; p value = 1.85×10(-10)). CONCLUSIONS: We did not identify new genome-wide significant associations with longevity and did not replicate earlier findings except for APOE and FOXO3. Our inability to find new associations with survival to ages ≥90 years because longevity represents multiple complex traits with heterogeneous genetic underpinnings, or alternatively, that longevity may be regulated by rare variants that are not captured by standard genome-wide genotyping and imputation of common variants.
Keywords: Aged; Aged, 80 and over; Apolipoproteins E; Cell Adhesion Molecules; Cohort Studies; Female; Forkhead Box Protein O3; Forkhead Transcription Factors; Genome-Wide Association Study; Humans; Longevity; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Kainic Acid

Habitual sleep duration is associated with BMI and macronutrient intake and may be modified by CLOCK genetic variants. - Dashti, Hassan S; Follis, Jack L; Smith, Caren E; Tanaka, Toshiko; Cade, Brian E; Gottlieb, Daniel J; Hruby, Adela; Jacques, Paul F; Lamon-Fava, Stefania; Richardson, Kris; Saxena, Richa; Scheer, Frank A J L; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Short sleep duration has been associated with greater risks of obesity, hypertension, diabetes, and cardiovascular disease. Also, common genetic variants in the human Circadian Locomotor Output Cycles Kaput (CLOCK) show associations with ghrelin and total energy intake. OBJECTIVES: We examined associations between habitual sleep duration, body mass index (BMI), and macronutrient intake and assessed whether CLOCK variants modify these associations. DESIGN: We conducted inverse-variance weighted, fixed-effect meta-analyses of results of adjusted associations of sleep duration and BMI and macronutrient intake as percentages of total energy as well as interactions with CLOCK variants from 9 cohort studies including up to 14,906 participants of European descent from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. RESULTS: We observed a significant association between sleep duration and lower BMI (β ± SE = 0.16 ± 0.04, P < 0.0001) in the overall sample; however, associations between sleep duration and relative macronutrient intake were evident in age- and sex-stratified analyses only. We observed a significant association between sleep duration and lower saturated fatty acid intake in younger (aged 20-64 y) adults (men: 0.11 ± 0.06%, P = 0.03; women: 0.10 ± 0.05%, P = 0.04) and with lower carbohydrate (-0.31 ± 0.12%, P < 0.01), higher total fat (0.18 ± 0.09%, P = 0.05), and higher PUFA (0.05 ± 0.02%, P = 0.02) intakes in older (aged 65-80 y) women. In addition, the following 2 nominally significant interactions were observed: between sleep duration and rs12649507 on PUFA intake and between sleep duration and rs6858749 on protein intake. CONCLUSIONS: Our results indicate that longer habitual sleep duration is associated with lower BMI and age- and sex-specific favorable dietary behaviors. Differences in the relative intake of specific macronutrients associated with short sleep duration could, at least in part, explain previously reported associations between short sleep duration and chronic metabolic abnormalities. In addition, the influence of obesity-associated CLOCK variants on the association between sleep duration and macronutrient intake suggests that longer habitual sleep duration could ameliorate the genetic predisposition to obesity via a favorable dietary profile.
Keywords: Adult; Body Mass Index; CLOCK Proteins; Cohort Studies; Cross-Sectional Studies; Diet; Dietary Proteins; Energy Intake; European Continental Ancestry Group; Fatty Acids, Unsaturated; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Sleep; Young Adult

HMG-coenzyme A reductase inhibition, type 2 diabetes, and bodyweight: evidence from genetic analysis and randomised trials. - Swerdlow, Daniel I; Preiss, David; Kuchenbaecker, Karoline B; Holmes, Michael V; Engmann, Jorgen E L; Shah, Tina; Sofat, Reecha; Stender, Stefan; Johnson, Paul C D; Scott, Robert A; Leusink, Maarten; Verweij, Niek; et al. (Lancet, 2015)
BACKGROUND: Statins increase the risk of new-onset type 2 diabetes mellitus. We aimed to assess whether this increase in risk is a consequence of inhibition of 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR), the intended drug target. METHODS: We used single nucleotide polymorphisms in the HMGCR gene, rs17238484 (for the main analysis) and rs12916 (for a subsidiary analysis) as proxies for HMGCR inhibition by statins. We examined associations of these variants with plasma lipid, glucose, and insulin concentrations; bodyweight; waist circumference; and prevalent and incident type 2 diabetes. Study-specific effect estimates per copy of each LDL-lowering allele were pooled by meta-analysis. These findings were compared with a meta-analysis of new-onset type 2 diabetes and bodyweight change data from randomised trials of statin drugs. The effects of statins in each randomised trial were assessed using meta-analysis. FINDINGS: Data were available for up to 223 463 individuals from 43 genetic studies. Each additional rs17238484-G allele was associated with a mean 0·06 mmol/L (95% CI 0·05-0·07) lower LDL cholesterol and higher body weight (0·30 kg, 0·18-0·43), waist circumference (0·32 cm, 0·16-0·47), plasma insulin concentration (1·62%, 0·53-2·72), and plasma glucose concentration (0·23%, 0·02-0·44). The rs12916 SNP had similar effects on LDL cholesterol, bodyweight, and waist circumference. The rs17238484-G allele seemed to be associated with higher risk of type 2 diabetes (odds ratio [OR] per allele 1·02, 95% CI 1·00-1·05); the rs12916-T allele association was consistent (1·06, 1·03-1·09). In 129 170 individuals in randomised trials, statins lowered LDL cholesterol by 0·92 mmol/L (95% CI 0·18-1·67) at 1-year of follow-up, increased bodyweight by 0·24 kg (95% CI 0·10-0·38 in all trials; 0·33 kg, 95% CI 0·24-0·42 in placebo or standard care controlled trials and -0·15 kg, 95% CI -0·39 to 0·08 in intensive-dose vs moderate-dose trials) at a mean of 4·2 years (range 1·9-6·7) of follow-up, and increased the odds of new-onset type 2 diabetes (OR 1·12, 95% CI 1·06-1·18 in all trials; 1·11, 95% CI 1·03-1·20 in placebo or standard care controlled trials and 1·12, 95% CI 1·04-1·22 in intensive-dose vs moderate dose trials). INTERPRETATION: The increased risk of type 2 diabetes noted with statins is at least partially explained by HMGCR inhibition. FUNDING: The funding sources are cited at the end of the paper.
Keywords: Aged; Body Mass Index; Body Weight; Cholesterol, HDL; Cholesterol, LDL; Diabetes Mellitus, Type 2; Female; Genetic Testing; Humans; Hydroxymethylglutaryl CoA Reductases; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Male; Middle Aged; Polymorphism, Single Nucleotide; Randomized Controlled Trials as Topic; Risk Factors

Integrative pathway genomics of lung function and airflow obstruction. - Gharib, Sina A; Loth, Daan W; Soler Artigas, Maria; Birkland, Timothy P; Wilk, Jemma B; Wain, Louise V; Brody, Jennifer A; Obeidat, Ma'en; Hancock, Dana B; Tang, Wenbo; Rawal, Rajesh; Boezen, H Marike; et al. (Hum Mol Genet, 2015)
Chronic respiratory disorders are important contributors to the global burden of disease. Genome-wide association studies (GWASs) of lung function measures have identified several trait-associated loci, but explain only a modest portion of the phenotypic variability. We postulated that integrating pathway-based methods with GWASs of pulmonary function and airflow obstruction would identify a broader repertoire of genes and processes influencing these traits. We performed two independent GWASs of lung function and applied gene set enrichment analysis to one of the studies and validated the results using the second GWAS. We identified 131 significantly enriched gene sets associated with lung function and clustered them into larger biological modules involved in diverse processes including development, immunity, cell signaling, proliferation and arachidonic acid. We found that enrichment of gene sets was not driven by GWAS-significant variants or loci, but instead by those with less stringent association P-values. Next, we applied pathway enrichment analysis to a meta-analyzed GWAS of airflow obstruction. We identified several biologic modules that functionally overlapped with those associated with pulmonary function. However, differences were also noted, including enrichment of extracellular matrix (ECM) processes specifically in the airflow obstruction study. Network analysis of the ECM module implicated a candidate gene, matrix metalloproteinase 10 (MMP10), as a putative disease target. We used a knockout mouse model to functionally validate MMP10's role in influencing lung's susceptibility to cigarette smoke-induced emphysema. By integrating pathway analysis with population-based genomics, we unraveled biologic processes underlying pulmonary function traits and identified a candidate gene for obstructive lung disease.
Keywords: Airway Obstruction; Animals; Cell Proliferation; European Continental Ancestry Group; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Humans; Immune System; Lung; Male; Metabolic Networks and Pathways; Mice; Phenotype; Polymorphism, Single Nucleotide; Signal Transduction

Low-frequency and rare exome chip variants associate with fasting glucose and type 2 diabetes susceptibility. - Wessel, Jennifer; Chu, Audrey Y; Willems, Sara M; Wang, Shuai; Yaghootkar, Hanieh; Brody, Jennifer A; Dauriz, Marco; Hivert, Marie-France; Raghavan, Sridharan; Lipovich, Leonard; Hidalgo, Bertha; Fox, Keolu; et al. (Nat Commun, 2015)
Fasting glucose and insulin are intermediate traits for type 2 diabetes. Here we explore the role of coding variation on these traits by analysis of variants on the HumanExome BeadChip in 60,564 non-diabetic individuals and in 16,491 T2D cases and 81,877 controls. We identify a novel association of a low-frequency nonsynonymous SNV in GLP1R (A316T; rs10305492; MAF=1.4%) with lower FG (β=-0.09±0.01 mmol l(-1), P=3.4 × 10(-12)), T2D risk (OR[95%CI]=0.86[0.76-0.96], P=0.010), early insulin secretion (β=-0.07±0.035 pmolinsulin mmolglucose(-1), P=0.048), but higher 2-h glucose (β=0.16±0.05 mmol l(-1), P=4.3 × 10(-4)). We identify a gene-based association with FG at G6PC2 (pSKAT=6.8 × 10(-6)) driven by four rare protein-coding SNVs (H177Y, Y207S, R283X and S324P). We identify rs651007 (MAF=20%) in the first intron of ABO at the putative promoter of an antisense lncRNA, associating with higher FG (β=0.02±0.004 mmol l(-1), P=1.3 × 10(-8)). Our approach identifies novel coding variant associations and extends the allelic spectrum of variation underlying diabetes-related quantitative traits and T2D susceptibility.
Keywords: African Continental Ancestry Group; Blood Glucose; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Exome; Fasting; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Glucagon-Like Peptide-1 Receptor; Glucose-6-Phosphatase; Humans; Insulin; Mutation Rate; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide

Mendelian randomization of blood lipids for coronary heart disease. - Holmes, Michael V; Asselbergs, Folkert W; Palmer, Tom M; Drenos, Fotios; Lanktree, Matthew B; Nelson, Christopher P; Dale, Caroline E; Padmanabhan, Sandosh; Finan, Chris; Swerdlow, Daniel I; Tragante, Vinicius; van Iperen, Erik P A; et al. (Eur Heart J, 2015)
AIMS: To investigate the causal role of high-density lipoprotein cholesterol (HDL-C) and triglycerides in coronary heart disease (CHD) using multiple instrumental variables for Mendelian randomization. METHODS AND RESULTS: We developed weighted allele scores based on single nucleotide polymorphisms (SNPs) with established associations with HDL-C, triglycerides, and low-density lipoprotein cholesterol (LDL-C). For each trait, we constructed two scores. The first was unrestricted, including all independent SNPs associated with the lipid trait identified from a prior meta-analysis (threshold P < 2 × 10(-6)); and the second a restricted score, filtered to remove any SNPs also associated with either of the other two lipid traits at P ≤ 0.01. Mendelian randomization meta-analyses were conducted in 17 studies including 62,199 participants and 12,099 CHD events. Both the unrestricted and restricted allele scores for LDL-C (42 and 19 SNPs, respectively) associated with CHD. For HDL-C, the unrestricted allele score (48 SNPs) was associated with CHD (OR: 0.53; 95% CI: 0.40, 0.70), per 1 mmol/L higher HDL-C, but neither the restricted allele score (19 SNPs; OR: 0.91; 95% CI: 0.42, 1.98) nor the unrestricted HDL-C allele score adjusted for triglycerides, LDL-C, or statin use (OR: 0.81; 95% CI: 0.44, 1.46) showed a robust association. For triglycerides, the unrestricted allele score (67 SNPs) and the restricted allele score (27 SNPs) were both associated with CHD (OR: 1.62; 95% CI: 1.24, 2.11 and 1.61; 95% CI: 1.00, 2.59, respectively) per 1-log unit increment. However, the unrestricted triglyceride score adjusted for HDL-C, LDL-C, and statin use gave an OR for CHD of 1.01 (95% CI: 0.59, 1.75). CONCLUSION: The genetic findings support a causal effect of triglycerides on CHD risk, but a causal role for HDL-C, though possible, remains less certain.
Keywords: Case-Control Studies; Cholesterol, HDL; Coronary Artery Disease; Female; Gene Frequency; Genotype; Genotyping Techniques; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Polymorphism, Single Nucleotide; Risk Assessment; Triglycerides

Meta-Analysis of Genome-Wide Association Studies Identifies Genetic Risk Factors for Stroke in African Americans. - Carty, Cara L; Keene, Keith L; Cheng, Yu-Ching; Meschia, James F; Chen, Wei-Min; Nalls, Mike; Bis, Joshua C; Kittner, Steven J; Rich, Stephen S; Tajuddin, Salman; Zonderman, Alan B; Evans, Michele K; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: The majority of genome-wide association studies (GWAS) of stroke have focused on European-ancestry populations; however, none has been conducted in African Americans, despite the disproportionately high burden of stroke in this population. The Consortium of Minority Population Genome-Wide Association Studies of Stroke (COMPASS) was established to identify stroke susceptibility loci in minority populations. METHODS: Using METAL, we conducted meta-analyses of GWAS in 14 746 African Americans (1365 ischemic and 1592 total stroke cases) from COMPASS, and tested genetic variants with P<10(-6) for validation in METASTROKE, a consortium of ischemic stroke genetic studies in European-ancestry populations. We also evaluated stroke loci previously identified in European-ancestry populations. RESULTS: The 15q21.3 locus linked with lipid levels and hypertension was associated with total stroke (rs4471613; P=3.9×10(-8)) in African Americans. Nominal associations (P<10(-6)) for total or ischemic stroke were observed for 18 variants in or near genes implicated in cell cycle/mRNA presplicing (PTPRG, CDC5L), platelet function (HPS4), blood-brain barrier permeability (CLDN17), immune response (ELTD1, WDFY4, and IL1F10-IL1RN), and histone modification (HDAC9). Two of these loci achieved nominal significance in METASTROKE: 5q35.2 (P=0.03), and 1p31.1 (P=0.018). Four of 7 previously reported ischemic stroke loci (PITX2, HDAC9, CDKN2A/CDKN2B, and ZFHX3) were nominally associated (P<0.05) with stroke in COMPASS. CONCLUSIONS: We identified a novel genetic variant associated with total stroke in African Americans and found that ischemic stroke loci identified in European-ancestry populations may also be relevant for African Americans. Our findings support investigation of diverse populations to identify and characterize genetic risk factors, and the importance of shared genetic risk across populations.
Keywords: African Americans; Case-Control Studies; Cohort Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors; Stroke

Novel loci associated with usual sleep duration: the CHARGE Consortium Genome-Wide Association Study. - Gottlieb, D J; Hek, K; Chen, T-H; Watson, N F; Eiriksdottir, G; Byrne, E M; Cornelis, M; Warby, S C; Bandinelli, S; Cherkas, L; Evans, D S; Grabe, H J; et al. (Mol Psychiatry, 2015)
Usual sleep duration is a heritable trait correlated with psychiatric morbidity, cardiometabolic disease and mortality, although little is known about the genetic variants influencing this trait. A genome-wide association study (GWAS) of usual sleep duration was conducted using 18 population-based cohorts totaling 47 180 individuals of European ancestry. Genome-wide significant association was identified at two loci. The strongest is located on chromosome 2, in an intergenic region 35- to 80-kb upstream from the thyroid-specific transcription factor PAX8 (lowest P=1.1 × 10(-9)). This finding was replicated in an African-American sample of 4771 individuals (lowest P=9.3 × 10(-4)). The strongest combined association was at rs1823125 (P=1.5 × 10(-10), minor allele frequency 0.26 in the discovery sample, 0.12 in the replication sample), with each copy of the minor allele associated with a sleep duration 3.1 min longer per night. The alleles associated with longer sleep duration were associated in previous GWAS with a more favorable metabolic profile and a lower risk of attention deficit hyperactivity disorder. Understanding the mechanisms underlying these associations may help elucidate biological mechanisms influencing sleep duration and its association with psychiatric, metabolic and cardiovascular disease.
Keywords: Adult; African Americans; Aged; Dyssomnias; European Continental Ancestry Group; Female; Genetic Association Studies; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Self Report; Sleep

Plasma Levels of Soluble Interleukin-2 Receptor α: Associations With Clinical Cardiovascular Events and Genome-Wide Association Scan. - Durda, Peter; Sabourin, Jeremy; Lange, Ethan M; Nalls, Mike A; Mychaleckyj, Josyf C; Jenny, Nancy Swords; Li, Jin; Walston, Jeremy; Harris, Tamara B; Psaty, Bruce M; Valdar, William; Liu, Yongmei; et al. (Arterioscler Thromb Vasc Biol, 2015)
OBJECTIVE: Interleukin (IL) -2 receptor subunit α regulates lymphocyte activation, which plays an important role in atherosclerosis. Associations between soluble IL-2Rα (sIL-2Rα) and cardiovascular disease (CVD) have not been widely studied and little is known about the genetic determinants of sIL-2Rα levels. APPROACH AND RESULTS: We measured baseline levels of sIL-2Rα in 4408 European American (EA) and 766 African American (AA) adults from the Cardiovascular Health Study (CHS) and examined associations with baseline CVD risk factors, subclinical CVD, and incident CVD events. We also performed a genome-wide association study for sIL-2Rα in CHS (2964 EAs and 683 AAs) and further combined CHS EA results with those from two other EA cohorts in a meta-analysis (n=4464 EAs). In age, sex- and race- adjusted models, sIL-2Rα was positively associated with current smoking, type 2 diabetes mellitus, hypertension, insulin, waist circumference, C-reactive protein, IL-6, fibrinogen, internal carotid wall thickness, all-cause mortality, CVD mortality, and incident CVD, stroke, and heart failure. When adjusted for baseline CVD risk factors and subclinical CVD, associations with all-cause mortality, CVD mortality, and heart failure remained significant in both EAs and AAs. In the EA genome-wide association study analysis, we observed 52 single-nucleotide polymorphisms in the chromosome 10p15-14 region, which contains IL2RA, IL15RA, and RMB17, that reached genome-wide significance (P<5×10(-8)). The most significant single-nucleotide polymorphism was rs7911500 (P=1.31×10(-75)). The EA meta-analysis results were highly consistent with CHS-only results. No single-nucleotide polymorphisms reached statistical significance in the AAs. CONCLUSIONS: These results support a role for sIL-2Rα in atherosclerosis and provide evidence for multiple-associated single-nucleotide polymorphisms at chromosome 10p15-14.
Keywords: Adult; African Americans; Age Distribution; Aged; Cardiovascular Diseases; Cohort Studies; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Incidence; Interleukin-2 Receptor alpha Subunit; Kaplan-Meier Estimate; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Prospective Studies; Risk Assessment; Sex Distribution; Survival Analysis

Population genomic analysis of 962 whole genome sequences of humans reveals natural selection in non-coding regions. - Yu, Fuli; Lu, Jian; Liu, Xiaoming; Gazave, Elodie; Chang, Diana; Raj, Srilakshmi; Hunter-Zinck, Haley; Blekhman, Ran; Arbiza, Leonardo; Van Hout, Cris; Morrison, Alanna; Johnson, Andrew D; et al. (PLoS One, 2015)
Whole genome analysis in large samples from a single population is needed to provide adequate power to assess relative strengths of natural selection across different functional components of the genome. In this study, we analyzed next-generation sequencing data from 962 European Americans, and found that as expected approximately 60% of the top 1% of positive selection signals lie in intergenic regions, 33% in intronic regions, and slightly over 1% in coding regions. Several detailed functional annotation categories in intergenic regions showed statistically significant enrichment in positively selected loci when compared to the null distribution of the genomic span of ENCODE categories. There was a significant enrichment of purifying selection signals detected in enhancers, transcription factor binding sites, microRNAs and target sites, but not on lincRNA or piRNAs, suggesting different evolutionary constraints for these domains. Loci in "repressed or low activity regions" and loci near or overlapping the transcription start site were the most significantly over-represented annotations among the top 1% of signals for positive selection.
Keywords: DNA, Intergenic; Genetic Loci; Humans; Metagenomics; Open Reading Frames; Polymorphism, Single Nucleotide

Prospective study of circulating factor XI and incident venous thromboembolism: The Longitudinal Investigation of Thromboembolism Etiology (LITE). - Folsom, Aaron R; Tang, Weihong; Roetker, Nicholas S; Heckbert, Susan R; Cushman, Mary; Pankow, James S (Am J Hematol, 2015)
Elevated plasma concentrations of coagulation factor XI may increase risk of venous thromboembolism (VTE), but prospective data are limited. We studied prospectively the associations of plasma factor XI and a key F11 genetic variant with incident VTE in whites and African-Americans. We measured factor XI in 16,299 participants, initially free of VTE, in two prospective population cohorts. We also measured the F11 single nucleotide polymorphism rs4241824, which a genome-wide association study had linked to factor XI concentration. During follow-up, we identified 606 VTEs. The age, race, sex, and study-adjusted hazard ratio of VTE increased across factor XI quintiles (P < 0.001 for trend), and the hazard ratio was 1.51 (95% CI 1.16, 1.97) for the highest versus lowest quintile overall, and was 1.42 (95% CI 1.03, 1.95) in whites and 1.72 (95% CI 1.08, 2.73) in African-Americans. In whites, the F11 variant was associated with both factor XI concentration and VTE incidence (1.15-fold greater incidence of VTE per risk allele). In African-Americans, these associations were absent. In conclusion, this cohort study documented that an elevated plasma factor XI concentration is a risk factor for VTE over extended follow-up, not only in whites but also in African-Americans. In whites, the association of the F11 genetic variant with VTE suggests a causal relation, but we did not observe this genetic relation in African-Americans.
Keywords: African Americans; Aged; Alleles; European Continental Ancestry Group; Factor XI; Female; Gene Expression; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Prospective Studies; Risk Factors; United States; Venous Thromboembolism

Rare and low-frequency variants and their association with plasma levels of fibrinogen, FVII, FVIII, and vWF. - Huffman, Jennifer E; de Vries, Paul S; Morrison, Alanna C; Sabater-Lleal, Maria; Kacprowski, Tim; Auer, Paul L; Brody, Jennifer A; Chasman, Daniel I; Chen, Ming-Huei; Guo, Xiuqing; Lin, Li-An; Marioni, Riccardo E; et al. (Blood, 2015)
Fibrinogen, coagulation factor VII (FVII), and factor VIII (FVIII) and its carrier von Willebrand factor (vWF) play key roles in hemostasis. Previously identified common variants explain only a small fraction of the trait heritabilities, and additional variations may be explained by associations with rarer variants with larger effects. The aim of this study was to identify low-frequency (minor allele frequency [MAF] ≥0.01 and <0.05) and rare (MAF <0.01) variants that influence plasma concentrations of these 4 hemostatic factors by meta-analyzing exome chip data from up to 76,000 participants of 4 ancestries. We identified 12 novel associations of low-frequency (n = 2) and rare (n = 10) variants across the fibrinogen, FVII, FVIII, and vWF traits that were independent of previously identified associations. Novel loci were found within previously reported genes and had effect sizes much larger than and independent of previously identified common variants. In addition, associations at KCNT1, HID1, and KATNB1 identified new candidate genes related to hemostasis for follow-up replication and functional genomic analysis. Newly identified low-frequency and rare-variant associations accounted for modest amounts of trait variance and therefore are unlikely to increase predicted trait heritability but provide new information for understanding individual variation in hemostasis pathways.
Keywords: Cohort Studies; Factor VII; Factor VIII; Fibrinogen; Gene Frequency; Genetic Association Studies; Genetic Variation; Humans; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Potassium Channels; von Willebrand Factor

Common variants in DRD2 are associated with sleep duration: the CARe consortium. - Cade, Brian E; Gottlieb, Daniel J; Lauderdale, Diane S; Bennett, David A; Buchman, Aron S; Buxbaum, Sarah G; De Jager, Philip L; Evans, Daniel S; Fulop, Tibor; Gharib, Sina A; Johnson, W Craig; Kim, Hyun; et al. (Hum Mol Genet, 2016)
Sleep duration is implicated in the etiologies of chronic diseases and premature mortality. However, the genetic basis for sleep duration is poorly defined. We sought to identify novel genetic components influencing sleep duration in a multi-ethnic sample. Meta-analyses were conducted of genetic associations with self-reported, habitual sleep duration from seven Candidate Gene Association Resource (CARe) cohorts of over 25 000 individuals of African, Asian, European and Hispanic American ancestry. All individuals were genotyped for ∼50 000 SNPs from 2000 candidate heart, lung, blood and sleep genes. African-Americans had additional genome-wide genotypes. Four cohorts provided replication. A SNP (rs17601612) in the dopamine D2 receptor gene (DRD2) was significantly associated with sleep duration (P = 9.8 × 10(-7)). Conditional analysis identified a second DRD2 signal with opposite effects on sleep duration. In exploratory analysis, suggestive association was observed for rs17601612 with polysomnographically determined sleep latency (P = 0.002). The lead DRD2 signal was recently identified in a schizophrenia GWAS, and a genetic risk score of 11 additional schizophrenia GWAS loci genotyped on the IBC array was also associated with longer sleep duration (P = 0.03). These findings support a role for DRD2 in influencing sleep duration. Our work motivates future pharmocogenetics research on alerting agents such as caffeine and modafinil that interact with the dopaminergic pathway and further investigation of genetic overlap between sleep and neuro-psychiatric traits.
Keywords: Cohort Studies; Ethnic Groups; Humans; Polymorphism, Single Nucleotide; Polysomnography; Receptors, Dopamine D2; Sleep; Time Factors

Genome-Wide Association Analysis of Young-Onset Stroke Identifies a Locus on Chromosome 10q25 Near HABP2. - Cheng, Yu-Ching; Stanne, Tara M; Giese, Anne-Katrin; Ho, Weang Kee; Traylor, Matthew; Amouyel, Philippe; Holliday, Elizabeth G; Malik, Rainer; Xu, Huichun; Kittner, Steven J; Cole, John W; O'Connell, Jeffrey R; et al. (Stroke, 2016)
BACKGROUND AND PURPOSE: Although a genetic contribution to ischemic stroke is well recognized, only a handful of stroke loci have been identified by large-scale genetic association studies to date. Hypothesizing that genetic effects might be stronger for early- versus late-onset stroke, we conducted a 2-stage meta-analysis of genome-wide association studies, focusing on stroke cases with an age of onset <60 years. METHODS: The discovery stage of our genome-wide association studies included 4505 cases and 21 968 controls of European, South-Asian, and African ancestry, drawn from 6 studies. In Stage 2, we selected the lead genetic variants at loci with association P<5×10(-6) and performed in silico association analyses in an independent sample of ≤1003 cases and 7745 controls. RESULTS: One stroke susceptibility locus at 10q25 reached genome-wide significance in the combined analysis of all samples from the discovery and follow-up stages (rs11196288; odds ratio =1.41; P=9.5×10(-9)). The associated locus is in an intergenic region between TCF7L2 and HABP2. In a further analysis in an independent sample, we found that 2 single nucleotide polymorphisms in high linkage disequilibrium with rs11196288 were significantly associated with total plasma factor VII-activating protease levels, a product of HABP2. CONCLUSIONS: HABP2, which encodes an extracellular serine protease involved in coagulation, fibrinolysis, and inflammatory pathways, may be a genetic susceptibility locus for early-onset stroke.
Keywords: Adult; African Continental Ancestry Group; Age of Onset; Aged; Asian Continental Ancestry Group; Brain Ischemia; Chromosomes, Human, Pair 10; Computer Simulation; DNA, Intergenic; European Continental Ancestry Group; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide; Serine Endopeptidases; Stroke

Genome-Wide Association Study for Incident Myocardial Infarction and Coronary Heart Disease in Prospective Cohort Studies: The CHARGE Consortium. - Dehghan, Abbas; Bis, Joshua C; White, Charles C; Smith, Albert Vernon; Morrison, Alanna C; Cupples, L Adrienne; Trompet, Stella; Chasman, Daniel I; Lumley, Thomas; Völker, Uwe; Buckley, Brendan M; Ding, Jingzhong; et al. (PLoS One, 2016)
BACKGROUND: Data are limited on genome-wide association studies (GWAS) for incident coronary heart disease (CHD). Moreover, it is not known whether genetic variants identified to date also associate with risk of CHD in a prospective setting. METHODS: We performed a two-stage GWAS analysis of incident myocardial infarction (MI) and CHD in a total of 64,297 individuals (including 3898 MI cases, 5465 CHD cases). SNPs that passed an arbitrary threshold of 5×10-6 in Stage I were taken to Stage II for further discovery. Furthermore, in an analysis of prognosis, we studied whether known SNPs from former GWAS were associated with total mortality in individuals who experienced MI during follow-up. RESULTS: In Stage I 15 loci passed the threshold of 5×10-6; 8 loci for MI and 8 loci for CHD, for which one locus overlapped and none were reported in previous GWAS meta-analyses. We took 60 SNPs representing these 15 loci to Stage II of discovery. Four SNPs near QKI showed nominally significant association with MI (p-value<8.8×10-3) and three exceeded the genome-wide significance threshold when Stage I and Stage II results were combined (top SNP rs6941513: p = 6.2×10-9). Despite excellent power, the 9p21 locus SNP (rs1333049) was only modestly associated with MI (HR = 1.09, p-value = 0.02) and marginally with CHD (HR = 1.06, p-value = 0.08). Among an inception cohort of those who experienced MI during follow-up, the risk allele of rs1333049 was associated with a decreased risk of subsequent mortality (HR = 0.90, p-value = 3.2×10-3). CONCLUSIONS: QKI represents a novel locus that may serve as a predictor of incident CHD in prospective studies. The association of the 9p21 locus both with increased risk of first myocardial infarction and longer survival after MI highlights the importance of study design in investigating genetic determinants of complex disorders.
Keywords: Aged; Cohort Studies; Cooperative Behavior; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Myocardial Infarction; Polymorphism, Single Nucleotide; Prospective Studies

Interaction of methylation-related genetic variants with circulating fatty acids on plasma lipids: a meta-analysis of 7 studies and methylation analysis of 3 studies in the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium. - Ma, Yiyi; Follis, Jack L; Smith, Caren E; Tanaka, Toshiko; Manichaikul, Ani W; Chu, Audrey Y; Samieri, Cecilia; Zhou, Xia; Guan, Weihua; Wang, Lu; Biggs, Mary L; Chen, Yii-der I; et al. (Am J Clin Nutr, 2016)
BACKGROUND: DNA methylation is influenced by diet and single nucleotide polymorphisms (SNPs), and methylation modulates gene expression. OBJECTIVE: We aimed to explore whether the gene-by-diet interactions on blood lipids act through DNA methylation. DESIGN: We selected 7 SNPs on the basis of predicted relations in fatty acids, methylation, and lipids. We conducted a meta-analysis and a methylation and mediation analysis with the use of data from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) consortium and the ENCODE (Encyclopedia of DNA Elements) consortium. RESULTS: On the basis of the meta-analysis of 7 cohorts in the CHARGE consortium, higher plasma HDL cholesterol was associated with fewer C alleles at ATP-binding cassette subfamily A member 1 (ABCA1) rs2246293 (β = -0.6 mg/dL, P = 0.015) and higher circulating eicosapentaenoic acid (EPA) (β = 3.87 mg/dL, P = 5.62 × 10(21)). The difference in HDL cholesterol associated with higher circulating EPA was dependent on genotypes at rs2246293, and it was greater for each additional C allele (β = 1.69 mg/dL, P = 0.006). In the GOLDN (Genetics of Lipid Lowering Drugs and Diet Network) study, higher ABCA1 promoter cg14019050 methylation was associated with more C alleles at rs2246293 (β = 8.84%, P = 3.51 × 10(18)) and lower circulating EPA (β = -1.46%, P = 0.009), and the mean difference in methylation of cg14019050 that was associated with higher EPA was smaller with each additional C allele of rs2246293 (β = -2.83%, P = 0.007). Higher ABCA1 cg14019050 methylation was correlated with lower ABCA1 expression (r = -0.61, P = 0.009) in the ENCODE consortium and lower plasma HDL cholesterol in the GOLDN study (r = -0.12, P = 0.0002). An additional mediation analysis was meta-analyzed across the GOLDN study, Cardiovascular Health Study, and the Multi-Ethnic Study of Atherosclerosis. Compared with the model without the adjustment of cg14019050 methylation, the model with such adjustment provided smaller estimates of the mean plasma HDL cholesterol concentration in association with both the rs2246293 C allele and EPA and a smaller difference by rs2246293 genotypes in the EPA-associated HDL cholesterol. However, the differences between 2 nested models were NS (P > 0.05). CONCLUSION: We obtained little evidence that the gene-by-fatty acid interactions on blood lipids act through DNA methylation.
Keywords: Apolipoproteins E; ATP Binding Cassette Transporter 1; Cholesterol, HDL; Cohort Studies; Diet; DNA Methylation; Eicosapentaenoic Acid; Epigenesis, Genetic; Fatty Acids; Gene Expression Regulation; Humans; Lipids; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Triglycerides

A novel Alzheimer disease locus located near the gene encoding tau protein. - Jun, G; Ibrahim-Verbaas, C A; Vronskaya, M; Lambert, J-C; Chung, J; Naj, A C; Kunkle, B W; Wang, L-S; Bis, J C; Bellenguez, C; Harold, D; Lunetta, K L; et al. (Mol Psychiatry, 2016)
APOE ɛ4, the most significant genetic risk factor for Alzheimer disease (AD), may mask effects of other loci. We re-analyzed genome-wide association study (GWAS) data from the International Genomics of Alzheimer's Project (IGAP) Consortium in APOE ɛ4+ (10 352 cases and 9207 controls) and APOE ɛ4- (7184 cases and 26 968 controls) subgroups as well as in the total sample testing for interaction between a single-nucleotide polymorphism (SNP) and APOE ɛ4 status. Suggestive associations (P<1 × 10(-4)) in stage 1 were evaluated in an independent sample (stage 2) containing 4203 subjects (APOE ɛ4+: 1250 cases and 536 controls; APOE ɛ4-: 718 cases and 1699 controls). Among APOE ɛ4- subjects, novel genome-wide significant (GWS) association was observed with 17 SNPs (all between KANSL1 and LRRC37A on chromosome 17 near MAPT) in a meta-analysis of the stage 1 and stage 2 data sets (best SNP, rs2732703, P=5·8 × 10(-9)). Conditional analysis revealed that rs2732703 accounted for association signals in the entire 100-kilobase region that includes MAPT. Except for previously identified AD loci showing stronger association in APOE ɛ4+ subjects (CR1 and CLU) or APOE ɛ4- subjects (MS4A6A/MS4A4A/MS4A6E), no other SNPs were significantly associated with AD in a specific APOE genotype subgroup. In addition, the finding in the stage 1 sample that AD risk is significantly influenced by the interaction of APOE with rs1595014 in TMEM106B (P=1·6 × 10(-7)) is noteworthy, because TMEM106B variants have previously been associated with risk of frontotemporal dementia. Expression quantitative trait locus analysis revealed that rs113986870, one of the GWS SNPs near rs2732703, is significantly associated with four KANSL1 probes that target transcription of the first translated exon and an untranslated exon in hippocampus (P ⩽ 1.3 × 10(-8)), frontal cortex (P ⩽ 1.3 × 10(-9)) and temporal cortex (P⩽1.2 × 10(-11)). Rs113986870 is also strongly associated with a MAPT probe that targets transcription of alternatively spliced exon 3 in frontal cortex (P=9.2 × 10(-6)) and temporal cortex (P=2.6 × 10(-6)). Our APOE-stratified GWAS is the first to show GWS association for AD with SNPs in the chromosome 17q21.31 region. Replication of this finding in independent samples is needed to verify that SNPs in this region have significantly stronger effects on AD risk in persons lacking APOE ɛ4 compared with persons carrying this allele, and if this is found to hold, further examination of this region and studies aimed at deciphering the mechanism(s) are warranted.
Keywords: Alzheimer Disease; Apolipoprotein E4; Chromosomes, Human, Pair 17; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; tau Proteins

Rooted in risk: genetic predisposition for low-density lipoprotein cholesterol level associates with diminished low-density lipoprotein cholesterol response to statin treatment. - Smit, Roelof Aj; Postmus, Iris; Trompet, Stella; Barnes, Michael R; Warren, Helen; Arsenault, Benoit J; Chasman, Daniel I; Cupples, L Adrienne; Hitman, Graham A; Krauss, Ronald M; Li, Xiaohui; Psaty, Bruce M; et al. (Pharmacogenomics, 2016)
AIMS: To utilize previously reported lead SNPs for low-density lipoprotein cholesterol (LDL-c) levels to find additional loci of importance to statin response, and examine whether genetic predisposition to LDL-c levels associates with differential statin response. METHODS: We investigated effects on statin response of 59 LDL-c SNPs, by combining summary level statistics from the Global Lipids Genetics and Genomic Investigation of Statin Therapy consortia. RESULTS: Lead SNPs for APOE, SORT1 and NPC1L1 were associated with a decreased LDL-c response to statin treatment, as was overall genetic predisposition for increased LDL-c levels as quantified with 59 SNPs, with a 5.4% smaller statin response per standard deviation increase in genetically raised LDL-c levels. CONCLUSION: Genetic predisposition for increased LDL-c level may decrease efficacy of statin therapy.
Keywords: Cholesterol, LDL; Genetic Predisposition to Disease; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Pharmacogenetics; Polymorphism, Single Nucleotide; Triglycerides

Twenty-eight genetic loci associated with ST-T-wave amplitudes of the electrocardiogram. - Verweij, Niek; Mateo Leach, Irene; Isaacs, Aaron; Arking, Dan E; Bis, Joshua C; Pers, Tune H; van den Berg, Marten E; Lyytikäinen, Leo-Pekka; Barnett, Phil; Wang, Xinchen; Soliman, Elsayed Z; van Duijn, Cornelia M; et al. (Hum Mol Genet, 2016)
The ST-segment and adjacent T-wave (ST-T wave) amplitudes of the electrocardiogram are quantitative characteristics of cardiac repolarization. Repolarization abnormalities have been linked to ventricular arrhythmias and sudden cardiac death. We performed the first genome-wide association meta-analysis of ST-T-wave amplitudes in up to 37 977 individuals identifying 71 robust genotype-phenotype associations clustered within 28 independent loci. Fifty-four genes were prioritized as candidates underlying the phenotypes, including genes with established roles in the cardiac repolarization phase (SCN5A/SCN10A, KCND3, KCNB1, NOS1AP and HEY2) and others with as yet undefined cardiac function. These associations may provide insights in the spatiotemporal contribution of genetic variation influencing cardiac repolarization and provide novel leads for future functional follow-up.
Keywords: Adaptor Proteins, Signal Transducing; Arrhythmias, Cardiac; Basic Helix-Loop-Helix Transcription Factors; Brugada Syndrome; Cardiac Conduction System Disease; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Heart Conduction System; Humans; Male; NAV1.5 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Repressor Proteins; Shab Potassium Channels; Shal Potassium Channels

Assessing the causal relationship between obesity and venous thromboembolism through a Mendelian Randomization study. - Lindström, Sara; Germain, Marine; Crous-Bou, Marta; Smith, Erin N; Morange, Pierre-Emmanuel; van Hylckama Vlieg, Astrid; de Haan, Hugoline G; Chasman, Daniel; Ridker, Paul; Brody, Jennifer; de Andrade, Mariza; Heit, John A; et al. (Hum Genet, 2017)
Observational studies have shown an association between obesity and venous thromboembolism (VTE) but it is not known if observed associations are causal, due to reverse causation or confounding bias. We conducted a Mendelian Randomization study of body mass index (BMI) and VTE. We identified 95 single nucleotide polymorphisms (SNPs) that have been previously associated with BMI and assessed the association between genetically predicted high BMI and VTE leveraging data from a previously conducted GWAS within the INVENT consortium comprising a total of 7507 VTE cases and 52,632 controls of European ancestry. Five BMI SNPs were associated with VTE at P < 0.05, with the strongest association seen for the FTO SNP rs1558902 (OR 1.07, 95% CI 1.02-1.12, P = 0.005). In addition, we observed a significant association between genetically predicted BMI and VTE (OR = 1.59, 95% CI 1.30-1.93 per standard deviation increase in BMI, P = 5.8 × 10). Our study provides evidence for a causal relationship between high BMI and risk of VTE. Reducing obesity levels will likely result in lower incidence in VTE.
Keywords: Adult; Body Mass Index; Case-Control Studies; European Continental Ancestry Group; Female; Genome-Wide Association Study; Humans; Incidence; Logistic Models; Male; Mendelian Randomization Analysis; Obesity; Polymorphism, Single Nucleotide; Proportional Hazards Models; Venous Thromboembolism

Association Between Telomere Length and Risk of Cancer and Non-Neoplastic Diseases: A Mendelian Randomization Study. - Haycock, Philip C; Burgess, Stephen; Nounu, Aayah; Zheng, Jie; Okoli, George N; Bowden, Jack; Wade, Kaitlin Hazel; Timpson, Nicholas J; Evans, David M; Willeit, Peter; Aviv, Abraham; Gaunt, Tom R; et al. (JAMA Oncol, 2017)
Importance: The causal direction and magnitude of the association between telomere length and incidence of cancer and non-neoplastic diseases is uncertain owing to the susceptibility of observational studies to confounding and reverse causation. Objective: To conduct a Mendelian randomization study, using germline genetic variants as instrumental variables, to appraise the causal relevance of telomere length for risk of cancer and non-neoplastic diseases. Data Sources: Genomewide association studies (GWAS) published up to January 15, 2015. Study Selection: GWAS of noncommunicable diseases that assayed germline genetic variation and did not select cohort or control participants on the basis of preexisting diseases. Of 163 GWAS of noncommunicable diseases identified, summary data from 103 were available. Data Extraction and Synthesis: Summary association statistics for single nucleotide polymorphisms (SNPs) that are strongly associated with telomere length in the general population. Main Outcomes and Measures: Odds ratios (ORs) and 95% confidence intervals (CIs) for disease per standard deviation (SD) higher telomere length due to germline genetic variation. Results: Summary data were available for 35 cancers and 48 non-neoplastic diseases, corresponding to 420 081 cases (median cases, 2526 per disease) and 1 093 105 controls (median, 6789 per disease). Increased telomere length due to germline genetic variation was generally associated with increased risk for site-specific cancers. The strongest associations (ORs [95% CIs] per 1-SD change in genetically increased telomere length) were observed for glioma, 5.27 (3.15-8.81); serous low-malignant-potential ovarian cancer, 4.35 (2.39-7.94); lung adenocarcinoma, 3.19 (2.40-4.22); neuroblastoma, 2.98 (1.92-4.62); bladder cancer, 2.19 (1.32-3.66); melanoma, 1.87 (1.55-2.26); testicular cancer, 1.76 (1.02-3.04); kidney cancer, 1.55 (1.08-2.23); and endometrial cancer, 1.31 (1.07-1.61). Associations were stronger for rarer cancers and at tissue sites with lower rates of stem cell division. There was generally little evidence of association between genetically increased telomere length and risk of psychiatric, autoimmune, inflammatory, diabetic, and other non-neoplastic diseases, except for coronary heart disease (OR, 0.78 [95% CI, 0.67-0.90]), abdominal aortic aneurysm (OR, 0.63 [95% CI, 0.49-0.81]), celiac disease (OR, 0.42 [95% CI, 0.28-0.61]) and interstitial lung disease (OR, 0.09 [95% CI, 0.05-0.15]). Conclusions and Relevance: It is likely that longer telomeres increase risk for several cancers but reduce risk for some non-neoplastic diseases, including cardiovascular diseases.
Keywords: Adult; Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Germ-Line Mutation; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Neoplasms; Polymorphism, Single Nucleotide; Risk Assessment; Telomere; Telomere Homeostasis

Dairy consumption, systolic blood pressure, and risk of hypertension: Mendelian randomization study. - Ding, Ming; Huang, Tao; Bergholdt, Helle Km; Nordestgaard, Børge G; Ellervik, Christina; Qi, Lu (BMJ, 2017)
Objective To examine whether previous observed inverse associations of dairy intake with systolic blood pressure and risk of hypertension were causal.Design Mendelian randomization study using the single nucleotide polymorphism rs4988235 related to lactase persistence as an instrumental variable.Setting CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium.Participants Data from 22 studies with 171 213 participants, and an additional 10 published prospective studies with 26 119 participants included in the observational analysis.Main outcome measures The instrumental variable estimation was conducted using the ratio of coefficients approach. Using meta-analysis, an additional eight published randomized clinical trials on the association of dairy consumption with systolic blood pressure were summarized.Results Compared with the CC genotype (CC is associated with complete lactase deficiency), the CT/TT genotype (TT is associated with lactose persistence, and CT is associated with certain lactase deficiency) of LCT-13910 (lactase persistence gene) rs4988235 was associated with higher dairy consumption (0.23 (about 55 g/day), 95% confidence interval 0.17 to 0.29) serving/day; P<0.001) and was not associated with systolic blood pressure (0.31, 95% confidence interval -0.05 to 0.68 mm Hg; P=0.09) or risk of hypertension (odds ratio 1.01, 95% confidence interval 0.97 to 1.05; P=0.27). Using LCT-13910 rs4988235 as the instrumental variable, genetically determined dairy consumption was not associated with systolic blood pressure (β=1.35, 95% confidence interval -0.28 to 2.97 mm Hg for each serving/day) or risk of hypertension (odds ratio 1.04, 0.88 to 1.24). Moreover, meta-analysis of the published clinical trials showed that higher dairy intake has no significant effect on change in systolic blood pressure for interventions over one month to 12 months (intervention compared with control groups: β=-0.21, 95% confidence interval -0.98 to 0.57 mm Hg). In observational analysis, each serving/day increase in dairy consumption was associated with -0.11 (95% confidence interval -0.20 to -0.02 mm Hg; P=0.02) lower systolic blood pressure but not risk of hypertension (odds ratio 0.98, 0.97 to 1.00; P=0.11).Conclusion The weak inverse association between dairy intake and systolic blood pressure in observational studies was not supported by a comprehensive instrumental variable analysis and systematic review of existing clinical trials.
Keywords: Blood Pressure; Dairy Products; Feeding Behavior; Genetic Predisposition to Disease; Humans; Hypertension; Lactase; Mendelian Randomization Analysis; Observational Studies as Topic; Polymorphism, Single Nucleotide; Randomized Controlled Trials as Topic

Genetically Determined Plasma Lipid Levels and Risk of Diabetic Retinopathy: A Mendelian Randomization Study. - Sobrin, Lucia; Chong, Yong He; Fan, Qiao; Gan, Alfred; Stanwyck, Lynn K; Kaidonis, Georgia; Craig, Jamie E; Kim, Jihye; Liao, Wen-Ling; Huang, Yu-Chuen; Lee, Wen-Jane; Hung, Yi-Jen; et al. (Diabetes, 2017)
Results from observational studies examining dyslipidemia as a risk factor for diabetic retinopathy (DR) have been inconsistent. We evaluated the causal relationship between plasma lipids and DR using a Mendelian randomization approach. We pooled genome-wide association studies summary statistics from 18 studies for two DR phenotypes: any DR (N = 2,969 case and 4,096 control subjects) and severe DR (N = 1,277 case and 3,980 control subjects). Previously identified lipid-associated single nucleotide polymorphisms served as instrumental variables. Meta-analysis to combine the Mendelian randomization estimates from different cohorts was conducted. There was no statistically significant change in odds ratios of having any DR or severe DR for any of the lipid fractions in the primary analysis that used single nucleotide polymorphisms that did not have a pleiotropic effect on another lipid fraction. Similarly, there was no significant association in the Caucasian and Chinese subgroup analyses. This study did not show evidence of a causal role of the four lipid fractions on DR. However, the study had limited power to detect odds ratios less than 1.23 per SD in genetically induced increase in plasma lipid levels, thus we cannot exclude that causal relationships with more modest effect sizes exist.
Keywords: Aged; Diabetic Retinopathy; Female; Genome-Wide Association Study; Humans; Lipids; Male; Mendelian Randomization Analysis; Middle Aged; Polymorphism, Single Nucleotide; Risk

Genome-Wide Association Study Meta-Analysis of Long-Term Average Blood Pressure in East Asians. - Li, Changwei; Kim, Yun Kyoung; Dorajoo, Rajkumar; Li, Huaixing; Lee, I-Te; Cheng, Ching-Yu; He, Meian; Sheu, Wayne H-H; Guo, Xiuqing; Ganesh, Santhi K; He, Jiang; Lee, Juyoung; et al. (Circ Cardiovasc Genet, 2017)
BACKGROUND: Genome-wide single marker and gene-based meta-analyses of long-term average (LTA) blood pressure (BP) phenotypes may reveal novel findings for BP. METHODS AND RESULTS: We conducted genome-wide analysis among 18 422 East Asian participants (stage 1) followed by replication study of ≤46 629 participants of European ancestry (stage 2). Significant single-nucleotide polymorphisms and genes were determined by a P<5.0×10-8 and 2.5×10-6, respectively, in joint analyses of stage-1 and stage-2 data. We identified 1 novel ARL3 variant, rs4919669 at 10q24.32, influencing LTA systolic BP (stage-1 P=5.03×10-8, stage-2 P=8.64×10-3, joint P=2.63×10-8) and mean arterial pressure (stage-1 P=3.59×10-9, stage-2 P=2.35×10-2, joint P=2.64×10-8). Three previously reported BP loci (WBP1L, NT5C2, and ATP2B1) were also identified for all BP phenotypes. Gene-based analysis provided the first robust evidence for association of KCNJ11 with LTA systolic BP (stage-1 P=8.55×10-6, stage-2 P=1.62×10-5, joint P=3.28×10-9) and mean arterial pressure (stage-1 P=9.19×10-7, stage-2 P=9.69×10-5, joint P=2.15×10-9) phenotypes. Fourteen genes (TMEM180, ACTR1A, SUFU, ARL3, SFXN2, WBP1L, CYP17A1, C10orf32, C10orf32-ASMT, AS3MT, CNNM2, and NT5C2 at 10q24.32; ATP2B1 at 12q21.33; and NCR3LG1 at 11p15.1) implicated by previous genome-wide association study meta-analyses were also identified. Among the loci identified by the previous genome-wide association study meta-analysis of LTA BP, we transethnically replicated associations of the KCNK3 marker rs1275988 at 2p23.3 with LTA systolic BP and mean arterial pressure phenotypes (P=1.27×10-4 and 3.30×10-4, respectively). CONCLUSIONS: We identified 1 novel variant and 1 novel gene and present the first direct evidence of relevance of the KCNK3 locus for LTA BP among East Asians.
Keywords: Asian Continental Ancestry Group; Blood Pressure; Far East; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Phenotype; Polymorphism, Single Nucleotide

Low-Frequency Synonymous Coding Variation in CYP2R1 Has Large Effects on Vitamin D Levels and Risk of Multiple Sclerosis. - Manousaki, Despoina; Dudding, Tom; Haworth, Simon; Hsu, Yi-Hsiang; Liu, Ching-Ti; Medina-Gómez, Carolina; Voortman, Trudy; van der Velde, Nathalie; Melhus, Håkan; Robinson-Cohen, Cassianne; Cousminer, Diana L; Nethander, Maria; et al. (Am J Hum Genet, 2017)
Vitamin D insufficiency is common, correctable, and influenced by genetic factors, and it has been associated with risk of several diseases. We sought to identify low-frequency genetic variants that strongly increase the risk of vitamin D insufficiency and tested their effect on risk of multiple sclerosis, a disease influenced by low vitamin D concentrations. We used whole-genome sequencing data from 2,619 individuals through the UK10K program and deep-imputation data from 39,655 individuals genotyped genome-wide. Meta-analysis of the summary statistics from 19 cohorts identified in CYP2R1 the low-frequency (minor allele frequency = 2.5%) synonymous coding variant g.14900931G>A (p.Asp120Asp) (rs117913124[A]), which conferred a large effect on 25-hydroxyvitamin D (25OHD) levels (-0.43 SD of standardized natural log-transformed 25OHD per A allele; p value = 1.5 × 10(-88)). The effect on 25OHD was four times larger and independent of the effect of a previously described common variant near CYP2R1. By analyzing 8,711 individuals, we showed that heterozygote carriers of this low-frequency variant have an increased risk of vitamin D insufficiency (odds ratio [OR] = 2.2, 95% confidence interval [CI] = 1.78-2.78, p = 1.26 × 10(-12)). Individuals carrying one copy of this variant also had increased odds of multiple sclerosis (OR = 1.4, 95% CI = 1.19-1.64, p = 2.63 × 10(-5)) in a sample of 5,927 case and 5,599 control subjects. In conclusion, we describe a low-frequency CYP2R1 coding variant that exerts the largest effect upon 25OHD levels identified to date in the general European population and implicates vitamin D in the etiology of multiple sclerosis.
Keywords: Cholestanetriol 26-Monooxygenase; Cytochrome P450 Family 2; Gene Frequency; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Multiple Sclerosis; Polymorphism, Single Nucleotide; Risk Factors; Vitamin D; Vitamin D Deficiency

Phenotype-Specific Association of Single-Nucleotide Polymorphisms with Heart Failure and Preserved Ejection Fraction: a Genome-Wide Association Analysis of the Cardiovascular Health Study. - Kao, David P; Stevens, Laura M; Hinterberg, Michael A; Görg, Carsten (J Cardiovasc Transl Res, 2017)
Little is known about genetics of heart failure with preserved ejection fraction (HFpEF) in part because of the many comorbidities in this population. To identify single-nucleotide polymorphisms (SNPs) associated with HFpEF, we analyzed phenotypic and genotypic data from the Cardiovascular Health Study, which profiled patients using a 50,000 SNP array. Results were explored using novel SNP- and gene-centric tools. We performed analyses to determine whether some SNPs were relevant only in certain phenotypes. Among 3804 patients, 7 clinical factors and 9 SNPs were significantly associated with HFpEF; the most notable of which was rs6996224, a SNP associated with transforming growth factor-beta receptor 3. Most SNPs were associated with HFpEF only in the absence of a clinical predictor. Significant SNPs represented genes involved in myocyte proliferation, transforming growth factor-beta/erbB signaling, and extracellular matrix formation. These findings suggest that genetic factors may be more important in some phenotypes than others.
Keywords: Aged; Computational Biology; Databases, Genetic; European Continental Ancestry Group; Female; Gene Expression Profiling; Genetic Markers; Genetic Predisposition to Disease; Genome-Wide Association Study; Heart Failure; Humans; Male; Oligonucleotide Array Sequence Analysis; Phenotype; Polymorphism, Single Nucleotide; Predictive Value of Tests; Prognosis; Proteoglycans; Receptors, Transforming Growth Factor beta; Risk Assessment; Risk Factors; Stroke Volume; United States

Rare coding variants in PLCG2, ABI3, and TREM2 implicate microglial-mediated innate immunity in Alzheimer's disease. - Sims, Rebecca; van der Lee, Sven J; Naj, Adam C; Bellenguez, Céline; Badarinarayan, Nandini; Jakobsdottir, Johanna; Kunkle, Brian W; Boland, Anne; Raybould, Rachel; Bis, Joshua C; Martin, Eden R; Grenier-Boley, Benjamin; et al. (Nat Genet, 2017)
We identified rare coding variants associated with Alzheimer's disease in a three-stage case-control study of 85,133 subjects. In stage 1, we genotyped 34,174 samples using a whole-exome microarray. In stage 2, we tested associated variants (P < 1 × 10-4) in 35,962 independent samples using de novo genotyping and imputed genotypes. In stage 3, we used an additional 14,997 samples to test the most significant stage 2 associations (P < 5 × 10-8) using imputed genotypes. We observed three new genome-wide significant nonsynonymous variants associated with Alzheimer's disease: a protective variant in PLCG2 (rs72824905: p.Pro522Arg, P = 5.38 × 10-10, odds ratio (OR) = 0.68, minor allele frequency (MAF)cases = 0.0059, MAFcontrols = 0.0093), a risk variant in ABI3 (rs616338: p.Ser209Phe, P = 4.56 × 10-10, OR = 1.43, MAFcases = 0.011, MAFcontrols = 0.008), and a new genome-wide significant variant in TREM2 (rs143332484: p.Arg62His, P = 1.55 × 10-14, OR = 1.67, MAFcases = 0.0143, MAFcontrols = 0.0089), a known susceptibility gene for Alzheimer's disease. These protein-altering changes are in genes highly expressed in microglia and highlight an immune-related protein-protein interaction network enriched for previously identified risk genes in Alzheimer's disease. These genetic findings provide additional evidence that the microglia-mediated innate immune response contributes directly to the development of Alzheimer's disease.
Keywords: Adaptor Proteins, Signal Transducing; Alzheimer Disease; Amino Acid Sequence; Case-Control Studies; Exome; Gene Expression Profiling; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Immunity, Innate; Linkage Disequilibrium; Membrane Glycoproteins; Microglia; Odds Ratio; Phospholipase C gamma; Polymorphism, Single Nucleotide; Protein Interaction Maps; Receptors, Immunologic; Sequence Homology, Amino Acid

Rare coding variants pinpoint genes that control human hematological traits. - Mousas, Abdou; Ntritsos, Georgios; Chen, Ming-Huei; Song, Ci; Huffman, Jennifer E; Tzoulaki, Ioanna; Elliott, Paul; Psaty, Bruce M; Auer, Paul L; Johnson, Andrew D; Evangelou, Evangelos; Lettre, Guillaume; et al. (PLoS Genet, 2017)
The identification of rare coding or splice site variants remains the most straightforward strategy to link genes with human phenotypes. Here, we analyzed the association between 137,086 rare (minor allele frequency (MAF) <1%) coding or splice site variants and 15 hematological traits in up to 308,572 participants. We found 56 such rare coding or splice site variants at P<5x10-8, including 31 that are associated with a blood-cell phenotype for the first time. All but one of these 31 new independent variants map to loci previously implicated in hematopoiesis by genome-wide association studies (GWAS). This includes a rare splice acceptor variant (rs146597587, MAF = 0.5%) in interleukin 33 (IL33) associated with reduced eosinophil count (P = 2.4x10-23), and lower risk of asthma (P = 2.6x10-7, odds ratio [95% confidence interval] = 0.56 [0.45-0.70]) and allergic rhinitis (P = 4.2x10-4, odds ratio = 0.55 [0.39-0.76]). The single new locus identified in our study is defined by a rare p.Arg172Gly missense variant (rs145535174, MAF = 0.05%) in plasminogen (PLG) associated with increased platelet count (P = 6.8x10-9), and decreased D-dimer concentration (P = 0.018) and platelet reactivity (P<0.03). Finally, our results indicate that searching for rare coding or splice site variants in very large sample sizes can help prioritize causal genes at many GWAS loci associated with complex human diseases and traits.
Keywords: Asthma; Databases, Genetic; Endometriosis; Female; Fibrin Fibrinogen Degradation Products; Gene Frequency; Genetic Loci; Genome, Human; Genome-Wide Association Study; Humans; Interleukin-33; Linear Models; Logistic Models; Male; Mutation, Missense; Phenotype; Plasminogen; Platelet Count; Polymorphism, Single Nucleotide; Principal Component Analysis; Protein Splicing; Rhinitis, Allergic; Sequence Analysis, DNA

Single-trait and multi-trait genome-wide association analyses identify novel loci for blood pressure in African-ancestry populations. - Liang, Jingjing; Le, Thu H; Edwards, Digna R Velez; Tayo, Bamidele O; Gaulton, Kyle J; Smith, Jennifer A; Lu, Yingchang; Jensen, Richard A; Chen, Guanjie; Yanek, Lisa R; Schwander, Karen; Tajuddin, Salman M; et al. (PLoS Genet, 2017)
Hypertension is a leading cause of global disease, mortality, and disability. While individuals of African descent suffer a disproportionate burden of hypertension and its complications, they have been underrepresented in genetic studies. To identify novel susceptibility loci for blood pressure and hypertension in people of African ancestry, we performed both single and multiple-trait genome-wide association analyses. We analyzed 21 genome-wide association studies comprised of 31,968 individuals of African ancestry, and validated our results with additional 54,395 individuals from multi-ethnic studies. These analyses identified nine loci with eleven independent variants which reached genome-wide significance (P < 1.25×10-8) for either systolic and diastolic blood pressure, hypertension, or for combined traits. Single-trait analyses identified two loci (TARID/TCF21 and LLPH/TMBIM4) and multiple-trait analyses identified one novel locus (FRMD3) for blood pressure. At these three loci, as well as at GRP20/CDH17, associated variants had alleles common only in African-ancestry populations. Functional annotation showed enrichment for genes expressed in immune and kidney cells, as well as in heart and vascular cells/tissues. Experiments driven by these findings and using angiotensin-II induced hypertension in mice showed altered kidney mRNA expression of six genes, suggesting their potential role in hypertension. Our study provides new evidence for genes related to hypertension susceptibility, and the need to study African-ancestry populations in order to identify biologic factors contributing to hypertension.
Keywords: African Americans; Animals; Basic Helix-Loop-Helix Transcription Factors; Blood Pressure; Cadherins; Case-Control Studies; Female; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Male; Membrane Proteins; Mice; Multifactorial Inheritance; Polymorphism, Single Nucleotide

Systems biology approach to late-onset Alzheimer's disease genome-wide association study identifies novel candidate genes validated using brain expression data and Caenorhabditis elegans experiments. - Mukherjee, Shubhabrata; Russell, Joshua C; Carr, Daniel T; Burgess, Jeremy D; Allen, Mariet; Serie, Daniel J; Boehme, Kevin L; Kauwe, John S K; Naj, Adam C; Fardo, David W; Dickson, Dennis W; Montine, Thomas J; et al. (Alzheimers Dement, 2017)
INTRODUCTION: We sought to determine whether a systems biology approach may identify novel late-onset Alzheimer's disease (LOAD) loci. METHODS: We performed gene-wide association analyses and integrated results with human protein-protein interaction data using network analyses. We performed functional validation on novel genes using a transgenic Caenorhabditis elegans Aβ proteotoxicity model and evaluated novel genes using brain expression data from people with LOAD and other neurodegenerative conditions. RESULTS: We identified 13 novel candidate LOAD genes outside chromosome 19. Of those, RNA interference knockdowns of the C. elegans orthologs of UBC, NDUFS3, EGR1, and ATP5H were associated with Aβ toxicity, and NDUFS3, SLC25A11, ATP5H, and APP were differentially expressed in the temporal cortex. DISCUSSION: Network analyses identified novel LOAD candidate genes. We demonstrated a functional role for four of these in a C. elegans model and found enrichment of differentially expressed genes in the temporal cortex.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Animals, Genetically Modified; Antigens, Neoplasm; Caenorhabditis elegans; Disease Models, Animal; Early Growth Response Protein 1; Female; Gene Expression Regulation; Genome-Wide Association Study; Heparin-binding EGF-like Growth Factor; Humans; Male; Membrane Transport Proteins; Mitochondrial ADP, ATP Translocases; NADH Dehydrogenase; Polymorphism, Single Nucleotide; Protein Interaction Maps; RNA Interference; Systems Biology; Temporal Lobe

Genome-wide association meta-analysis of circulating odd-numbered chain saturated fatty acids: Results from the CHARGE Consortium. - de Oliveira Otto, Marcia C; Lemaitre, Rozenn N; Sun, Qi; King, Irena B; Wu, Jason H Y; Manichaikul, Ani; Rich, Stephen S; Tsai, Michael Y; Chen, Y D; Fornage, Myriam; Weihua, Guan; Aslibekyan, Stella; et al. (PLoS One, 2018)
BACKGROUND: Odd-numbered chain saturated fatty acids (OCSFA) have been associated with potential health benefits. Although some OCSFA (e.g., C15:0 and C17:0) are found in meats and dairy products, sources and metabolism of C19:0 and C23:0 are relatively unknown, and the influence of non-dietary determinants, including genetic factors, on circulating levels of OCSFA is not established. OBJECTIVE: To elucidate the biological processes that influence circulating levels of OCSFA by investigating associations between genetic variation and OCSFA. DESIGN: We performed a meta-analysis of genome-wide association studies (GWAS) of plasma phospholipid/erythrocyte levels of C15:0, C17:0, C19:0, and C23:0 among 11,494 individuals of European descent. We also investigated relationships between specific single nucleotide polymorphisms (SNPs) in the lactase (LCT) gene, associated with adult-onset lactase intolerance, with circulating levels of dairy-derived OCSFA, and evaluated associations of candidate sphingolipid genes with C23:0 levels. RESULTS: We found no genome-wide significant evidence that common genetic variation is associated with circulating levels of C15:0 or C23:0. In two cohorts with available data, we identified one intronic SNP (rs13361131) in myosin X gene (MYO10) associated with C17:0 level (P = 1.37×10-8), and two intronic SNP (rs12874278 and rs17363566) in deleted in lymphocytic leukemia 1 (DLEU1) region associated with C19:0 level (P = 7.07×10-9). In contrast, when using a candidate-gene approach, we found evidence that three SNPs in LCT (rs11884924, rs16832067, and rs3816088) are associated with circulating C17:0 level (adjusted P = 4×10-2). In addition, nine SNPs in the ceramide synthase 4 (CERS4) region were associated with circulating C23:0 levels (adjusted P<5×10-2). CONCLUSIONS: Our findings suggest that circulating levels of OCSFA may be predominantly influenced by non-genetic factors. SNPs associated with C17:0 level in the LCT gene may reflect genetic influence in dairy consumption or in metabolism of dairy foods. SNPs associated with C23:0 may reflect a role of genetic factors in the synthesis of sphingomyelin.
Keywords: Fatty Acids; Genome-Wide Association Study; Humans; Introns; Lactase; Myosins; Polymorphism, Single Nucleotide; Sphingomyelins; Sphingosine N-Acyltransferase; Tumor Suppressor Proteins

GWAS and colocalization analyses implicate carotid intima-media thickness and carotid plaque loci in cardiovascular outcomes. - Franceschini, Nora; Giambartolomei, Claudia; de Vries, Paul S; Finan, Chris; Bis, Joshua C; Huntley, Rachael P; Lovering, Ruth C; Tajuddin, Salman M; Winkler, Thomas W; Graff, Misa; Kavousi, Maryam; Dale, Caroline; et al. (Nat Commun, 2018)
Carotid artery intima media thickness (cIMT) and carotid plaque are measures of subclinical atherosclerosis associated with ischemic stroke and coronary heart disease (CHD). Here, we undertake meta-analyses of genome-wide association studies (GWAS) in 71,128 individuals for cIMT, and 48,434 individuals for carotid plaque traits. We identify eight novel susceptibility loci for cIMT, one independent association at the previously-identified PINX1 locus, and one novel locus for carotid plaque. Colocalization analysis with nearby vascular expression quantitative loci (cis-eQTLs) derived from arterial wall and metabolic tissues obtained from patients with CHD identifies candidate genes at two potentially additional loci, ADAMTS9 and LOXL4. LD score regression reveals significant genetic correlations between cIMT and plaque traits, and both cIMT and plaque with CHD, any stroke subtype and ischemic stroke. Our study provides insights into genes and tissue-specific regulatory mechanisms linking atherosclerosis both to its functional genomic origins and its clinical consequences in humans.
Keywords: ADAMTS9 Protein; Amino Acid Oxidoreductases; Carotid Intima-Media Thickness; Coronary Disease; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Lod Score; Plaque, Atherosclerotic; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors

Strong impact of natural-selection-free heterogeneity in genetics of age-related phenotypes. - Kulminski, Alexander M; Huang, Jian; Loika, Yury; Arbeev, Konstantin G; Bagley, Olivia; Yashkin, Arseniy; Duan, Matt; Culminskaya, Irina (Aging (Albany NY), 2018)
A conceptual difficulty in genetics of age-related phenotypes that make individuals vulnerable to disease in post-reproductive life is genetic heterogeneity attributed to an undefined role of evolution in establishing their molecular mechanisms. Here, we performed univariate and pleiotropic genome-wide meta-analyses of 20 age-related phenotypes leveraging longitudinal information in a sample of 33,431 individuals and dealing with the natural-selection-free genetic heterogeneity. We identified 142 non-proxy single nucleotide polymorphisms (SNPs) with phenotype-specific (18 SNPs) and pleiotropic (124 SNPs) associations at genome-wide level. Univariate meta-analysis identified two novel (11.1%) and replicated 16 SNPs whereas pleiotropic meta-analysis identified 115 novel (92.7%) and nine replicated SNPs. Pleiotropic associations for most novel (93.9%) and all replicated SNPs were strongly impacted by the natural-selection-free genetic heterogeneity in its unconventional form of antagonistic heterogeneity, implying antagonistic directions of genetic effects for directly correlated phenotypes. Our results show that the common genome-wide approach is well adapted to handle homogeneous univariate associations within Mendelian framework whereas most associations with age-related phenotypes are more complex and well beyond that framework. Dissecting the natural-selection-free genetic heterogeneity is critical for gaining insights into genetics of age-related phenotypes and has substantial and unexplored yet potential for improving efficiency of genome-wide analysis.
Keywords: Aging; Computational Biology; Gene Expression Regulation; Genome-Wide Association Study; Genotype; Humans; Polymorphism, Single Nucleotide

Associations of variants In the hexokinase 1 and interleukin 18 receptor regions with oxyhemoglobin saturation during sleep. - Cade, Brian E; Chen, Han; Stilp, Adrienne M; Louie, Tin; Ancoli-Israel, Sonia; Arens, Raanan; Barfield, Richard; Below, Jennifer E; Cai, Jianwen; Conomos, Matthew P; Evans, Daniel S; Frazier-Wood, Alexis C; et al. (PLoS Genet, 2019)
Sleep disordered breathing (SDB)-related overnight hypoxemia is associated with cardiometabolic disease and other comorbidities. Understanding the genetic bases for variations in nocturnal hypoxemia may help understand mechanisms influencing oxygenation and SDB-related mortality. We conducted genome-wide association tests across 10 cohorts and 4 populations to identify genetic variants associated with three correlated measures of overnight oxyhemoglobin saturation: average and minimum oxyhemoglobin saturation during sleep and the percent of sleep with oxyhemoglobin saturation under 90%. The discovery sample consisted of 8,326 individuals. Variants with p < 1 × 10(-6) were analyzed in a replication group of 14,410 individuals. We identified 3 significantly associated regions, including 2 regions in multi-ethnic analyses (2q12, 10q22). SNPs in the 2q12 region associated with minimum SpO2 (rs78136548 p = 2.70 × 10(-10)). SNPs at 10q22 were associated with all three traits including average SpO2 (rs72805692 p = 4.58 × 10(-8)). SNPs in both regions were associated in over 20,000 individuals and are supported by prior associations or functional evidence. Four additional significant regions were detected in secondary sex-stratified and combined discovery and replication analyses, including a region overlapping Reelin, a known marker of respiratory complex neurons.These are the first genome-wide significant findings reported for oxyhemoglobin saturation during sleep, a phenotype of high clinical interest. Our replicated associations with HK1 and IL18R1 suggest that variants in inflammatory pathways, such as the biologically-plausible NLRP3 inflammasome, may contribute to nocturnal hypoxemia.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cell Adhesion Molecules, Neuronal; Computational Biology; Extracellular Matrix Proteins; Female; Gene Regulatory Networks; Genetic Variation; Genome-Wide Association Study; Hexokinase; Humans; Hypoxia; Interleukin-18 Receptor alpha Subunit; Male; Middle Aged; Nerve Tissue Proteins; NLR Family, Pyrin Domain-Containing 3 Protein; Oxygen; Oxyhemoglobins; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Serine Endopeptidases; Sleep; Sleep Apnea Syndromes; Young Adult

A catalog of genetic loci associated with kidney function from analyses of a million individuals. - Wuttke, Matthias; Li, Yong; Li, Man; Sieber, Karsten B; Feitosa, Mary F; Gorski, Mathias; Tin, Adrienne; Wang, Lihua; Chu, Audrey Y; Hoppmann, Anselm; Kirsten, Holger; Giri, Ayush; et al. (Nat Genet, 2019)
Chronic kidney disease (CKD) is responsible for a public health burden with multi-systemic complications. Through trans-ancestry meta-analysis of genome-wide association studies of estimated glomerular filtration rate (eGFR) and independent replication (n = 1,046,070), we identified 264 associated loci (166 new). Of these, 147 were likely to be relevant for kidney function on the basis of associations with the alternative kidney function marker blood urea nitrogen (n = 416,178). Pathway and enrichment analyses, including mouse models with renal phenotypes, support the kidney as the main target organ. A genetic risk score for lower eGFR was associated with clinically diagnosed CKD in 452,264 independent individuals. Colocalization analyses of associations with eGFR among 783,978 European-ancestry individuals and gene expression across 46 human tissues, including tubulo-interstitial and glomerular kidney compartments, identified 17 genes differentially expressed in kidney. Fine-mapping highlighted missense driver variants in 11 genes and kidney-specific regulatory variants. These results provide a comprehensive priority list of molecular targets for translational research.
Keywords: Chromosome Mapping; European Continental Ancestry Group; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Inheritance Patterns; Kidney Function Tests; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Quantitative Trait, Heritable; Renal Insufficiency, Chronic; Uromodulin

Genome-Wide Association Study of Apparent Treatment-Resistant Hypertension in the CHARGE Consortium: The CHARGE Pharmacogenetics Working Group. - Irvin, Marguerite R; Sitlani, Colleen M; Floyd, James S; Psaty, Bruce M; Bis, Joshua C; Wiggins, Kerri L; Whitsel, Eric A; Stürmer, Til; Stewart, James; Raffield, Laura; Sun, Fangui; Liu, Ching-Ti; et al. (Am J Hypertens, 2019)
BACKGROUND: Only a handful of genetic discovery efforts in apparent treatment-resistant hypertension (aTRH) have been described. METHODS: We conducted a case-control genome-wide association study of aTRH among persons treated for hypertension, using data from 10 cohorts of European ancestry (EA) and 5 cohorts of African ancestry (AA). Cases were treated with 3 different antihypertensive medication classes and had blood pressure (BP) above goal (systolic BP ≥ 140 mm Hg and/or diastolic BP ≥ 90 mm Hg) or 4 or more medication classes regardless of BP control (nEA = 931, nAA = 228). Both a normotensive control group and a treatment-responsive control group were considered in separate analyses. Normotensive controls were untreated (nEA = 14,210, nAA = 2,480) and had systolic BP/diastolic BP < 140/90 mm Hg. Treatment-responsive controls (nEA = 5,266, nAA = 1,817) had BP at goal (<140/90 mm Hg), while treated with one antihypertensive medication class. Individual cohorts used logistic regression with adjustment for age, sex, study site, and principal components for ancestry to examine the association of single-nucleotide polymorphisms with case-control status. Inverse variance-weighted fixed-effects meta-analyses were carried out using METAL. RESULTS: The known hypertension locus, CASZ1, was a top finding among EAs (P = 1.1 × 10-8) and in the race-combined analysis (P = 1.5 × 10-9) using the normotensive control group (rs12046278, odds ratio = 0.71 (95% confidence interval: 0.6-0.8)). Single-nucleotide polymorphisms in this locus were robustly replicated in the Million Veterans Program (MVP) study in consideration of a treatment-responsive control group. There were no statistically significant findings for the discovery analyses including treatment-responsive controls. CONCLUSION: This genomic discovery effort for aTRH identified CASZ1 as an aTRH risk locus.
Keywords: Aged; Antihypertensive Agents; Black or African American; Blood Pressure; Case-Control Studies; DNA (Cytosine-5-)-Methyltransferases; DNA Methyltransferase 3A; DNA-Binding Proteins; Drug Resistance; Dystrophin-Associated Proteins; Europe; Female; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Myosin Heavy Chains; Myosin Type V; Neuropeptides; Pharmacogenetics; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Risk Assessment; Risk Factors; Transcription Factors; United States; White People

Genomewide Association Study of Statin-Induced Myopathy in Patients Recruited Using the UK Clinical Practice Research Datalink. - Carr, Daniel F; Francis, Ben; Jorgensen, Andrea L; Zhang, Eunice; Chinoy, Hector; Heckbert, Susan R; Bis, Joshua C; Brody, Jennifer A; Floyd, James S; Psaty, Bruce M; Molokhia, Mariam; Lapeyre-Mestre, Maryse; et al. (Clin Pharmacol Ther, 2019)
Statins can be associated with myopathy. We have undertaken a genomewide association study (GWAS) to discover and validate genetic risk factors for statin-induced myopathy in a "real-world" setting. One hundred thirty-five patients with statin myopathy recruited via the UK Clinical Practice Research Datalink were genotyped using the Illumina OmniExpress Exome version 1.0 Bead Chip and compared with the Wellcome Trust Case-Control Consortium (n = 2,501). Nominally statistically significant single nucleotide polymorphism (SNP) signals in the GWAS (P < 5 × 10 ) were further evaluated in several independent cohorts (comprising 332 cases and 449 drug-tolerant controls). Only one (rs4149056/c.521C>T in the SLCO1B1 gene) SNP was genomewide significant in the severe myopathy (creatine kinase > 10 × upper limit of normal or rhabdomyolysis) group (P = 2.55 × 10 ; odds ratio 5.15; 95% confidence interval 3.13-8.45). The association with SLCO1B1 was present for several statins and replicated in the independent validation cohorts. The data highlight the role of SLCO1B1 c.521C>T SNP as a replicable genetic risk factor for statin myopathy. No other novel genetic risk factors with a similar effect size were identified.
Keywords: Adverse Drug Reaction Reporting Systems; Case-Control Studies; Databases, Factual; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Liver-Specific Organic Anion Transporter 1; Muscular Diseases; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Reproducibility of Results; Risk Factors; Severity of Illness Index; United Kingdom

Genome-wide meta-analysis of SNP and antihypertensive medication interactions on left ventricular traits in African Americans. - Do, Anh N; Zhao, Wei; Baldridge, Abigail S; Raffield, Laura M; Wiggins, Kerri L; Shah, Sanjiv J; Aslibekyan, Stella; Tiwari, Hemant K; Limdi, Nita; Zhi, Degui; Sitlani, Colleen M; Taylor, Kent D; et al. (Mol Genet Genomic Med, 2019)
BACKGROUND: Left ventricular (LV) hypertrophy affects up to 43% of African Americans (AAs). Antihypertensive treatment reduces LV mass (LVM). However, interindividual variation in LV traits in response to antihypertensive treatments exists. We hypothesized that genetic variants may modify the association of antihypertensive treatment class with LV traits measured by echocardiography. METHODS: We evaluated the main effects of the three most common antihypertensive treatments for AAs as well as the single nucleotide polymorphism (SNP)-by-drug interaction on LVM and relative wall thickness (RWT) in 2,068 participants across five community-based cohorts. Treatments included thiazide diuretics (TDs), angiotensin converting enzyme inhibitors (ACE-Is), and dihydropyridine calcium channel blockers (dCCBs) and were compared in a pairwise manner. We performed fixed effects inverse variance weighted meta-analyses of main effects of drugs and 2.5 million SNP-by-drug interaction estimates. RESULTS: We observed that dCCBs versus TDs were associated with higher LVM after adjusting for covariates (p = 0.001). We report three SNPs at a single locus on chromosome 20 that modified the association between RWT and treatment when comparing dCCBs to ACE-Is with consistent effects across cohorts (smallest p = 4.7 × 10 , minor allele frequency range 0.09-0.12). This locus has been linked to LV hypertrophy in a previous study. A marginally significant locus in BICD1 (rs326641) was validated in an external population. CONCLUSIONS: Our study identified one locus having genome-wide significant SNP-by-drug interaction effect on RWT among dCCB users in comparison to ACE-I users. Upon additional validation in future studies, our findings can enhance the precision of medical approaches in hypertension treatment.
Keywords: African Americans; Angiotensin-Converting Enzyme Inhibitors; Antihypertensive Agents; Calcium Channel Blockers; Humans; Observational Studies as Topic; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Sodium Chloride Symporter Inhibitors; Ventricular Dysfunction, Left

Alzheimer Disease Pathology-Associated Polymorphism in a Complex Variable Number of Tandem Repeat Region Within the MUC6 Gene, Near the AP2A2 Gene. - Katsumata, Yuriko; Fardo, David W; Bachstetter, Adam D; Artiushin, Sergey C; Wang, Wang-Xia; Wei, Angela; Brzezinski, Lena J; Nelson, Bela G; Huang, Qingwei; Abner, Erin L; Anderson, Sonya; Patel, Indumati; et al. (J Neuropathol Exp Neurol, 2020)
We found evidence of late-onset Alzheimer disease (LOAD)-associated genetic polymorphism within an exon of Mucin 6 (MUC6) and immediately downstream from another gene: Adaptor Related Protein Complex 2 Subunit Alpha 2 (AP2A2). PCR analyses on genomic DNA samples confirmed that the size of the MUC6 variable number tandem repeat (VNTR) region was highly polymorphic. In a cohort of autopsied subjects with quantitative digital pathology data (n = 119), the size of the polymorphic region was associated with the severity of pTau pathology in neocortex. In a separate replication cohort of autopsied subjects (n = 173), more pTau pathology was again observed in subjects with longer VNTR regions (p = 0.031). Unlike MUC6, AP2A2 is highly expressed in human brain. AP2A2 expression was lower in a subset analysis of brain samples from persons with longer versus shorter VNTR regions (p = 0.014 normalizing with AP2B1 expression). Double-label immunofluorescence studies showed that AP2A2 protein often colocalized with neurofibrillary tangles in LOAD but was not colocalized with pTau proteinopathy in progressive supranuclear palsy, or with TDP-43 proteinopathy. In summary, polymorphism in a repeat-rich region near AP2A2 was associated with neocortical pTau proteinopathy (because of the unique repeats, prior genome-wide association studies were probably unable to detect this association), and AP2A2 was often colocalized with neurofibrillary tangles in LOAD.
Keywords: Adaptor Protein Complex 2; Adaptor Protein Complex alpha Subunits; Aged; Aged, 80 and over; Alzheimer Disease; Autopsy; Cohort Studies; Female; Genome-Wide Association Study; Genotype; Humans; Male; Minisatellite Repeats; Mucin-6; Neurofibrillary Tangles; Polymorphism, Genetic; Polymorphism, Single Nucleotide; TDP-43 Proteinopathies

Association of Genetic Variation With Keratoconus. - McComish, Bennet J; Sahebjada, Srujana; Bykhovskaya, Yelena; Willoughby, Colin E; Richardson, Andrea J; Tenen, Abi; Charlesworth, Jac C; Macgregor, Stuart; Mitchell, Paul; Lucas, Sionne E M; Mills, Richard A; Mackey, David A; et al. (JAMA Ophthalmol, 2020)
Importance: Keratoconus is a condition in which the cornea progressively thins and protrudes in a conical shape, severely affecting refraction and vision. It is a major indication for corneal transplant. To discover new genetic loci associated with keratoconus and better understand the causative mechanism of this disease, we performed a genome-wide association study on patients with keratoconus. Objective: To identify genetic susceptibility regions for keratoconus in the human genome. Design, Setting, and Participants: This study was conducted with data from eye clinics in Australia, the United States, and Northern Ireland. The discovery cohort of individuals with keratoconus and control participants from Australia was genotyped using the Illumina HumanCoreExome single-nucleotide polymorphism array. After quality control and data cleaning, genotypes were imputed against the 1000 Genomes Project reference panel (phase III; version 5), and association analyses were completed using PLINK version 1.90. Single-nucleotide polymorphisms with P < 1.00 × 10-6 were assessed for replication in 3 additional cohorts. Control participants were drawn from the cohorts of the Blue Mountains Eye Study and a previous study of glaucoma. Replication cohorts were from a previous keratoconus genome-wide association study data set from the United States, a cohort of affected and control participants from Australia and Northern Ireland, and a case-control cohort from Victoria, Australia. Data were collected from January 2006 to March 2019. Main Outcomes and Measures: Associations between keratoconus and 6 252 612 genetic variants were estimated using logistic regression after adjusting for ancestry using the first 3 principal components. Results: The discovery cohort included 522 affected individuals and 655 control participants, while the replication cohorts included 818 affected individuals (222 from the United States, 331 from Australia and Northern Ireland, and 265 from Victoria, Australia) and 3858 control participants (2927 from the United States, 229 from Australia and Northern Ireland, and 702 from Victoria, Australia). Two novel loci reached genome-wide significance (defined as P < 5.00 × 10-8), with a P value of 7.46 × 10-9 at rs61876744 in patatin-like phospholipase domain-containing 2 gene (PNPLA2) on chromosome 11 and a P value of 6.35 × 10-12 at rs138380, 2.2 kb upstream of casein kinase I isoform epsilon gene (CSNK1E) on chromosome 22. One additional locus was identified with a P value less than 1.00 × 10-6 in mastermind-like transcriptional coactivator 2 (MAML2) on chromosome 11 (P = 3.91 × 10-7). The novel locus in PNPLA2 reached genome-wide significance in an analysis of all 4 cohorts (P = 2.45 × 10-8). Conclusions and Relevance: In this relatively large keratoconus genome-wide association study, we identified a genome-wide significant locus for keratoconus in the region of PNPLA2 on chromosome 11.
Keywords: Adult; Female; Fuchs' Endothelial Dystrophy; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Keratoconus; Lipase; Logistic Models; Male; Middle Aged; Polymorphism, Single Nucleotide

Genetic loci associated with prevalent and incident myocardial infarction and coronary heart disease in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. - Hahn, Julie; Fu, Yi-Ping; Brown, Michael R; Bis, Joshua C; de Vries, Paul S; Feitosa, Mary F; Yanek, Lisa R; Weiss, Stefan; Giulianini, Franco; Smith, Albert Vernon; Guo, Xiuqing; Bartz, Traci M; et al. (PLoS One, 2020)
BACKGROUND: Genome-wide association studies have identified multiple genomic loci associated with coronary artery disease, but most are common variants in non-coding regions that provide limited information on causal genes and etiology of the disease. To overcome the limited scope that common variants provide, we focused our investigation on low-frequency and rare sequence variations primarily residing in coding regions of the genome. METHODS AND RESULTS: Using samples of individuals of European ancestry from ten cohorts within the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, both cross-sectional and prospective analyses were conducted to examine associations between genetic variants and myocardial infarction (MI), coronary heart disease (CHD), and all-cause mortality following these events. For prevalent events, a total of 27,349 participants of European ancestry, including 1831 prevalent MI cases and 2518 prevalent CHD cases were used. For incident cases, a total of 55,736 participants of European ancestry were included (3,031 incident MI cases and 5,425 incident CHD cases). There were 1,860 all-cause deaths among the 3,751 MI and CHD cases from six cohorts that contributed to the analysis of all-cause mortality. Single variant and gene-based analyses were performed separately in each cohort and then meta-analyzed for each outcome. A low-frequency intronic variant (rs988583) in PLCL1 was significantly associated with prevalent MI (OR = 1.80, 95% confidence interval: 1.43, 2.27; P = 7.12 × 10-7). We conducted gene-based burden tests for genes with a cumulative minor allele count (cMAC) ≥ 5 and variants with minor allele frequency (MAF) < 5%. TMPRSS5 and LDLRAD1 were significantly associated with prevalent MI and CHD, respectively, and RC3H2 and ANGPTL4 were significantly associated with incident MI and CHD, respectively. No loci were significantly associated with all-cause mortality following a MI or CHD event. CONCLUSION: This study identified one known locus (ANGPTL4) and four new loci (PLCL1, RC3H2, TMPRSS5, and LDLRAD1) associated with cardiovascular disease risk that warrant further investigation.
Keywords: Aging; Coronary Artery Disease; Cross-Sectional Studies; Europe; European Continental Ancestry Group; Genetic Loci; Genome-Wide Association Study; Humans; Myocardial Infarction; Polymorphism, Single Nucleotide; Prospective Studies

Whole genome sequence analysis of pulmonary function and COPD in 19,996 multi-ethnic participants. - Zhao, Xutong; Qiao, Dandi; Yang, Chaojie; Kasela, Silva; Kim, Wonji; Ma, Yanlin; Shrine, Nick; Batini, Chiara; Sofer, Tamar; Taliun, Sarah A Gagliano; Sakornsakolpat, Phuwanat; Balte, Pallavi P; et al. (Nat Commun, 2020)
Chronic obstructive pulmonary disease (COPD), diagnosed by reduced lung function, is a leading cause of morbidity and mortality. We performed whole genome sequence (WGS) analysis of lung function and COPD in a multi-ethnic sample of 11,497 participants from population- and family-based studies, and 8499 individuals from COPD-enriched studies in the NHLBI Trans-Omics for Precision Medicine (TOPMed) Program. We identify at genome-wide significance 10 known GWAS loci and 22 distinct, previously unreported loci, including two common variant signals from stratified analysis of African Americans. Four novel common variants within the regions of PIAS1, RGN (two variants) and FTO show evidence of replication in the UK Biobank (European ancestry n ~ 320,000), while colocalization analyses leveraging multi-omic data from GTEx and TOPMed identify potential molecular mechanisms underlying four of the 22 novel loci. Our study demonstrates the value of performing WGS analyses and multi-omic follow-up in cohorts of diverse ancestry.
Keywords: Adult; African Americans; Aged; Aged, 80 and over; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Calcium-Binding Proteins; Feasibility Studies; Female; Follow-Up Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Intracellular Signaling Peptides and Proteins; Lung; Male; Middle Aged; Polymorphism, Single Nucleotide; Protein Inhibitors of Activated STAT; Pulmonary Disease, Chronic Obstructive; Respiratory Physiological Phenomena; Small Ubiquitin-Related Modifier Proteins; Whole Genome Sequencing

Association of low-frequency and rare coding variants with information processing speed. - Bressler, Jan; Davies, Gail; Smith, Albert V; Saba, Yasaman; Bis, Joshua C; Jian, Xueqiu; Hayward, Caroline; Yanek, Lisa; Smith, Jennifer A; Mirza, Saira S; Wang, Ruiqi; Adams, Hieab H H; et al. (Transl Psychiatry, 2021)
Measures of information processing speed vary between individuals and decline with age. Studies of aging twins suggest heritability may be as high as 67%. The Illumina HumanExome Bead Chip genotyping array was used to examine the association of rare coding variants with performance on the Digit-Symbol Substitution Test (DSST) in community-dwelling adults participating in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. DSST scores were available for 30,576 individuals of European ancestry from nine cohorts and for 5758 individuals of African ancestry from four cohorts who were older than 45 years and free of dementia and clinical stroke. Linear regression models adjusted for age and gender were used for analysis of single genetic variants, and the T5, T1, and T01 burden tests that aggregate the number of rare alleles by gene were also applied. Secondary analyses included further adjustment for education. Meta-analyses to combine cohort-specific results were carried out separately for each ancestry group. Variants in RNF19A reached the threshold for statistical significance (p = 2.01 × 10) using the T01 test in individuals of European descent. RNF19A belongs to the class of E3 ubiquitin ligases that confer substrate specificity when proteins are ubiquitinated and targeted for degradation through the 26S proteasome. Variants in SLC22A7 and OR51A7 were suggestively associated with DSST scores after adjustment for education for African-American participants and in the European cohorts, respectively. Further functional characterization of its substrates will be required to confirm the role of RNF19A in cognitive function.
Keywords: Adult; Aging; Cognition; Genome-Wide Association Study; Geroscience; Humans; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Identification of putative causal loci in whole-genome sequencing data via knockoff statistics. - He, Zihuai; Liu, Linxi; Wang, Chen; Le Guen, Yann; Lee, Justin; Gogarten, Stephanie; Lu, Fred; Montgomery, Stephen; Tang, Hua; Silverman, Edwin K; Cho, Michael H; Greicius, Michael; et al. (Nat Commun, 2021)
The analysis of whole-genome sequencing studies is challenging due to the large number of rare variants in noncoding regions and the lack of natural units for testing. We propose a statistical method to detect and localize rare and common risk variants in whole-genome sequencing studies based on a recently developed knockoff framework. It can (1) prioritize causal variants over associations due to linkage disequilibrium thereby improving interpretability; (2) help distinguish the signal due to rare variants from shadow effects of significant common variants nearby; (3) integrate multiple knockoffs for improved power, stability, and reproducibility; and (4) flexibly incorporate state-of-the-art and future association tests to achieve the benefits proposed here. In applications to whole-genome sequencing data from the Alzheimer's Disease Sequencing Project (ADSP) and COPDGene samples from NHLBI Trans-Omics for Precision Medicine (TOPMed) Program we show that our method compared with conventional association tests can lead to substantially more discoveries.
Keywords: Algorithms; Causality; Computer Simulation; Data Interpretation, Statistical; Datasets as Topic; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Markov Chains; Models, Genetic; Polymorphism, Single Nucleotide; Reproducibility of Results; Whole Genome Sequencing

Rare variants in the endocytic pathway are associated with Alzheimer's disease, its related phenotypes, and functional consequences. - Zhan, Lingyu; Li, Jiajin; Jew, Brandon; Sul, Jae Hoon (PLoS Genet, 2021)
Late-onset Alzheimer's disease (LOAD) is the most common type of dementia causing irreversible brain damage to the elderly and presents a major public health challenge. Clinical research and genome-wide association studies have suggested a potential contribution of the endocytic pathway to AD, with an emphasis on common loci. However, the contribution of rare variants in this pathway to AD has not been thoroughly investigated. In this study, we focused on the effect of rare variants on AD by first applying a rare-variant gene-set burden analysis using genes in the endocytic pathway on over 3,000 individuals with European ancestry from three large whole-genome sequencing (WGS) studies. We identified significant associations of rare-variant burden within the endocytic pathway with AD, which were successfully replicated in independent datasets. We further demonstrated that this endocytic rare-variant enrichment is associated with neurofibrillary tangles (NFTs) and age-related phenotypes, increasing the risk of obtaining severer brain damage, earlier age-at-onset, and earlier age-of-death. Next, by aggregating rare variants within each gene, we sought to identify single endocytic genes associated with AD and NFTs. Careful examination using NFTs revealed one significantly associated gene, ANKRD13D. To identify functional associations, we integrated bulk RNA-Seq data from over 600 brain tissues and found two endocytic expression genes (eGenes), HLA-A and SLC26A7, that displayed significant influences on their gene expressions. Differential expressions between AD patients and controls of these three identified genes were further examined by incorporating scRNA-Seq data from 48 post-mortem brain samples and demonstrated distinct expression patterns across cell types. Taken together, our results demonstrated strong rare-variant effect in the endocytic pathway on AD risk and progression and functional effect of gene expression alteration in both bulk and single-cell resolution, which may bring more insight and serve as valuable resources for future AD genetic studies, clinical research, and therapeutic targeting.
Keywords: Alzheimer Disease; Endocytosis; Genome-Wide Association Study; Humans; Phenotype; Polymorphism, Single Nucleotide; Whole Genome Sequencing

Whole-genome sequencing in diverse subjects identifies genetic correlates of leukocyte traits: The NHLBI TOPMed program. - Mikhaylova, Anna V; McHugh, Caitlin P; Polfus, Linda M; Raffield, Laura M; Boorgula, Meher Preethi; Blackwell, Thomas W; Brody, Jennifer A; Broome, Jai; Chami, Nathalie; Chen, Ming-Huei; Conomos, Matthew P; Cox, Corey; et al. (Am J Hum Genet, 2021)
Many common and rare variants associated with hematologic traits have been discovered through imputation on large-scale reference panels. However, the majority of genome-wide association studies (GWASs) have been conducted in Europeans, and determining causal variants has proved challenging. We performed a GWAS of total leukocyte, neutrophil, lymphocyte, monocyte, eosinophil, and basophil counts generated from 109,563,748 variants in the autosomes and the X chromosome in the Trans-Omics for Precision Medicine (TOPMed) program, which included data from 61,802 individuals of diverse ancestry. We discovered and replicated 7 leukocyte trait associations, including (1) the association between a chromosome X, pseudo-autosomal region (PAR), noncoding variant located between cytokine receptor genes (CSF2RA and CLRF2) and lower eosinophil count; and (2) associations between single variants found predominantly among African Americans at the S1PR3 (9q22.1) and HBB (11p15.4) loci and monocyte and lymphocyte counts, respectively. We further provide evidence indicating that the newly discovered eosinophil-lowering chromosome X PAR variant might be associated with reduced susceptibility to common allergic diseases such as atopic dermatitis and asthma. Additionally, we found a burden of very rare FLT3 (13q12.2) variants associated with monocyte counts. Together, these results emphasize the utility of whole-genome sequencing in diverse samples in identifying associations missed by European-ancestry-driven GWASs.
Keywords: Asthma; Biomarkers; Dermatitis, Atopic; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Leukocytes; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Polymorphism, Single Nucleotide; Prognosis; Proteome; Pulmonary Disease, Chronic Obstructive; Quantitative Trait Loci; United Kingdom; United States; Whole Genome Sequencing

Cross-Ancestry Investigation of Venous Thromboembolism Genomic Predictors. - Thibord, Florian; Klarin, Derek; Brody, Jennifer A; Chen, Ming-Huei; Levin, Michael G; Chasman, Daniel I; Goode, Ellen L; Hveem, Kristian; Teder-Laving, Maris; Martinez-Perez, Angel; Aïssi, Dylan; Daian-Bacq, Delphine; et al. (Circulation, 2022)
BACKGROUND: Venous thromboembolism (VTE) is a life-threatening vascular event with environmental and genetic determinants. Recent VTE genome-wide association studies (GWAS) meta-analyses involved nearly 30 000 VTE cases and identified up to 40 genetic loci associated with VTE risk, including loci not previously suspected to play a role in hemostasis. The aim of our research was to expand discovery of new genetic loci associated with VTE by using cross-ancestry genomic resources. METHODS: We present new cross-ancestry meta-analyzed GWAS results involving up to 81 669 VTE cases from 30 studies, with replication of novel loci in independent populations and loci characterization through in silico genomic interrogations. RESULTS: In our genetic discovery effort that included 55 330 participants with VTE (47 822 European, 6320 African, and 1188 Hispanic ancestry), we identified 48 novel associations, of which 34 were replicated after correction for multiple testing. In our combined discovery-replication analysis (81 669 VTE participants) and ancestry-stratified meta-analyses (European, African, and Hispanic), we identified another 44 novel associations, which are new candidate VTE-associated loci requiring replication. In total, across all GWAS meta-analyses, we identified 135 independent genomic loci significantly associated with VTE risk. A genetic risk score of the significantly associated loci in Europeans identified a 6-fold increase in risk for those in the top 1% of scores compared with those with average scores. We also identified 31 novel transcript associations in transcriptome-wide association studies and 8 novel candidate genes with protein quantitative-trait locus Mendelian randomization analyses. In silico interrogations of hemostasis and hematology traits and a large phenome-wide association analysis of the 135 GWAS loci provided insights to biological pathways contributing to VTE, with some loci contributing to VTE through well-characterized coagulation pathways and others providing new data on the role of hematology traits, particularly platelet function. Many of the replicated loci are outside of known or currently hypothesized pathways to thrombosis. CONCLUSIONS: Our cross-ancestry GWAS meta-analyses identified new loci associated with VTE. These findings highlight new pathways to thrombosis and provide novel molecules that may be useful in the development of improved antithrombosis treatments.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Humans; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Thrombosis; Venous Thromboembolism

Large-scale genome-wide association study of coronary artery disease in genetically diverse populations. - Tcheandjieu, Catherine; Zhu, Xiang; Hilliard, Austin T; Clarke, Shoa L; Napolioni, Valerio; Ma, Shining; Lee, Kyung Min; Fang, Huaying; Chen, Fei; Lu, Yingchang; Tsao, Noah L; Raghavan, Sridharan; et al. (Nat Med, 2022)
We report a genome-wide association study (GWAS) of coronary artery disease (CAD) incorporating nearly a quarter of a million cases, in which existing studies are integrated with data from cohorts of white, Black and Hispanic individuals from the Million Veteran Program. We document near equivalent heritability of CAD across multiple ancestral groups, identify 95 novel loci, including nine on the X chromosome, detect eight loci of genome-wide significance in Black and Hispanic individuals, and demonstrate that two common haplotypes at the 9p21 locus are responsible for risk stratification in all populations except those of African origin, in which these haplotypes are virtually absent. Moreover, in the largest GWAS for angiographically derived coronary atherosclerosis performed to date, we find 15 loci of genome-wide significance that robustly overlap with established loci for clinical CAD. Phenome-wide association analyses of novel loci and polygenic risk scores (PRSs) augment signals related to insulin resistance, extend pleiotropic associations of these loci to include smoking and family history, and precisely document the markedly reduced transferability of existing PRSs to Black individuals. Downstream integrative analyses reinforce the critical roles of vascular endothelial, fibroblast, and smooth muscle cells in CAD susceptibility, but also point to a shared biology between atherosclerosis and oncogenesis. This study highlights the value of diverse populations in further characterizing the genetic architecture of CAD.
Keywords: Coronary Artery Disease; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors

Multi-ancestry genetic study of type 2 diabetes highlights the power of diverse populations for discovery and translation. - Mahajan, Anubha; Spracklen, Cassandra N; Zhang, Weihua; Ng, Maggie C Y; Petty, Lauren E; Kitajima, Hidetoshi; Yu, Grace Z; Rüeger, Sina; Speidel, Leo; Kim, Young Jin; Horikoshi, Momoko; Mercader, Josep M; et al. (Nat Genet, 2022)
We assembled an ancestrally diverse collection of genome-wide association studies (GWAS) of type 2 diabetes (T2D) in 180,834 affected individuals and 1,159,055 controls (48.9% non-European descent) through the Diabetes Meta-Analysis of Trans-Ethnic association studies (DIAMANTE) Consortium. Multi-ancestry GWAS meta-analysis identified 237 loci attaining stringent genome-wide significance (P < 5 × 10), which were delineated to 338 distinct association signals. Fine-mapping of these signals was enhanced by the increased sample size and expanded population diversity of the multi-ancestry meta-analysis, which localized 54.4% of T2D associations to a single variant with >50% posterior probability. This improved fine-mapping enabled systematic assessment of candidate causal genes and molecular mechanisms through which T2D associations are mediated, laying the foundations for functional investigations. Multi-ancestry genetic risk scores enhanced transferability of T2D prediction across diverse populations. Our study provides a step toward more effective clinical translation of T2D GWAS to improve global health for all, irrespective of genetic background.
Keywords: Diabetes Mellitus, Type 2; Ethnicity; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Risk Factors

Non-linear machine learning models incorporating SNPs and PRS improve polygenic prediction in diverse human populations. - Elgart, Michael; Lyons, Genevieve; Romero-Brufau, Santiago; Kurniansyah, Nuzulul; Brody, Jennifer A; Guo, Xiuqing; Lin, Henry J; Raffield, Laura; Gao, Yan; Chen, Han; de Vries, Paul; Lloyd-Jones, Donald M; et al. (Commun Biol, 2022)
Polygenic risk scores (PRS) are commonly used to quantify the inherited susceptibility for a trait, yet they fail to account for non-linear and interaction effects between single nucleotide polymorphisms (SNPs). We address this via a machine learning approach, validated in nine complex phenotypes in a multi-ancestry population. We use an ensemble method of SNP selection followed by gradient boosted trees (XGBoost) to allow for non-linearities and interaction effects. We compare our results to the standard, linear PRS model developed using PRSice, LDpred2, and lassosum2. Combining a PRS as a feature in an XGBoost model results in a relative increase in the percentage variance explained compared to the standard linear PRS model by 22% for height, 27% for HDL cholesterol, 43% for body mass index, 50% for sleep duration, 58% for systolic blood pressure, 64% for total cholesterol, 66% for triglycerides, 77% for LDL cholesterol, and 100% for diastolic blood pressure. Multi-ancestry trained models perform similarly to specific racial/ethnic group trained models and are consistently superior to the standard linear PRS models. This work demonstrates an effective method to account for non-linearities and interaction effects in genetics-based prediction models.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Machine Learning; Multifactorial Inheritance; Polymorphism, Single Nucleotide

Rare coding variants in 35 genes associate with circulating lipid levels-A multi-ancestry analysis of 170,000 exomes. - Hindy, George; Dornbos, Peter; Chaffin, Mark D; Liu, Dajiang J; Wang, Minxian; Selvaraj, Margaret Sunitha; Zhang, David; Park, Joseph; Aguilar-Salinas, Carlos A; Antonacci-Fulton, Lucinda; Ardissino, Diego; Arnett, Donna K; et al. (Am J Hum Genet, 2022)
Large-scale gene sequencing studies for complex traits have the potential to identify causal genes with therapeutic implications. We performed gene-based association testing of blood lipid levels with rare (minor allele frequency < 1%) predicted damaging coding variation by using sequence data from >170,000 individuals from multiple ancestries: 97,493 European, 30,025 South Asian, 16,507 African, 16,440 Hispanic/Latino, 10,420 East Asian, and 1,182 Samoan. We identified 35 genes associated with circulating lipid levels; some of these genes have not been previously associated with lipid levels when using rare coding variation from population-based samples. We prioritize 32 genes in array-based genome-wide association study (GWAS) loci based on aggregations of rare coding variants; three (EVI5, SH2B3, and PLIN1) had no prior association of rare coding variants with lipid levels. Most of our associated genes showed evidence of association among multiple ancestries. Finally, we observed an enrichment of gene-based associations for low-density lipoprotein cholesterol drug target genes and for genes closest to GWAS index single-nucleotide polymorphisms (SNPs). Our results demonstrate that gene-based associations can be beneficial for drug target development and provide evidence that the gene closest to the array-based GWAS index SNP is often the functional gene for blood lipid levels.
Keywords: Alleles; Blood Glucose; Case-Control Studies; Computational Biology; Databases, Genetic; Diabetes Mellitus, Type 2; Exome; Genetic Predisposition to Disease; Genetic Variation; Genetics, Population; Genome-Wide Association Study; Humans; Lipid Metabolism; Lipids; Liver; Molecular Sequence Annotation; Multifactorial Inheritance; Open Reading Frames; Phenotype; Polymorphism, Single Nucleotide

Whole genome sequence association analysis of fasting glucose and fasting insulin levels in diverse cohorts from the NHLBI TOPMed program. - DiCorpo, Daniel; Gaynor, Sheila M; Russell, Emily M; Westerman, Kenneth E; Raffield, Laura M; Majarian, Timothy D; Wu, Peitao; Sarnowski, Chloe; Highland, Heather M; Jackson, Anne; Hasbani, Natalie R; de Vries, Paul S; et al. (Commun Biol, 2022)
The genetic determinants of fasting glucose (FG) and fasting insulin (FI) have been studied mostly through genome arrays, resulting in over 100 associated variants. We extended this work with high-coverage whole genome sequencing analyses from fifteen cohorts in NHLBI's Trans-Omics for Precision Medicine (TOPMed) program. Over 23,000 non-diabetic individuals from five race-ethnicities/populations (African, Asian, European, Hispanic and Samoan) were included. Eight variants were significantly associated with FG or FI across previously identified regions MTNR1B, G6PC2, GCK, GCKR and FOXA2. We additionally characterize suggestive associations with FG or FI near previously identified SLC30A8, TCF7L2, and ADCY5 regions as well as APOB, PTPRT, and ROBO1. Functional annotation resources including the Diabetes Epigenome Atlas were compiled for each signal (chromatin states, annotation principal components, and others) to elucidate variant-to-function hypotheses. We provide a catalog of nucleotide-resolution genomic variation spanning intergenic and intronic regions creating a foundation for future sequencing-based investigations of glycemic traits.
Keywords: Diabetes Mellitus, Type 2; Fasting; Glucose; Humans; Insulin; National Heart, Lung, and Blood Institute (U.S.); Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Precision Medicine; Receptors, Immunologic; United States

Multi-ancestry transcriptome-wide association analyses yield insights into tobacco use biology and drug repurposing. - Chen, Fang; Wang, Xingyan; Jang, Seon-Kyeong; Quach, Bryan C; Weissenkampen, J Dylan; Khunsriraksakul, Chachrit; Yang, Lina; Sauteraud, Renan; Albert, Christine M; Allred, Nicholette D D; Arnett, Donna K; Ashley-Koch, Allison E; et al. (Nat Genet, 2023)
Most transcriptome-wide association studies (TWASs) so far focus on European ancestry and lack diversity. To overcome this limitation, we aggregated genome-wide association study (GWAS) summary statistics, whole-genome sequences and expression quantitative trait locus (eQTL) data from diverse ancestries. We developed a new approach, TESLA (multi-ancestry integrative study using an optimal linear combination of association statistics), to integrate an eQTL dataset with a multi-ancestry GWAS. By exploiting shared phenotypic effects between ancestries and accommodating potential effect heterogeneities, TESLA improves power over other TWAS methods. When applied to tobacco use phenotypes, TESLA identified 273 new genes, up to 55% more compared with alternative TWAS methods. These hits and subsequent fine mapping using TESLA point to target genes with biological relevance. In silico drug-repurposing analyses highlight several drugs with known efficacy, including dextromethorphan and galantamine, and new drugs such as muscle relaxants that may be repurposed for treating nicotine addiction.
Keywords: Biology; Drug Repositioning; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Tobacco Use; Transcriptome

Whole-Genome Sequencing Analysis of Human Metabolome in Multi-Ethnic Populations. - Feofanova, Elena V; Brown, Michael R; Alkis, Taryn; Manuel, Astrid M; Li, Xihao; Tahir, Usman A; Li, Zilin; Mendez, Kevin M; Kelly, Rachel S; Qi, Qibin; Chen, Han; Larson, Martin G; et al. (Nat Commun, 2023)
Circulating metabolite levels may reflect the state of the human organism in health and disease, however, the genetic architecture of metabolites is not fully understood. We have performed a whole-genome sequencing association analysis of both common and rare variants in up to 11,840 multi-ethnic participants from five studies with up to 1666 circulating metabolites. We have discovered 1985 novel variant-metabolite associations, and validated 761 locus-metabolite associations reported previously. Seventy-nine novel variant-metabolite associations have been replicated, including three genetic loci located on the X chromosome that have demonstrated its involvement in metabolic regulation. Gene-based analysis have provided further support for seven metabolite-replicated loci pairs and their biologically plausible genes. Among those novel replicated variant-metabolite pairs, follow-up analyses have revealed that 26 metabolites have colocalized with 21 tissues, seven metabolite-disease outcome associations have been putatively causal, and 7 metabolites might be regulated by plasma protein levels. Our results have depicted the genetic contribution to circulating metabolite levels, providing additional insights into understanding human disease.
Keywords: Ethnicity; Genome-Wide Association Study; Humans; Metabolome; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Multi-omics and pathway analyses of genome-wide associations implicate regulation and immunity in verbal declarative memory performance. - Mei, Hao; Simino, Jeannette; Li, Lianna; Jiang, Fan; Bis, Joshua C; Davies, Gail; Hill, W David; Xia, Charley; Gudnason, Vilmundur; Yang, Qiong; Lahti, Jari; Smith, Jennifer A; et al. (Alzheimers Res Ther, 2024)
BACKGROUND: Uncovering the functional relevance underlying verbal declarative memory (VDM) genome-wide association study (GWAS) results may facilitate the development of interventions to reduce age-related memory decline and dementia. METHODS: We performed multi-omics and pathway enrichment analyses of paragraph (PAR-dr) and word list (WL-dr) delayed recall GWAS from 29,076 older non-demented individuals of European descent. We assessed the relationship between single-variant associations and expression quantitative trait loci (eQTLs) in 44 tissues and methylation quantitative trait loci (meQTLs) in the hippocampus. We determined the relationship between gene associations and transcript levels in 53 tissues, annotation as immune genes, and regulation by transcription factors (TFs) and microRNAs. To identify significant pathways, gene set enrichment was tested in each cohort and meta-analyzed across cohorts. Analyses of differential expression in brain tissues were conducted for pathway component genes. RESULTS: The single-variant associations of VDM showed significant linkage disequilibrium (LD) with eQTLs across all tissues and meQTLs within the hippocampus. Stronger WL-dr gene associations correlated with reduced expression in four brain tissues, including the hippocampus. More robust PAR-dr and/or WL-dr gene associations were intricately linked with immunity and were influenced by 31 TFs and 2 microRNAs. Six pathways, including type I diabetes, exhibited significant associations with both PAR-dr and WL-dr. These pathways included fifteen MHC genes intricately linked to VDM performance, showing diverse expression patterns based on cognitive status in brain tissues. CONCLUSIONS: VDM genetic associations influence expression regulation via eQTLs and meQTLs. The involvement of TFs, microRNAs, MHC genes, and immune-related pathways contributes to VDM performance in older individuals.
Keywords: Aged; Cognition; Genome-Wide Association Study; Humans; Memory; MicroRNAs; Multiomics; Polymorphism, Single Nucleotide

X-chromosome and kidney function: evidence from a multi-trait genetic analysis of 908,697 individuals reveals sex-specific and sex-differential findings in genes regulated by androgen response elements. - Scholz, Markus; Horn, Katrin; Pott, Janne; Wuttke, Matthias; Kühnapfel, Andreas; Nasr, M Kamal; Kirsten, Holger; Li, Yong; Hoppmann, Anselm; Gorski, Mathias; Ghasemi, Sahar; Li, Man; et al. (Nat Commun, 2024)
X-chromosomal genetic variants are understudied but can yield valuable insights into sexually dimorphic human traits and diseases. We performed a sex-stratified cross-ancestry X-chromosome-wide association meta-analysis of seven kidney-related traits (n = 908,697), identifying 23 loci genome-wide significantly associated with two of the traits: 7 for uric acid and 16 for estimated glomerular filtration rate (eGFR), including four novel eGFR loci containing the functionally plausible prioritized genes ACSL4, CLDN2, TSPAN6 and the female-specific DRP2. Further, we identified five novel sex-interactions, comprising male-specific effects at FAM9B and AR/EDA2R, and three sex-differential findings with larger genetic effect sizes in males at DCAF12L1 and MST4 and larger effect sizes in females at HPRT1. All prioritized genes in loci showing significant sex-interactions were located next to androgen response elements (ARE). Five ARE genes showed sex-differential expressions. This study contributes new insights into sex-dimorphisms of kidney traits along with new prioritized gene targets for further molecular research.
Keywords: Androgens; Chromosomes, Human, X; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Kidney; Male; Polymorphism, Single Nucleotide; Response Elements; Tetraspanins